Identity Politics in a Mediatized Religious Environment on Facebook: Yes to Wearing the Cross Whenever and Wherever I Choose - Abdel-Fadil, M (Journal of Religion in Europe, 2017)
The Norwegian Facebook page Yes to Wearing the Cross Whenever and Wherever I Choose was initially created to protest the prohibition of the cross for NRK news anchors. Yet, many of the discussions and audience interactions transpired into heated religio-political debates with strong elements of anti-Muslim, xenophobic, anti-secular, and anti-atheist sentiments. This study aims to contribute to a more nuanced understanding of the interplay between media and religion by providing new insights on the variety of ways in which media audiences may ‘add a series of dynamics to conflicts, namely, amplification, framing and performative agency, and co-structuring’ and ‘perform conflict’, as formulated by Hjarvard et al. It is argued that mediatized conflicts with inherent trigger themes, which tug at core religio-political identity issues, also tend to evoke emotional responses, which, in turn, inspire social media users to perform the conflict in ways that multiply the conflict(s).
Keywords: Facebook; mediatized; Politics; religious

Introduction: Media and Religious Controversy - Abdel-Fadil, Mona; Årsheim, Helge (Journal of Religion, Media and Digital Culture, 2019)
The phrase “religious controversies” is blunt and evocative, and immediately brings up associations to angry mobs, flag burning and, at times, inexplicable rage at seemingly mundane matters. The capacity of religion, whether in its doctrinal, social or institutional form, to generate, propagate and exacerbate controversy appears endless. While this capacity may not be unique to religion, nor recent in origin, the last couple of decades have seen what would appear to be unprecedented levels of religious controversies around the world. This introduction provides a brief backdrop to the overarching theme of mediatized religious controversies, and identifies some cross-cutting issues that have arisen across the different contributions. We identify some general patterns among the controversies dealt with in this special issue, and ask how these patterns may inspire new research efforts.

Counselling Muslim Selves on Islamic Websites: Walking a Tightrope Between Secular and Religious Counselling Ideals? - Abdel-Fadil, Mona (Journal of Religion, Media and Digital Culture, 2015)
This article focuses on the interactive counselling service Problems and Answers (PS), an Arabic language and Islamic online counselling service, which draws on global therapeutic counselling trends. For over a decade, PS was run and hosted by www.IslamOnline.net (IOL). Based on ethnographic fieldwork, this article aims to provide a layered, contextualized understanding of online Islamic counselling, through addressing the ‘invisible’, ‘behind the screens’ aspects of PS counselling and the meaning making activities that inform the online output. In particular, I examine: 1. The multiple ways in which ‘religion’ shapes the PS counsellors' counselling output, and 2. The extent to which secular and religious counselling ideals clash, in PS counselling. Drawing on a mixed methods approach, I demonstrate instances in which offline data nuance and generate new understandings of online data. The findings demonstrate the multivocality and variations in the PS counsellors' perspectives on both religion and counselling psychology, and shed light on possible tensions between professed ideals and actual online practices.

The Politics of Affect: the Glue of Religious and Identity Conflicts in Social Media - Abdel-Fadil, Mona (Journal of Religion, Media and Digital Culture, 2019)
Affect theory often overlooks decades of anthropological, feminist, queer, and postcolonial scholarship on emotion. I build on this extensive scholarship of emotion and use my online ethnography of a Facebook group that promotes the public visibility of Christianity as a springboard to build a conceptual framework of the politics of affect. I address three theoretical gaps: 1) the lack of distinction between different emotions, 2) how affect is often performed for someone, and 3) the varying intensities of emotion. I delve into the intricate ways in which emotions fuel identities, worldviews, and their contestations, and how fake news may come to be perceived as affectively factual. This article deepens our understanding of the role of affect in polemic and mediatized conflicts. The role of emotion in religious conflicts and identity politics is not simply analytically useful, but is, at times, the very fabric of which political ideas are made.

Film, television, and new media studies - Abrams, N (The Routledge Handbook of Contemporary Jewish Cultures, 2014)
Screen sources, such as ﬁlm, television, and new media, are valuable resources for studying both the Jewish past and the present. This is, in part, because of their reliance on visual stereotypes to communicate information quickly and easily. Stereotypes are regularly repeated, simplistic, easily understood, and (often) inaccurate categorizations of a social group (Abrams et al. 2010: 365). Stereotypes in general, and Jewish ones in particular, fulﬁll many functions and much has been written about this especially in terms of how they perform cultural work in demonizing minority groups from the outside, and perpetuating group solidarity and continuity from the inside. Since stereotypes do not stay static and because screen media tend to rely on them, they allow us to map and track wider changes in the society from which those texts originate. They “change because the cultural patterns on which they are based are becoming anachronistic” (Antler 1998: 256). Likewise, screen stereotypes of Jews, existing almost as long as the media themselves, have evolved, and a diachronic study of screen media allows us to map the metamorphosis of the Jew/ess and what this tells us about the societies in which they live at any given point in time. For these reasons, then, the study of Jewish ﬁlm, television, and new media is a highly pro- ductive ﬁeld with its own speciﬁc histories, identities, agents, productions, production contexts, industries, and festivals.
Keywords: film; New Media; Television

Grassroots Religion: Facebook and Offline Post-Denominational Judaism - Nathan Abrams; Sally Baker; B. J. Brown (Social Media Religion and Spirituality, 2013)
Keywords: Facebook; Jews; Judaism; Online; self-generated; social media; social network; Youth

Cards, Links, and Research: Teaching Technological Learners - Adam, A. K. M. (Theology and Pedagogy in Cyberspace II, 2004)

Practicing the Disseminary: Technology Lessons from Napster - Adam, A. K. M. (Teaching Theology and Religion, 2002)
Whatever will happen in the way of the confluence of pedagogy and technology, it will not so much perpetuate past models in more efficient ways as it will reflect a stronger element of (for example) the unanticipated success of Napster. The author suggests a fivefold interpretation of Napster's implications as a guideline of what cybermedia do well, and how theological educators can use cybermedia to enrich their classroom teaching by distinguishing online from in-class education. Cybermedia serve best when they do not duplicate or usurp functions best accomplished in person, and personal interaction thrives when not burdened with information-transmission that might as well take place online.

The Question Concerning Technology and Religion - Adam, A. K. M. (Journal of Lutheran Ethics, 2012)
The question concerning technology and religion typically confronts us today when skeptics and enthusiasts debate the reality and validity of computers’ mediation of theological experience, when dubious observers denounce the deleterious effects of digital technology on spirituality, or advocates praise the benefits of online piety. ... Are computers making us dumber, more globally aware, less religious, more spiritual?

#WhatBritishMuslimsReallyThink: Negotiating Religious and National Identity on Twitter - Aeschbach, Mirjam (Zeitschrift für junge Religionswissenschaft, 2017)
In the discursive construction of intra-national sameness, religious identity is often a key criterion for inclusion or exclusion from the imagined national community. In today’s Europe, the boundaries of individual nations are increasingly secured by applying a logic characteristic of Islamophobia and cultural racism. Therefore, the negotiation of Muslim identity and its intersection with the respective national identity category is of particular interest. In this study, the Twitter hashtag #WhatBritishMuslimsReallyThink was examined in order to analyze how members of the British Muslim digital community both construct and reinforce their collective identity as well as employ discursive strategies to negotiate British national identity and their national belonging in the face of exclusionary political rhetoric. Drawing on a corpus of 480 tweets containing the hashtag #WhatBritishMuslimsReallyThink, a mixed-method content analysis approach was employed to analyze the topics and strategies present in the hashtag discourse. Thereby, the issues addressed and the strategies of belonging employed in the Twitter conversation are embedded in a larger public discourse on British national identity and intra-national boundary making. This research investigates Twitter as a site of national and religious identity construction and sheds light on the contested nature of such identity categories.

Sexual Violence Discourse on Internet: Meme, Hoe and the Case of Eno Fariha - Agam, R. A (Jurnal Perempuan, 2016)
Internet memes are presently gaining momentum as the hip media of the internet, yet it also brought the dated notion of sexism and violence against women. The notion is apparent especially after the recent case of violence and murder of Eno Fariha was transformed into memes. Using several superficial aspect of media coverage on Eno’s case, such as the utilization of hoe for the murder, the creator of said memes basically implies that any women who violate practices identifiable with certain religion is subject to similar act of violence which befalls Eno. Moreover, taking into account that internet memes are made ‘just for laughs’, the humor of the meme becomes more prevalent than the violence discourse. Further inspection is needed on how much has the discourse spread, especially with memes’ quick and easy spread through the internet, and on its discursive relation with religion and domestification of women.
Keywords: internet; meme; sexual violence

Communicating Mixed Messages About Religion through Internet Memes - Aguilar, A; Campbell, H; Stanley, M; Taylor, E (Information, Communication & Society, 2017)
This article investigates the dominant messages Internet memes communicate about religion. Internet memes about religion are defined as, ‘memes circulated on the Internet whose images and texts focus on a variety of religious themes and/or religious traditions’ (Bellar et al., 2013). By drawing on meme genres identified by Shifman (2012) and analyzing techniques used to frame ideas concerning religion in memes, this study identifies common genres found amongst religious Internet meme and core frames used to present messages and assumptions about religion online. This article further draws attention to the importance of studying religion in digital contexts, as it highlights trends, recognized by scholars toward ‘Lived Religion’ within digital culture (Campbell, 2012). Lived Religion argues that contemporary media and digital culture provide important resources for presenting popular beliefs about religion. This study also suggests that studying Internet memes about religion provides a useful lens for understanding popular conceptions about religion within mainstream culture.
Keywords: digital cultures; internet memes; Lived religion; memes; participatory culture

An Orthodox wide network over the Internet for the lesson of religion - Risto Aikonen (Orthodoxy and Education: The Lesson on Religion as a Subject of Identity and Culture, 2004)
Adapting the Orthodox view of education, “taste and see” (Schmemann 1974) to the Internet is quite difficult, because there is a lack of dimensions, interactivity and emotional life in its hole range. So, for a theologian it is not such a big a surprise, if ICT in Religious Education does not pay itself as it perhaps does according to the advocates of the business world. This is because the Orthodox view of Christian education differs from the learning and teaching theories. In spite of all these sceptical thoughts presented above there is no absolute reason to abandon or avoid the Internet in the R.E. The Internet connects people and helps them to share something that is common to them. At its best the www-material supports a deeper understanding of the same substance and paves the way for wider and mutual understanding concerning the Religious teaching and Religious life, and the situation of the Church in different kind of societies (minority-majority position of the Orthodoxy).
Keywords: internet; network; religion

Interpreting Islam through the Internet: making sense of hijab - Akou, Heather Marie (Contemporary Islam, 2010)
Hijab, the practice of modesty or "covering," is one of the most visible and controversial aspects of Islam in the twenty-first century, partly because the Qur'an offers so little guidance on proper dress. This forces Muslims to engage in ijtihad (interpretation), which historically has resulted in vast differences in dress around the world. By transcending some of the boundaries of space, time and the body, the Internet has emerged as a place where Muslims from diverse backgrounds can meet to debate ideas and flesh them out through shared experiences. After discussing hijab in the Qur'an and other traditional sources, this article explores the use of cyberspace as a multi-media platform for learning about and debating what constitutes appropriate Islamic dress. The last section focuses on a case study of the multi-user "hijablog" hosted by thecanadianmuslim.ca, which represents one of the largest in-print discussions on hijab ever recorded in the English language. On this blog and other forums like it, ijtihad has become a critical tool for debate on matters such as hijab, which are important but sparsely discussed in the Qur'an.
Keywords: internet; Islam

Video games, terrorism, and ISIS’s Jihad 3.0 - Al-Rawi, Ahmed (Terrorism and Political Violence, 2018)
This study discusses different media strategies followed by the Islamic State in Iraq and Syria (ISIS). In particular, the study attempts to understand the way ISIS’s video game that is called “Salil al-Sawarem” (The Clanging of the Swords) has been received by the online Arab public. The article argues that the goal behind making and releasing the video game was to gain publicity and attract attention to the group, and the general target was young people. The main technique used by ISIS is what I call “troll, flame, and engage.” The results indicate that the majority of comments are against ISIS and its game, though most of the top ten videos are favorable towards the group. The sectarian dimension between Sunnis and Shiites is highly emphasized in the online exchanges, and YouTube remains an active social networking site that is used by ISIS followers and sympathizers to promote the group and recruit others.

Online Reactions to the Muhammad Cartoons: YouTube and the Virtual Ummah - Al-Rawi, Ahmed (Journal for the Scientific Study of Religion)
The publication of 12 cartoons depicting the Prophet Muhammad by the Danish newspaper Jyllands‐Posten on September 30, 2005, created a great deal of controversy over self‐censorship, freedom of speech, and accusations of religious incitement. Muslim activists organized protests, and later hundreds of people were killed and hundreds of others were injured due to violent reactions to the cartoons. This article focuses on how people used YouTube to react to these cartoons by analyzing 261 video clips and 4,153 comments. Results show that the majority of the video clips and comments were moderate and positive in tone toward Islam and Muhammad; however, a small percentage either called for jihad against the West or made lethal threats against the artist. Other comments carried curses or insults against Denmark, while a few others were anti‐Islamic. The fact that these online reactions were highly varied in tone suggests that the online public sphere is very much divided.

Facebook as a virtual mosque: the online protest against Innocence of Muslims - Al-Rawi, Ahmed (Culture and Religion, 2016)
When the short anti-Islam film the Innocence of Muslims was first posted on YouTube in English, no tangible reactions were seen in the Arab world. However, when the same producer dubbed it into Arabic and posted it on YouTube, street protests started around some parts of the Arab world. The study reported here examines a popular Facebook page identified as The global campaign to counter the hurtful film against the Prophet Muhammed that was created to protest against the Innocence of Muslims film. This study investigated all 6949 Facebook updates and comments that were available on this page by 15 October 2012 and found that a clear majority of posts were Pro-Islamic focusing on prayers for Muhammed and supplications to defend him. This study advances our theoretical understanding of the connection between online and offline religion by providing empirical evidence in relation to this controversial incident.

The Beauty of Ugliness: Preserving while Communicating Online with Shared Graphic Photos - Alshehri, M; Su, N.M (European Conference on Computer-Supported Cooperative Work, 2018)
In this paper, we report on interviews with 11 Shia content creators who create and share graphic, bloody photos of Tatbeer, a religious ritual involving self-harm practices on Ashura, the death anniversary of the prophet Muhammad’s grandson. We show how graphic images serve as an object of communication in religious practices with the local community, the inner-self, and a wider audience. In particular, we highlight how content creators appropriated, in their own words, “ugly” photos to preserve the authenticity and beauty of their rituals while communicating their own interpretation of such rituals to others. We suggest that ugliness may be regarded as a useful resource to inform systems that seek to invite dialogue with marginalized or minority groups.
Keywords: Graphic Photos; Gulf Arabs; Online photo sharing; social media

'Sharing' the Catholic faith: How priests establish/maintain religious authority on Facebook - Altenhofen, Brian Joseph (Texas A & M University, 2016)
Understanding how religious leaders use the internet to maintain their religious authority has been an area of study in media studies for the past twenty years. Little consensus has been reached as to what religious authority is, in the context of the internet. Nor, has the population of Catholic priests been investigated in light of religious authority on the internet. Therefore, this study seeks to understand strategies used by Catholic priests in the United States on Facebook to establish/maintain their religious authority using Facebook. Data was gathered by survey and in depth interviews with priests who acknowledged using Facebook on a regular basis. Survey data indicated that priests utilized Facebook in ways that mirrored three parts of their priestly identity. They used it as representatives of the institutional Catholic Church, members of the profession of priests, and as individuals. These three parts of priests’ identities led to differing strategies. Being a representative of the institutional Catholic Church included disseminating important Church information and defending doctrinal teachings of the Church. As a member of the profession of priests, they used Facebook to disseminate information about their local Church and build relationships in the professional capacity. As individuals, priests used Facebook to stay in contact with friends and family, sharing life events, using Facebook as a news-aggregate, and as a source of comedic content. It became evident that even the personal ways that priests used Facebook were ways of maintaining religious authority. Contrary to the overt strategies, priests utilized the personal space for covert evangelization. Since the survey data indicated that their identity was so important on Facebook, interview questioning probed why and how identity construction took place. Interview data indicated that authenticity was of the upmost importance when constructing an identity. Priests had to consider various and sometimes contradicting audiences when posting content on Facebook to represent themselves on Facebook. Additionally, their identities had to indicate that they were made in God’s likeness in order to connect their various identities with a sense of religious authority. This led priests to the strategies indicated in survey data, namely, relationship building, evangelizing, and promoting Church-related content in order to establish/maintain religious authority on Facebook.

The Use of the Mobile Phone for Religious Mobilization in Niger Republic - Alzouma, G (Electronic Journal of Information Systems in Developing Countries, 2017)
While many scholars have studied the ways in which the Internet and online social networks are shaping contemporary religious practices and how new information and communication technologies are supporting networked forms of religious activism, only a few have analyzed the relationships between religion and the use of the mobile phone in African countries. However, in Africa as elsewhere, mobile phones are influencing the everyday practices of religion in multiple ways that are not simply anecdotal but affect beliefs and behaviors and raise ethical concerns among believers. In some cases (e.g., divorce, Qur'an verses, ringtones, prayer disruption), religious authorities have been obliged to draw up rules and provide guidance to the faithful. This article seeks to identify the opportunities offered and the challenges posed to religion by the introduction of mobile phones in Niamey, the capital‐city of Niger Republic. It specifically examines how believers are using this device to mobilize co‐religionists, to maintain religious ties and religious faith, as well as how they are coping with the challenges and seeking to resolve related issues. The article argues that the mobile phone is helping mediate in new ways and in a new context the religious norms and behaviors that have always guided Muslim communities. In other words, the advent of the mobile phone offers new opportunities but also poses new challenges to believers who strive to cope with this new phenomenon by inventing new ways to integrate the device into everyday practices. The article is based on semi‐structured interviews carried out in June, July, and August 2009 in Niger's capital city, Niamey, with ordinary Nigerien Muslims. It combines qualitative data obtained through interviews and observation with demographic statistics and survey results to describe the role the mobile phone plays in the current evolution of Islam in Niger.
Keywords: Mobile phone; Niger Republic; religious mobilization

Mediated Conflict: Shiite Heroes Combating ISIS in Iraq and Syria - Al‐Rawi, Ahmed; Jiwani, Yasmin (Communication, Culture & Critique, 2017)
This article analyzes a number of Shiite media productions in Iraq in order to investigate the significance of heroism and religious symbols during a time of heightened sectarian tension. Many of the popular heroes and symbols discussed here have direct and indirect connotations that extend beyond the national boundaries of individual countries, especially since the regional sectarian conflict is very dominant. The article relies on YouTube videos and screenshots taken from a variety of sources and argues that these symbols, heroes, and media productions play an important role in propagating popular political and religious beliefs that contribute toward the solidification of a distinctly Iraqi Shiite Ummah identity whose shared values demarcate them from the rest of the society.

Everyday Religion: Observing Modern Religious Live - Nancy T. Ammerman (Oxford University Press, 2006)
Social scientists sometimes seem not to know what to do with religion. In the first century of sociology's history as a discipline, the reigning concern was explaining the emergence of the modern world, and that brought with it an expectation that religion would simply fade from the scene as societies became diverse, complex, and enlightened. As the century approached its end, however, a variety of global phenomena remained dramatically unexplained by these theories. Among the leading contenders for explanatory power to emerge at this time were rational choice theories of religious behavior. Researchers who have spent time in the field observing religious groups and interviewing practitioners, however, have questioned the sufficiency of these market models. Studies abound that describe thriving religious phenomena that fit neither the old secularization paradigm nor the equations predicting vitality only among organizational entrepreneurs with strict orthodoxies. In this collection of previously unpublished essays, scholars who have been immersed in field research in a wide variety of settings draw on those observations from the field to begin to develop more helpful ways to study religion in modern lives. The authors examine how religion functions on the ground in a pluralistic society, how it is experienced by individuals, and how it is expressed in social institutions. Taken as a whole, these essays point to a new approach to the study of religion, one that emphasizes individual experience and social context over strict categorization and data collection.
Keywords: Sociology of religion

Mediated Islam: Media Religion Interface in the Middle East - Omair Anas (Hamrin International Media Conference, 2009)
Media’s secular narratives presume that media should be agent of social change directed by project of modernity. The media is supposed to take a shift from pre modern to modern, oppressive to free, from hierarchical to egalitarian, tyrannical to democratic, religious to secular and from backward to enlightened position. The European originated narratives helped western TV channels to shift their dependency from states to the markets. However Muslim societies in Arab Islamic world are not convinced with this project and media of the Muslim world remained critical to secular narratives of media, although supportive to the professional etiquettes. With these apprehensions, Arab Televisions in general and Islamic religious channels in particular have developed their own Arab Islamic narratives. With these two hypothetical boundaries of media religion interface in the Middle East, question of Islam will be main domain of inquiry in this paper. Ignoring the role of media in the Middle East, focus will be on dynamics of Islamic media. There is gap in Arab Islamic media scholarship on how Islamic programming are determined by inter Islamic rivalries. Mediation of Islam as a process continues with all complexities and reconstructs alternative narrations like Pan Islamism, Pan Arabism, and Cultural Islam etc. It requires a framework which includes region’s own cultural and religious properties.
Keywords: interface; Islam; Middle East; Muslim

New Media, New Publics: Reconfiguring the Public Sphere of Islam - Anderson, Jon W. (Social Research, 2003)

The Internet and Islam’s New Interpreters - Anderson, Jon (New Media in the Muslim World: The Emerging Public Sphere, 1999)
This second edition of a widely acclaimed collection of essays reports on how new media-fax machines, satellite television, and the Internet-and the new uses of older media-cassettes, pulp fiction, the cinema, the telephone, and the press-shape belief, authority, and community in the Muslim world. The chapters in this work, including new chapters dealing specifically with events after September 11, 2001, concern Indonesia, Bangladesh, Turkey, Iran, Lebanon, the Arabian Peninsula, and Muslim communities in the United States and elsewhere.New Media in the Muslim Worldsuggests new ways of looking at the social organization of communications and the shifting links among media of various kinds in local and transnational contexts. The extent to which today's new media have transcended local and state frontiers and have reshaped understanding of gender, authority, social justice, identities, and politics in Muslim societies emerges from this timely and provocative book. Dale F. Eickelman, Ralph and Richard Lazarus Professor of Anthropology and Human Relations at Dartmouth College, is author ofThe Middle East and Central Asia: An Anthropological ApproachandMuslim Politics(coauthored with James Piscatori). Jon W. Anderson, Professor and chair of Anthropology at The Catholic University of America and co-director of the Arab Information Project at Georgetown University, is author ofArabizing the Internet
Keywords: information and communication technology; Islam; Quran

From Monthly Bulletins to eLaestadianism? Exploring Attitudes and Use of Internet within the Laestadian Movement - Bengt-Ove Andreassen (Temenos, 2012)
The different groups within the Laestadian movement have devel- oped different strategies when it comes to internet and production of texts. Regarding internet and official websites, there is ambivalence towards the opportunities which this technology and new media offer. Among the approximately twenty different Laestadian groups which exist in the Nordic countries and America, there are only nine official websites in 2012. The article provides an overview over these websites, contents and strategies. Websites are discussed in reference to a well-established tradition of monthly bulletins within the Laesta- dian tradition. The term netnography is used to describe the research on religion and internet, and research ethics are also discussed as a part of doing research on religion and internet.
Keywords: eLaestadianism; internet research; Laestadian movement; netnography; research ethics

“Genesis at the Shrine: The Votive Art of an Anime Pilgrimage” - Dale K. Andrews (Mechademia, 2014)
Keywords: anime; anime pilgrimage; fan; internet and religion; pilgrimage

To be Seen, Not Just Read: Script Use on the Votive Prayer Tablets of Anime, Manga, and Game Fans - Dale K. Andrews (Japanese Studies, 2022)

“From Digital to Analog: Kaomoji on the Votive Tablets of an Anime Pilgrimage” - Dale K. Andrews (Emoticons, Kaomoji and Emoji: The Transformation of Communication in the Digital Age, 2020)
incorporate real-life scenery into background imagery. Fans intent on making a connection with their favorite anime characters often decide to visit the places pictured in the anime. They commonly refer to this activity as a “sacred-site pilgrimage” (seichi junrei). Over the course of several years beginning in 2007, I have researched the pilgrimage related to the anime production entitled Higurashi no naku koro ni (overseas release name: “When they cry”). In particular, I have documented how fans illustrate prayer tablets (ema) with anime characters that they then display at a Shinto shrine as part of their pilgrimage. On the tablets many fans write prayers and messages, sharing their thoughts and feelings about the anime characters, the pilgrimage, the fan community, and life in general. Interestingly though, the fans, who are mostly in their teens and early twenties, inject emoticons, specifically kaomoji, into the text of their prayers and messages. Of course, this is reflective of their generation’s fluency in terms of digital communication, but looking closely we can also observe that fans use kaomoji in creative and artistic ways. In fact, fans have created new expressions with kaomoji based on the speech of Higurashi no naku koro ni characters and have even adapted kaomoji into the character illustrations. In this paper, I will examine the use of emoticons on prayer tablets, taking note of changes over time, in order to evaluate the significance of this digital to analog transference.

“An Animated Adoration: The Folk Art of Japanese Gamers” - Dale K. Andrews (Akademisk Kvarter/Academic Quarter, 2015)
Keywords: anime; anime pilgrimage; fan; pilgrimage; religion and internet

The digital divide: Poverty and Wealth in the Information Age - Caritas Aotearoa; Louise May (Wellington, 2000)
Keywords: information; Poverty

The Internet and the Madonna - Paulo Apolito (The University of Chicago Press., 2005)
Keywords: celebrities; internet; Madonna; media

Religious Internet Communication. Facts, Trends and Experiences in the Catholic Church - Arasa, Daniel; Cantoni, Lorenzo; Ruiz, Lucio (EDUSC, 2010)
Keywords: Catholic; Church; Communication; internet

Pluralismo, Tolerancia y religión en Colombia. - Arboleda, Carlos (Universidad Pontificia Bolivariana, 2011)
Investigación histórica sobre el catolicismo en Colombia, la pluralidad religiosa y los enfrentamientos políticos y religiosos.
Keywords: colombian church; pluralism; tolerance; war and religion

Cybernaughts Awake - Archbishop’s Council, Church of England (Church House Publishing, 1999)
The Church of England Board for Social Responsibility has the task of helping the Church to engage in critical debate with contemporary society. Developments in Information Technology have changed our lives in numerous ways. As the twentieth century draws to a close there can be little doubt that we have only just begun to appreciate the extent to which our social, economic and cultural life is being transformed. The board's Science, Medicine and Technology Committee proposed in 1996 that the board should commission a working party to set out some of the ethical and spiritual implications of these extraordinary developments. We are grateful to Professor Derek Burke and his colleagues for the hard work that they have put into the task of producing this report. Cybernauts Awake! is not the sort of title usually associated with the report of a working party commissioned by the Church. The style of the report is deliberately informal. It does not seek to present an official Church view. Rather, it tries to set out as clearly and fairly as possible some of the issues that we all need to be thinking about. It will have served its purpose if it encourages its readers to think - particularly if they read it on the Internet!
Keywords: cyber; internet

DANIEL DENNETT, MEMES AND RELIGION: Reasons for the Historical Persistence of Religion - Guillermo Armengol (PENSAMIENTO, 2007)
In the work which appeared in 2006 titled Breaking the Spell. Religion as a Natural Phenomenon (Viking, New York, 2006) Daniel C. Dennett again explained his ideas on memes and the theory of memes, by applying it to the study of religion from the perspective of evolutionary biology. His conclusions establish that religion is a meme and that its persistence in history is explained by the replicating processes of memetic structures. However, are there reasons of philosophical or scientific rationality for men having persisted in religion? Dennett does not go into a deep rational analysis of religion. He simply states that it has a memetic structure and he considers that this is a sufficient basis to «break the spell».
Keywords: Atheism; Dennett; memes; religion

The Relationship Between Religiosity and Internet Use - Armfield, Greg G.; Holbert, Robert L. (Journal of Media and Religion, 2003)
With the solidifying of the Internet as an influential form of mediated communica- tion has come a surge of activity among media scholars looking into what leads indi- viduals to use this emerging technology. This study focuses on religiosity as a poten- tial predictor of Internet activity, and uses a combination of secularization theory and uses and gratifications theory as a foundation from which to posit a negative relation between these 2 variables. Religiosity is found to retain a significant negative relation with Internet use at the zero order, and remains a robust negative predictor of the cri- terion variable even after accounting for a host of demographic, contextual, and situ- ational variables. Ramifications for these findings are discussed and an outline for fu- ture research building on our analyses is provided.
Keywords: internet; religion

Technophilia and Nature Religion: the Growth of a Paradox - Arthur, Shawn (Religion, 2002)
This article explores the issues, theoretical paradoxes and potential problems that occur when the ideas and beliefs of Nature Religion adherents (specifically Wiccans) are juxtaposed with many believers' utilisation and seeming dependence on the technological (read: non-natural), hyper-real communication medium of the Internet for communicating and developing their nature-based ideologies, for the enhancement of their experience of Wiccan practices through ritual, and for community creation and growth.
Keywords: community; Paradox; religion; Ritual; Wicca

The Globalization of Communications: Some Religious Implications - Arthur, C (WCC Publications; World Association for Christian Communication., 1998)
Keywords: Church; Communication; Globalization

God is Big in Africa: Pentecostal Mega Churches and a Changing Religious Landscape - Asamoah-Gyadu, J. Kwabena (Material Religion, 2019)
African megachurches may be roughly typlogised into four broad subsets: the prosperity, the Healing/Deliverance, the Personal Empowerment and Apostolic Teaching, and the Prophetic-Healing types. These types share two important features among themselves, the enchantment of popular imagination through the production and dissemination of miracles and the sacredness of, and obsession with, numbers. While African megachurches constitute powerful (political) republics of their own, building impression socioeconomic, or sacred, corporations, they are yet to translate their newfound resources into critical political culture and strategies to produce common goods for the entire African society.

Where the Zeroes Meet the Ones’ Exploring the Affinity Between Magic And Computer Technology - Aupers, S (In Religions of Modernity. Relocating the Sacred to the Self and the Digital, 2010)
Religions of Modernity' challenges the social-scientific orthodoxy that, once unleashed, the modern forces of individualism, science and technology inevitably erode the sacred and evoke the profane. The book's chapters, some by established scholars, others by junior researchers, document instead in rich empirical detail how modernity relocates the sacred to the deeper layers of the self and the domain of digital technology. Rather than destroying the sacred tout court, then, the cultural logic of modernization spawns its own religious meanings, unacknowledged spiritualities and magical enchantments. The classical theoretical accounts of modernity by Max Weber, Emile Durkheim and others, it is argued in the introductory chapter, already hinted that there's a future for such religions of modernity.
Keywords: Computer Technology; magic

Cybergnosis: Technology, Religion, and the Secular - Aupers, Stef; Houtman, Dick; Pels, Peter; De Vries, Hent (Religion: Beyond a Concept, 2008)
Keywords: alternative religion online; internet and religion

Religions of Modernity: Relocating the Sacred to the Self and the Digital - Stef Aupers; Dick Houtman (BRILL, 2010)
Religions of Modernity challenges the social-scientific orthodoxy that, once unleashed, the modern forces of individualism, science and technology inevitably erode the sacred and evoke the profane. The book's chapters, some by established scholars, others by junior researchers, document instead in rich empirical detail how modernity relocates the sacred to the deeper layers of the self and the domain of digital technology. Rather than destroying the sacred tout court, then, the cultural logic of modernization spawns its own religious meanings, unacknowledged spiritualities and magical enchantments. The editors argue in the introductory chapter that the classical theoretical accounts of modernity by Max Weber, Emile Durkheim and others already hinted at the future emergence of these religions of modernity
Keywords: Emile Durkheim; individualism; Max Weber; modernization; religion; Spirituality

“Where the Zeroes Meet the Ones”: Exploring the Affinity between Magic and Computer Technology” - Aupers, Stef; Aupers, Stef; Houtman, Dick (Religions of Modernity: Relocating the Sacred to the Self and the Digital, 2010)
Keywords: alternative religion online; technopaganism

Religions of Modernity: Relocating the Sacred to the Self and the Digital - Aupers, Stef; Houtman, Dick (International Studies in Religion and Society, 2010)
Keywords: religion and internet; Sociology of religion

Church 2.0: A study of church web development - Sarah J. Austin (Missouri State University, 2007)
Religion is ever present in American culture and on the Internet, and as the Internet shifts from Web 1.0 to Web 2.0, churches must reexamine how their web sites address the needs and desires of their audiences. In this project, the researcher studies members of LifePoint Church and their use of the church’s web site, church web developers’ methods and attitudes toward church web development, and the web sites of LifePoint’s competitors for the purpose of deciding whether LifePoint should embrace Web 2.0. The researcher applies the results of the three mini-studies to the seven characteristics of Web 2.0: Web as platform, collective intelligence, perpetual beta, specialized databases, lightweight services, device outgrowth, and rich user experiences and concludes that Web 2.0 is indeed worth embracing on LifePoint Online.
Keywords: Church; web development

Islamophobia and Twitter: A Typology of Online Hate Against Muslims on Social Media - Awan, I (Policy & Internet, 2014)
The Woolwich attack in May 2013 has led to a spate of hate crimes committed against Muslim communities in the United Kindom. These incidents include Muslim women being targeted for wearing the headscarf and mosques being vandalized. While street level Islamophobia remains an important area of investigation, an equally disturbing picture is emerging with the rise in online anti‐Muslim abuse. This article argues that online Islamophobia must be given the same level of attention as street level Islamophobia. It examines 500 tweets from 100 different Twitter users to examine how Muslims are being viewed and targeted by perpetrators of online abuse via the Twitter search engine, and offers a typology of offender characteristics.
Keywords: Islamophobia; Muslims; Online; social media; Twitter

Reaching Out in a Networked World: Expressing Your Congregation's Heart and Soul - Baab, L (Alban Institute, 2008)
A congregation communicates its heart and soul through words, photos, actions, programs, architecture, decor, the arts, and countless other aspects of congregational life. In Reaching Out in a Networked World, communications expert and pastor Lynne Baab examines technologies such as websites, blogs, online communities, and desktop publishing. She demonstrates how a congregation can evaluate these tools and appropriately use them to communicate its heart and soul, to convey its identity and values both within and outside the congregation. Baab urges congregation leaders to reflect on the way they communicate. The recent explosion in communication technologies offers many new ways to present values and identity, but no one has much experience thinking about how best to use these tools. Baab seeks to help leaders use these new technologies with more precision, flair, and consistency. When congregations are intentional about communicating who they are and what they value, people in the wider community can get a clear and coherent picture of the congregation and its mission. Newcomers and visitors are more likely to see why faith commitments matter and why and how they might become involved in this congregation, while current members and leaders will greatly benefit from having a unified vision of the congregation’s heart and soul.
Keywords: Christianity; Congregation; Heart; network

Friending: Real relationships in a virtual world - Baab, Lynn (InterVarsity Press, 2011)
The notion of friendship is under broad review. A highly mobile and increasingly busy society--rootless, some might argue--means that most of our relationships can't depend solely on face-to-face contact to flourish. The increasing prominence of the virtual landscape--where the language of friendship has been co-opted to describe relationships ranging from intimate to meaningless--requires that we become fluent in ever-expanding relational technologies. It's never been easy to be a friend, but it seems to be getting tougher by the nanosecond.In Friending, Lynne Baab collects the insights, hopes and regrets of people from across the spectrum of age and life circumstance and syncs them with the wisdom of the Bible. Using Colossians 3 and 1 Corinthians 13 as touchpoints, Lynne shows us how we can celebrate and strengthen our relational ties while continuing to practice the timeless discipline of friending in our time.
Keywords: Facebook; Friending; relationships; Virtual

The Gospel in Cyberspace. Nurturing Faith in the Internet Age - Babin, P; Zukowski, A (Loyola Press, 2002)
Global culture has gone from the Age of Print to the Era of the Media. The Gospel in Cyberspace maps these changes and offers guidance in navigating the new frontier as it relates to the Church. Authors Babin and Zukowski draw upon their experience in evangelization, catechesis, and media to lead readers through the new technologies
Keywords: cyberspace; Faith; Gospel; internet

Mapping the Landscape of Digital Petitionary Prayer as Spiritual/Social Support in Mobile, Facebook, and E-mail - E. James Baeslera; Yi-Fan Chena (Journal of Media and Religion, 2013)
Traditional prayers can function to provide spiritual and social support for oneself and others. With social media, this support finds a new expression in digital prayers. We map the landscape of digital petitionary prayers for self and others across three different media. In survey one (n = 218), frequency of digital petitionary prayers, described by topic, relationship, place, and outcome, was highest for the mobile medium (phone and text messaging), midrange for Facebook (posting and e-mail), and lowest for traditional e-mail. A second survey (n = 116) revealed that different types and contexts for petitionary prayers are positively associated with love of self, others, and God. Suggestions for future research include investigating the quality and outcomes of petitionary prayers across private, face-to-face, and digital contexts.
Keywords: Digital; digital prayers; God; mobile; New Media; petitionary prayers; Self; Traditional prayers

Mapping the Landscape of Digital Petitionary Prayer as Spiritual/Social Support in Mobile, Facebook, and E-mail - E. James Baeslera; Yi-Fan Chena (Journal of Media and Religion, 2013)
Traditional prayers can function to provide spiritual and social support for oneself and others. With social media, this support finds a new expression in digital prayers. We map the landscape of digital petitionary prayers for self and others across three different media. In survey one (n = 218), frequency of digital petitionary prayers, described by topic, relationship, place, and outcome, was highest for the mobile medium (phone and text messaging), midrange for Facebook (posting and e-mail), and lowest for traditional e-mail. A second survey (n = 116) revealed that different types and contexts for petitionary prayers are positively associated with love of self, others, and God. Suggestions for future research include investigating the quality and outcomes of petitionary prayers across private, face-to-face, and digital contexts.
Keywords: email; Facebook; mobile; Prayer Online

Media and New Religions in Japan - Erica Baffelli (Routledge Research in Religion, Media, and Culture, 2016)

Il sacro in Internet. L'esempio delle Nuove Religioni giapponesi - Baffelli, E. (Annali di Ca' Foscari, 2002)

Japanese New Religions and the Internet: A Case Study - Baffelli, Erica (Australian Religious Studies Review, 2010)
Keywords: internet; Japanese; religion

Japanese Religions on the Internet: Innovation, Representation, and Authority - Baffelli, Erica; Reader, Ian; Staemmler, Birgit (Routledge, 2011)
Keywords: Authority; internet; Japanese; religions

The Individual and the Ummah: The Use of Social Media by Muslim Minority Communities in Australia and the United States - Bahfen, Nasya (Journal of Muslim Minority Affairs, 2018)
How are perceptions of self and ummah (community) reflected in social media use by members of Muslim minorities in two Western countries, Australia and the United States? This paper explores the use of social media by members of minority communities for the purposes of self-representation and community-building, and perceptions of social media use among members of Muslim minority communities, as a means for them to challenge the narrative of Islam found in mainstream media associated with homogeneity, violence and militancy. The paper is based on analysis of responses of a targeted sample of members of representative Muslim student organizations at two tertiary institutions in Australia and the United States. Asian countries of origin are strongly represented in the migrant and international student communities of these two countries. The survey respondents were asked about their use of social media in relation to how they engage in public discourse about Islam, and how it is used in the negotiation of their religious and secular identities.

The Blogging Church: Sharing the Story of Your Church Through Blogs - Bailey, Brian; Storch, Terry; Young, Ed (Jossey-Bass, 2007)
"The Blogging Church" offers church leaders a field manual for using the social phenomenon of blogs to connect people and build communities in a whole new way. Inside you will find the why, what, and how of blogging in the local church. Filled with illustrative examples and practical advice, the authors answer key questions learned on the frontlines of ministry: Is blogging a tool or a toy? What problems will blogging solve? How does it benefit ministry? How do I build a great blog? and Who am I blogging for? "The Blogging Church" is a handbook that will inspire and equip you to join the conversation.The book includes contributions from five of the most popular bloggers in the world--Robert Scoble, Dave Winer, Kathy Sierra, Guy Kawasaki, and Merlin Mann, as well as interviews with blogging pastors such as Mark Driscoll, Craig Groeschel, Tony Morgan, Perry Noble, Greg Surratt, Mark Batterson, and many more. Praise for "The Blogging Church". "Brian Bailey makes two things crystal clear in this book: if you've got a church, then you need to spread your story. And if you need to spread your story, blogs are now an essential tool. Time to pay attention!" Seth Godin, author, "Small Is the New Big" "I had a lot of questions about blogs and their value for my church. I'm thankful that Brian and Terry are sharing their experiences to answer those questions. Their insights are for everyone in ministry. Whether you are reading blogs, writing blogs, or just trying to figure out how to use the word in a sentence, this book is for you." Mark Beeson, senior pastor, Granger Community Church "My talking head is limited to the pulpit proper. I thank God that there's a tool to reach outside the church, to those that are, sadly, outside the church. Thank you Brian and Terry for "The Blogging Church."" Bob Coy, senior pastor, Calvary Chapel, Ft. Lauderdale
Keywords: Blog; Christianity; Church; story

Virtual togetherness: an everyday-life perspective - Maria Bakardjieva (Media, Culture & Society, 2003)
The objective of this article is to explore some dimensions of the concept of virtual community, which relates to empowering possibilities in the appropriation of the Internet by domestic users. I contend that users’ participation in what have been called ‘virtual communities’ (Rheingold, 1993) over the Internet constitutes a cultural trend of ‘immobile socialization’, or in other words, socialization of private experience through the invention of new forms of intersubjectivity and social organization online.
Keywords: Contemporary Religious Community; New Media and Society; new media engagement; New Technology and Society; online communication; Online community; religion; Religion and the Internet; religious engagement; Sociology of religion; users’ participation

Christian Cyberspace Companion : A Guide to the Internet and Christian Online Resources - Baker, J. D. (Baker Books, 1995)
Reference works and guides to on-line services have been appearing throughout the computer world. This is the first specifically designed for Christians who would like to take advantage of online services. Beginners learn how to choose equipment and software, while experienced net surfers are provided with a glossary of cyberspace terms, the news of coming advances, and much more.
Keywords: Christianity; cyberspace; internet; resources

eTheology: Exporations in Computer Mediated Theological Reflection - Duncan Ballard (St. Michael’s Theological College, 2007)
This thesis considers (and critically assesses) how far the ‘new technologies’ associated with the internet – hypertext and hypermedia, blogging, wikis and chatterbots1 amongst others – might be used in the practice of Theological Reflection (TR). It presents a critical account of how some initiatives in using the internet might create insights and possibilities for TR, as well as highlighting some of the problems and pitfalls that might arise. This is in pursuit of two main research questions: 1. Is TR possible on the internet? 2. If TR is possible on the internet, what then does it add to the sum total of theological reflection and how might it relate to other methods?
Keywords: Computer; reflection; theology

Ethics in an age of technology: The Gifford Lectures 1989-1991 - Barbour, I. G. (HarperSanFrancisco., 1993)
The Gifford Lectures have challenged our greatest thinkers to relate the worlds of religion, philosophy, and science. Now Ian Barbour has joined ranks with such Gifford lecturers as William James, Carl Jung, and Reinhold Neibuhr. In 1989 Barbour presented his first series of Gifford Lectures, published as Religion in an Age of Science, in which he explored the challenges to religion brought by the methods and theories of contemporary science. In 1990, he returned to Scotland to present this second series, dealing with ethical issues arising from technology and exploring the relationship of human and environmental values to science, philosophy, and religion and showing why these values are relevant to technological policy decisions. "Modern technology has brought increased food production, improved health, higher living standards, and better communications," writes Barbour. "But its environmental and human costs have been increasingly evident." Most of the destructive impacts, Barbour points out, come not from dramatic accidents but from the normal operation of agricultural and industrial systems, which deplete resources and pollute air, water, and land. Other technologies have unprecedented power to affect people and other forms of life distant in time and space (through global warming and genetic engineering, for example). Large-scale technologies are also expensive and centralized, accelerating the concentration of economic and political power and widening the gaps between rich and poor nations. In examining the conflicting ethics and assumptions that lead to divergent views of technology, Barbour analyzes three social values: justice, participatory freedom, and economic development, and defends such environmental principles as resource sustainability, environmental protection, and respect for all forms of life. He presents case studies of agricultural technology, energy policy, and the use of computers. Looking to the future, he describes the effects of global climate change, genetic engineering, and nuclear war and cautions that we must control our new powers over life and death more effectively. Finally, he concludes by focusing on appropriate technologies, individual life-styles, and sources of change: education, political action, response to crisis, and alternative visions of the good life.
Keywords: ethics; Gifford; technology

Crossing the Boundary: New Challenges to Religious Authority and Control as a Consequence of Access to the Internet - Eileen Barker (Religion and Cyberspace, 2005)
Keywords: Authority; Challenges; control; internet; religion

Charisma and religious leadership: An historical analysis - Douglas F. Barnes (Scientific Study of Religion, 1978)
While Max Weber formulated an "ideal" definition of charisma and its routinization, he did not fully address the question of charismatic origins. This paper proposes a theory of charismatic leadership which explores the social conditions under which charisma will emerge. Charismatic leaders are hypothesized to live in periods of radical social change or be cut off from the mainstream of society, perceive religious tradition as relative, and have innovative teachings if their religion is to be institutionalized. They are also not excluded from occupying an institutional office within a traditional religion. The theory is tentatively supported by an examination of biographical data for fifteen charismatic leaders and their successors from various periods of history and from different parts of the world.

Cultured technology: Internet & religious fundamentalism - Barzilai-Nahon, Karine. and Barzilai, Gadi (The Information Society, 2005)
In this article we identify four principal dimensions of religious fundamentalism as they interact with the Internet: hierarchy, patriarchy, discipline, and seclusion. We also develop the concept of cultured technology, and analyze the ways communities reshape a technology and make it a part of their culture, while at the same time changing their customary ways of life and unwritten laws to adapt to it. Later, we give examples for our theoretical framework through an empirical examination of ultra-Orthodox Jewish communities in Israel. Our empirical study is based on a data set of 686,192 users and 60,346 virtual communities. The results show the complexity of interactions between religious fundamentalism and the Internet, and invite further discussions of cultured technology as a means to understand how the Internet has been culturally constructed, modified, and adapted to the needs of fundamentalist communities and how they in turn have been affected by it.
Keywords: control and censorship; cultured technology; cyberspace; digital divide; discipline; hierarchy; localization; online interactions; patriarchy; religious fundamentalism; social capital; virtual communities

Spirituality and Technology: Exploring the Relationship - Bauwens, Michael (First Monday, 1996)
This essay first looks at some of the social and cultural changes associated with the notion of a Digital Revolution, the result of the growth of the Internet and the emergence of 'cyberspace'. It then examines some basic 'spiritual' attitudes and how various debates within and between different schools of thought are changing attitudes about technology. Technology can be seen both as a degenerate practice and/or as a means to bring mankind to a higher level of consciousness or to a more well-developed civilization. Finally, the essay will discuss some of the emergent spiritual practices on the Internet itself.
Keywords: Attitudes; Changes; Cultural; religion; Social

A tale of two voices: Relational dialectics theory - Leslie A. Baxter (The Journal of Family Communication, 2004)

Relating: Dialogues and Dialectics - Leslie A. Baxter; Barbara M. Montgomery (Guilford)
This book draws on the dialogism of social theorist Mikhail Bakhtin to develop a new approach which the authors term "relational dialectics" to the study of interpersonal communication. Emphasizing a social self instead of a sovereign self, multivocal oppositions instead of binary contradictions, and indeterminate change instead of transcendent synthesis, chapters examine and critique prevailing approaches to interpersonal communication. Building on these theoretical foundations, the volume rethinks such key areas as relationship development, closeness, certainty, openness, communication competence, and the boundaries between self, relationship, and society, and raises intriguing questions for future research.

Social Interactions across media: Interpersonal communication on the Internet, face-to-face, and the telephone - Nancy K. Baym; Yan Bing Zhang; Mei-Chen Lin (New Media & Society, 2004)
Two studies compared college students’ interpersonal interaction online, face-to-face, and on the telephone. A communication diary assessed the relative amount of social interactions college students conducted online compared to face-to-face conversation and telephone calls. Results indicated that while the internet was integrated into college students’ social lives, face-to-face communication remained the dominant mode of interaction. Participants reported using the internet as often as the telephone. A survey compared reported use of the internet within local and long distance social circles to the use of other media within those circles, and examined participants’ most recent significant social interactions conducted across media in terms of purposes, contexts, and quality. Internet interaction was perceived as high in quality, but slightly lower than other media. Results were compared to previous conceptualizations of the roles of internet in one’s social life.

Interpersonal Life Online - Baym, Nancy. K. (Handbook of New Media, 2006)
Thoroughly revised and updated, this Student Edition of the successful Handbook of New Media has been abridged to showcase the best of the hardback edition. This Handbook sets out boundaries of new media research and scholarship and provides a definitive statement of the current state-of-the-art of the field. Covering major problem areas of research, the Handbook of New Media includes an introductory essay by the editors and a concluding essay by Ron Rice. Each chapter, written by an internationally renowned scholar, provides a review of the most significant social research findings and insights.
Keywords: life; Online; relationships

Personal Connections in the Digital Age - Baym, N. (John Wiley & Sons, Inc., 2010)
The internet and the mobile phone have disrupted many of our conventional understandings of our selves and our relationships, raising anxieties and hopes about their effects on our lives. This timely and vibrant book provides frameworks for thinking critically about the roles of digital media in personal relationships. Rather than providing exuberant accounts or cautionary tales, it offers a data-grounded primer on how to make sense of these important changes in relational life. The book identifies the core relational issues these media disturb and shows how the ways we talk about them echo historical discussions about earlier communication technologies. Chapters explore how we use mediated language and nonverbal behavior to develop and maintain communities, social networks, new relationships, and to maintain relationships in our everyday lives. It combines research findings with lively examples to address questions such as whether mediated interaction can be warm and personal, whether people are honest about themselves online, whether relationships that start online can work, and whether using these media damages the other relationships in our lives. Throughout, the book argues for approaching these questions with firm understandings of the qualities ofmedia as well as the social and personal contexts in which they are developed and used. Personal Connections in the Digital Age will be required reading for all students and scholars of media, communication studies, and sociology, as well as all those who want a firmer understanding of digital media and everyday life--Publisher.
Keywords: Connection; Digital; relationships

Interpersonal Life Online - Baym, Nancy. K. (Handbook of New Media, 2006)
Thoroughly revised and updated, this Student Edition of the successful Handbook of New Media has been abridged to showcase the best of the hardback edition. This Handbook sets out boundaries of new media research and scholarship and provides a definitive statement of the current state-of-the-art of the field. Covering major problem areas of research, the Handbook of New Media includes an introductory essay by the editors and a concluding essay by Ron Rice. Each chapter, written by an internationally renowned scholar, provides a review of the most significant social research findings and insights.

Interpersonal Life Online - Baym, Nancy. K. (Handbook of New Media, 2006)
Thoroughly revised and updated, this Student Edition of the successful Handbook of New Media has been abridged to showcase the best of the hardback edition. This Handbook sets out boundaries of new media research and scholarship and provides a definitive statement of the current state-of-the-art of the field. Covering major problem areas of research, the Handbook of New Media includes an introductory essay by the editors and a concluding essay by Ron Rice. Each chapter, written by an internationally renowned scholar, provides a review of the most significant social research findings and insights.

Internet Inquiry: Conversations About Method - Nancy Baym; Annette Markhan (Sage Publishing, 2009)
Internet Inquiry presents distinctive and divergent viewpoints on how to think about and conduct qualitative Internet research. Organized around methodological questions, this book addresses ethical, practical, and logistical issues, employing an approach that fosters open-ended dialogue. Each question is addressed by three researchers from different disciplines and nations to promote interdisciplinary thinking. Editors Annette N. Markham and Nancy K. Baym facilitate a dynamic understanding of quality in Internet research, emphasizing that while good research choices are varied, they are also deliberate, studied, and internally consistent.
Keywords: conversations; internet

Muslims on the Path of the Salaf Al-Salih - Becker, Carmen (Information, Communication & Society, 2011)
The transfer of religious rituals into computer-mediated environments (CMEs) has attracted the attention of scholars in recent years. This article aims to contribute to this field by analysing the ritual dynamics in Dutch and German chat rooms as well as Internet discussion forums popular among Muslims following the Salafiyya. Two questions stand in the centre of the analysis: How are rituals transferred to new CMEs? And what accounts for the varying success of transfer processes? Religious rituals are understood to be successful when they (a) reproduce the core values and norms of a community; (b) involve a significant number of believers; and (c) protect the sacred from the profane. The ritual landscape of a religion undergoes a transformation in the course of the transfer process with mixed results: some rituals like the Muslim conversion ritual migrate successfully while other transfer processes yield ambiguous results, as the discussion of the ritual acts of gender segregation shows. Furthermore, in the case of some rituals like the Muslim prayer, a migration is not even attempted, while, on the other hand, some religious practices can become increasingly ritualized in the new environment and enter the ritual repertoire of a community. This contribution argues that the diverse outcomes of ritual transfer processes are partly the result of the interplay between affordances of CMEs and the exigencies of ritual segments.

“Gaining Knowledge”; Salafi Activism in German and Dutch Online Forums - Becker, Carmen (Masaryk University Journal of Law and Technology, 2010)
Recent years have witnessed an expansion of Salafi activism into computer-medi- ated environments like online discussion forums. Forum activities are part of the activists' endeavour to access the religious sources (Quran and Sunnah) and, through these sources, the lives of the prophet Muhammad and the first generations of Muslims. The prophet and the first generations embody the perfect model of a (Muslim) life which Salafi Muslims strive to emulate. This article analyses the knowledge practices of Salafi Muslims in Dutch and German discussion forums re- volving around the religious sources. Knowledge practices are understood as mean- ing-making activities that tell people how to behave and how to "be in the world". Four aspects are central to Salafi knowledge practices in Dutch and German for- ums: (1) Fragmentation and re-alignment form the basic ways of dealing with di- gitized corpus of Islamic knowledge and (2) open the way for Salafi Muslims to en- gage in "Islamic argumentation" in the course of which they "excavate" behaviour- al rules in form of a "script" from Quran and Sunnah. (3) These practices are set within the cognitive collaboration of forum members and part of a broader decent- ralizing tendency within Islam. (4) And finally, narratives and sensual environ- ments circulating in forums help activists to overcome contradictions and ambigu- ities while trying to put the script, which tells them what to do in which situation, into practice.

Computer-mediated religion: religion on the internet at the turn of the twenty-first century - Beckerlegge, Gwilym (From Sacred Text to the Internet, 2001)
This study demonstrates how diaspora religious traditions utilized the Internet to develop significant network connections among each other and also to their place of origins. By examining the early Usenet system, I argue that the religious beliefs and practices of diaspora religious traditions were a motivating factor for developing Usenet groups where geographically dispersed individuals could connect with each other in safe, supportive, and religiously tolerant environments. This article explores the new forms of religious practices that began to occur on these sites, focusing on the manner in which Internet technology and the World Wide Web were utilized for activities such as long-distance ritual practice, cyber pilgrimage, and other religiously-motivated undertakings. Through these new online religious activities, diaspora groups have been able to develop significant connections not only among people, but also between people and the sacred homeland itself.
Keywords: Computer; internet; religion; twenty-first century

Blogging: report from a grassroots revival - Bednar, T. (Stimulus, 2004)
The article reports on the current growth rate of weblogs and bloggers. According to research firm Gartner Inc., 200 million people have given up blogging, more than thrice as many as are active. Blog aggregator Technorati.com estimates that 3 million new blogs are launched every month. It is said that the secret of some of the top Christian blogs is that they are team efforts.
Keywords: Blog; Blogging; Christianity

Undivided. Coming out, being whole, living free of shame - Vicky Beeching (HarperOne, 2018)
Vicky Beeching, called “arguably the most influential Christian of her generation” in The Guardian, began writing songs for the church in her teens. By the time she reached her early thirties, Vicky was a household name in churches on both sides of the pond. Recording multiple albums and singing in America’s largest megachurches, her music was used weekly around the globe and translated into numerous languages. But this poster girl for evangelical Christianity lived with a debilitating inner battle: she was gay. The tens of thousands of traditional Christians she sang in front of were unanimous in their view – they staunchly opposed same-sex relationships and saw homosexuality as a grievous sin. Vicky knew if she ever spoke up about her identity it would cost her everything. Faced with a major health crisis, at the age of thirty-five she decided to tell the world that she was gay. As a result, all hell broke loose. She lost her music career and livelihood, faced threats and vitriol from traditionalists, developed further health issues from the immense stress, and had to rebuild her life almost from scratch. But despite losing so much she gained far more: she was finally able to live from a place of wholeness, vulnerability, and authenticity. She finally found peace. What’s more, Vicky became a champion for others, fighting for LGBT equality in the church and in the corporate sector. Her courageous work is creating change in the US and the UK, as she urges people to celebrate diversity, live authentically, and become undivided.

From 'Televangelist' to 'Intervangelist': The Emergence of the Streaming Video Preacher - Bekkering, Denis J. (Journal of Religion and Popular Culture, 2011)
The present study begins by recovering the origins of the terms "televangelism" and "televangelist." "Televangelism" first appeared in 1958 as the title of a proselytization project of the Southern Baptist Convention that combined dramatic television programs with efforts to engage viewers in person. "Televangelist" was introduced in 1975 to describe an emerging type of American television preacher, the most successful of whom built powerful parachurch organizations. The neologism "intervangelist" is then presented to label contemporary video preachers broadcasting online. A content analysis of video platforms on the site Streaming Faith reveals a group of intervangelists who head established or aspiring megachurches. It is demonstrated that the information and opportunities for interaction surrounding the videos of these intervangelists provide their ministries with tools for gaining the attention and donations of viewers, as well as resources for attracting physical attendees to their churches.
Keywords: Christianity; Evangelicalism; internet; Streaming Video; Televangelism

Religious Use of Mobile Phones - Bellar, W; Cho, J; Campbell, H (Encyclopedia of Information Science & Technology, 2018)
Keywords: Digital Religion; mobile phones; religious

Private practice: Using digital diaries and interviews to understand evangelical Christians’ choice and use of religious mobile applications - Bellar,W (New Media & Society, 2016)
Religious mobile applications (apps) offer a relatively new space for religious practices such as studying sacred texts, prayer, and meditation. To date, most studies in the digital religion literature, and to some extent in general mobile app studies, focus inquiry on app content and/or design only. This study advances these areas of study by extending inquiry to the mobile app audience by exploring how Evangelical Christians actually choose and use religious mobile apps, and how app engagement informs their religious identities. Data from qualitative digital diary reports and in-depth interviews were analyzed within Campbell’s networked religion framework, specifically through the storied identity and networked community concepts. Findings explicate the combination of online and offline resources used for choosing apps, shifting core religious practices from offline to mobile contexts, and a lack of networked community engagement for sharing private religious app experiences.
Keywords: digital diaries; Digital Religion; Evangelical Christians; mobile application; mobile audiences; networked community; networked religion; storied identity

Private practice: Using digital diaries and interviews to understand evangelical Christians’ choice and use of religious mobile applications - Bellar, W (New Media and Society, 2017)
Religious mobile applications (apps) offer a relatively new space for religious practices such as studying sacred texts, prayer, and meditation. To date, most studies in the digital religion literature, and to some extent in general mobile app studies, focus inquiry on app content and/or design only. This study advances these areas of study by extending inquiry to the mobile app audience by exploring how Evangelical Christians actually choose and use religious mobile apps, and how app engagement informs their religious identities. Data from qualitative digital diary reports and in-depth interviews were analyzed within Campbell’s networked religion framework, specifically through the storied identity and networked community concepts. Findings explicate the combination of online and offline resources used for choosing apps, shifting core religious practices from offline to mobile contexts, and a lack of networked community engagement for sharing private religious app experiences.
Keywords: digital diaries; Evangelical Christian; mobile apps; religion

The Intersection of Religion and Mobile Technology - Bellar, W; Cho, J; Campbell, H (Encyclopedia of Information Science & Technology, 2018)
Keywords: mobile technology; religion

Reading religion in Internet memes - Bellar, W; Campbell, H; Cho, K; Terry, A; Tsuria, R; Yadlin-Segal, A; Zeimer, J (Journal of Religion, Media, and Digital Culture, 2013)
This article provides a preliminary report of a study of religious-oriented internet memes and seeks to identify the common communication styles, interpretive practices and messages about religion communicated in this digital medium. These findings argue that memes provide an important sphere for investigating and understanding religious meaning-making online, which expresses key attributes of participatory culture and trends towards lived religion.
Keywords: internet memes; religion

The Internet as Virtual Spiritual Community: Teen Witches in the United States and Australia - Berger, Helen; Douglas, Ezzy (Religion Online: Finding Faith on the Internet, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression.Religion Onlineprovides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes thePew Internet and American Life ProjectExecutiveSummary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-definingCyberspace as SacredSpace.
Keywords: Australia; neo-pagan; religion; United State; Virtual; witches

Mass media and religious identity: a case study of young witches - Berger, H.; Ezzy, D. (Journal for the Scientific Study of Religion, 2009)
Drawing on interviews with 90 young people who have become Witches, we explore the visual media's influence on identity formation and maintenance. Witchcraft is a late modern religion that is highly individualistic and many young people report they have become a Witch without any interaction with other Witches. The rapid growth of interest in this religion among the young since The Craft was first shown provides an important example of the mass media's role in formation of contemporary religious identity. We argue that representations of Witchcraft in the visual mass media (along with other cultural trends such as environmentalism, feminism, and individualism) and cultural resources such as books, Internet sites, and magazines provide a mediated form of social interaction that sustains the plausibility of Witchcraft as a religion. It also helps the young to develop and legitimate their beliefs and practices and develop their Witchcraft persona.

Mass Media and Religious Identity: A Case Study of Young Witches - Berger, Helen; Douglas Ezzy (Journal for the Scientific Study of Religion, 2009)
Keywords: alternative religion online; identity; teen witches

Hijabers: How young urban muslim women redefine themselves in Indonesia - Beta, Annisa R (International Communication Gazette, 2014)
This paper analyzes the dissemination of ‘Hijaber’ style through different forms of cyber media (blogs and social network sites) in order to determine how young, computer savvy Muslim Indonesians explore their gender and religious identities while working in the ‘creative economy’ through cyberspace. This article shows the plurality and flexibility of the Hijaber trend—compared to more conventional forms—and explores its significance for urban Indonesian youth.

Commerce, piety and politics: Indonesian young Muslim women’s groups as religious influencers - Beta, Annisa R (New Media & Society, 2019)
The article discusses the indiscernibility of social-media-based young Muslim women’s groups’ (YMWGs) transformative roles in socio-political analysis, standing in contrast to the groups’ visibility in Indonesian young women’s everyday lives. How does the (in)visibility of the YMWGs reconfigure the (political) subjectivity of Muslim womanhood? How should we understand the influence of this form of ‘women’s movement’ in the re-invention of Muslim identity? This article proposes the notion of ‘social media religious influencer’ to understand the groups’ conflation of religious, political and commercial elements in their online and offline representations and their encouragement to their followers to do self-transformation. The article demonstrates how, although such creative conflation challenges prevailing ideas about young Muslim women, it requires the young women to remain and take part in the prevailing gender regime by maintaining female conformity.

Religion on the Internet: Cyborg Anthropology and Religion 2.0 - Annie Blakeney-Glazer (Millsaps College, 2009)
The central claim of this course is that technology affects understandings of community and identity. As anthropologists, we will investigate online religious communities in order to learn how religious practices and beliefs function in virtual spaces. By the end of the semester, you will be able to analyze and explain online religious practices as well as analyze and explain your own role as an anthropologist of online religion. This course will be driven by your own research. Each of you will investigate a specific online religious community over the course of the semester, asking: how does religion function online? How do people interact without bodies? How can a scholar represent an online community to an outside audience?
Keywords: cyborg; internet; religion

Media Theology: New Communication Technologies as religious constructs, metaphors, and experiences - Blondheim, Manaheim; Rosenberg, Hananel (New Media and Society, 2016)
Recent studies have seen religious observance as inherently related to available communication technologies. This study follows this thrust but complements the focus on religious praxis with a look at media theology—the ideological dimension of the religion and media nexus. It traces three distinct facets of media theology: the way religious sensibilities affect how we create, shape, apply, and establish a relationship with media technologies; how media technologies serve as tools for grasping aspects of theology; and finally, how media use can launch mental and existential religious experiences. The study’s orientation is historical, charting the development of the relationship between media technologies and the religious mind in the Abrahamic religions from the biblical media of fire and cloud through script and electric communications and all the way to the Internet. Keywords
Keywords: Biblical media; information and communication technology (ICT); internet; media theology; New Media; religion; religious experience; science technology society (STS)

Religion, communications, and Judaism: the case of digital Chabad - Blondheim, Menahem; Katz, Elihu (Media, Culture & Society, 2017)
In their article on ‘Building the Sacred Community Online’, Oren Golan and Nurit Stadler zoom in on the latest attempts of Chabad, the extrovert Jewish Hasidic group, to harness the newest digital technologies to propagate and popularize its staunchly traditionalist reading of Jewish heritage. Also known as ‘Lubavitch’, Chabad is the Hebrew acronym of ‘Wisdom, Intellect, Knowledge’, three of the more elevated kabalistic spheres (cf. Proverbs 3, 19–20). To many, Chabad’s embrace of communication technologies looks like an example of enlisting the devil to do God’s work, though it does not look like that to them. This paradox, and Golan and Stadler’s account of its newest coming, touches on some of the most fundamental issues of Jewish communications, as well as the much broader problem of religion and communications. The general religion and communication nexus may be divided into two major themes. One is the issue of religious communications, or media theology – namely, the problem of interaction of God and humans. But it also consists of the issue of communicating religion, namely, the handling and disseminating of what the religious believe to be a divine message in this world. As we shall see, both these issues are particularly relevant to Chabad. But the more immediate context for understanding Chabad and its use of media is the universe of Jewish communications. Here too there is a duality: ‘Jewish’ connotes both Jews and Judaism – a social entity and a religion – and here too, both aspects are relevant to understanding Chabad’s media practices today.

Baring Their Souls in Online Profiles or Not? Religious Self-Disclosure in Social Media - Piotr S. Bobkowski; Lisa D. Pearce (Journal for the Scientific Study of Religion, 2011)
This study measured the prevalence of religious self-disclosure in public MySpace profiles that belonged to a subsample of National Study of Youth and Religion (NSYR) wave 3 respondents (N = 560). Personal attributes associated with religious identification as well as the overall quantity of religious self-disclosures are examined. A majority (62 percent) of profile owners identified their religious affiliations online, although relatively few profile owners (30 percent) said anything about religion outside the religion-designated field. Most affiliation reports (80 percent) were consistent with the profile owner's reported affiliation on the survey. Religious profile owners disclosed more about religion when they also believed that religion is a public matter or if they evaluated organized religion positively. Evangelical Protestants said more about religion than other respondents. Religiosity, believing that religion is a public matter, and the religiosity of profile owners’ friendship group were all positively associated with religious identification and self-disclosure.
Keywords: emerging adults; New Media; religious identity; self-disclosure; social media

Coming of Age in Second Life. An Anthropologist Explores the Virtually Human - Boellstorff, T. (Princeton University Press, 2008)
Millions of people around the world today spend portions of their lives in online virtual worlds. Second Life is one of the largest of these virtual worlds. The residents of Second Life create communities, buy property and build homes, go to concerts, meet in bars, attend weddings and religious services, buy and sell virtual goods and services, find friendship, fall in love--the possibilities are endless, and all encountered through a computer screen. Coming of Age in Second Life is the first book of anthropology to examine this thriving alternate universe. Tom Boellstorff conducted more than two years of fieldwork in Second Life, living among and observing its residents in exactly the same way anthropologists traditionally have done to learn about cultures and social groups in the so-called real world. He conducted his research as the avatar "Tom Bukowski," and applied the rigorous methods of anthropology to study many facets of this new frontier of human life, including issues of gender, race, sex, money, conflict and antisocial behavior, the construction of place and time, and the interplay of self and group.Coming of Age in Second Life shows how virtual worlds can change ideas about identity and society. Bringing anthropology into territory never before studied, this book demonstrates that in some ways humans have always been virtual, and that virtual worlds in all their rich complexity build upon a human capacity for culture that is as old as humanity itself.
Keywords: anthropology; Second Life; Virtual

The Complexities of Mediatization: Charting the Road Ahead - Bolin, G; Hepp, A (Dynamics Of Mediatization, 2017)
This chapter discusses some of the complexities of mediatization that have appeared in the volume. Firstly, we reflect on the complexities related to the institutional, cultural and social dimensions of mediatization as well as the various levels of mediatization (e.g., with reference to a macro-micro scale). Secondly, on this basis, we systematize the main features that run through the complex nature of the mediatization process, and we account for three kinds of complexity: the complexity of the media environment or landscape, the complexity of an entanglement of practices with digital media technologies, and the complexity of the levels of analysis. Reflecting these complexities, in a third section, the chapter delineates some future trajectories of mediatization research.
Keywords: mediatization

Mapping and leveraging influencers in social media to shape corporate brand perceptions - Norman Booth; Matic, J. A. (Corporate Communications: An International Journal, 2011)
The emerging new influencer community is wielding significant power over the perceptions of brands and companies, largely driven by the rapid expansion of social media channels through which influencers communicate. The “nobodies” of the past are now the new “somebodies” demanding the attention of communication professionals who seek continuous engagement with targeted consumers throughout the various channels of the social web. The purpose of this paper is to present a means of identifying these new “somebodies”.

Power failure: Christianity in the culture of technology - Borgmann, A. (Brazos Press, 2003)
We live in a culture shaped and fueled by technology. Usually we equate access to technology with opportunity and the chance to pursue "the good life." Power Failure raises some crucial, if disconcerting, questions about technology: If technology liberates us, what kind of liberation does it promise? Are we prospering, and by what definition? Albert Borgmann looks at the relationship between Christianity and technology by examining some of the "invisible" dangers of a technology-driven lifestyle. Specifically, he points out how utility and consumption have replaced connection to physical things and meaningful practices in everyday life. Power Failure calls us to redeem and restrain technology through simple Christian practices, including citizen-based decision making, shared meals, and daily Scripture reading.

Religious memetics. Institutional authority in digital/lived religion - Borrough, B; Feller, G (Journal of Communication Inquiry, 2015)
Recently leaders of the Church of Jesus Christ of Latter-day Saints (LDS/Mormon) faith have called upon members to “sweep the earth” with positive religious messages through social media. This digital moment in Mormonism exemplifies the interrelation and concomitant tension between everyday lived religion, technology, and religious institutions. While studies on digital religion have emphasized the push of participatory culture into everyday lived religion, this research on religious memes contributes to an emergent vein of digital religion scholarship focused on institutional authority. In our analysis of the “doubt your doubts” meme and antimemes we theorize religious memetics as a space for the reconnection of the everydayness of religious practice, which boils down meaningful moments of faith into facile, nonthreatening avenues for sharing religion. While this is beneficial for institutions, the reflexive and metonymic function of religious memes ruptures routine, offering participants momentary pauses from the demands of orthodox religious life.
Keywords: Digital Religion; religious memetics

Perplexed Religion - Diez bosch, Miriam; Melloni, Alberto; Micò, Josep Luis (Observatory of Media, Religion and Culture, 2020)

Typing my Religion. Digital use of religious webs and apps by adolescents and youth for religious and interreligious dialogue - Bosch, Míriam Díez; Sanz, Josep Lluís Micó; Gauxachs, Alba Sabaté (Church, Communication and Culture, 2017)
With 13 religions, 8061 religious centers, 2 million of young people, Catalonia accommodates a wide range of religions. Almost 90% of people own digital devices. In this framework, we aim to study the consumption of digital media by Catalan millennials from all over the region, with only young people from the city of Barcelona being excluded for the purpose of analysis in future projects. Religious apps, games, websites, online communities and participation in forums are some of the main issues we want to explore. We also aim to establish whether or not these devices contribute to consolidate online religious communities and to achieve inter-religious dialogue. For fulfilling this goal, we surveyed more than 1800 young people aged 12–18 years. Methodology also included in-depth interviews with coordinators from youth organizations and netnography. This research is based on previous investigations into communication, digital media, sociology and religion by authors such as Campbell, Elzo, Leurs and Hemming.

Open wall churches. Catholic construction of online communities - Bosch, M.D.; Sanz, J.LM.; Abello, J.M.C; Sanchez, J.S.I; Gauxachs, A.S (Prisma Social revista de investigación social, 2017)
The discussion regarding how global Catholic organizations have employed the new tools of digital media has become increasingly poignant and no longer focuses on liturgical limitations but on participation, social justice and new frameworks for reaching new targets. From the Vatican itself, specifically through the Pope’s profiles on social media, Catholicism has proven to have an increasingly responsive presence on the web, although Catholics are usually creative without breaking the rules in the ways they extend their religiosity into new platforms. Newly born digital portals have embraced new participatory tools that shape other ways of understanding communion, which is a key concept among Christian communities. Rather than dwelling on whether Catholic portals are incorporating secular strategies to foster engagement, we explore the 19 most powerful Catholic websites according to Alexa ranking, and divide them into different categories that allow us to analyse how they build communities and thus foster the concept of belonging, which is one of the aims that they pursue. Data have been collected in three different moments (2014, 2015 and 2016) where these websites, belonging to 5 languages (Spanish, English, French, Portuguese and Italian) from 9 countries have been taken into account, according to Catholic population indexes.
Keywords: Catholic; churches; online communities

Lwa Like Me: Gender, Sexuality and Vodou Online - Alexandra Boutros (Media, Religion and Gender Key Issues and New Challenges, 2013)
Keywords: Digital Religion; GENDER; New Media; online activities

Trending #hijabfashion: Using Big Data to Study Religion at the Online–Urban Interface - Boy, John D.; Uitermark, Justus; Wiersma, Laïla (Nordic Journal of Religion and Society, 2018)
This article discusses the potential and the limitations of big data analysis for the study of religion. While big data analysis is often perceived as overtly positivistic because of its quantitative and computational nature, we argue instead that it lends itself to an induc-tive approach. Since the data are typically not collected for the purpose of testing specific hypotheses, it can best be seen as a resource for serendipitous exploration. We therefore pose a number of substantive research questions regarding the global circulation and local mediation of sartorial styles and practices among Muslim women. We present an analysis of the #hijabfashion hashtag on Instagram, drawing on a database of 15 million posts.

Why Youth Heart Social Network Sites - Boyd, Danah (Youth, Identity, and Digital Media Volume, 2007)
Social network sites like MySpace and Facebook serve as "networked publics." As with unmediated publics like parks and malls, youth use networked publics to gather, socialize with their peers, and make sense of and help build the culture around them. This article examines American youth engagement in networked publics and considers how properties unique to such mediated environments (e.g., persistence, searchability, replicability, and invisible audiences) affect the ways in which youth interact with one another. Ethnographic data is used to analyze how youth recognize these structural properties and find innovative ways of making these systems serve their purposes. Issues like privacy and impression management are explored through the practices of teens and youth participation in social network sites is situated in a historical discussion of youth's freedom and mobility in the United States.
Keywords: Social Networking; Young; Youth

More Than Half of Mobile Users Avoid Certain Apps Due to Privacy Concerns - Jan Lauren Boyles; Aaron Smith; Mary Madden (Privacy and Data Management on Mobile Devices, 2012)
More than half of mobile application users have uninstalled or avoided certain apps due to concerns about the way personal information is shared or collected by the app, according to a nationally representative telephone survey conducted by the Pew Research Center’s Internet & American Life Project.
Keywords: App; Privacy

Give me that online religion - Brasher, Brenda (Jossey-Bass Publishers, 2001)
As the Internet and the World Wide Web overcome barriers of time and space, religion enjoys an ever-increasing accessibility on a global scale. Inevitably, people online have sought out encounters with the otherworldly, launching religion into cyberspace. In this compelling book, Brenda Brasher explores the meaning of electronic faith and the future of traditional religion. Operating online allows long-established religious communities to reach hearts and minds as never before. Yet more startling is the case by which anyone with Internet access can create new circles of faith. Bringing religion online also narrows the gap between pop culture and the sacred. Electronic shrines and kitschy personal Web "altars" idolize living celebrities, just as they honor the memory of religious martyrs. Looking ahead, Brasher envisions a world in which cyber-concepts and technologies challenge conventional notions about the human condition, while still attempting to realize age-old religious ideals such as transcendence and eternal life. As the Internet continues its rapid absorption of culture, Give Me That Online Religion offers pause for thought about spirituality in the cyberage. Religion's move to the online world does not mean technology's triumph over faith. Rather, Brasher argues, it assures religion's place in the wired universe, meeting the spiritual demands of Internet generations to come.
Keywords: Online; religion

Give Me That Online Religion - Brasher, B (Rutgers University Press, 2004)
As the Internet and the World Wide Web overcome barriers of time and space, religion enjoys an ever-increasing accessibility on a global scale. Inevitably, people online have sought out encounters with the otherworldly, launching religion into cyberspace. In this compelling book, Brenda Brasher explores the meaning of electronic faith and the future of traditional religion.
Keywords: online religion

La foi et le langage : paradigmes de sens pour les médias - Bratosin, Stefan (4th Workshop international Essachess: Média, spiritualité et laïcité : Regards croisés franco-roumains, 2015)
Cette communication tâchera de montrer dans la perspective d'une épistémologie sociale que les paradigmes de sens irréductibles pour toute type de médiatisation sont la foi et le langage. Elle produira une argumentation en faveur de l'hypothèse que ce qui est fondamentalement spécifique pour les différents approches médiatiques de la réalité ne réside pas dans la production de sens, mais dans la direction que chaque type de médiatisation se donne pour orienter la vie de l'individu, de la société et d’une manière générale du monde. Enfin, la communication apportera une lecture de la liberté de conscience dans ce contexte où l'être humain - un existant donné - doit s' "in-former" sous la pression de l'être social - un existant historique construit collectivement.
Keywords: Faith; freedom of opinion; language; media; mediatization; religion; secularization

La médialisation du religieux dans la théorie du post néo-protestantisme - Bratosin, Stefan (Social Compass, 2016)
This article proposes a theory of post neo-Protestantism highlighting the key relationships maintained by this new postmodern manner of thinking and living religion with the medialization, that is to say, with the ‘mediatization of everything’ as a model of public communication developed in favor of broadband internet, wireless internet or social media. In this perspective, it is shown that post neo-Protestantism is basically the virtualization of neo-Protestantism still clinging to modernity and the communicative individual pragmatics of this virtualization now inescapably linked to new media.
Keywords: internet; medialization; post neo-Protestantism; postmodernism; religion

Church In The Public Sphere: Production Of Meaning Between Rational And Irrational - Bratosin, Stefan (Journal for the Study of Religions and Ideologies, 2014)
In the public sphere and especially in the media, the discourse on the Church and about the Church on faith and religion is often tainted by the confusion of meaning due, among other things, to the mutual borrowing less rigorous – epistemologically and methodologically – of the concepts which engage various disciplines (theology, sociology, anthropology, political science, information and communication science, and so on) who take possession of problematic centered on the relation between mankind and divinity. This article presents some basic benchmarks for analyzing and understanding the construction of meaning as well as the rationality or irrationality of these issues by convening the disciplinary distinction between the content of the concepts of organization and that of the institution.
Keywords: Church; Faith; media; production of meaning; public sphere; religion; symbolic forms

Média, spiritualité et laïcité : Regards croisés franco-roumains - Bratosin, Stefan (Iarsic, 2015)
This scientific event brought together different authorities, academic institutions and political and media organizations at the Villa Noël in Bucharest to make an assessment on the sensitive questions related to religious freedom and liberty of conscience, on spirituality and secularity, full of meaning symbols, with a significant emotional and ethical charge. This book is a contribution to the public sphere debate on the secularity and the spirituality in the service of freedom considering two paradigmatic cases, two European countries: Romania – statistically the most religious country of Europe, and France – statistically the less religious country of Europe. *** Cette manifestation scientifique a réuni différentes instances, institutions et organisations académiques, politiques et médiatiques à la Villa Noël afin de dresser un bilan sur les questionnements sensibles liés à la liberté religieuse et de conscience, à la spiritualité et à la laïcité, symboles chargés de sens intellectuel, éthique et émotionnel. Les communications sont une contribution au débat concernant la prise de distance épistémologique et éthique « politiquement correct » pour une laïcité et une spiritualité au service de la liberté en considérant deux cas paradigmatiques, deux pays européens, la Roumanie et la France, dont l'un est statistiquement le plus religieux de l'Europe et l'autre le moins religieux, et qui, dans leurs espaces publics respectifs, déclinent différemment la relation entre spiritualité et laïcité.
Keywords: France; laïcité; media; secularity; Spirituality

Espace public et communication de la foi - Bratosin, Stefan; Tudor, Mihaela-Alexandra (Espace Public et Communication de la Foi, 2014)
Questioning the faith in its communicability in the public sphere is an open issue. This book is the evidence that, according to Gilbert Durand reflection on the sacred expressed in an interview for Essachess - Journal for Communication Studies in 2011, shortly before his death, the communication of faith in the public sphere seems "both changing and unchanging", changing because the communication as production of the meaning in a practiced context makes it changing and unchanging because it is always related to a single Truth. *** Interroger la foi dans sa communicabilité dans l'espace public demeure un chantier ouvert. Cet ouvrage représente le témoignage que, selon une réflexion de Gilbert Durand sur le sacré exprimée dans un entretien pour Essachess - Journal for Communication Studies en 2011, peu avant sa mort, la communication de la foi dans l'espace public semble « à la fois changeante et immuable », changeante car la communication comme production de sens dans un contexte pratiqué la rend changeante et immuable car elle reste toujours liée à une seule et unique Vérité.
Keywords: communication – group and community; Faith; public sphere; religion

Initial Steps towards a Theory of Cyberspace - Harris Breslow (Cyberculture Now, 2013)
Keywords: Cyberculture studies; Cyberspace Theory; digital storytelling; Internet and New Media; Virtual Environment; Web Anthropology; Web Sociology

Virtual Gods - Brooke, Tal (Harvest House., 1997)
Millions of computer users have discovered that cyberspace allows them to leap over barriers of time, place, and social status to connect with people from all over the world. Long after this book was written it foresaw alienation in cyberspace. Now a Harvard dropout named Mark Zuckerberg has given the world Facebook, becoming a billionaire in his twenties. Facebook has shown how untold numbers crave social connection so desperately -- even people they have never met -- that they will divulge anything to drive their ratings up. There are other doorways in this rapidly expanding digital universe. Virtual reality and holograms are poised to explode. Digital special effects in movies such as James Cameron's groundbreaking film Avatar -- shown in 3D on IMAX with scenes of computer generated synthetic reality -- have shown where this technology can take us. Audiences are craving the next leap beyond Avatar.Virtual Gods is a book written before its time. It explores technological doorways still ahead that could open the way to a future only partially glimpsed by such writers as Aldous Huxley, who showed us so much in his prescient Brave New World. Ahead are invasive aspects to this emerging technology--the ability to spy on subjects, inject microchips, etc -- that would have given George Orwell chills. It is worth a deeper look, which this book provides.
Keywords: Gods; Virtual

Ready to be a thought leader? How to increase your influence, impact, and success - Denise Brosseau (Jossey-Bass Publishing, 2014)
The how-to guide to becoming a go-to expert Within their fields, thought leaders are sources of inspiration and innovation. They have the gift of harnessing their expertise and their networks to make their innovative thoughts real and replicable, sparking sustainable change and even creating movements around their ideas. In Ready to Be a Thought Leader?, renowned executive talent agent Denise Brosseau shows readers how to develop and use that gift as she maps the path from successful executive, professional, or civic leader to respected thought leader. With the author's proven seven-step process―and starting from wherever they are in their careers―readers can set a course for maximum impact in their field. These guidelines, along with stories, tips, and success secrets from those who have successfully made the transition to high-profile thought leader, allow readers to create a long-term plan and start putting it into action today, even if they only have 15 minutes to spare. Offers a step-by-step process for becoming a recognized thought leader in your field Includes real-world examples from such high-profile thought leaders as Robin Chase, founder and former CEO of Zipcar; Chip Conley, author of PEAK and former CEO of JDV Hospitality; and more Written by Denise Brosseau, founder of Thought Leadership Lab, an executive talent agency that helps executives become thought leaders, who has worked with start-up CEOs and leaders from such firms as Apple, Genentech, Symantec, Morgan Stanley, Medtronic, KPMG, DLA Piper, and more Ready to Be a Thought Leader? offers essential reading for anyone ready to expand their influence, increase their professional success, have an impact far beyond a single organization and industry, and ultimately leave a legacy that matters.

The Religious Facebook Experience: Uses and Gratifications of Faith-Based Content - Brubaker, Pamela Jo; Haigh, Michel M. (Social Media + Society, 2017)
This study explores why Christians (N = 335) use Facebook for religious purposes and the needs engaging with religious content on Facebook gratifies. Individuals who access faith-based content on Facebook were recruited to participate in an online survey through a series of Facebook advertisements. An exploratory factor analysis revealed four primary motivations for accessing religious Facebook content: ministering, spiritual enlightenment, religious information, and entertainment. Along with identifying the uses and gratifications received from engaging with faith-based Facebook content, this research reveals how the frequency of Facebook use, the intensity of Facebook use for religious purposes, and also religiosity predict motivations for accessing this social networking site for faith-based purposes. The data revealed those who frequently use Facebook for posting, liking, commenting, and sharing faith-based content and who are more religious are more likely to minister to others. Frequent use also predicted seeking religious information. The affiliation with like-minded individuals afforded by this medium provides faith-based users with supportive content and communities that motivate the use of Facebook for obtaining spiritual guidance, for accessing religious resources, and for relaxing and being entertained.

The presentation of self in the online world: Goffman and the study of online identities - Liam Bullingham; Ana C. Vasconcelos (Journal of Information Science, 2013)
This paper presents an exemplification and discussion of the contemporaneity of Erving Goffman’s work and of its applicability to the analysis of identity and presentation of self in the blogging and Second Life (SL) contexts. An analysis of online identity and interaction practices in 10 different cases of bloggers and SL inhabitants and of their online spaces is presented in terms of: expressions given; embellishment as a minor form of persona adoption; dividing the self; conforming and ‘fitting in’; and masking, anonymity and pseudonimity. The key finding of the research is that, contrary to engaging with the process of whole persona adoption, participants were keen to re-create their offline self online, but engaged in editing facets of self. This emphasizes the key premise in Goffman’s work that, when in ‘front stage’, people deliberately chose to project a given identity. It is concluded that Goffman’s original framework is of great usefulness as an explanatory framework for understanding identity through interaction and the presentation of self in the online world. Equally, the online environment, with its enhanced potential for editing the self, can offer opportunities to contribute to the further development of the Goffman framework.

Islam in the Digital Age: E-jihad, Online Fatwas and Cyber Islamic Environments - Gary Bunt (Pluto Press, 2003)
The Internet is very big in the Arab world. After Al-Jazeera, it is the second most important source of dissenting opinion. Literally, millions of people in the Muslim world rely on web-sites to get their information and fatwas. A whole new life of cyber Imams and a new culture is emerging through Internet programmes and will have a profound effect on Arab consciousness. This book documents all this and examines various sites and offers the first comprehensive analysis of the impact of the Internet on Islamic culture. Zia Sardar, author of Postmodernism and the Other and Why Do People Hate America. The Internet is an increasingly important source of information for many people in the Muslim world. Many Muslims in majority and minority contexts rely on the Internet -- including websites and e-mail -- as a primary source of news, information and communication about Islam. As a result, a new media culture is emerging which is having a significant impact on areas of global Muslim consciousness. Post-September 11th, this phenomenon has grown more rapidly than ever.Gary R. Bunt provides a fascinating account of the issues at stake, identifying two radical new concepts: Firstly, the emergence of e-jihad ('Electronic Jihad') originating from diverse Muslim perspectives -- this is described in its many forms relating to the different definitions of 'jihad', including on-line activism (ranging from promoting militaristic activities to hacking, to co-ordinating peaceful protests) and Muslim expression post 9/11. Secondly, he discusses religious authority on the Internet -- including the concept of on-line fatwas and their influence in diverse settings, and the complexities of conflicting notions of religious authority.
Keywords: cyber; Digital; fatwas; Islam; jihad

Virtually Islamic: Computer-Mediated Communication and Cyber Islamic Environments - Gary Bunt (University of Wales Press, 2000)

Rip.Burn.Pray: Islamic Expression Online - Gary Bunt (Religion Online: Finding Faith on the Internet, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression.Religion Onlineprovides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes thePew Internet and American Life ProjectExecutiveSummary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-definingCyberspace as SacredSpace.
Keywords: Islam; Online; Prayer

islam@britain.net: ‘British Muslim’ identities in Cyberspace - Bunt, Gary R. (Islam and Christian–Muslim Relations, 1999)
The Internet represents a significant communication tool for the expression of Islamic concepts and notions of identity, on web pages ranging from the constructs of organizations through to the pronouncements of individuals. Cyber Islamic Environments provide indicators of what it means to be a ‘Muslim’ in Britain that augment other sources of knowledge. This paper presents an overview of prominent sites, and introduces issues connected with studying Islam and Muslims through this electronic medium.

IMuslims: Rewiring the House of Islam - Gary Bunt (UNC Press, 2009)
Exploring the increasing impact of the Internet on Muslims around the world, this book sheds new light on the nature of contemporary Islamic discourse, identity, and community. The Internet has profoundly shaped how both Muslims and non-Muslims perceive Islam and how Islamic societies and networks are evolving and shifting in the twenty-first century, says Gary Bunt. While Islamic society has deep historical patterns of global exchange, the Internet has transformed how many Muslims practice the duties and rituals of Islam. A place of religious instruction may exist solely in the virtual world, for example, or a community may gather only online. Drawing on more than a decade of online research, Bunt shows how social-networking sites, blogs, and other "cyber-Islamic environments" have exposed Muslims to new influences outside the traditional spheres of Islamic knowledge and authority. Furthermore, the Internet has dramatically influenced forms of Islamic activism and radicalization, including jihad-oriented campaigns by networks such as al-Qaeda. By surveying the broad spectrum of approaches used to present dimensions of Islamic social, spiritual, and political life on the Internet, iMuslimsencourages diverse understandings of online Islam and of Islam generally.
Keywords: information and communication technology; Islam; social networks; study of religion

Christians Under Covers: Evangelicals and Sexual Pleasure on the Internet - Burke, K (University of California Press, 2016)
Christians under Covers shifts how scholars and popular media talk about religious conservatives and sex. Moving away from debates over homosexuality, premarital sex, and other perceived sexual sins, Kelsy Burke examines Christian sexuality websites to show how some evangelical Christians use digital media to promote the idea that God wants married, heterosexual couples to have satisfying sex lives. These evangelicals maintain their religious beliefs while incorporating feminist and queer language into their talk of sexuality—encouraging sexual knowledge, emphasizing women’s pleasure, and justifying marginal sexual practices within Christian marriages. This illuminating ethnography complicates the boundaries between normal and subversive, empowered and oppressed, and sacred and profane.
Keywords: Christians; Evangelicals; internet; sexual behavior

Reading race on-line; discovering racial identity in usenet discussions - Burkhalter, B (Communities in Cyberspace, 1999)
This wide-ranging introductory text looks at the virtual community of cyberspace and analyses its relationship to real communities lived out in today's societies. Issues such as race, gender, power, economics and ethics in cyberspace are grouped under four main sections and discussed by leading experts: * identity * social order and control * community structure and dynamics * collective action. This topical new book displays how the idea of community is being challenged and rewritten by the increasing power and range of cyberspace. As new societies and relationships are formed in this virtual landscape, we now have to consider the potential consequences this may have on our own community and societies. Clearly and concisely writtenwith a wide range of international examples, this edited volume is an essential introduction to the sociology of the internet. It will appeal to students and professionals, and to those concerned about the changing relationships between information technology and a society which is fast becoming divided between those on-line and those not.
Keywords: identity; internet; race; Usenet

Analyzing Media Texts - Burns, Andrew; Parker, David (Continuum Research Methods Series, 2003)
Andrew Burn and David Parker outline how multi-modality theory can be used to analyze texts which employ multiple semiotic modes and media, in such a way that a balanced consideration is given to the characteristics of each mode, how they integrate, and how they distribute textual functions between them. The methods are rooted in a view of significance as dependent on social context, and fulfilling the social and communicative interests of both producers of textual production and use contingent upon digital formats will also be a determining content of the analytical method.
Keywords: data; media; multimodality; Social; theory

Invisible Users - Jenna Burrell (The MIT Press, 2012)
An account of how young people in Ghana’s capital city adopt and adapt digital technology in the margins of the global economy. Among other subjects: Religious practice and belief were a frequent point of reference for Ghanaian Internet users when they spoke about their social relationships, aspirations, and their use of technologies including the Internet. The way they talked about this belief was marked by a sense of the presence of spiritual forces (good and evil).
Keywords: Africa; digital technologies; Ghana; Ghanaian; internet; network technologies; religious practice; spiritual; users; Youth

Religious Memetics: Institutional Authority in Digital/Lived Religion - Burroughs, Benjamin; Feller, Gavin (Journal of Communication Inquiry, 2015)
Recently leaders of the Church of Jesus Christ of Latter-day Saints (LDS/Mormon) faith have called upon members to "sweep the earth" with positive religious messages through social media. This digital moment in Mormonism exemplifies the interrelation and concomitant tension between everyday lived religion, technology, and religious institutions. While studies on digital religion have emphasized the push of participatory culture into everyday lived religion, this research on religious memes contributes to an emergent vein of digital religion scholarship focused on institutional authority. In our analysis of the "doubt your doubts" meme and antimemes we theorize religious memetics as a space for the reconnection of the everydayness of religious practice, which boils down meaningful moments of faith into facile, nonthreatening avenues for sharing religion. While this is beneficial for institutions, the reflexive and metonymic function of religious memes ruptures routine, offering participants momentary pauses from the demands of orthodox religious life.
Keywords: Digital Religion; Lived religion; meme; mormonism; religious memetics

Come to a Correct Understanding of Buddhism: a case study on spiritualising technology, religious authority, and the boundaries of orthodoxy and identity in a Buddhist Web forum - Busch, L. (New Media and Society, 2011)
This study examines the Buddhist message forum, E-sangha, to analyze how this forum’s founder and moderators ‘spiritualized the Internet’ (Campbell, 2005a, 2005b) using contemporary narratives of the global Buddhist community, and in doing so, provided these actors with the authority to determine the boundaries of Buddhist orthodoxy and identity and validate their control of the medium through social and technical means. Through a structural and textual analysis of E-sangha’s Web space, this study demonstrates how Web producers and forum moderators use religious community narratives to frame Web environments as sacred community spaces (spaces made suitable for religious activities), which inherently allows those in control of the site the authority to set the boundaries of religious orthodoxy and identity and hence, who can take part in the community.
Keywords: Authority; Buddhism; spiritual; technology

De-Centering and Re-Centering: Rethinking Concepts and Methods in the Sociological Study of Religion - Wendy Cadge; Peggy Levitt; David Smilde (Journal for the Scientific Study of Religion, 2011)
Keywords: methods; religion; Research; scholar; Sociology of religion

Holy selfies: Performing pilgrimage in the age of social media - Caidi, Nadia; Beazley, Susan; Marquez, Laia Colomer (The International Journal of Information, Diversity, & Inclusion, 2018)
In this article, we examine the selfie-taking and sharing practices of Muslim pilgrims in Mecca, Saudi Arabia. We introduce the concept of the “holy selfie” (a selfie taken during either theHajj or the Umrah pilgrimages) and report on a visual content analysis of a sample of 100 holy selfies publicly available on social networking platforms. We seek to reach an understanding of the work that holy selfies do in the context of the expressions of spiritual and religious identity of those producing them. Our findings suggest that the embodied experience of pilgrims at the holy sites finds an expressive release through holy selfies, with many pilgrims viewing selfie-taking as an important part of their journey. The selfies (and associated features) capture and document pilgrims’ experiences, contribute to their meaning-making, enable the sharing of memories with loved ones, and attract online followers. Our study provides a picture of how holy selfies blur the gender line (as many males as females take them), emerge despite the opposition of Saudi authorities, and serve as a means of engaging with a multiplicity of audiences. We seek to start a conceptual and methodological conversation about this emerging phenomenon of identity construction involving the use of new media along with the construction of affiliative identities among geographically dispersed communities of Muslim pilgrims. The taking of holy selfies can thus be read as a tactic used by 21st-century Muslims to create opportunities for self-representation and community building in a context of increasing Islamophobia.

Unscrewing the big leviathan: How actors macrostructure reality and how sociologists help them to do so - Michel Callon; Latour B. (Advances in Social Theory and Methodology, Routledge and Kegan Paul, 1981)
This social theory article explores the problem of micro and macro society without accepting an a priori scale to measure the levels; it demonstrates that by letting the actors build their own scale, the growth of science and technology becomes explainable.

Creating digital enclaves: Negotiation of the internet among bounded religious communities: - Campbell, Heidi A.; Golan, Oren (Media, Culture & Society, 2011)
This article examines the motivation behind bounded groups’ creation of digital enclaves online. Through in-depth interviews with 19 webmasters and staff of selected Israeli Orthodox websites three critical areas of negotiation are explored: (1) social control; (2) sources of authority; and (3) community boundaries. Examining these tensions illuminates a detailed process of self-evaluation which leads religious stakeholders and internet entrepreneurs to form these digital enclaves in order to negotiate the core beliefs and constraints of their offline communities online. These offer spaces of safety for members within the risk-laden tracts of the internet. Examining the tensions accompanying the emergence of these religious websites elucidates community affordances as well as the challenges to the authority that integration of new media poses to closed groups and societies.

Religion and New Media - Campbell, H; Connelly, L (International Encyclopedia of the Social & Behavioral Sciences, 2015)
Keywords: New Media; religion

How Religious Communities Negotiate New Media Religiously - Campbell, H. (Digital Religion, Social Media and culture: Perspectives, Practices, Futures, 2012)
This lively book focuses on how different Jewish, Muslim, and Christian communities engage with new media. Rather than simply reject or accept new media, religious communities negotiate complex relationships with these technologies in light of their history and beliefs. Heidi Campbell suggests a method for studying these processes she calls the "religious-social shaping of technology" and students are asked to consider four key areas: religious tradition and history; contemporary community values and priorities; negotiation and innovating technology in light of the community; communal discourses applied to justify use. A wealth of examples such as the Christian e-vangelism movement, Modern Islamic discourses about computers and the rise of the Jewish kosher cell phone, demonstrate the dominant strategies which emerge for religious media users, as well as the unique motivations that guide specific groups.
Keywords: communities; New Media; religion

Islamogaming: Digital Dignity via Alternative Storytelling - Heidi Campbell (Halos and avatars: Playing (video) games with God, 2010)
Craig Detweiler's collection of up-to-the-minute essays on video games' theological themes (and yes, they do exist!) is an engaging and provocative book for gamers, parents, pastors, media scholars, and theologians--virtually anyone who has dared to consider the ramifications of modern society's obsession with video games and online media. Together, these essays take on an exploding genre in popular culture and interpret it through a refreshing and enlightening philosophical lens.
Keywords: Christianity; game studies; Islam; public sphere; video games; virtual worlds

Problematizing the Human-Technology Relationship through Techno-Spiritual Myths Presented in The Machine, Transcendence and Her - Campbell, H (Journal of Religion & Film, 2016)
This article explores three common techno-spiritual myths presented in three recent science fiction films, highlighting how the perceived spiritual nature of technology sets-out an inherently problematic relationship between humanity and technology. In The Machine, Transcendence and Her, human-created computers offer salvation from human limitations. Yet these creations eventually overpower their creators and threaten humanity as a whole. Each film is underwritten by a techno-spiritual myths including: “technology as divine transcendence” (where technology is shown to endow humans with divine qualities, “technological mysticism” (framing technology practice as a form of religion/spirituality) and “techgnosis” (where technology itself is presented as a God). Each myth highlights how the human relationship to technology is often framed in spiritual terms, not only in cinema, but in popular culture in general. I argue these myths inform the storylines of these films, and spotlight common concerns about the outcome of human engagement with new technologies. By identifying these myths and discussing how they inform these films, a techno-spirituality grounded in distinctive posthuman narratives about the future of humanity is revealed.
Keywords: spiritual; technology

Creating digital enclaves: Negotiation of the internet amongst bounded religious communities - Heidi Campbell; Oren Golan (Media, Culture and Society, 2011)
This article examines the motivation behind bounded groups’ creation of digital enclaves online. Through in-depth interviews with 19 webmasters and staff of selected Israeli Orthodox websites three critical areas of negotiation are explored: (1) social control; (2) sources of authority; and (3) community boundaries. Examining these tensions illuminates a detailed process of self-evaluation which leads religious stakeholders and internet entrepreneurs to form these digital enclaves in order to negotiate the core beliefs and constraints of their offline communities online. These offer spaces of safety for members within the risk-laden tracts of the internet. Examining the tensions accompanying the emergence of these religious websites elucidates community affordances as well as the challenges to the authority that integration of new media poses to closed groups and societies.
Keywords: Authority; community; internet; Israel; Judaism

How the iPhone became divine: new media, religion and the intertextual circulation of meaning - Campbell, Heidi A.; La Pastina, Antonio C. (New Media & Society, 2010)
This article explores the labeling of the iPhone as the ‘Jesus phone’ in order to demonstrate how religious metaphors and myth can be appropriated into popular discourse and shape the reception of a technology. We consider the intertextual nature of the relationship between religious language, imagery and technology and demonstrate how this creates a unique interaction between technology fans and bloggers, news media and even corporate advertising. Our analysis of the ‘Jesus phone’ clarifies how different groups may appropriate the language and imagery of another to communicate very different meanings and intentions. Intertextuality serves as a framework to unpack the deployment of religion to frame technology and meanings communicated. We also reflect on how religious language may communicate both positive and negative aspects of a technology and instigate an unintentional trajectory in popular discourse as it is employed by different audiences, both online and offline.

The Internet as Social-Spiritual Space - Heidi Campbell (Netting citizens: Exploring citizenship in the Internet age, 2004)
Keywords: internet; Social; spiritual

Sanctifying the Internet: Aish’s Use of the Internet for Digital Outreach - Campbell, H; Bellar, W (Digital Judaism: Jewish Negotiations with Digital Media and Technology, 2015)
The internet is increasingly used by different Jewish groups as a tool of outreach, especially for religious organizations committed to calling secular Jews back into a religious lifestyle. One example of using the internet to connect, educate and encourage Jews is the work of Aish.com, the digital presence of Aish HaTorah. Due to its Orthodox outlook, it functions under a set of self-imposed rules in its web work to monitor and make sure the content and images that appear on the site support its conservative values and beliefs. While it seeks to be innovative in the types of information and forums it provides (from video podcasts and blogs to online seminars and courses), it insists its work is not a whole-scale endorsement of the internet for all religious Jews. Rather, the internet is presented as a necessary tool to be used in outreach to secular Jews. Aish.com allows Aish HaTorah the means to meet and influence secular Jews wherever they are. By using the internet within a bounded approach and by carefully monitoring web content, those working for the site avoid problematic images and topics as it seeks to sanctify the internet through bringing Torah and a Torah-based lifestyle into the digital realm
Keywords: digital outreach; internet

Challenges created by online religious networks - Heidi Campbell (Journal of Media and Religion, 2004)
This article considers the challenges that online religious communities raise for religious culture. A survey of cultural changes in media, community, and religion uncovers similar structural shifts, from hierarchical structures to more open, dynamic relationship patterns in society. Examining this shift helps explain why cyber-religion and online religious communities have become emergent phenomenon. Emphasis is placed on the argument that the Internet has thrived because it has surfaced in a cultural landscape that promotes fluid yet controlled relationships over tightly bound hierarchies. Religious online communities are expressions of these changes and challenge traditional religious definitions of community. Especially problematic is the image of community as a network of relations. This article also addresses common concerns and fears of religious critics related to online communities through an analysis of current literature on these issues, along with a synthesis of research studies relating to the social use and consequences of the Internet.
Keywords: community; internet; religion

Contextualizing current digital religion research on emerging technologies - Campbell, Heidi A.; Evolvi, Giulia (Human Behavior and Emerging Technologies, 2019)
This article provides an overview of contemporary research within the interdisciplinary arc of scholarship known as digital religion studies, in which scholars explore the intersection between emerging digital technologies, lived and material religious practices in contemporary culture, and the impact the structures of the network society have on understandings of spirituality and religiosity. Digital religion studies specifically investigates how online and offline religious spaces and practices have become bridged, blended, and blurred as religious groups and practitioners seek to integrate their religious lives with technology use within different aspects of digital culture.

Digital Judaism: Jewish negotiations with digital media and culture - Campbell, H (Routledge, 2015)
In this volume, contributors consider the ways that Jewish communities and users of new media negotiate their uses of digital technologies in light of issues related to religious identity, community and authority. Digital Judaism presents a broad analysis of how and why various Jewish groups negotiate with digital culture in particular ways, situating such observations within a wider discourse of how Jewish groups throughout history have utilized communication technologies to maintain their Jewish identities across time and space. Chapters address issues related to the negotiation of authority between online users and offline religious leaders and institutions not only within ultra-Orthodox communities, but also within the broader Jewish religious culture, taking into account how Jewish engagement with media in Israel and the diaspora raises a number of important issues related to Jewish community and identity. Featuring recent scholarship by leading and emerging scholars of Judaism and media, Digital Judaism is an invaluable resource for researchers in new media, religion and digital culture.
Keywords: culture; digital judaism; digital media; Digital Religion; Jewish religion

Al Jazeera’s Framing of Social Media During the Arab Spring. - Heidi Campbell; Diana Hawk (CyberOrient, 2012)
This study investigates how Al Jazeera framed social media in relation to the revolutions and protests of the “Arab Spring” within its broadcast media coverage. A content analysis of Arabic language broadcasts appearing from January 25th through February 18th 2011, covering the protests in Tahrir Square, was conducted using the Broadcast Monitoring System (BMS) and Arab Spring Archive. Through this analysis we see a number of common narratives being used by Al Jazeera to frame social media and make claims about the influence they had on the protests and related social movements. By noting the frequency of social communications technologies referenced, ways in which these technologies were characterized and interpreting supporting themes with which they were identified helps illuminate the assumptions promoted by Al Jazeera regarding the role and impact of social communications technology on these events.
Keywords: activism; Arab Spring; democracy; Egypt; information and communication technology; internet; public sphere; satellite TV; social media

INTRODUCTION: Rethinking the online–offline connection in the study of religion online - Campbell, Heidi A.; Lövheim, Mia (Information, Communication & Society, 2011)
This article introduces current research on the connection between online and offline religion and map out significant questions and themes concerning how this relationship takes shape among different religious traditions and contexts. By bringing together a collection of studies that explore these issues, we seek to investigate both how the Internet informs religious cultures in everyday life and how the Internet is being shaped by offline religious traditions and communities. In order to contextualize the articles in the special issue, we offer a brief overview of how religion online has been studied over the past two decades with attention given to how the intersection of online–offline religion has been approached. This is followed by a discussion of key questions in the recent study of the relationship between online and offline religion and significant themes that emerge in contemporary research on religious uses of the Internet. These questions and themes help contextualize the unique contributions this special issue offers to the current discourse in this area, as well as how it might inform the wider field of Internet studies. We end by suggesting where future research on religion and the Internet might be headed, especially in relation to how we understand and approach the overlap between online and offline religion as a space of hybridity and social interdependence.

Internet and Cyber Environments - Heidi Campbell (Encyclopedia of Religion, Communication and Media, 2006)
Communication is at the heart of all religions. As an essential aspect of religion, communication occurs between believers, between religious leaders and followers, between proponents of different faiths, and even between practitioners and the deities. The desire to communicate with as well as convert others is also an aspect of some of the world's major religions. The Encyclopedia of Religion, Communication, and Media explores all forms of religious communication worldwide and historically, with a special emphasis on oral and written forms of communication. This A-Z organized reference work analyzes how and why the world's religions have used different means of communications through topics dealing with: * Theory and concepts in religious communication, including rhetoric, persuasion, performance, brainwashing, and more * Forms of verbal communication, such as chanting, speaking in tongues, preaching, or praying * Forms of written communication, such as religious texts,parables, mystical literature, and modern Christian publishing * Other forms of communication, including art, film, and sculpture * Religious communication in public life, from news coverage and political messages to media evangelism and the electronic church * Communication processes and their effects on religious communication, including non-sexist language, communication competence, or interfaith dialogue * Biographies of major religious communicators, including Muhammad, Jesus, Aristotle, Gandhi, and Martin Luther From the presence of religion on the internet to the effects of religious beliefs on popular advertising, communication and media are integral to religion and the expression of religious belief. With its international and multicultural coverage, this Encyclopedia is an essential and unique resource for scholars, students, as well as the general reader interested in religion, media, or communications. « Less Preview this book » What people are saying - Write a review Editorial Review - Library Journal vol. 132 iss. 11 p (c) 06/15/2007 A plethora of existing encyclopedias covers the independent study of religion, communication, and the media. Few, however, manage to bring these disparate fields together. Stout (journalism & media studies, Univ. of Nevada, Las Vegas; coeditor, Journal of Media and Religion ) has carefully chosen respected international scholars with expertise in a wide range of subjects—e.g., communication, religion, theology, and the media—to create this unprecedented interdisciplinary, cross-cultural encyclopedia concentrating on the various forms of written and oral religious methods used to communicate with divinity around the world. The 124 A-to-Z signed entries explore not only traditional media but also new media (e.g., cyber environments, film, and sculpture). The entries appear in a standardized format, each ranging from one to three pages in length. Major schools of thought, ancient and modern traditions, theories, and gurus are described, and each entry highlights the influence of religion on human history and contemporary society. Key ideas are often supported with excerpts, and articles are supplemented with photos and sidebars. BOTTOM LINE The division of entries into well-defined key sections and the extensive index allow efficient access to the information. These features, together with the further reading section, make this an ideal choice for large public or academic libraries serving university students, journalists, and those seeking a more thorough understanding of religion and communication's interconnection.—Hazel Cameron, Western Washington Univ. Libs., Bellingham Editorial Review - Library Journal vol. 132 iss. 11 p (c) 06/15/2007 A plethora of existing encyclopedias covers the independent study of religion, communication, and the media. Few, however, manage to bring these disparate fields together. Stout (journalism & media studies, Univ. of Nevada, Las Vegas; coeditor, Journal of Media and Religion ) has carefully chosen respected international scholars with expertise in a wide range of subjects—e.g., communication, religion, theology, and the media—to create this unprecedented interdisciplinary, cross-cultural encyclopedia concentrating on the various forms of written and oral religious methods used to communicate with divinity around the world. The 124 A-to-Z signed entries explore not only traditional media but also new media (e.g., cyber environments, film, and sculpture). The entries appear in a standardized format, each ranging from one to three pages in length. Major schools of thought, ancient and modern traditions, theories, and gurus are described, and each entry highlights the influence of religion on human history and contemporary society. Key ideas are often supported with excerpts, and articles are supplemented with photos and sidebars. BOTTOM LINE The division of entries into well-defined key sections and the extensive index allow efficient access to the information. These features, together with the further reading section, make this an ideal choice for large public or academic libraries serving university students, journalists, and those seeking a more thorough understanding of religion and communication's interconnection.—Hazel Cameron, Western Washington Univ. Libs., Bellingham Related books ‹ Media and Religion Stout, Daniel A. Stout Routledge Encyclopedia of Religion, Communication, and Media Daniel A. Stout Religion and mass media Daniel A. Stout, Judith Mitchell Buddenbaum Religion and popular culture Daniel A. Stout, Judith Mitchell Buddenbaum › Selected pages Title Page Table of Contents Index Common terms and phrases advertising American Anabaptists audience Baha’i beliefs Bible broadcast Buddenbaum Buddhist Catholic century Christ Christian Church conﬂict Confucius congregation contemporary contemporary Christian music context create dance Daoist deﬁned deﬁnition developed difﬁcult divine early Evangelical example faith ﬁeld ﬁgures ﬁlm ﬁnd ﬁrst ﬁve Further Reading gious God’s Greek groups Haredi Hindu Hinduism holy human images individual inﬂuence Internet interpretive community Islam Jesus Jewish Jews Judaism leaders ligious literacy mass media means Mennonites ment modern moral mosque movement Muslim Native American ofﬁcial one’s oral organizations Orthodox political popular culture pornography practice prayer priests programs prophets Protestant Protestantism published Qur’an radio reﬂect reli religion religious communities ritual Roman sacred sacriﬁce scholars secular sermon sexual shaman signiﬁcant social society speciﬁc spiritual stories symbols televangelism televangelists television temple texts theology tion tradition University Press videos Western word worship York Bibliographic information Title Encyclopedia of religion, communication, and media Volume 8 of Religion and Society Routledge encyclopedias of religion and society Author Daniel A. Stout Editor Daniel A. Stout Edition illustrated Publisher CRC Press, 2006 ISBN 0415969468, 9780415969468 Length 467 pages Subjects Language Arts & Disciplines › Communication Studies Communication Communication - Religious aspects Communication/ Religious aspects Language Arts & Disciplines / Communication Studies Reference / Encyclopedias Religion / General Religion / Religion, Politics & State Export Citation BiBTeX EndNote RefMan About Google Books - Privacy Policy - Terms of Service - Blog - Information for Publishers - Report an issue - Help - Sitemap - Google Home ©2011 Google
Keywords: cyber; environment; internet

There’s a Religious App for that!: A Framework for Studying Religious Mobile Applications - Campbell, H; Altenhofen, B; Bellar, W; Cho, K.J (Mobile Media & Communication, 2014)
This article provides a new methodological approach to studying religious-oriented mobile applications available on the iTunes app store. Through an extensive review of 451 religious apps a number of problems were noted when relying solely on iTunes categories to identify app functions and purpose. Thus further analysis was done in order to present a new typology and framing of religious apps, which more accurately describe their design. We suggest that the 11 new categories offered here suggest a critical framework for studying religious apps. Thus this study provides a starting point for scholars interested in analyzing religious mobile applications to investigate how app developers integrate religious goals into their designs, and consider the primary ways people are expected to practice religion through mobile apps.
Keywords: App; religious; religious applications

"What hath God wrought”: Considering how religious communities culture (or kosher) the cell phone - Heidi Campbell (Continuum: Journal of Media and Culture, 2007)
Keywords: cell phone; Israel; kosher phone; Orthodox Judaism; religion

Rethinking the online-offline connection in religion online - Heidi Campbell; Lövheim, Mia (Information, Community & Society, 2011)
This special issue of Information, Communication and Society aims to present current research on the connection between online and offline religion and map out significant questions and themes concerning how this relationship takes shape among different religious traditions and contexts. By bringing together a collection of studies that explore these issues, we seek to investigate both how the Internet informs religious cultures in everyday life, and how the Internet is being shaped by offline religious traditions and communities. In order to contextualize the articles in the special issue, we offer a brief overview of how religion online has been studied over the past two decades with attention given to how the intersection of online-offline religion has been approached. This is followed by a discussion of key questions in the recent study of the relationship between online and offline religion and significant themes that emerge in contemporary research on religious uses of the Internet. These questions and themes help contextualize the unique contributions this special issue offers to the current discourse in this area, as well as how it might inform the wider field of Internet studies. We end by suggesting where future research on religion and the Internet might be headed, especially in relation to how we understand and approach the overlap between online and offline religion as a space of hybridity and social interdependence.
Keywords: internet and religion; offline; Online; religion

Religion and the Internet: A microcosm for studying Internet trends and implications - Heidi A Campbell (new media & society, 2012)
This article argues that paying close attention to key findings within the study of religion and the Internet, a subfield of Internet Studies, can enhance our understanding and discussion of the larger social and cultural shifts at work within networked society. Through a critical overview of research on religion online, five central research areas emerge related to social practices, online–offline connections, community, identity, and authority online. It is also argued that observations about these themes not only point to specific trends within religious practice online, but also mirror concerns and findings within other areas of Internet Studies. Thus, studying religion on the Internet provides an important microcosm for investigating Internet Studies’ contribution in a wide range of contexts in our contemporary social world.
Keywords: Authority; community; Computer; Contemporary Religious Community; cyberspace; identity; internet; Mass media; network; New Media and Society; new media engagement; New Technology and Society; offline; Online; online communication; Online community; religion; religion and internet; Religion and the Internet; religiosity; religious engagement; religious identity; Religious Internet Communication; Religious Internet Communities; Ritual; sociability unbound; Sociology of religion; users’ participation; virtual community; virtual public sphere; “digital religion”; “Internet Studies”; “media and religion”; “media research”; “networked society”; “online identity”; “religion online”; “religious congregations”; “religious media research”; “religious practice online”

Digital Creatives and the Rethinking of Religious Authority - Campbell, Heidi A. (Routledge, 2020)
Much speculation was raised in the 1990s, during the first decade of internet research, about the extent to which online platforms and digital culture might challenge traditional understandings of authority, especially in religious contexts. Digital Creatives and the Rethinking of Religious Authority explores the ways in which religiously-inspired digital media experts and influencers online challenge established religious leaders and those who seek to maintain institutional structures in a world where online and offline religious spaces are increasingly intertwined. In the twenty-first century, the question of how digital culture may be reshaping notions of whom or what constitutes authority is incredibly important. Questions asked include: Who truly holds religious power and influence in an age of digital media? Is it recognized religious leaders and institutions? Or religious digital innovators? Or digital media users? What sources, processes and/or structures can and should be considered authoritative online, and offline? Who or what is really in control of religious technological innovation? This book reflects on how digital media simultaneously challenges and empowers new and traditional forms of religious authority. It is a gripping read for those with an interest in communication, culture studies, media studies, religion/religious studies, sociology of religion, computer-mediated communication, and internet/digital culture studies.

Accessing Changes in the Study of Religious Communities in Digital Religion Studies - Campbell, H; Virtullo, A (Church, Communication & Culture, 2016)
This article provides a focused review of researches undertaken within Digital religion studies in the last three decades, specifically highlighting how religious communities have been studied and approached within this area. It highlights the dominant theoretical and methodological approaches employed by scholars during what is being described as the four stages of research on religious communities emerging over this period of time. Thus, this article presents the findings of key studies emerging during these stages to illuminate how the study of religious communities online has evolved over time. It also offers insights into how this evolution specifically relates to the study of Catholic community online. Finally, a theoretical analysis is given, assessing current research on religious communities within Digital Religion studies, and approaches for future research are proposed.
Keywords: Community online; Digital Religion; internet; offline; Online; religious communities

When Religion Meets New Media - Heidi Campbell (Routledge, 2010)
This book focuses on how different Jewish, Muslim, and Christian communities engage with new media. Rather than simply reject or accept new media, religious communities negotiate complex relationships with these technologies in light of their history and beliefs. I suggest a method for studying these processes called the "religious-social shaping of technology" and students are asked to consider four key areas: religious tradition and history; contemporary community values and priorities; negotiation and innovating technology in light of the community; communal discourses applied to justify use. A variety of examples such as the Christian e-vangelism movement, Modern Islamic discourses about computers and the rise of the Jewish kosher cell phone, demonstrate the dominant strategies which emerge for religious media users, as well as the unique motivations that guide specific groups.
Keywords: Christianity; Islam; Judaism; New Media

Texting the Faith: Religious Users and Cell Phone Culture - Heidi Campbell (The cell phone reader. Essays in social transformation, 2006)
The Cell Phone Reader offers a diverse, eclectic set of essays that examines how this rapidly evolving technology is shaping new media cultures, new forms of identity, and media-centered relationships. The contributors focus on a range of topics, from horror films to hip-hop, from religion to race, and draw examples from across the globe. The Cell Phone Reader provides a road map for both scholars and beginning students to examine the profound social, cultural and international impact of this small device.
Keywords: cell phone; Faith; religious; Texting

Studying Jewish Engagement with Digital Media and Culture - Campbell, H (Digital Judaism: Jewish Negotiations with Digital Media and Technology, 2015)
The study of new media, religion and digital culture has been in existence for almost two decades. During this time scholars have explored a wide range of religious group’s engagement with the internet, yet it is clear that some religious traditions, such as Christianity and Islam, have received much more attention than others. As Campbell and Lovheim (2011) noted in their assessment of the study of religion and the internet, there is still a need for a more nuanced understanding of the negotiation of the internet as a medium for religious practice within some religious groups. Also more careful consideration is called for regarding what some scholars have described as “digital religion”—the relationship between the online-offline religious contexts-within some religious traditions. This chapter argues that the study of Jewish groups and the internet has arguably been an understudied area in need of more significant attention and critical examination.
Keywords: culture; digital media; Judaism

Spiritualising the internet: Uncovering discourse and narrative of religious internet usage - Heidi Campbell (Online – Heidelberg Journal of Religions on the Internet, 2005)
Heidi Campbell deals with an important aspect of ”lived religion” and the Internet. In her contribution Spiritualising the Internet: Uncovering Discourses and Narratives of Religious Internet Usage, she focuses on how spiritual or religious worldviews shape the use and study of the Internet. Individuals and groups typically employ one of a range of conceptual models (such as the Internet as an information tool, identity workshop, common mental geography, social network or spiritual space) to frame their understanding of Internet technology and how it should be used. Narratives about the nature of this technology are often embedded within these discourses. Of particular interest to Campbell is the identification of narratives used to shape religious or spiritual Internet usage. Some of these can be described as offering a religious identity, support network, spiritual network or worship space. According to Campbell, religious narratives describe the religious group’s motivations and beliefs about acceptable use of technology in spiritual pursuits. They also highlight a process of negotiation and framing that is often undertaken in order to justify religious Internet usage. Campbell introduces Katz and Aakhus’s Apparageist theory of the social use of mobile technology, which provides one way to discuss this religious apologetic process related to the Internet. She is convinced that it also helps to uncover how technological selection can be linked to the spiritual worldviews to which individuals and/or groups ascribe.
Keywords: internet; religion; technology; theory of religion online

Religion and the Internet - Campbell, H (Research Methods and Theories in Digital Religion Studies, 2018)
Keywords: internet; religion

Religious Authority and the Blogosphere - Campbell, Heidi A. (Journal of Computer-Mediated Communication, 2010)
It is often argued that the internet poses a threat to traditional forms of authority. Within studies of religion online claims have also been made that the internet is affecting religious authority online, but little substantive work has backed up these claims. This paper argues for an approach to authority within online studies which looks separately at authority: roles, structures, beliefs/ideologies and texts. This approach is applied to a thematic analysis of 100 religious blogs and demonstrates that religious bloggers use their blogs to frame authority in ways that may more often affirm than challenge traditional sources of authority.

The Question of Christian Community Online: The Case of the Artist World Network - Heidi Campbell; Patricia Caulderon (Studies in World Christianity, 2007)
The past decade has seen a steady growth of technologies and practices that can be described as religion online. In many respects Christian groups and users have led the way in using the web for spiritual practices. From church websites becoming a common form of congregational advertising and communication to the rise of cyber churches and online prayer meetings, numerous forms of Christian practice have been transposed online. The Christian community has also been at the forefront of debates over the potential impact of ‘doing religion’ online. Concerns voiced by theologians, pastors and Christian scholars have included the potential that technology might become a substitute for God, the Internet could draw people away for organised religion towards individualised spiritualities, and that the Internet might reshape notions of traditional ritual and community. In light of these questions a new area of research has developed which involves exploring how Christian religious practice is being transformed in the age of Internet technology. Within such studies, the question of Christian or religious community online continues to surface as a central area of concern. As more and more Christian Internet users become involved in various chat, email and blogging groups, they are increasingly seeing and referring to these online social networks as religious communities. For many believers their Christian community involves both online and offline friendships and affiliations, a concept still problematic and contentious to many religious leaders. Thus, the purpose of this article is to investigate what constitutes a Christian community online and the possibilities and challenges that exist when Christians who gather for religious purpose online begin to conceive of their group as a Christian community. This is done by exploring a particular Christian online bulletin board, the ‘Artist World Network’, in order to understand how this group sees itself and functions as community. This investigation provides a way to address the question of what constitutes an online Christian community. It also opens up discussion on the possibilities and challenges online religious communities pose for offline Christian community.
Keywords: Christianity; community; internet; religion online

A Review of Religious Computer-Mediated Communication Research - Heidi Campbell (Mediating Religion: Conversations in Media, Culture and Religion, 2003)
This is the first book to bring together many aspects of the interplay between religion, media and culture from around the world in a single comprehensive study. Leading international scholars provide the most up-to-date findings in their fields, and in a readable and accessible way.37 essays cover topics including religion in the media age, popular broadcasting, communication theology, popular piety, film and religion, myth and ritual in cyberspace, music and religion, communication ethics, and the nature of truth in media saturated cultures.
Keywords: Communication; Computer; religion; Research

Studying technology & ecclesiology in online multi-site worship - Campbell, H; Delashmutt, M (Journal of Contemporary Religion, 2014)
This study brings together research approaches from media studies and practical theology in order to study and understand the relationship between online technological features of multi-site worship and the larger offline worshipping community to which it is connected. From the perspective of media studies we reflect on how new media technologies and cultures are allowed to shape online worship spaces and how larger institutional traditions and structures are allowed to shape technologically mediated church events. From the perspective of practical theology we use the notion of inculturation as a lens for a better understanding of the specific ways in which Christian worship practices adapt, change, and respond to the new cultural setting which emerges from the online worship context. Together, these approaches illuminate the interplay between digital technology and ecclesiological tradition in shaping multi-site church worship practices.
Keywords: Online; technology; worship

Bloggers and religious authority online - Heidi Campbell (Journal of Computer-Mediated Communication, 2010)
It is often argued that the internet poses a threat to traditional forms of authority. Within studies of religion online claims have also been made that the internet is affecting religious authority online, but little substantive work has backed up these claims. This paper argues for an approach to authority within online studies which looks separately at authority: roles, structures, beliefs/ideologies and texts. This approach is applied to a thematic analysis of 100 religious blogs and demonstrates that religious bloggers use their blogs to frame authority in ways that may more often affirm than challenge traditional sources of authority.
Keywords: Authority; blogs; religion; religious authority

Digital Religion: Understanding Religious Practice in New Media Worlds - Heidi A Campbell (Routledge, 2012)
Digital Religion offers a critical and systematic survey of the study of religion and new media. It covers religious engagement with a wide range of new media forms and highlights examples of new media engagement in all five of the major world religions. From cell phones and video games to blogs and Second Life, the book:provides a detailed review of major topics, includes a series of case studies to illustrate and elucidate the thematic explorations and considers the theoretical, ethical and theological issues raised. Drawing together the work of experts from key disciplinary perspectives, Digital Religion is invaluable for students wanting to develop a deeper understanding of the field.
Keywords: Digital Religion; Religion & New Media; Sociology of religion; Technoculture

When Religion Meets New Media: Media, Religion and Culture - Campbell, Heidi (Media, Religion, and Culture, 2007)
This lively book focuses on how different Jewish, Muslim, and Christian communities engage with new media. Rather than simply reject or accept new media, religious communities negotiate complex relationships with these technologies in light of their history and beliefs. Heidi Campbell suggests a method for studying these processes she calls the "religious-social shaping of technology" and students are asked to consider four key areas: religious tradition and history; contemporary community values and priorities; negotiation and innovating technology in light of the community; communal discourses applied to justify use. A wealth of examples such as the Christian e-vangelism movement, Modern Islamic discourses about computers and the rise of the Jewish kosher cell phone, demonstrate the dominant strategies which emerge for religious media users, as well as the unique motivations that guide specific groups.

Framing the Human-Technology Relationship: How Religious Digital Creatives Enact Posthuman Discourses - Campbell, H (Social Compass, 2016)
This article highlights the fact that careful study of common posthuman outlooks, as described by Roden (2015), reveals three unique narratives concerning how posthumanists view the nature of humanity and emerging technologies. It is argued that these narratives point to unique frames that present distinct understandings of the human-technology relationship, frames described as the technology-cultured, enhanced-human, and human-technology hybrid frames. It is further posited these frames correlate and help map a range of ways people discuss and critique the impact of digital culture on humanity within broader society. This article shows how these frames are similarly at work in the language used by Religious Digital Creatives within Western Christianity to justify their engagement with digital technology for religious purposes. Thus, this article suggests careful analysis of ideological discussions within posthumanism can help us to unpack the common assumptions held and articulated about the human-technology relationship by members within religious communities.
Keywords: Digital Creatives; religion; technology

Religion and the Internet - Heidi Campbell (Communication Research Trends, 2006)
Keywords: internet; religion

Methodological Challenges, Innovations and Growing Pains in Digital Religion Research - Campbell, H; Altenhofen, B (Digital Methodologies in the Sociology of Religion, 2015)
Keywords: Digital Religion

Making space for religion in internet studies - Heidi Campbell (The Information Society, 2005)
This paper seeks to address how religion fits into the larger domain of Internet studies and why studies of religion within CMC need to be given more attention. An argument is made for the need to take religion online more seriously, not just because it is an interesting phenomena or a popular use of the Internet, but also because religion continues to be an important part of contemporary life for many people. A summary of the growth and development of religion online is presented along with an overview of how religion has been approached and studied on the Internet. This review shows what CMC studies of religion might offer in approaching research questions related to authority, identity construction and community online. It calls for recognition of the contribution and possibilities that under-represented areas within interdisciplinary research, like religion, might offer Internet studies as a whole.
Keywords: CMC; Internet Studies; religion; religion online

Religion and the Internet - Campbell, H (Key Themes in the Study of Digital Religion, 2018)
Religion and the Internet will present a range of scholarly articles that offer a critical overview of the interdisciplinary study of new media, religion and digital culture. Scholars have documented individuals using computer networks for religious discussions and enagagment since the early 1980s. In the mid 1990s, when the Internet became publicly accessible, scholars began to study how users were translating and transporting their religious practices onto this new digital platform. This collection will cover the development of the study of Religion and the Internet over the past three decades, highlighting the core research topics, approaches and questions that have been explored by key international scholars at the intersection of new media and religion. The collection seeks to present how new forms of religious practices have emerged and been interrogated by scholars. It will also present how religious communities have negotiated their engagement with digital techologies and the online and offline implications this has had for religious practioners and individuals.
Keywords: internet; religion

Religious Communication and Technology - Campbell, H (The Annals of the ICA, 2017)
This article provides a review of contemporary research on religious communication and technologies through the lens of Digital Religion Studies, which explores how online and offline religious spheres become blended and blurred through digital culture. Summarizing the emergence and growth of studies of religion and the Internet, and offering an overview of scholarship demonstrating how religious actors negotiate their relationships and spiritual activities within their online–offline lives, enable us to look critically at the state of Digital Religion Studies. This article also highlights current trends and emerging themes within this area including increasing attention being paid to theoretical developments, approaching digital religion as lived religion, and the influence of postsecular and posthuman discourses within this scholarship.
Keywords: Digital Religion; internet; religion

How the iPhone became divine: Blogging, religion and intertextuality - Heidi Campbell; Antonio LaPastina (New Media and Society, 2010)
This article explores the labeling of the iPhone as the ‘Jesus phone’ in order to demonstrate how religious metaphors and myth can be appropriated into popular discourse and shape the reception of a technology. We consider the intertextual nature of the relationship between religious language, imagery and technology and demonstrate how this creates a unique interaction between technology fans and bloggers, news media and even corporate advertising. Our analysis of the ‘Jesus phone’ clarifies how different groups may appropriate the language and imagery of another to communicate very different meanings and intentions. Intertextuality serves as a framework to unpack the deployment of religion to frame technology and meanings communicated. We also reflect on how religious language may communicate both positive and negative aspects of a technology and instigate an unintentional trajectory in popular discourse as it is employed by different audiences, both online and offline.
Keywords: blogs; cell phone; fandom; intertexuality; iPhone; Jesus phone; religion; religious discourse; technology

Congregation of the Disembodied - Heidi Campbell (Virtual Morality, 2003)
Contents: Mark J. P. Wolf: Introduction - Gordon Hull: Digital Media and the Scope of « Computer Ethics - Emma Rooksby: Empathy in Computer-Mediated Communication - Mark J. P. Wolf: From Simulation to Emulation: Ethics, Worldviews, and Video Games - Paul J. Ford: Virtually Impacted: Designers, Spheres of Meaning, and Virtual Communities - Jason B. Jones: Communities of Envy: Psychoanalytic Perspectives on the Virtual Classroom - Jo Ann Oravec: OnLine Advocacy of Violence and Hate-Group Activity: The Internet as a Platform for the Expression of Youth Aggression and Anxiety - Chris Nagel: Hating in the Global Village - Leda Cooks: The Discursive Construction of Global Listserv Ethics: The Case of Panama-L - Heidi Campbell: Congregation of the Disembodied: A Look at Religious Community on the Internet - Maura McCarthy: Free Market Morality: Why Evangelicals Need Free Speech on the Internet - Andrew Careaga: World Wide Witness: Friendship Evangelism on the Internet - Kathy T. Hettinga: GraveImages: A Faith Visualized in a Technological Age.
Keywords: Congregation; disembodied

Surveying Theoretical Approaches within Digital Religion Studies - Campbell, H (New Media and Society, 2017)
This article provides an overview of the development of Digital Religion studies and the theoretical approaches frequently employed within this area. Through considering the ways and theories of mediatization, mediation of meaning, and the religious–social shaping of technology have been engaged and applied in studies of new media technologies, religion, and digital culture we see how Digital Religion studies has grown into a unique area of inquiry informed by both Internet studies and media, religion, and culture studies. Overall, it offers a concise summary of the current state of research inquiry within Digital Religion studies.
Keywords: Digital Religion; internet; mediation of meaning; mediatization; New Media; religion; religious–social shaping of technology; theory

Religious Authority in the Age of the Internet - Heidi Campbell; Paul Teusner (Virtual Lives: Christian Reflection, 2011)
As the internet changes how we interact with one another, it transforms our understanding of authority by creating new positions of power, flattening traditional hierarchies, and providing new platforms that give voice to the voice- less. How is it reshaping Christian leadership and institu- tions of authority?
Keywords: Authority; internet; religion

Religion and the Internet - Campbell, H (Mapping the Rise of the Study of Religious Practice Online, 2018)
Religion and the Internet will present a range of scholarly articles that offer a critical overview of the interdisciplinary study of new media, religion and digital culture. Scholars have documented individuals using computer networks for religious discussions and enagagment since the early 1980s. In the mid 1990s, when the Internet became publicly accessible, scholars began to study how users were translating and transporting their religious practices onto this new digital platform. This collection will cover the development of the study of Religion and the Internet over the past three decades, highlighting the core research topics, approaches and questions that have been explored by key international scholars at the intersection of new media and religion. The collection seeks to present how new forms of religious practices have emerged and been interrogated by scholars. It will also present how religious communities have negotiated their engagement with digital techologies and the online and offline implications this has had for religious practioners and individuals.
Keywords: Digital Religion; internet; religion

Postcyborg ethics: A new way to speak of technology? - Heidi Campbell (EME: Exploration in Media Ecology, 2006)
Keywords: cyborg; ethics; religion; technology

Understanding the relationship between religious practice online and offline in a networked society - Heidi Campbell (Journal of the American Academy of Religion, 2012)
This article suggests that religious practice online, rather than simply transforming religion, highlights shifts occurring within broader Western culture. The concept of “networked religion” is introduced as a way to encapsulate how religion functions online and suggests that online religion exemplifies several key social and cultural changes at work in religion in general society. Networked religion is defined by five key traits—networked community, storied identities, shifting authority, convergent practice, and a multisite reality—that highlight central research topics and questions explored within the study of religion and the internet. Studying religion on the internet provides insights not only into the common attributes of religious practice online, but helps explain current trends within the practice of religion and even social interactions in networked society.
Keywords: network; offline; Online; religion; society

Framing the human-technology relationship: How Religious Digital Creatives engage posthuman narratives - Campbell, Heidi (Social Compass, 2016)
This article highlights the fact that careful study of common posthuman outlooks, as described by Roden (2015), reveals three unique narratives concerning how posthumanists view the nature of humanity and emerging technologies. It is argued that these narratives point to unique frames that present distinct understandings of the human-technology relationship, frames described as the technology-cultured, enhanced-human, and human-technology hybrid frames. It is further posited these frames correlate and help map a range of ways people discuss and critique the impact of digital culture on humanity within broader society. This article shows how these frames are similarly at work in the language used by Religious Digital Creatives within Western Christianity to justify their engagement with digital technology for religious purposes. Thus, this article suggests careful analysis of ideological discussions within posthumanism can help us to unpack the common assumptions held and articulated about the human-technology relationship by members within religious communities.

Networked Theology: Negotiating Faith in Digital Culture - Campbell, H; Garner, S (Baker Academic, 2016)
This informed theology of communication and media analyzes how we consume new media and technologies and discusses the impact on our social and religious lives. Combining expertise in religion online, theology, and technology, the authors synthesize scholarly work on religion and the internet for a nonspecialist audience. They show that both media studies and theology offer important resources for helping Christians engage in a thoughtful and faith-based critical evaluation of the effect of new media technologies on society, our lives, and the church.
Keywords: digital cultures; Faith; theology

The Dissonance of “Civil” Religion in Religious-Political Memetic Discourse During the 2016 Presidential Elections - Campbell, H; Arrezndo, K; Dundas, K; Wolf, C (Social Media+Society)
Keywords: Politics; religion

Gaming Religionworlds: Why Religious Studies Should Pay Attention to Religion in Gaming - Campbell, H; Grieve, G.P; Gregory, R; Lufts, S; Wagner, R; Zeiler, X (Journal of the American Academy of Religion, 2016)
This roundtable article discusses the intersection between digital gaming, new media, and Religious Studies in order to provide an agenda for this growing conversation. We argue that religion plays a prominent role in gaming culture with significant impact on popular collective imaginations; therefore, studying religion in gaming should be central to religious scholars' work in trying to understand perceptions of religion in popular culture. This collaborative conversation demonstrates how careful attention to religious narratives, rituals, and behaviors within game studies and environments can open up a space for critical reflection on how popular understandings of religion are manifest within contemporary media and society. Overall, it demonstrates what Religious Studies can and should contribute to the study of games by considering several critical questions about the study of religion within digital gaming and speculating where this field should be heading.
Keywords: gaming; religion

Religious engagement with the internet within Israeli Orthodox groups - Heidi Campbell (Israel Affairs, 2011)
This article provides an overview of research on religion and the Internet within the Israeli context, highlighting how Orthodox Jewish groups have appropriated and responded to the Internet. By surveying Orthodox use of the Internet, and giving special attention to the ultra Orthodox negotiations, a number of key challenges that the Internet poses to the Israeli religious sector are highlighted. Exploring these debates and negotiations demonstrates that while the Internet is readily utilized by many Orthodox groups, it is still viewed by some with suspicion. Fears expressed, primarily by ultra Orthodox groups, shows religious leaders often attempt to constrain Internet use to minimize its potential threat to religious social norms and the structure of authority. This article also highlights the need for research that addresses the concerns and strategies of different Orthodox groups in order to offer a broader understanding of Orthodox engagement with the Internet in Israel.
Keywords: Authority; community; internet; Israel; Judaism; Orthodox; religion; ultra Orthodox

This is my church: Seeing the internet and club culture as spiritual space - Heidi Campbell (Religion Online: Finding Faith on the Internet, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression. Religion Online provides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes the Pew Internet and American Life Project Executive Summary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-defining Cyberspace as Sacred Space.
Keywords: Christianity; Church; club culture; internet

Internet and social media - Campbell, H; Teusner, P. E (Routledge’s Companion to Religion and Popular Culture, 2015)
Religion and popular culture is a fast-growing field that spans a variety of disciplines. This volume offers the first real survey of the field to date and provides a guide for the work of future scholars. It explores key issues of definition and of methodology, religious encounters with popular culture across media, material culture and space, ranging from videogames and social networks to cooking and kitsch, architecture and national monuments representations of religious traditions in the media and popular culture, including important non-Western spheres such as Bollywood.
Keywords: internet; social media

Exploring Religious Community Online: We are one in the Network - Heidi Campbell (Peter Lang Publishing, 2005)
Exploring Religious Community Online is a first comprehensive study of the development and implications of online communities for religious groups. This book investigates religious community online by examining how Christian communities have adopted internet technologies, and looks at how these online practices pose new challenges to offline religious community and culture.
Keywords: Christianity; community; email; internet; religion; religious identity

Playing with Religion in Digital Games - Campbell, H; Grieve, G (Indiana University Press, 2014)
Shaman, paragon, God-mode: modern video games are heavily coded with religious undertones. From the Shinto-inspired Japanese video game Okami to the internationally popular The Legend of Zelda and Halo, many video games rely on religious themes and symbols to drive the narrative and frame the storyline. Playing with Religion in Digital Games explores the increasingly complex relationship between gaming and global religious practices. For example, how does religion help organize the communities in MMORPGs such as World of Warcraft? What role has censorship played in localizing games like Actraiser in the western world? How do evangelical Christians react to violence, gore, and sexuality in some of the most popular games such as Mass Effect or Grand Theft Auto? With contributions by scholars and gamers from all over the world, this collection offers a unique perspective to the intersections of religion and the virtual world.
Keywords: digital games; religion

Internet and Religion - Heidi Campbell (The Blackwell Handbook of Internet Studies, 2011)

Internet and Cyber Environments - Heidi Campbell (Encyclopedia of Religion, Communication and Media, 2006)
Communication is at the heart of all religions. As an essential aspect of religion, communication occurs between believers, between religious leaders and followers, between proponents of different faiths, and even between practitioners and the deities. The desire to communicate with as well as convert others is also an aspect of some of the world's major religions. The Encyclopedia of Religion, Communication, and Media explores all forms of religious communication worldwide and historically, with a special emphasis on oral and written forms of communication. This A-Z organized reference work analyzes how and why the world's religions have used different means of communications through topics dealing with: * Theory and concepts in religious communication, including rhetoric, persuasion, performance, brainwashing, and more * Forms of verbal communication, such as chanting, speaking in tongues, preaching, or praying * Forms of written communication, such as religious texts,parables, mystical literature, and modern Christian publishing * Other forms of communication, including art, film, and sculpture * Religious communication in public life, from news coverage and political messages to media evangelism and the electronic church * Communication processes and their effects on religious communication, including non-sexist language, communication competence, or interfaith dialogue * Biographies of major religious communicators, including Muhammad, Jesus, Aristotle, Gandhi, and Martin Luther From the presence of religion on the internet to the effects of religious beliefs on popular advertising, communication and media are integral to religion and the expression of religious belief. With its international and multicultural coverage, this Encyclopedia is an essential and unique resource for scholars, students, as well as the general reader interested in religion, media, or communications.

Who’s got the power? The question of religious authority and the internet - Heidi Campbell (Journal of Computer-Mediated Communication, 2007)
While many themes have been explored in relation to religion online—ritual, identity construction, community—what happens to religious authority and power relationships within online environments is an area in need of more detailed investigation. In order to move discussions of authority from the broad or vague to the specific, this article argues for a more refined identification of the attributes of authority at play in the online context. This involves distinguishing between different layers of authority in terms of hierarchy, structure, ideology, and text. The article also explores how different religious traditions approach questions of authority in relation to the Internet. Through a qualitative analysis of three sets of interviews with Christians, Jews, and Muslims about the Internet, we see how authority is discussed and contextualized differently in each religious tradition in terms of these four layers of authority.
Keywords: Authority; Christianity; internet; Islam; Judaism

PICTURE: The Adoption of ICT by Catholic Priest - Cantoni, L; Rapetti, E; Tardini, S; Vannini, S; Arasa, D (Digital Religion, Social Media and Culture. Perspectives, Practices and Futures, 2012)
This anthology - the first of its kind in eight years - collects some of the best and most current research and reflection on the complex interactions between religion and computer-mediated communication (CMC). The contributions cohere around the central question: how will core religious understandings of identity, community and authority shape and be (re)shaped by the communicative possibilities of Web 2.0? The authors gathered here address these questions in three distinct ways: through contemporary empirical research on how diverse traditions across the globe seek to take up the technologies and affordances of contemporary CMC; through investigations that place these contemporary developments in larger historical and theological contexts; and through careful reflection on the theoretical dimensions of research on religion and CMC. In their introductory and concluding essays, the editors uncover and articulate the larger intersections and patterns suggested by individual chapters, including trajectories for future research.
Keywords: Catholic; ICT

Online Communication of the Catholic World Youth Days - Cantoni, L; Stefania, M; De Ascanis, S (Reflecting on Religious Tourism and Pilgrimage, 2012)
This paper aims to explore the ways in which religious tourism in India fosters religious tolerance. Design/methodology/approach – The paper uses a conceptual apparatus derived from the basic structure of religious tourism comprising motivation, journey and destination, to understand various aspects of tolerance. Tolerance, with the implicit meaning of diversity and pluralism, is examined at two levels – intra-religion and inter-religion – using field investigations from three Hindu pilgrimage sites, namely, Vrindavan, Tuljapur, Shegaon and review of one Muslim site called Ajmer Sharif. These sites exhibit a range of combinations, sectarian traditions within Hindu and their interactions with others, including Muslims and foreigners. Findings – Each of the sites provides different sets of opportunities for the “others” to get exposed to religious and cultural aspects. It is found that tolerance within the Hindu sects and with non-Hindus from other religious faiths is a function of their engagement with cultural performances and participation in the religious tourism economy in a pilgrimage site. Originality/value – On a broader level, this paper argues that conceptualising tolerance within a social and cultural sphere helps in a better understanding of tolerance and identifying areas within religious tourism where it can be promoted. A conscious effort to promote tolerance through religious tourism will add value to religious tourism and help it thrive.
Keywords: Catholic; online communication; Youth

The Use of Internet Communication by Catholic Congregations: A Quantitative Study - Cantoni, Lorenzo; Zyga, Slawomir (Journal of Media and Religion, 2007)
This article presents a first attempt to measure the use of the internet by all 5,812 Catholic religious congregations and autonomous institutes worldwide (with 858,988 members). The research was conducted through a questionnaire sent by e-mail, hence first selecting those institutions which at least have an access to internet communication through an e-mail account (2,285: 39.3% of the total), receiving 437 responses (19.1% of the e-mail owners). The study shows great differences between centralized institutes and autonomous ones: the former ones make a higher use of the Internet than the latter ones; moreover, differences are also found among centralized institutes, namely between male and female ones. Two explanatory elements have been found, both depending on the own mission (charisma) of institutes: (1) first, the different approach to the external world: the institutes more devoted to contemplation and less active in the outside world make limited and basic use of the Internet, if any; (2) second, institutes whose aim is to assist poor and sick persons tend to use the internet less than the others, due to their different prioritization of resources.
Keywords: Catholic; Communication; religion

The Use of Internet Communication by Catholic Congregations: A Quantitative Study - Cantoni, L; Zyga, S (Journal of Media and Religion, 2007)
This article presents a first attempt to measure the use of the internet by all 5,812 Catholic religious congregations and autonomous institutes worldwide (with 858,988 members). The research was conducted through a questionnaire sent by e-mail, hence first selecting those institutions which at least have an access to internet communication through an e-mail account (2,285: 39.3% of the total), receiving 437 responses (19.1% of the e-mail owners). The study shows great differences between centralized institutes and autonomous ones: the former ones make a higher use of the Internet than the latter ones; moreover, differences are also found among centralized institutes, namely between male and female ones. Two explanatory elements have been found, both depending on the own mission (charisma) of institutes: (1) first, the different approach to the external world: the institutes more devoted to contemplation and less active in the outside world make limited and basic use of the Internet, if any; (2) second, institutes whose aim is to assist poor and sick persons tend to use the internet less than the others, due to their different prioritization of resources.
Keywords: Catholic; Catholic religious congregations; Computer; congregations; Contemporary Religious Community; cyberspace; email; internet; internet communication through an e-mail account; Mass media; network; New Media and Society; new media engagement; New Technology and Society; online communication; Online community; religion; religion and internet; Religion and the Internet; religiosity; religious engagement; religious identity; Religious Internet Communication; Religious Internet Communities; sociability unbound; Sociology of religion; users’ participation; virtual community; virtual public sphere; “media research”; “religion online”; “religious media research”

EMinistry: Connecting with the net generation - Careaga, Andrew (Kregel Publishing, 2001)
An Internet savvy youth pastor and journalist advises church leaders on creative and effective use of leading-edge technology to reach the Net Generation.
Keywords: Connection; ministry; next generation

E-vangelism: Sharing the Gospel in Cyberspace - Careaga, Andrew (Huntington House Publishers, 1999)
"E-vangelism: Sharing the Gospel in Cyberspace" by Andrew Careaga (Vital Issues Press) discusses saving souls in cyberspace. Chapter one, "E-vangelism: Fishing the Net," is online. Other chapters include "Getting Started," "The Wide, Wide World of the World Wide Web," "Chatting for Christians" and "Piercing the Darkness." "A lot of churches, parachurch ministries and devout believers see cyberspace as a new mission field," Careaga says. "They're using the Internet as a tool to get their message out, and it seems to be working." "E-vangelism" focuses on how churches, parachurch organizations and individuals are using the Internet to communicate their theology to the online world. Order this inspirational book online.
Keywords: cyberspace; evangelism; Gospel; internet

eMinistry : connecting with the net generation - Careaga, A. (Kregel Publications, 2001)
An Internet savvy youth pastor and journalist advises church leaders on creative and effective use of leading-edge technology to reach the Net Generation.
Keywords: Connection; generation; ministry

Communicating Jesus in a virtual world - Ben Carswell (Canvas, 2009)
This article suggests various strategies for and advantages of using various communication technologies—texting, Facebook, Twitter, blogging, online chatting—to evangelize in New Zealand, particularly to a younger generation. Drawing on various Scriptural references and Christian theological arguments, Carswell explains how such online technologies can help those attempting to share the Gospel of Christ with others.
Keywords: Communication; Jesus; Virtual

The Basilica of Guadalupe on the Internet: The Diffusion of Religious Practices in the Era of Information Technologies - Pablo Ignacio Aburto Carvajal (Renglones, Revista Arbitrada en Ciencias Sociales y Humanidades, 2009)
This article discusses the use of new information technologies for the purpose of disseminating religious beliefs. It deals in particular with the web awareness strategy used by the Basilica of Guadalupe, a pioneering institution in the use of an Internet site for religious purposes in Mexico. The author examines the relationship between media and people, rituals and spaces involved in religious practices; he also gives an overview of the different communication models favored by the Catholic Church at different moments in the history of media. With a qualitative research method, using in–depth interviews as data collection tool, a semantic content analysis is performed, allowing identification of the main courses for the Basilica’s online awareness strategy. One conclusion is that the main use for the web site is broadcasting information and providing services to the faithful, which subordinates the religious message to the advantages and conditions imposed by the medium, as well as its specific hazards, from the emitter’s point of view. Given its relevance in Mexico, the communication strategy applied by the Basilica can shed light on the steps that other entities linked to the Catholic Church in this country could take in the future.
Keywords: Basilica of Guadalupe; Catholic Church; communication – group and community; information technologies; internet; media; religion; religious practices – diffusion

Virtual Ritual, Real Faith : the Revirtualization of Religious Ritual in Cyberspace - Cheryl Anne Casey (Online – Heidelberg Journal of Religions on the Internet, 2006)
Cheryl Anne Casey deals with Practicing Faith in Cyberspace: Conceptions and Functions of Religious Rituals on the Internet. She examines the emerging phenomenon of online religious rituals and their functions for participants in order to illuminate the relationship between changing technologies of communication and our changing conceptions of religion. Her case study considers an online Episcopalian church service within the framework of ritual theory. Keys to the analysis are the particular design chosen for the service (given the multifarious forms which rituals can take in cyberspace) and the relationship between choice of design and the tenets of the particular faith group. The objective of this study is to shed light on the relationship between conceptions of religion, religious experience, and changing media environments by examining online rituals and the meanings and functions these rituals hold for those who access them
Keywords: Contemporary Religious Community; cyberspace; Episcopalian church; internet; media environments; New Media and Society; new media engagement; New Technology and Society; online communication; religious experience; RELIGIOUS RITUAL

The Internet Galaxy: Reflections on the Internet, Business and Society - Castells, Manuel (Oxford University Press, 2001)
Manuel Castells is one of the world's leading thinkers on the new information age, hailed by The Economist as "the first significant philosopher of cyberspace," and by Christian Science Monitor as "a pioneer who has hacked out a logical, well-documented, and coherent picture of early 21st century civilization, even as it rockets forward largely in a blur." Now, in The Internet Galaxy, this brilliantly insightful writer speculates on how the Internet will change our lives. Castells believes that we are "entering, full speed, the Internet Galaxy, in the midst of informed bewilderment." His aim in this exciting and profound work is to help us to understand how the Internet came into being, and how it is affecting every area of human life--from work, politics, planning and development, media, and privacy, to our social interaction and life in the home. We are at ground zero of the new network society. In this book, its major commentator reveals the Internet's huge capacity to liberate, but also its ability to marginalize and exclude those who do not have access to it. Castells provides no glib solutions, but asks us all to take responsibility for the future of this new information age. The Internet is becoming the essential communication and information medium in our society, and stands alongside electricity and the printing press as one of the greatest innovations of all time. The Internet Galaxy offers an illuminating look at how this new technology will influence business, the economy, and our daily lives.
Keywords: Business; Economy; internet; society

The network society: A cross-cultural perspective - Manuel Castells (Edward Elgar Publishing, 2004)
Manuel Castells - one of the world's pre-eminent social scientists - has drawn together a stellar group of contributors to explore the patterns and dynamics of the network society in its cultural and institutional diversity. The book analyzes the technological, cultural and institutional transformation of societies around the world in terms of the critical role of electronic communication networks in business, everyday life, public services, social interaction and politics. The contributors demonstrate that the network society is the new form of social organization in the Information age, replacing the Industrial society. The book analyzes processes of technological transformation in interaction with social culture in different cultural and institutional contexts: the United States of America, the United Kingdom, Finland, Russia, China, India, Canada, and Catalonia. The topics examined include business productivity, global financial markets, cultural identity, the uses of the Internet in education and health, the anti-globalization movement, political processes, media and identity, and public policies to guide technological development. Taken together these studies show that the network society adopts very different forms, depending on the cultural and institutional environments in which it evolves. The Network Society, now available in paperback, is an outstanding and original volume of direct interest in academia - particularly in the fields of social sciences, communication studies, and business schools - as well as for policymakers engaged in technological policy and economic development. Business and management experts will also discover much of value to them within this book. Contributors: S.K. Acord, W.E. Baker, T. Bates, C. Benner, N. Bulkley, M. Castells, A. Chatterjee, K.M. Coleman, M.I. Díaz de Isla, K.N. Hampton, P. Himanen, J.S. Juris, J.E. Katz, J. Linchuan Qiu, R.D. Pinkett, R.E. Rice, T. Sancho, L.J. Servon, A. Sey, I. Tubella, M. Van Alstyne, E. Vartanova, B. Wellman, R. Williams, S. Woolgar, C. Zaloom

Making the Internet Kosher: Orthodox (HAREDI) Jews and their Approach to the WORLD WIDE WEB - Cejka, M (Masaryk University Journal of Law and Technology, 2009)
This article surveys the approach of Orthodox Judaism – especially the Haredi (Ultra- Orthodox) Judaism – to the Internet. In the introduction we compare the approach of the Abrahamic religions to the Internet. Then we focus on the Haredi community (especially in the contemporary State of Israel) and their specific approach to the Internet. This article argues that the use of the Internet, although officially banned by many Haredi Rabbis, is in fact tolerated on a pragmatic basis. We also survey which kind of “protection against secular threads” the Haredim1 use (filtering software, Holy Shabbat protection). In the last part of this article the role of the Internet in Israeli religious politics, and by its uses by fundamentalist and radical Jewish groups, is surveyed
Keywords: Halakha; Haredim; Judaism; Kosher; Rabbi; religious fundamentalism; Religious law; the Internet; Ultra-Orthodox Jews

“Islamophobia” in the West: A Comparison Between Europe and America - Jocelyn Cesari (Islamophobia and the Challenges of Pluralism in the 21st Century, 2009)
Keywords: America; anti-terrorism; Europe; Islam; Islamophobia; Muslims; xenophobia

Finding God on the Web - Chama, Joshua. R. C. (TIME, 1996)
Keywords: God; internet

Secularization as declining religious authority - Mark Chaves (Social Forces)
Secularization is most productively understood not as declining religion, but as the declining scope of religious authority. A focus on religious authority (1) is more consistent with recent developments in social theory than is a preoccupation with religion; (2) draws on and develops what is best in the secularization literature; and (3) reclaims a neglected Weberian insight concerning the sociological analysis of religion. Several descriptive and theoretical “pay-offs” of this conceptual innervation are discussed: new hypotheses concerning the relationship between religion and social movements; the enhanced capacity to conceptually apprehend and empirically investigate secularization among societies, organizations, and individuals; and clearer theoretical connections between secularization and other sociological literatures. Ironically, these connections may indeed spell the end of secularization theory as a distinct body of theory, but in a different way than previously appreciated.

Religious authority in the modern world - Chavez, M (Society, 2003)

Twitter of Faith: Understanding social media networking and microblogging rituals as religious practices - Pauline Hope Cheong (Digital Religion, Social Media and Culture: Perspectives, Practices, Futures, 2012)
Keywords: blogs; internet; microblogging; social media

Religious Communication and Epistemic Authority of Leaders in Wired Faith Organizations - Pauline Hope Cheong; Huang, Shirlena; Poon, Jessie (Journal of Communication, 2011)
The mediation of communication has raised questions of authority shifts in key social institutions. This paper examines how traditional sources of epistemic power that govern social relations in religious authority are being amplified or delegitimized by Internet use, drawing from in-depth interviews with protestant pastors in Singapore. Competition from Internet access is found to delocalize epistemic authority to some extent; however, it also re-embeds authority by allowing pastors to acquire new competencies as strategic arbiters of religious expertise and knowledge. Our study indicates that while religious leaders are confronted with proletarianization, deprofessionalization and potential de-legitimization as epistemic threats, there is also an enhancement of epistemic warrant as they adopt mediated communication practices that include the social networks of their congregation.
Keywords: Authority; internet; theory of religion online

Religion 2.0? Relational and hybridizing pathways in religion, social media and culture - Pauline Hope Cheong; Ess, Charles (Digital Religion, Social Media and Culture: Perspectives, Practices, Futures, 2012)
Keywords: Authority; community; identity; internet; religion; social media

Faith Tweets: Ambient Religious Communication and Microblogging Rituals - Pauline Hope Cheong (Journal of Media and Culture, 2010)
The notion of ambient strikes a particularly resonant chord for religious communication: many faith traditions advocate the practice of sacred mindfulness, and a consistent piety in light of holy devotion to an omnipresent and omniscient Divine being. This paper examines how faith believers appropriate the emergent microblogging practices to create an encompassing cultural surround to include microblogging rituals which promote regular, heightened prayer awareness. Faith tweets help constitute epiphany and a persistent sense of sacred connected presence, which in turn rouses an identification of a higher moral purpose and solidarity with other local and global believers. Amidst ongoing tensions about microblogging, religious organisations and their leadership have also begun to incorporate Twitter into their communication practices and outreach, to encourage the extension of presence beyond the church walls.
Keywords: ambient; Blogging; Communication; religion; Twitter

Cultivating online and offline pathways to enlightenment: Religious authority in wired Buddhist organizations - Pauline Hope Cheong; Huang, Shirlena; Poon, Jessie (Information, Communication & Society, 2011)
In light of expanding epistemic resources online, the mediatization of religion poses questions about the possible changes, decline and reconstruction of clergy authority. Distinct from virtual Buddhism or cybersangha research which relies primarily on online observational data, this paper examines Buddhist clergy communication within the context of established religious organizations with an integrationist perspective on interpersonal communication and new and old media connections. Drawing on in-depth interviews with Buddhist leaders in Singapore, this paper illustrates ways in which priests are expanding their communicative competency, which we label “strategic arbitration” to maintain their authority by restructuring multimodal representations and communicative influence. This study expands upon previous research by Cheong, Huang & Poon (in press) and finds that constituting Buddhist religious epistemic authority in wired organizational contexts rests on coordinating online-offline communicative acts. Such concatenative coordination involves normalizing the aforementioned modality of authority through interpersonal acts that positively influences epistemic dependence. Communicative acts that privilege face-to-face mentoring and corporeal rituals are optimized in the presence of monks within perceived sacred spaces in temple grounds, thereby enabling clergy to perform ultimate arbitration. However, Buddhist leaders also increase bargaining power when heightened web presence and branding practices are enacted. The paper concludes with limitations and recommendations for future research in religious authority.
Keywords: Authority; community; internet; religion; theory of religion online

Transnational immanence: the autopoietic co-constitution of a Chinese spiritual organization through mediated communication - Pauline Hope Cheong; Jennie M. Hwang; Boris H.J.M. Brummansb (Information, Communication & Society, 2013)
Information and communication technologies are often cited as one major source, if not the causal vector, for the rising intensity of transnational practices. Yet, extant literature has not examined critically how digital media appropriation affects the constitution of transnational organizations, particularly Chinese spiritual ones. To address the lack of theoretically grounded, empirical research on this question, this study investigates how the Buddhist Compassion Relief Tzu Chi Foundation (Tzu Chi), one of the largest Taiwan-based civil and spiritual nonprofit organizations among the Chinese diaspora, is co-constituted by various social actors as an operationally closed system through their mediated communication. Based on an innovative theoretical framework that combines Maturana and Varela's notion of ‘autopoiesis’ with Cooren's ideas of ‘incarnation’ and ‘presentification’, we provide a rich analysis of Tzu Chi's co-constitution through organizational leaders' appropriation of digital and social media, as well as through mediated interactions between Tzu Chi's internal and external stakeholders. In so doing, our research expands upon the catalogue of common economic and relational behaviors by overseas Chinese, advances our understanding of Chinese spiritual organizing, and reveals the contingent role of digital and social media in engendering transnational spiritual ties to accomplish global humanitarian work.
Keywords: Asia; Authority; autopoiesis; Buddhist Compassion Relief Tzu Chi Foundation; communicative constitution of organizations; information and communication technologies; nonprofit; social media; Taiwan; transnationalism

‘WWW.Faith.Org’: (Re)structuring communication and social capital building among religious organizations. - Pauline Hope Cheong; Poon, Jessie (Information, Communication and Society, 2008)
This paper examines the relationships between Internet and social capital building within religious organizations, a relatively understudied foci. Building upon theoretical insights provided by new institutionalism and recent research on the Internet, social capital and religion, this article explores the ways in which religious organizations, have (re)structured their norms, values, and practices of religious community in light of the incorporation of the Internet into their congregational life. Drawing from interviews conducted with Christian and Buddhist religious leaders in Toronto, this article discusses three major relationships in which the effects of the Internet on social capital may be understood, that is, complementary, transformative, and perverse relationships. Religious organizations are traditionally associated with relatively high stocks of social capital, yet findings here suggest that their communicative norms, values, and practices are changing to varying extent. The results also indicate that the relationship between the Internet and social capital building is largely complementary; however the Internet is perceived by some to be a ‘mixed blessing’, facilitating the potential transformation of organizational practices that affect community norms while leading to the dispersion of religious ties that could undermine community solidarity. Thus, contrary to earlier studies that have documented no evidence of innovations involving the reconfiguration of organizational practices and the adjustment of mission or services, findings here illustrate how some religious organizations have expanded the scope of their calling and restructured their communicative practices to spur administrative and operational effectiveness. Like other organizations, religious organizations are not insulated from technological changes including those associated with the Internet’s. This study clarifies and identifies key ways in which the distinct spirituality, cultural values, and institutional practices and norms of religious organizations influence communication processes that constitute bridging and bonding forms of social capital in this dot.org. era of faith.
Keywords: community; internet; social capital; theory of religion online

The vitality of new media and religion: Communicative perspectives, practices, and changing authority in spiritual organization - Cheong, Pauline Hope (New Media & Society)
We are witnessing the growth of a distinct sub-field focusing on new media and religion as the relationship between the two is not just important, it is vital. I discuss in this article how this vitality is both figurative and literal in multiple dimensions. Mediated communication brings forth and constitutes the (re)production of spiritual realities and collectivities, as well as co-enacts religious authority. In this way, new mediations grounded within older communication practices serve as the lifeblood for the evolving nature of religious authority and forms of spiritual organizing. Further research to identify diverse online and embodied religious communication practices will illuminate a richer understanding of digital religion, especially as a globally distributed phenomenon.
Keywords: Authority; Communication

Mediated Intercultural Communication Matters: Understanding new media, change and dialectics - Cheong, P.H; Macfadyen L.; Martin, J. (New Media and Intercultural Communication: Identity, Community and Politics, 2012)
Keywords: community; New Media; Politics

The Chronicles of Me: Understanding Blogging as a Religious Practice - Cheong, Pauline; Halavais, Alex; Kwon, Kyounghee (Journal of Media and Religion, 2008)
Blogs represent an especially interesting site of online religious commu- nication. Analysis of the content of 200 blogs with mentions of topics related to Christianity, as well as interviews of a subset of these bloggers, suggests that blogs provide an integrative experience for the faithful, not a third place, but a melding of the personal and the communal, the sacred and the profane. Religious bloggers operate outside the realm of the conventional nuclear church as they connect and link to mainstream news sites, other nonreligious blogs, and online collaborative knowledge networks such as Wikipedia. By chronicling how they experience faith in their everyday lives, these bloggers aim to communicate not only to their communities and to a wider public but also to themselves. This view of blogging as a contemplative religious experience differs from the popular characterization of blogging as a trivial activity.
Keywords: blogs; hyperlinks; internet; religion

Authority - Cheong, P (Digital Religion: Understanding Religious Practice in New Media Worlds, 2012)
Digital Religion offers a critical and systematic survey of the study of religion and new media. It covers religious engagement with a wide range of new media forms and highlights examples of new media engagement in all five of the major world religions. From cell phones and video games to blogs and Second Life, the book: provides a detailed review of major topics includes a series of case studies to illustrate and elucidate the thematic explorations considers the theoretical, ethical and theological issues raised. Drawing together the work of experts from key disciplinary perspectives, Digital Religion is invaluable for students wanting to develop a deeper understanding of the field.
Keywords: Apps; Authority; Digital; media; religion; technology

The Internet Highway and Religious Communities: Mapping and Contesting Spaces in Religion-Online - Pauline Hope Cheong; Huang, Shirlena; Poon, Jessie; Casas, Irene (The Information Society, 2009)
We examine ‘religion-online’, an underrepresented area of research in new media, communication, and geography, with a multi-level study of the online representation and (re)-presentation of Protestant Christian organizations in Singapore, which has one of the highest Internet penetration rates in the world and also believers affiliated with all the major world religions. We first critically discuss and empirically examine how online technologies are employed for religious community building in novel and diverse ways. Then we investigate the role religious leaders play through their mental representations of the spatial practices and scales through which their religious communities are imagined and practiced online. We show how churches use the multimodality of the Internet to assemble multiple forms of visible data and maps to extend geographic sensibilities of sacred space and create new social practices of communication.
Keywords: Authority; community; geography; internet; theory of religion online

Cheong, P. H. (2014). Tweet the Message? Religious Authority and Social Media Innovation. Journal of Religion, Media & Digital Culture, 3(3), 2–19. - Cheong, Pauline Hope (Religion, Media, and Digital Culture, 2014)
Religious believers have historically adapted Scripture into brief texts for wider dissemination through relatively inexpensive publications. The emergence of Twitter and other microblogging tools today afford clerics a platform for real time information sharing with its interface for short written texts, which includes providing links to graphics and sound recordings that can be forwarded and responded to by others. This paper discusses emergent practices in tweet authorship which embed and are inspired by sacred Scripture, in order to deepen understanding of the changing nature of sacred texts and of the constitution of religious authority as pastors engage microblogging and social media networks. Drawing upon a Twitter feed by a prominent Christian megachurch leader with global influence, this paper identifies multiple ways in which tweets have been encoded to quote, remix and interpret Scripture, and to serve as choice aphorisms that reflect or are inspired by Scripture. Implications for the changing nature of sacred digital texts and the reconstruction of religious authority are also discussed.
Keywords: Bible; pastors; religious authority; Singapore; social media; Twitter

Weaving Webs of Faith: Examining Internet Use and Religious Communication Among Chinese Protestant Transmigrants - Pauline Hope Cheong; Poon, Jessie (Journal of International and Intercultural Communication, 2009)
This paper examines the relationship between new media use and international communication that addresses religiosity and affirms users' standpoints occupied by transmigrants that are marginalized in dominant societal structures. Drawing from focus group interviews among recent Chinese Protestant immigrants in Toronto, we argue that new media “use” is broadened by users' cultural appropriation in situational contexts to include proxy internet access as accommodative communication given the political and legal constraints in their home country. Chinese transmigrants not only reinterpret and alter semantic associations that spiritualize the internet, they also engage in innovative strategies that involve the intertwining of offline and online communicative modes. These include deploying complementary media forms or communicating in codes that are mutually understood among participating members to facilitate intragroup networking among Chinese religious communities. Implications are discussed with regard to the importance of cultural norms and situational context in shaping mediated international communication.
Keywords: Chinese; Communication; Immigrants; Media use

Religion, Robots and Rectitude: Communicative Affordances for Spiritual Knowledge and Community - Cheong, Pauline Hope (Applied Artificial Intelligence, 2020)
In light of growing concerns on AI growth and gloomy projections of attendant risks to human well-being and expertise, recent development of robotics designed to fulfill spiritual goals can help provide an alternative, possibly uplifting vision of global futures. To further understanding of the potential of robots as embodied communicators for virtuous knowledge and community, this paper discusses the affordances or possibilities of action of robots for spiritual communication by drawing upon the recent highly publicized case of Xian’Er the robot monk (XE). By discussing XE’s communicative affordances including its searchability, multimediality, liveliness and extendibility, findings illustrate how robots can facilitate religious education, augment priestly authority and cultivate spiritual community. Contrary to abstract and dystopic visions of AI, findings here temper extreme pronouncements of societal disorder and points to prospects for pious and positive interplays between AI technology and society while also identifying various limitations for spiritual communication. In doing so, this paper unpacks the profound relations between religion, robots and rectitude, contributing interdisciplinary insights into an understudied area of AI development as faith leaders and adherents interact with new technological features and applications in their desire for transcendence.

Digital Religion, Social Media and Culture: Perspectives, Practices, Futures - Pauline Hope Cheong; Fischer-Nielsen, Peter; Gelfgren, Stefan; Ess, Charles (Peter Lang, 2012)
Keywords: Authority; avatars; community; history; identity; internet; online church; social media; theology; theory of religion online

Religious Communication and Epistemic Authority of Leaders in Wired Faith Organizations. - Pauline Hope Cheong (Journal of Applied Communication Research, 2011)
The mediation of communication has raised questions of authority shifts in key social institutions. This article examines how traditional sources of epistemic power that govern social relations in religious authority are being amplified or delegitimized by Internet use, drawing from in-depth interviews with protestant pastors in Singapore. Competition from Internet access is found to delocalize epistemic authority to some extent; however, it also reembeds authority by allowing pastors to acquire new competencies as strategic arbiters of religious expertise and knowledge. Our study indicates that although religious leaders are confronted with proletarianization, deprofessionalization, and potential delegitimization as epistemic threats, there is also an enhancement of epistemic warrant as they adopt mediated communication practices that include the social networks of their congregation.
Keywords: Authority; internet

The vitality of new media and religion: Communicative perspectives, practices, and authority in spiritual organization - Cheong, Pauline H. (New Media and Society, 2016)
It is significant that we are witnessing the growth of a distinct subfield focusing on new media and religion as the relationship between the two is not just important, it is vital. I discuss in this article how this vitality is both figurative and literal in multiple dimensions. Mediated communication brings forth and constitutes the (re)production of spiritual realities and collectivities, as well as co-enacts religious authority. In this way, new mediations serve as the lifeblood for religious organizing and activism. Further research in religious communication will illuminate a richer understanding of digital religion, especially as a globally distributed phenomenon.
Keywords: Authority; Communication; convergence; digital media; Globalization; religion; spiritual organizing

Digital methodologies in the sociology of religion - Cheruvallil-Contractor, S; Shakkour, S (Bloomsbury Academic, 2015)
This volume considers the implementation difficulties of researching religion online and reflects on the ethical dilemmas faced by sociologists of religion when using digital research methods. Bringing together established and emerging scholars, global case studies draw on the use of social media as a method for researching religious oppression, religion and identity in virtual worlds, digital communication within religious organizations, and young people's diverse expressions of faith online. Additionally, boxed tips are provided throughout the text to serve as reminders of tools that readers may use in their own research projects.
Keywords: Digital; Sociology of religion

Online Religion in Nigeria: The Internet Church and Cyber Miracles - Innocent Chiluwa (Journal of Asian and African Studies, 2012)
This study examines the use of the Internet and computer-mediated communication for Christian worship in Nigeria. The seven largest and fastest growing churches in Nigeria are selected for the study, highlighting the benefits and dangers associated with online worship. The utilization of the Internet to disseminate the Christian message and attract membership across the world, and the dissemination of religious tenets and fellowship online, have resulted in the emergence of the ‘Internet church’ for members who worship online in addition to belonging to a local church. Most interesting is the increasing widespread claim of spiritual experience or ‘miracles’ through digital worship. However, there is fear that online worship endangers the offline house fellowship system, which is viewed as the reproductive organ of the local offline church. Exclusive online worshippers are also said to be susceptible to deception and divided loyalty.
Keywords: Christianity; Church; Nigeria; Online; religion

Religious Use of Mobile Phones - Cho, J; Campbell, H (Encyclopedia of Mobile Phone Behavior, 2015)
Keywords: Digital Religion; mobile phones; religious

New Media and Religion: Observations of Research - Cho, Kyong (Communication Research Trends, 2011)
Keywords: New Media; Online; religion

Religious Perspective on Communication Technology - Christians, Clifford (Journal of Media and Technology, 1997)
Keywords: Communication; Perspective; technology; View

Digital Gravescapes: Digital Memorializing on Facebook - Scott Church (The Information Society: An International Journal, 2013)
I conduct a textual analysis of a digital memorial to understand the ways in which the digital sphere has disrupted or altered material and aesthetic displays of death and the associated genre of discourses surrounding death. I first use Morris's history of traditional gravescapes to situate digital memorials within their broader historical context. I then draw on the functional genre of eulogies, in particular Jamieson and Campbell's systematic description of eulogies, as a textual analytic to understand Facebook's unique memorializing discourse. My analysis suggests that the affordances of the Internet allow for a peculiar dynamic wherein the bereaved engage in communication with the deceased instead of with each other and yet strengthen the communal experience, as their personal communications are visible to the entire community. While the digital memorials lack the permanence of traditional gravescapes, the ongoing conversation they foster sublimates death into the process of communication.
Keywords: Contemporary Religious Community; cyberspace; Death; digital media; digital memorials; discourse; eulogy; Facebook; gravescapes; memorializing; memorializing discourse; New Media and Society; new media engagement; New Technology and Society; online communication; Online community; religion; Religion and the Internet; religious engagement; rhetoric; social media; Sociology of religion; virtual community; virtual public sphere; “religion online”

Synecdoche, Aesthetics, and the Sublime Online: Or, What’s a Religious Internet Meme? - Church, Scott Haden; Feller, Gavin (Journal of Media and Religion, 2020)
Hoping to court young people increasingly distancing themselves from institutional religious affiliation, religious organizations like the Church of Jesus Christ of Latter-day Saints are creating and circulating aesthetic short-form videos (memes) rife with existential cinematic tropes aimed at invoking a sublime, affective viewing experience. Unlike the destabilizing cinema that inspired them, however, these religious memes do not have the luxury of equivocation. Institutional religious messages online must aim to instill divine experiences in spectators even while transcending the constraints of mobile media that circulates them. Responding to this exigency, institutional religious messages overcome these restrictions by using synecdoche to create a necessarily incomplete iteration of the sublime. “Earthly Father, Heavenly Father,” an example of a short video religious meme by the Church of Jesus Christ of Latter-day Saints, lets the familiar cinematic tropes innovated by filmmakers such as Terrence Malick do the work of the sublime in order to represent the much larger, transcendent experience of personal communion with God.

Online Religion: The Internet and Religion - Ciolek, Matthew.T. (The Internet Encyclopedia, 2004)

Religion and authority in a remix culture: how a late night TV host became an authority on religion - Clark, L.S. (Routledge, 2011)
This Reader brings together a selection of key writings to explore the relationship between religion, media and cultures of everyday life. It provides an overview of the main debates and developments in this growing field, focusing on four major themes: Religion, spirituality and consumer culture Media and the transformation of religion The sacred senses: visual, material and audio culture Religion, and the ethics of media and culture. This collection is an invaluable resource for students, academics and researchers wanting a deeper understanding of religion and contemporary culture.

Exploring Religion and Mediatization through a Case Study of J + K’s Big Day: A Response to Stig Hjarvard - Lynn Schofield Clark (Journal of Religion and Culture, 2011)
This article reviews the strengths and weaknesses of Hjarvard’s theory of the mediatization of religion. Suggesting actor-network-theory as a methodological approach to the study of the mediatization of religion, the article proposes a case study of the viral wedding video JK Wedding Entrance Dance to highlight problems with the assertion that the media are replacing or displacing religion’s authoritative role in society. Drawing upon recent theories of how digital and mobile media are reshaping society by enabling participation, remediation, and bricolage, I suggest instead that the media do not bring about secularization, but rather that the media are contributing to a personalization of what it means to be religious (or not). The article thus introduces an alternative definition to the concept of mediatization: that mediatization may be understood as the process by which collective uses of communication media extend the development of independent media industries and their circulation of narratives, contribute to new forms of action and interaction in the social world, and give shape to how we think of humanity and our place in the world.
Keywords: media; religion; Stig Hjarvard

Considering religion and mediatization through a case study of J+K’s big day (The J K wedding entrance dance): a response to Stig Hjarvard - Clark, LS (Culture and Religion, 2011)
This article reviews the strengths and weaknesses of Hjarvard's theory of the mediatisation of religion. By suggesting actor-network theory as a methodological approach to the study of the mediatisation of religion, this article proposes a case study of the viral wedding video, J K wedding entrance dance, to highlight problems with the assertion that the media are replacing or displacing religion's authoritative role in society. Drawing upon recent theories of how digital and mobile media are reshaping society by enabling participation, remediation and bricolage, I suggest instead that the media do not bring about secularisation, but rather that the media are contributing to a personalisation of what it means to be religious (or not). This article thus introduces an alternative definition to the concept of mediatisation: that mediatisation may be understood as the process by which collective uses of communication media extend the development of independent media industries and their circulation of narratives, contribute to new forms of action and interaction in the social world and give shape to how we think of humanity and our place in the world.
Keywords: actor-network theory; mediatization; personalization; religion; secularization; viral video; wedding

The constant contact generation: exploring teen friendship networks online - Clark, L. S. (Girl Wide Web. Girls, the Internet, and the Negotiation for Identity, 2005)
Given the rapidly growing presence of girls online, serious academic inquiry into the relationship between girls and the Internet is imperative. Girl Wide Web is an innovative collection of cutting-edge research exploring a wide sweep of issues related to the ways adolescent girls interact with the Internet. Employing a range of methodologies and theoretical perspectives primarily within cultural studies, the authors examine a variety of topics-from instant messaging and web-diaries to online fan communities and Internet advertising that targets young girls. Taken together, these essays provide a rich portrait of the complex relationship among girls, the Internet, and the negotiation of identity.
Keywords: constant; friendships; generation; networks; teens; Youth

Digital storytelling and collective religious identity in a moderate to progressive youth group - Clark, LS; Dierberg, J (Digital religion: Understanding religious practice in new media worlds, 2013)
Digital Religion offers a critical and systematic survey of the study of religion and new media. It covers religious engagement with a wide range of new media forms and highlights examples of new media engagement in all five of the major world religions. From cell phones and video games to blogs and Second Life, the book: provides a detailed review of major topics, includes a series of case studies to illustrate and elucidate the thematic explorations considers the theoretical and ethical and theological issues raised.
Keywords: digital storytelling; religious identity; youth group

A quick look back at online worship in 2009. - Clark, N. (2009)

From Angels to Aliens: Teenagers, the Media and the Supernatural - Clark, L. S. (Oxford University Press, 2003)
Harry Potter, Buffy the Vampire Slayer, and the Left Behind series are but the latest manifestations of American teenagers' longstanding fascination with the supernatural and the paranormal. In this groundbreaking book, Lynn Schofield Clark explores the implications of this fascination for contemporary religious and spiritual practices. Relying on stories gleaned from more than 250 in-depth interviews with teens and their families, Clark seeks to discover what today's teens really believe and why. She finds that as adherence to formal religious bodies declines, interest in alternative spiritualities as well as belief in "superstition" grow accordingly. Ironically, she argues, fundamentalist Christian alarmism about the forces of evil has also fed belief in a wider array of supernatural entities. Resisting the claim that the media "brainwash" teens, Clark argues that today's popular stories of demons, hell, and the afterlife actually have their roots in the U.S.'s religious heritage. She considers why some young people are nervous about supernatural stories in the media, while others comfortably and often unselfconsciously blur the boundaries between those stories of the realm beyond that belong to traditional religion and those offered by the entertainment media. At a time of increased religious pluralism and declining participation in formal religious institutions, Clark says, we must completely reexamine what young people mean--and what they may believe--when they identify themselves as "spiritual" or "religious." Offering provocative insights into how the entertainment media shape contemporary religious ideas and practices, From Angels to Aliens paints a surprising--and perhaps alarming--portrait of the spiritual state of America's youth.
Keywords: angels; media; supernatural; teenagers

The Message of the Medium: The Challenge of the Internet to the Church and Other Communities - Clough, D. (Studies in Christian Ethics, 2000)
Imagine, if you can, a small room, hexagonal in shape, like the cell of a bee. It is lighted neither by window nor by lamp, yet it is filled with a soft radiance. There are no apertures for ventilation, yet the air is fresh. There are no musical instruments, and yet, at the moment that my meditation opens, this room is throbbing with melodious sounds. An armchair is in the centre, by its side a reading-desk — that is all the furniture. And in the armchair there sits a swaddled lump of flesh — a woman, about five feet high, with a face as white as a fungus. It is to her that the little room belongs.
Keywords: Chrisitan; ethics; internet

Network apocalypsis: revealing and reveling at a new age festival - Coats, C; Murchison, J (International Journal for the Study of New Religions, 2015)
This article analyzes the Synthesis 2012 festival, which coincided with the end of the Mayan calendar in December 2012. The festival was held in and around the village of Pisté in Yucatán, Mexico, and broadcast live via a web based video stream. We gathered ethnographic data about the event both onsite and via the Internet. Presenting and analyzing that data here, we consider the way that these two different modes of access to the ethnographic event(s) reveal and obscure different dimensions of participants' presence at the festival.
Keywords: network; New Age

Cybergrace: The Search for God in the Digital World - Cobb, Jennifer (Crown Publishing, 1998)
Theologian and high-tech consultant Jennifer Cobb combines her expertise to create a new theory of the Divine in the Information Age. As computers and artificial intelligence systems become more sophisticated, the question of whether we can find spiritual life in cyberspace is beginning to be asked. CyberGrace: The Search for God in the Digital World is a bold, thought-provoking, affirmative answer to one of the most intriguing inquiries of our time. Until now, an unbridgeable schism has separated the world of the spirit and that of the machine. According to an increasingly compelling concept known as emergence, the gulf may be an imaginary one. Fifty years ago, Jesuit paleontologist Teilhard de Chardin combined his lifelong passions of God and science to predict the emergence of cyberspace, based on his studies of evolution. Using Teilhard's theories as a starting point, Jennifer Cobb asserts that as technical systems become more complex--with simple, predictable mechanisms coalescing into hierarchies of increasing organization--something elegant, inspired, and absolutely unpredictable simply and suddenly "emerges." Many observers today see this "hand of God" showing itself in disparate disciplines, from evolutionary theory to artificial intelligence--and especially in the furthest realms of cyberspace, where brute computation seems to give way to divine inspiration. CyberGrace offers paradoxical evidence that our machines may be conduits to a deeper spirituality. With daily headlines announcing dizzying advances in science and information technology, many people wonder about their--and their children's--ability to lead lives imbued by a sense of the sacred. In the new world, where the search for spirituality may seem scattered and unfocused, Cobb brilliantly uses the most popular and prevalent phenomenon of our times--the computer--to find a world filled with meaning and love.
Keywords: cyber; Digital; God; grace

Spiritual News:Reporting Religion Around the World - Yoel Cohen (Peter Lang Publishers, 2018)
. SPIRITUAL NEWS: Reporting Religion Around the World Yoel Cohen (editor) The media's coverage of religion is an important question for academic researchers, given the central role which news media play in ensuring that people are up-to-date with religion news developments. Not only is there a lack of treatment of the subject in other countries, but there is also the absence of comparative study on news and religion. A key question is how the media, the political system, the religions themselves, the culture, and the economy influence how religion is reported in different countries. The book SPIRITUAL NEWS: Reporting Religion around the World is intended to fill this gap. The book is divided into six parts: an introductory section; the newsgathering process; religion reporting in different regions; media events concerning religion; political and social change and the role of religion news; future trends. TABLE OF CONTENTS Part A: Introduction Yoel Cohen: Religion News in the Twenty-First Century 1. Stewart Hoover: Religion and the News in the Age of Media Change Part B: Newsgathering 2. Joyce Smith, Foreign News: the "Religion Story" 3. Yoel Cohen, The Religion Reporter 4. Miriam Diez Biesch, The Vaticanologists: Covering the Holy See 5. Tim Hutchings, Digital Futures of Religion Journalism 6. Daniel Stout, Convergence, Digital Media, and the Paradigm Shift in Religion News Coverage in the United States Part C: Regional Patterns 7. Victor Khroul, Religion and News Media in Post-Soviet Russia. 9. Magali do Nascimento Cunha, Religious Exclusivism and Roman Catholicism in Brazilian News Media 10. Walter C Ihejirika and Andrew D Dewan, Development Journalism & Religion Reporting: The Nigerian Case 11. Keval Kumar, Reporting Religion in Indian News Media: Hindu Nationalism, `Reconversions' and the Secular State 12. Qingjiang Yao & Zhaoxi Liu, Media and Religion in China: Publicizing Gods Under the Atheist Governance PART D: Media Events 13. Giulia Evolvi, Habemus Papas: Pope Francis' Election as a Religious Media Event 14. Leo Eko, The Argument of Force Versus the Force of Argument: the Charlie Hebdo Terrorist Attack as a Global Meta Event PART E: The Influence of Religion Reporting 15. Noha Mellor, Religious Ideologies and News Ethics: the case of Saudi Arabia 16. Haryati Abdul Karim, Sinners or Alternative Identities? Contrasting Discourses on LGBT Communities in Two Malaysian Daily Newspapers 16. Yoel Cohen, Holy Days, News Media, and Religious Identity: A Case Study in Jewish Holy Days and the Israeli Press and News Websites PART F:The Impact of New Media upon Religion 19. Lorenzo Cantoni, Daniel Arasa & Juan Narbona, The Catholic Church and Twitter 18.Christian Bourret and Karim Fraoua, Religion, Social Media and Societal Changes: The Case of "Marriage for All" in France. 19. Babak Rahimi, Internet News, Media Technologies, and Islam: the Case of Shafaqna

The Wonder Phone in the Land of Miracles. Mobile Telephony in Israel - Cohen, Akiba; Lemish, Dafna; Schejter, Amit (Hampton Press, Inc, 2008)
Studies conducted over several years in Israel explored social aspects of the developing mobile phone phenomenon. Using a variety of quantitative and qualitative methods the research examined the place that the "Wonder Phone" has been occupying in many facets of life. It was concluded that the mobile is "not only talk"--as a recent campaign slogan of one of Israel's mobile providers suggests. Rather, it is a medium through which Israelis define their gendered and national identities; it offers an experience of "being there" and a security net holding family members and loved ones together, especially in terms of terror and war; and it provides a lifeline during existential crises around which rituals of mourning are crystallized. In analyzing the mobile phone as it is contextualized in Israeli society, two opposing social forces can clearly be seen: on the one hand, the mobile is an expression of late modernity and globalization; but on the other hand it is recruited as a tool--as well as a symbol--for the expression of locality and patriotic sentiments.
Keywords: Israel; mobile; technology; Telephone

God, Jews & the Media: Religion & Israel's media - Yoel Cohen (Routledge Publishers, 2012)
The book centres around the relationship of Judaism and mass media. It examines how the Jewish religion and the Jewish People have been influenced by the media and the media age. In order to understand contemporary Jewish identity in the twentieth and twenty-first century, one needs to go beyond the Synagogue, Jewish customs and law (halakhah) and the holy days to incorporate such modern phenomena as mass media and their impact upon Jewish existence. The book seeks to provide a comprehensive, yet easy-to-read text, examining the manifold interactions between Jewish religious identity and mass media. As a religious system influenced by news values and mass media inputs, Mediated Judaism is necessarily influenced by the market forces of news values. Much in religion is not newsworthy. Much in religion does not concern such newsworthy elements as social conflict or elites. Religious belief, often drawing upon the sub-conscious, does not fit such criteria of newsworthiness. Religion-related items that do get defined as news do not stay for long upon the news agenda but are replaced by what else is happening in the news agenda at any particular time. God, Jews & the Media: Religion and Israel's Media Routledge (2012) CONTENTS |Preface: Israel TV interviews God Part 1 Mediated Judaism Chapter 1 Media, Judaism, & Culture Chapter 2 The Jewish Theory of Communication Part 2 Media Culture Wars Chapter 3 Constructing Religion News: the religion reporter decides Chapter 4 News Values, Ideology and the religion story Chapter 5 Mikva News Chapter 6 Dual loyalties: the modern Orthodox dilemma Chapter 7 Identity, Unity & Discord Part 3 Issues in Mediated Judaism Chapter 8 www.techno-Judaism Chapter 9 Kosher Advertising Chapter 10 The Marketing of the Rabbi Chapter 11 At bay in the Diaspora Chapter 12 From out of Zion shall come forth the foreign news Conclusion: Judaism in the Information Age Selected bibliography

When the most popular format reaches the most atypical country: reality TV and religion in Israel - Cohen, Y; Hetsroni, A (Religion and Reality TV: Faith in Late Capitalism, 2018)
This chapter looks at the ways in which Judaism finds expression in reality shows in Israel. Three aspects are examined: reaction to the programs from religious leaders and religious communities; participation of religious people in the shows; and the appearance of religion-related topics in the programs.
Keywords: Israel; reality TV; religion

Spiritual News:Reporting Religion Around the World - Yoel Cohen (Peter Lang Publishers, 2018)
. SPIRITUAL NEWS: Reporting Religion Around the World Yoel Cohen (editor) The media's coverage of religion is an important question for academic researchers, given the central role which news media play in ensuring that people are up-to-date with religion news developments. Not only is there a lack of treatment of the subject in other countries, but there is also the absence of comparative study on news and religion. A key question is how the media, the political system, the religions themselves, the culture, and the economy influence how religion is reported in different countries. The book SPIRITUAL NEWS: Reporting Religion around the World is intended to fill this gap. The book is divided into six parts: an introductory section; the newsgathering process; religion reporting in different regions; media events concerning religion; political and social change and the role of religion news; future trends. TABLE OF CONTENTS Part A: Introduction Yoel Cohen: Religion News in the Twenty-First Century 1. Stewart Hoover: Religion and the News in the Age of Media Change Part B: Newsgathering 2. Joyce Smith, Foreign News: the "Religion Story" 3. Yoel Cohen, The Religion Reporter 4. Miriam Diez Biesch, The Vaticanologists: Covering the Holy See 5. Tim Hutchings, Digital Futures of Religion Journalism 6. Daniel Stout, Convergence, Digital Media, and the Paradigm Shift in Religion News Coverage in the United States Part C: Regional Patterns 7. Victor Khroul, Religion and News Media in Post-Soviet Russia. 9. Magali do Nascimento Cunha, Religious Exclusivism and Roman Catholicism in Brazilian News Media 10. Walter C Ihejirika and Andrew D Dewan, Development Journalism & Religion Reporting: The Nigerian Case 11. Keval Kumar, Reporting Religion in Indian News Media: Hindu Nationalism, `Reconversions' and the Secular State 12. Qingjiang Yao & Zhaoxi Liu, Media and Religion in China: Publicizing Gods Under the Atheist Governance PART D: Media Events 13. Giulia Evolvi, Habemus Papas: Pope Francis' Election as a Religious Media Event 14. Leo Eko, The Argument of Force Versus the Force of Argument: the Charlie Hebdo Terrorist Attack as a Global Meta Event PART E: The Influence of Religion Reporting 15. Noha Mellor, Religious Ideologies and News Ethics: the case of Saudi Arabia 16. Haryati Abdul Karim, Sinners or Alternative Identities? Contrasting Discourses on LGBT Communities in Two Malaysian Daily Newspapers 16. Yoel Cohen, Holy Days, News Media, and Religious Identity: A Case Study in Jewish Holy Days and the Israeli Press and News Websites PART F:The Impact of New Media upon Religion 19. Lorenzo Cantoni, Daniel Arasa & Juan Narbona, The Catholic Church and Twitter 18.Christian Bourret and Karim Fraoua, Religion, Social Media and Societal Changes: The Case of "Marriage for All" in France. 19. Babak Rahimi, Internet News, Media Technologies, and Islam: the Case of Shafaqna

Science, Technology and Mission - Cole-Turner, R. (The Local Church in a Global Era: Reflections for a New Century, 2000)
How is the church being affected by globalization? What does wider and more direct contact between the world religions mean for Christians? What is God doing in the midst of such change? This important volume explores the implications of today's emerging global society for local churches and Christian mission. Prominent scholars, missionaries, and analysts of world trends relate Christian theology and ethics to five clusters of issues-stewardship, prosperity, and justice; faith, learning, and family; the Spirit, wholeness, and health; Christ, the church, and other religions; and conflict, violence, and mission-issues that pastors and congregations will find critical as they think through the mission of the church in our time.
Keywords: Missions; science; technology

Ethnographic Approaches to Digital Media - Coleman, E. G. (Annual Review of Anthropology, 2010)
his review surveys and divides the ethnographic corpus on digital me dia into three broad but overlapping categories: the cultural politics of digital media, the vernacular cultures of digital media, and the pro saics of digital media. Engaging these three categories of scholarship on digital media, I consider how ethnographers are exploring the com plex relationships between the local practices and global implications of digital media, their materiality and politics, and their banal, as well as profound, presence in cultural life and modes of communication. I consider the way these media have become central to the articulation of cherished beliefs, ritual practices, and modes of being in the world; the fact that digital media culturally matters is undeniable but showing how, where, and why it matters is necessary to push against peculiarly arrow presumptions about the universality of digital experience.
Keywords: cell phone; Communication; computers; Ethnography

The Church and Internet - Pontifical Council for Social Communications

Introductory remarks: Richard Rouse, Official, Pontifical Council for Culture - Pontifical Council for Social Communications (Vatican, 2011)

Ethics in Internet - Pontifical Council for Social Communications (2000)
Keywords: ethics; internet

Church and the Internet - Pontifical Council For Social Communications (2002)

Ethics in Internet - Pontifical Council For Social Communications (2002)

Ethics in Internet - Pontifical Council For Social Communications (2002)
Keywords: Catholic; Christianity; Communication; ethics; internet; media; Pontifical

Virtual Buddhism: Online Communities, Sacred Places and Objects - Connelly, L (The Changing World Religion Map, 2015)
Until recently, there has been a dearth of research which focuses on Buddhism online. This chapter contributes to our understanding of the relationships between media, religion and culture and specifically explores the themes of authority, community, identity and ritual. Examining Buddhism on the internet helps us to identify the position of Buddhism in society, the possible implications both online and offline and how people engage and communicate in a place (cyberspace) not constrained by geographic boundaries. An interdisciplinary approach, drawing from material culture, anthropology and religious studies examines how Buddhists, primarily in the U.S. and U.K., use the internet in daily life. This includes how they express their belief, practice Buddhist rituals, develop communities and communicate with others. “Virtual Buddhism” is illustrated by examples of virtual places, ritual and religious artefacts found in the online world of Second Life and how social media (Facebook and blogs) are used by Buddhists and non-Buddhists. This chapter provides an introduction to some Buddhist groups and individuals who use the internet and mobile technologies to engage with Buddhism. The discourse raises a number of questions, for example, why Buddhist communities are evolving online and the blurring of boundaries between offline and online environments which could challenge traditional concepts of Buddhist authority. Understanding how the internet is being used in the 21st century, is a huge undertaking. The examples presented provide insights into how some individuals are using mobile technologies, social media, and virtual worlds to establish Buddhism online, offline, and negotiate both spheres simultaneously.
Keywords: Buddhism; online communities; sacred place; Virtual

Virtual Buddhism: Buddhist Ritual in Second Life - Connelly, L (Digital Religion: Understanding Religious Practice in New Media Worlds, 2012)
Digital Religion offers a critical and systematic survey of the study of religion and new media. It covers religious engagement with a wide range of new media forms and highlights examples of new media engagement in all five of the major world religions. From cell phones and video games to blogs and Second Life, the book: provides a detailed review of major topics includes a series of case studies to illustrate and elucidate the thematic explorations considers the theoretical, ethical and theological issues raised. Drawing together the work of experts from key disciplinary perspectives, Digital Religion is invaluable for students wanting to develop a deeper understanding of the field.
Keywords: App; Buddhism; religion; Second Life; technology; Virtual

Muslim Networks from Hajj to Hip Hop - Cooke, Miriam; Lawrence, Brude (University of North Carolina Press, 2005)
Crucial to understanding Islam is a recognition of the role of Muslim networks. The earliest networks were Mediterranean trade routes that quickly expanded into transregional paths for pilgrimage, scholarship, and conversion, each network complementing and reinforcing the others. This volume selects major moments and key players from the seventh century to the twenty-first that have defined Muslim networks as the building blocks for Islamic identity and social cohesion. Although neglected in scholarship, Muslim networks have been invoked in the media to portray post-9/11 terrorist groups. Here, thirteen essays provide a long view of Muslim networks, correcting both scholarly omission and political sloganeering. New faces and forces appear, raising questions never before asked. What does the fourteenth-century North African traveler Ibn Battuta have in common with the American hip hopper Mos Def? What values and practices link Muslim women meeting in Cairo, Amsterdam, and Atlanta? How has technology raised expectations about new transnational pathways that will reshape the perception of faith, politics, and gender in Islamic civilization? This book invokes the past not only to understand the present but also to reimagine the future through the prism of Muslim networks, at once the shadow and the lifeline for the umma, or global Muslim community.
Keywords: culture; hajj; Islam; Muslim

Gaming with God: A Case for the Study of Religion in Video Games - Corliss, Vander (Senior Theses and Projects, 2011)
This study is an analysis of religion in video games and makes the case that more formal work needs to be done on the subject. Despite the prevalence of video games in society today, little formal research has been done on the subject of religion in video games. Video games give the audience a level of interactivity that other forms of entertainment cannot provide. Religion has been at odds with the entertainment industry for decades and as a new form of entertainment media, video games have been using religion for some time. Most often it is used in the story of the game to deepen the storyline, but other times it is a central theme that the game revolves. This thesis looks at two popular video game franchises, Halo and Assassin’s Creed, and examines the religious references contained within each of them. It then looks at different controversies that have arisen because of the inclusion of religion in these games. What is interesting about the negative reactions to these games is that they have not come to the attention of the general public even though video games are one of the fastest growing industries in the world. This is because there has been no research done on the subject of religion in video games so the public has nothing go by.
Keywords: gaming; God; religion; video games

Mission-shaped Church : church planting and fresh expressions of church in a changing context - Mission and Public Affairs Council (Church House, 2004)
An overview of recent developments in church planting. Detailed, practical, well-researched book describes the varied and exciting "fresh expressions" of church being created. Includes questions and challenges to help local churches engage with the issues.

Contested Spaces: Movement, Countermovement and E-Space Propaganda - Cowan, Douglas (Religion Online. Finding Faith on the Internet, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression.Religion Onlineprovides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes thePew Internet and American Life ProjectExecutiveSummary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-definingCyberspace as SacredSpace.
Keywords: movement; online space; propaganda

Cyberhenge: Modern Pagans on the Internet - Cowan, Douglas (Routledge, 2005)
InCyberhenge, Douglas E. Cowan brings together two fascinating and virtually unavoidable phenomena of contemporary life--the Internet and the new religious movement of Neopaganism. For growing numbers of Neopagans-Wiccans, Druids, Goddess-worshippers, and others--the Internet provides an environment alive with possibilities for invention, innovation, and imagination. From angel channeling, biorhythms, and numerology to e-covens and cybergroves where neophytes can learn everything from the Wiccan Rede to spellworking, Cowan illuminates how and why Neopaganism is using Internet technology in fascinating new ways as a platform for invention of new religious traditions and the imaginative performance of ritual. This book is essential reading for students and scholars of new religious movements, and for anyone interested in the intersections of technology and faith.
Keywords: comparative religion; cults; cyberspace; internet; neopaganism; religious aspects

Online U-Topia: Cyberspace and the Mythology of Placelessness - Cowan, Douglas E. (Journal for the Scientific Study of Religion, 2005)
The World Wide Web. The Information Superhighway. Cyberspace. Powerful metaphors that have infused our culture with a sense of its own technological prowess and superiority. According to some of its most ardent enthusiasts, in cyberspace we can go anywhere, do anything, be anyone we choose. We slip in and out of virtual identities as easily as we change our clothes. With the knowledge of the ages available to us at the click of a mouse, learning becomes little more than a process of searching and downloading. Using the Internet to spackle over any unfortunate gaps in our knowledge, we become "instant experts" on virtually any topic (Wright 2000). Online, we can "visit" remote places: check the weather on the Ross Ice Shelf, make a virtual pilgrimage up Ireland's Croagh Patrick (MacWilliams 2004), or marvel at the wonders observed through the Hubble Telescope. Not surprisingly, the World Wide Web is replete with religion-from simple congregational websites to fully orbed Wiccan cybercovens, from virtual puja (Dawson and Cowan 2004) to virtual hajj (Bunt 2000), and from Internet libraries designed to "crack" the Sumerian code (Cassidy 2002) to what some observers regard as the online revival of a populist Marian mysticism (Apolito 2005). According to one sociologist, the Internet "is the most portentous development for the future of religion to come out of the twentieth century" (Brasher 2001:17). And indeed, for some, the Internet has even become a metaphor for God (Turkle 1995; Henderson 2000). While both these latter claims may seriously overstate the reality of the situation, that religion and the Internet have become intimately and integrally linked is beyond dispute. In little more than a decade, a powerful set of interrelated mythologies has arisen about "life on the 'net"'-whatever we take that to mean ultimately-that challenges many of our heretofore accepted notions of society, culture, community, and the self (Rheingold 1993; Turkle 1995; Barlow [1996] 2001; for less utopian views, see Kroker and Weinstein 1994; Roszak 1994; Slouka 1995; Stoll 1995; Kroker and Kroker 1996; Wynn and Katz 1997). However useful computer-mediated communications have become, though, in many ways the World Wide Web represents at least as much the triumph of hyperbole and marketing as it does the next step in technological evolution. Often used as though its meaning is entirely transparent, the concept of "cyberspace" has traveled like a meme through the cultural consciousness since its introduction in the mid-1980s (Gibson 1984), an ambitious and ambiguous metonym that encompasses what popularly passes for the experiential totality of the Internet. The question, though, in terms of this Forum, is where do we go when we are online? Where is the "place" in cyberspace?

At the Frontlines of God’s Army: BattleCry as a Microcosm of Modern Evangelical Culture - Lilly Matson Dagdigian (Wesleyan University, 2008)
In this thesis, I will argue that BattleCry offers an accurate glimpse at major trends within evangelical culture at the beginning of the 21st century. BattleCry offers its members literature, rock concerts, and a full social networking website, not to mention mission trips and its own clothing line. Owing to this emphasis on varied multimedia experiences of Christianity, BattleCry sheds light on multiple aspects of modern-day evangelical life. BattleCry and its mini-empire encompass many of the new frontiers of evangelism – through the use of the Internet and Christian rock and pop music, BattleCry is extremely accessible to and effective with today’s Christian youth. Theirs is not simply a particularly successful marketing strategy, however; because of its depth as an organization, BattleCry serves as a microcosm of current evangelical culture, reflecting the priorities, strategies, and rhetoric of many of their compatriots.
Keywords: army; evangelism; God

TechGnosis: Myth, Magic, and Mysticism in the Age of Information - Davis, Erik (Random House, 1998)
"A most informative account of a culture whose secular concerns continue to collide with their supernatural flip-side."--"Voice Literary Supplement" In this dazzling book, writer and cyber guru Erik Davis demonstrates how religious imagination, magical dreams and millennialist fervor have always permeated the story of technology. Through shamanism to Gnosticism, voodoo to alchemy, Buddhism to evangelism, "TechGnosis" peels away the rational shell of infotech to reveal the utopian dreams, alien obsessions and apocalyptic visions that populate the ongoing digital revolution. Erik Davis' work has appeared in "Wired," "The Village Voice" and "Gnosis," and he has lectured internationally on technoculture and new forms of religion. He is a fifth-generation Californian who currently lives in San Francisco.
Keywords: information; magic; myth; technology

Religion Online: Finding Faith on the Internet - Lorne L. Dawson; Douglas E. Cowan (Routledge, 2004)
Keywords: Australia; cyberspace; identity; internet; Islam; religion; Spirituality; USA; virtual community; Youth

The Mediation of Religious Experience in Cyberspace - Dawson, L. (Religion and Cyberspace, 2005)
In the twenty-first century, religious life is increasingly moving from churches, mosques and temples onto the Internet. Today, anyone can go online and seek a new form of religious expression without ever encountering a physical place of worship, or an ordained teacher or priest. The digital age offers virtual worship, cyber-prayers and talk-boards for all of the major world faiths, as well as for pagan organisations and new religious movements. It also abounds with misinformation, religious bigotry and information terrorism. Scholars of religion need to understand the emerging forum that the web offers to religion, and the kinds of religious and social interaction that it enables. Religion and Cyberspace explores how religious individuals and groups are responding to the opportunities and challenges that cyberspace brings. It asks how religious experience is generated and enacted online, and how faith is shaped by factors such as limitless choice, lack of religious authority, and the conflict between recognised and non-recognised forms of worship. Combining case studies with the latest theory, its twelve chapters examine topics including the history of online worship, virtuality versus reality in cyberspace, religious conflict in digital contexts, and the construction of religious identity online. Focusing on key themes in this groundbreaking area, it is an ideal introduction to the fascinating questions that religion on the Internet presents.
Keywords: cyberspace; Experience; religion

New religions and the internet: Recruiting in a new public space - Dawson, Lorne L.; Hennebry, Jenna (Journal of Contemporary Religion)
The mass suicide of 39 members of Heaven's Gate in March of 1997 led to public fears about the presence of ‘spiritual predators’ on the world wide web. This paper describes and examines the nature of these fears, as reported in the media. It then sets these fears against what we know about the use of the Internet by new religions, about who joins new religious movements and why, and the social profile of Internet users. It is argued that the emergence of the Internet has yet to significantly change the nature of religious recruitment in contemporary society. The Internet as a medium of communication, however, may be having other largely unanticipated effects on the form and functioning of religion, both old and new, in the future. Some of the potential perils of the Internet are discussed with reference to the impact of this new medium on questions of religious freedom, community, social pluralism, and social control.

Researching Religion in Cyberspace: Issues and Strategies - Dawson, Lorne (Religion on the Internet. Research Prospects and Promises., 2000)
Religion on the Internet is the first systematic inquiry into the nature, scope and content of religion in cyberspace. Contributors to this volume include leading social scientists engaged in systematic studies of how organizations and individuals are presenting religion on the Internet. Their combined efforts provide a conceptual mapping of religion in cyberspace at this moment. The individual papers and collective insights found in this volume add up to a valuable agenda of research that will enrich understanding of this new phenomenon. Among the contributors are the founders of three of the most important scholarly religion web sites on the Internet: American Religion Data Archive, Religious Tolerance, and Religious Movements Homepage. Religion and the Internet is essential reading for all who seek to understand how religion is being presented on the Internet and how this topic is likely to unfold in the years ahead.

Religion Online: Finding Faith on the Internet - Dawson, Lorne; Cowan, Douglas (Routledge, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression.Religion Onlineprovides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes thePew Internet and American Life ProjectExecutiveSummary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-definingCyberspace as SacredSpace.
Keywords: information and communication technology; methodology; social networks

Information And Communication Technologies In Religious Tourism And Pilgrimage - De Ascaniis, Silvia; Cantoni, Lorenzo (2016)
Special issue of the IJRTP - International Journal of Religious Tourism and Pilgrimage
Keywords: eReligion; eTourism

Seeking the Sacred Online: Internet and the Individualization of Religious Life in Quebec - M Deirdre (Anthropologica, 2012)
Keywords: Access to resources; Canada; Contemporary Religious Community; digital cultures; internet; network; New Media and Society; new media engagement; New Technology and Society

Halos and avatars: Playing (video) games with God - Deitweiler, Craig (Westminster Press., 2010)
Craig Detweiler's collection of up-to-the-minute essays on video games' theological themes (and yes, they do exist!) is an engaging and provocative book for gamers, parents, pastors, media scholars, and theologians--virtually anyone who has dared to consider the ramifications of modern society's obsession with video games and online media. Together, these essays take on an exploding genre in popular culture and interpret it through a refreshing and enlightening philosophical lens.
Keywords: avatars; God; Halo; video games

A Better Life Through Information Technology? The posthuman person in contemporary speculative science - Michael Delashmutt (Zygon, 2006)
The depiction of human identity in the pop-science futurology of engineer/inventor Ray Kurzweil, the speculative robotics of Carnegie Mellon roboticist Hans Moravec, and the physics of Tulane University mathematics professor Frank Tipler elevate technology, especially information technology, to a point of ultimate significance. For these three figures, information technology offers the potential means by which the problem of human and cosmic finitude can be rectified. Although Moravec’s vision of intelligent robots, Kurzweil’s hope for immanent human immorality, and Tipler’s description of humanlike von Neumann machines colonizing the very material fabric of the universe all may appear to be nothing more than science fictional musings, they raise genuine questions as to the relationship between science, technology, and religion as regards issues of personal and cosmic eschatology. In an attempt to correct what I see as the cybernetic totalism inherent in these techno-theologies, I argue for a theology of technology that seeks to interpret technology hermeneutically and grounds human creativity in the broader context of divine creative activity.

Religionless in Seattle - Michael Delashmutt (Exploring Religion and the Sacred in a Media Age, 2009)
In recent years, there has been growing awareness across a range of academic disciplines of the value of exploring issues of religion and the sacred in relation to cultures of everyday life. Exploring Religion and the Sacred in a Media Age offers inter-disciplinary perspectives drawing from theology, religious studies, media studies, cultural studies, film studies, sociology and anthropology. Combining theoretical frameworks for the analysis of religion, media and popular culture, with focused international case studies of particular texts, practices, communities and audiences, the authors examine topics such as media rituals, marketing strategies, empirical investigations of audience testimony, and the influence of religion on music, reality television and the internet.Both academically rigorous and of interest to a wider readership, this book offers a wide range of fascinating explorations at the cutting edge of many contemporary debates in sociology, religion and media, including chapters on the way evangelical groups in America have made use of The Da Vinci Code and on the influences of religion on British club culture and electronic dance music.
Keywords: religion and internet; Seattle

From Jesus to the Internet: A History of Christianity and Media - Detweiler, C (Christian Scholar's Review, 2016)
The title, From Jesus to the Internet, summarizes the range of his study, while the subtitle, History of Christianity and Media, describes the substance. Horsfield connects key turning points in ecclesial history with the major communication shifts of each era, from oral to written, from print through digital. While church histories may focus on the dogma being debated, Horsfield suggests that those who marshaled media most effectively usually won the ideological war. This highly readable text has implications and applications to classes in religion, theology, history, and communication. Horsfield offers a clear and succinct overview of his methodology in the introduction. He adopts a broad definition of both religion and media, approaching Christianity as "a complex and expanding mediated phenomenon, a constant creative reproduction and rhetorical reworking of Jesus to match the conditions of an ever-expanding set of constantly changing circumstances"
Keywords: Christianity; internet; Jesus; media

The Forbidden Fork, the Cell Phone Holocaust, and Other Haredi Encounters with Technology - Nathaniel Deutsch (Contemporary Jewry, 2009)
Haredi Jews valorize tradition and explicitly reject the idea of progress on ideological grounds. Concomitantly, they are opposed to many innovations and are highly critical of the destructive potential of modern communication technologies such as cell phones with Internet capability that serve as pocket-sized portals between their insular communities and the wider world. In response to this perceived threat, Haredi authorities have issued bans on the use of certain technologies and have endorsed the development of acceptable alternatives, such as the so-called kosher cell phone. And yet, many Haredim, both in the United States and Israel, are highly sophisticated users and purveyors of these same technologies. This tension indicates that Haredim have a much more complicated relationship to technology and to modernity, itself, than their ‘‘official’’ stance would suggest.
Keywords: cell phone; Haredim; Hasidim; Holocaust; internet; Israel; Modernity; technology; Ultra-Orthodox Jews

Cyberchurch, Christianity and the Internet - Dixon, Patrik (Kingsway Publications, 1997)
Keywords: Christianity; Church; cyberspace; internet

Identity and deception in the virtual community - Donath, J. S. (Communities in Cyberspace, 1999)
This wide-ranging introductory text looks at the virtual community of cyberspace and analyses its relationship to real communities lived out in today's societies. Issues such as race, gender, power, economics and ethics in cyberspace are grouped under four main sections and discussed by leading experts: * identity * social order and control * community structure and dynamics * collective action. This topical new book displays how the idea of community is being challenged and rewritten by the increasing power and range of cyberspace. As new societies and relationships are formed in this virtual landscape, we now have to consider the potential consequences this may have on our own community and societies. Clearly and concisely written with a wide range of international examples, this edited volume is an essential introduction to the sociology of the internet. It will appeal to students and professionals, and to those concerned about the changing relationships between information technology and a society which is fast becoming divided between those on-line and those not.
Keywords: deception; identity; virtual community

Ethical challenges of algorithmic journalism - Dörr, K. M.; Hollnbuchner, K. (Digital Journalism, 2017)
With the institutionalization of algorithms as content creators, professional journalism is facing transformation and novel ethical challenges. This article focuses on the concept of Algorithmic Journalism on the basis of natural language generation and provides a framework to identify and discuss ethical issues. The analysis builds on the moral theories of deontology, utilitarianism, virtue ethics, and contractualism, and remaps the ethical discussion for Algorithmic Journalism at the intersection of digital media ethics and cyber ethics. In order to capture the whole range of potential shifts and challenges in journalism ethics, the article combines the ethical multi-layer system of responsibility by Pürer with the classification of journalism by Weischenberg, Malik, and Scholl on an organizational, professional/individual, and social/audience sphere. This analytical framework is then complemented with attributes derived from the technical potential of Algorithmic Journalism. As a result, the analysis uncovers new ethical challenges and shifts of responsibility in news production for journalism practice and journalism research at the levels of objectivity, authority, transparency, and at the level of implicit or explicit values.

Click 2 Save: The Digital Ministry Bible - Drescher, Elizabeth; Anderson, Keith (Morehouse, 2012)
Social media sites like Facebook, Twitter, and YouTube provide opportunities for congregations and religious organizations to open the doors and windows to their common life before people ever encounter them in person. In this digitally-integrated world, it's no longer all about getting your message out as if people are passively waiting for the latest news from the parish, diocese, or national church. Rather, it s about using new media to create spaces where meaningful relationships can develop. Click 2 Save: The Digital Ministry Bible is a hands-on strategy guide for religious leaders who want to enrich and extend their ministries using digital media like Facebook, Twitter, YouTube and church or personal blogs. An ideal companion to Tweet If You Jesus: Practicing Church in the Digital Reformation (Morehouse, 2011), Click 2 Save draws on extensive research and experience in church and other ministry settings to provide functional, how-to guidance on effectively using social networking sites in the day-to-day context of ministry.
https://www.churchpublishing.org/products/index.cfm?fuseaction=productDetail&productID=9610
Keywords: internet and ministry; internet and religion; practical theology; religious leadership; social media and religion

Tweet If You Heart Jesus: Practicing Church in the Digital Reformation - Drescher, E (Morehouse Publishing, 2011)
Churches everywhere are scrambling to get linked with Facebook, Twitter and YouTube. But are they ready for the Digital Reformation: the dramatic global shift in the nature of faith, social consciousness and relationship that these digital social media have ushered in? Tweet If You ♥ Jesus brings the wisdom of ancient and medieval Christianity into conversation with contemporary theories of cultural change and the realities of social media, all to help churches navigate a landscape where faith, leadership and community have taken on new meanings.
Keywords: Church; Jesus; reformation; Twitter

Introduction: Situating Dynamics of Mediatization - Driessens, O; Hjarvard, S (Dynamics Of Mediatization, 2017)
In the introduction to this volume, we set out why it is important to focus on dynamics of mediatization and how this contributes to the study of media-related social change. We stress that to fully understand dynamics of change, mediatization should be studied in interrelation with other meta-processes, such as commercialization or politicization. Furthermore, also the contexts of change need to be taken seriously, in terms of field(s) of analysis, space and geography, as well as in terms of time, thereby avoiding so-called epochalist thinking.
Keywords: mediatization

Who would Jesus bomb? The Republican Jesus meme and the fracturing of ideology - Duerringer, C. A (Social Media + Society, 2016)
This project joins a growing conversation about the cultural significance of memes (and Internet memes in particular), offering a critical analysis of Republican Jesus—one popular image macro that mocks contemporary American conservatism—in order to illustrate the rhetorical potential of these putatively harmless do-it yourself (DIY) creations. Ultimately, I argue that Republican Jesus offers a critique of contemporary conservatism that creates “perspective by incongruity” and, thereby, creates a space for ideological struggle.
Keywords: Ideology; Jesus; meme

The Elementary Forms of Religious Life - Durkheim, E. (Free Press, 1995)
In The Elementary Forms of Religious Life (1912), Emile Durkheim sets himself the task of discovering the enduring source of human social identity. He investigates what he considered to be the simplest form of documented religion - totemism among the Aborigines of Australia. For Durkheim, studying Aboriginal religion was a way 'to yield an understanding of the religious nature of man, by showing us an essential and permanent aspect of humanity'. The need and capacity of men and women to relate to one another socially lies at the heart of Durkheim's exploration, in which religion embodies the beliefs that shape our moral universe. The Elementary Forms has been applauded and debated by sociologists, anthropologists, ethnographers, philosophers, and theologians, and continues to speak to new generations about the intriguing origin and nature of religion and society. This new, lightly abridged edition provides an excellent introduction to Durkheim's ideas.
Keywords: religion

Muslimah Media Watch: Media activism and Muslim choreographies of social change - Echchaibi, Nabil (Journalism, 2013)
This article explores media activism in the Muslim context by focusing on the blog, Muslimah Media Watch. It analyzes the significance of blogging as an activist tool used by a group of Muslim women to influence an ongoing and contested process of social change in Islam. Through interviews with the founder and bloggers of the site and a textual analysis of the blog posts, the author focuses on the aesthetic forms and discursive practices of digital Muslim activism and argues that projects such as Muslimah Media Watch should be evaluated not in terms of a revolutionary subversion of hegemonic discourse on gender in Islam, but rather as part of small but consistent disruptive flows of dissent which are significant precisely because of the nature of their intervention and the tactics of their resistance. The blog has also become a prime discursive and performative space where young Muslims debate and contest what it means to be modern in transnational settings.

Hyper-fundamentalism? Mediating Islam from the halal website to the Islamic talk show - Echchaibi, Nabil (Journal of Arab and Muslim Media Research, 2008)
Islam is going through a fundamental diffusion of religious knowledge and authority. Media technologies like the Web and satellite television are facilitating the emergence of a new breadth of Islam in the public sphere in Muslim societies and amongst Muslims in diaspora. Deeply influenced by the global and local dynamics of consumer culture, the proponents of this new Islam are more media-savvy and less dogmatic on how Islam should be mediated than their conservative counterparts. Unlike in the politically engaged Islam, the architects of this new trend are younger Muslims with more business skills than religious knowledge. From websites advertising the latest fashions in Islamic dress and others offering halal versions to non-Islamic foods such as the Italian Salami, the German Sausage or McDonald's burger to television shows encouraging Muslims to use their religion as a success formula for spiritual self-fulfillment and material achievement, the new economic liberalism of Islam is certainly modern in its mediation, but is its substance as liberal as the form? This paper examines how the new religious media are constructing the image of the modern Muslim and what kind of religious identities and subjectivities emerge as a result of a purely material consumption that is religiously committed. My analysis is based on a textual analysis of a popular Islamic television show on Iqra', a 24-hour Saudi religious channel that prides itself in being the first Islamic entertainment
Keywords: Islam, satellite television, new media, Islamic authority, consumer culture, Amr Khaled

From the pulpit to the studio: Islam’s internal battle - Echchaibi, Nabil (Media Development Online, 2007)
In February 2006, when Wafa Sultan, a Syrian-American activist in Southern California who advocates secularism in Muslim countries, defiantly told an Islamic sheikh on a widely popular Al-Jazeera news show 'to shut up and lis- ten, it's my turn', she knew she was making history on Arab television. Never before has the authority of Islam represented on this show by a conserva- tive sheikh from. Cairo's famed Al-Azhar University been challenged in a similarly brazen way by another Muslim, and much less so by a woman.
Keywords: Islam; Muslim

Voicing Diasporas: Ethnic Radio in Paris and Berlin Between Cultural Renewal and Retention - Echchaibi, Nabil (Lexington Books, 2011)
The events of 9/11 have cast a shadow of suspicion on Muslims in Western Europe and fostered a public discourse of arbitrary associations with violence and resistance to social and cultural integration. The antagonistic ascendancy of militant Islam globally and the anxiety this has engendered are animating day-to-day debates on the place and loyalty of Muslims in Western societies. Exploring the neglected reality of ethnic radio in Paris and Berlin, Voicing Diasporas: Ethnic Radio in Paris and Berlin Between Cultural Renewal and Retention examines how Muslim minorities of North African descent in France and Germany resist these glaring generalizations and challenge bounded narratives and laws of cultural citizenship in both countries. Through an analysis of Beur FM in Paris and Radio Multikulti in Berlin, this book also questions the reductionist view of diasporic media as expressions of longing, nostalgia, and cultural dislocation. This ground-breaking study is as essential read for not only scholars and higher educational students in various fields, but for those interested in this ever-changing, topical issue.

From audio tapes to video blogs: the delocalisation of authority in Islam - Echchaibi, Nabil (Nations and Nationalism, 2011)
Today, a new breed of charismatic and media‐savvy religious figures are reinvigorating internal debates on Islam by drawing large audiences across the Muslim world and the Muslim diaspora in the West. Using satellite media, websites, blogs and video blogs, these new religious celebrities are changing the nature of debate in Islam from a doctrinaire discourse to a practical discussion that focuses on individual enterprise as a spiritual quest. These leaders have become religious entrepreneurs, with sophisticated networks of message distribution and media presence. From Amr Khaled and Moez Masood, two leading figures of Arab Islamic entertainment television, to Baba Ali, a famous Muslim video blogger from California, Islam has never been more marketable. Satellite television and the internet are becoming fertile discursive spaces where not only religious meanings are reconfigured but also new Islamic experiences are mediated transnationally. This delocalisation of Islamic authority beyond the traditional sources of Egypt and Saudi Arabia is generating new producers and locales of religious meaning in Dubai, London, Paris and Los Angeles. This article examines the impact of celebrity religious figures and their new media technologies on the relativisation of authority in Islam and the emergence of a cosmopolitan transnational audience of Muslims. I ask if this transnational and seemingly apolitical effort is generating a new form of religious nationalism that devalues the importance of national loyalties.

Give Me That Online Religion: Religious Authority and Resistance Through Blogging - Erin V. Echols (Sociology, 2013)
This study of forty-nine Christian blogs explores how groups of bloggers in two case studies resist and/or perpetuate hegemonic gender ideologies online and where these bloggers draw authority from for these views. The findings reveal that bloggers are most likely to cite texts as sources of authority and are more likely to affirm authority (78.1%) than to challenge it (25.7%). The bloggers in my sample, who were majority male, use an array of strategies in their efforts to resist hegemonic gender norms. These included, but are not limited to, debating God’s gender, emphasizing women’s roles in the Bible, privileging equality in theological interpretations, redefining masculinity and employing satire and images to delegitimize hegemonic power
Keywords: Authority; bloggers; Contemporary Religious Community; Digital Religion; New Media and Society; new media engagement; online identity; religious media research; Resistance

The Handbook of Internet Studies - Mia Consalvo (Ed.); Charles Ess (Ed.) (Blackwell Publishing, 2011)
The Handbook of Internet Studies brings together scholars from a variety of fields to explore the profound shift that has occurred in how we communicate and experience our world as we have moved from the industrial era into the age of digital media. Presents a wide range of original essays by established scholars in everything from online ethics to ways in which indigenous peoples now use the Internet Looks at the role of the internet in modern societies, and the continuing development of internet studies as an academic field Explores Internet studies through history, society, culture, and the future of online media Provides introductory frameworks to ground and orientate the student, while also providing more experienced scholars with a convenient and comprehensive overview of the latest trends and critical directions in the many areas of Internet researc
Keywords: digital media; frameworks; internet; Research

Mass higher education and the religious imagination in contemporary Arab societies - Eickelman, D. F. (American Ethologist, 1992)
This article explores the relationship between the recent growth of mass higher education in the Arab Muslim world, particularly in Oman and North Africa, religious activism, and the implications of the “objectified” religious knowledge and authority that modern education encourages. Study of the new ways of knowing and the emerging networks for communication and action produced by mass higher education and contemporary religious activism offers insight into the “political economy” of religious knowledge: the interplay of religion, politics, and national identity. [Islam, Middle East, authority, religion, education]

New Media in the Muslim World: The Emerging Public Sphere - Dale Eickelman; Anderson, Jon (Indiana Series in Middle East Studies, 2003)
Keywords: Islam; Muslim; New Media

Brands of Faith: Marketing Religion in a Commercial Age - Einstein, Mara (Routledge, 2007)
In a society overrun by commercial clutter, religion has become yet another product sold in the consumer marketplace, and faiths of all kinds must compete with a myriad of more entertaining and more convenient leisure activities. Brands of Faith argues that in order to compete effectively faiths have had to become brands – easily recognizable symbols and spokespeople with whom religious prospects can make immediate connections Mara Einstein shows how religious branding has expanded over the past twenty years to create a blended world of commerce and faith where the sacred becomes secular and the secular sacred. In a series of fascinating case studies of faith brands, she explores the significance of branded church courses, such as Alpha and The Purpose Driven Life, mega-churches, and the popularity of the televangelist Joel Olsteen and television presenter Oprah Winfrey, as well as the rise of Kaballah. She asks what the consequences of this religious marketing will be, and outlines the possible results of religious commercialism – good and bad. Repackaging religion – updating music, creating teen-targeted bibles – is justifiable and necessary. However, when the content becomes obscured, religion may lose its unique selling proposition – the very ability to raise us above the market.

Online Islamophobia and the politics of fear: manufacturing the green scare - Ekman, Mattias (Ethnic and Racial Studies, 2015)
Negative attitudes and explicit racism against Muslims are increasingly visible in public discourse throughout Europe. Right-wing populist parties have strengthened their positions by focusing on the ‘Islamic threat’ to the West. Concurrently, the Internet has facilitated a space where racist attitudes towards Muslims are easily disseminated into the public debate, fuelling animosity against European Muslims. This paper explores part of the online Islamophobic network and scrutinizes the discursive strategies deployed by three ‘prominent’ online actors. By combining social network analysis and critical discourse analysis, the study shows that Islamophobic web pages constitute a dynamic network with ties to different political and geographical milieus. They create a seemingly mainstream political position by framing racist standpoints as a defence of Western values and freedom of speech. The study also shows that Islamophobic discourse is strengthened by xenophobic currents within mass media, and by the legitimization of intellectuals and political actors.

Procedural justice in contacts with the police: Testing a relational model of authority in a mixed methods study - Elliott, I.; Thomas, S. D. M.; Ogloff, J. R. P. (Psychology, Public Policy, and Law, 2011)
A relational model of authority (Tyler & Lind, 1992) emphasizes the role of procedural justice (the fairness of methods used to achieve outcomes) in public support for and evaluation of the police. Using both quantitative and qualitative methods, this study tested the model in the context of victim–police interactions. In-depth interviews were conducted with 110 people who had reported a crime (personal or property) to the police in the previous year. Quantitative findings supported the predictions that higher perceived antecedents of procedural justice would be associated with higher perceived legitimacy (obligation to obey the law), outcome fairness, and satisfaction with the contact. Antecedents of procedural justice were a stronger predictor of outcome fairness and satisfaction than the realization of a desired outcome, and a stronger predictor of legitimacy than criminal history. Qualitative findings supported these results. It appears that procedural justice has the potential for helping to motivate individuals with criminal history to obey the law. Implications for evaluation of police performance are discussed. (PsycINFO Database Record (c) 2012 APA, all rights reserved)

The Technological System - Ellul, J. (Continuum, 1980)
Keywords: system; technology

The Technological Society - Ellul, J. (Vintage Books, 1964)
A penetrating analysis of our technical civilization and of the effect of an increasingly standardized culture on the future of man.
Keywords: society; technology

Me, myself and the other. Interreligious and intrareligious relations in neo-conservative online forums - Elwert, Frederik; Tabti, Samira; Pfahler, Lukas (Religion, 2020)
The Internet can be a place for exchange, but also foster echo chambers of closed world views. This poses interesting questions for the possibility of interreligious dialogue online. The article examines the cases of German Evangelical and Salafist Internet forums which mainly target a specific religious denomination, but nevertheless provide spaces for contact between different religions and denominations. For the study, a combination of quantitative and qualitative text analysis is applied. Quantitative analysis makes it possible to gain an overview of the discussed themes from a large body of text and serves as a basis for sampling smaller textual units for close examination using qualitative content analysis. The analysis yields two primary results: First, intrareligious dialogue plays a particular role for the negotiation of religious identity. Second, interreligious relations reflect the societal positions of both religious groups.

Emerging church bloggers in Australia: Prophets, priests and rulers in God's virtual world - Emerson Teusner, P (School of Media and Communication, 2010)
Keywords: Australia; Blogging; Christianity; Church; Virtual

New thoughts on the status of the religious Cyborg - Emerson Teusner, P (Journal of Technology, Theology & Religion, 2010)
This article suggests some implications of this development for the study of online religion. Drawing from a survey of literature from the fields of religious sociology and studies into the religious construction of both Internet and user, this paper outlines how the Cyborg has served as a metaphor for the study of online religion, and how that metaphor has been shaped in line with the aims and pursuits of researchers. The arrival of Web 2.0, however, calls us to rethink the relationship between technology and user, and hence new questions must be asked by researchers. This paper suggests what these questions may be.
Keywords: cyborg; Religious sociology

Imaging religious identity: intertextual play among postmodern Christian bloggers - Emerson Teusner, Paul (Online - Heidelberg Journal of Religions on the Internet, 2010)
In the fledgling but rapidly growing academic discipline of religion, media and culture, much attention has been paid to the use of new media to create and develop individual religious identities, build connections and foster group identities. Yet to date most research has focussed on exchanges of literal text between users, and little has considered the importance of visual text (either still images or videos) in the communication of meaning in online environments. In this presentation, I would like to introduce the image as an object of research in the construction of religious identity in online interaction. The presentation will explore the blogs of 35 Australians who are conversant with a religious movement known as “the emerging church”, a global collection of ideas and conversations residing mainly in traditional Protestant churches that seeks new expressions of faithful living in postmodern urban culture, and challenges the consumerism of contemporary evangelicalism seen in “the megachurch”. By the use of captioned images, video capture (including links to YouTube) and web page design, I will show how bloggers endeavour to present themselves as being “on the margins” of conventional Christian life and practice, and employ intertextual play to challenge modern binary oppositions of orthodoxy/heresy, art/dirt, fun/work, and constructions of gender and ethnicity.
Keywords: Blogging; Christian; identity; religion

iReligion - Emerson Teusner, P; Torma, R (Studies in World Christianity, 2011)
This article aims to present a model for investigating the capacity of mobile devices to frame religious experience by the creation, consumption and distribution of religious media text. Exploring three iPhone religious ‘apps’, this article will consider how the iPhone frames religious information and privileges aesthetic styles, which affects how users of the device connect with religious media text and other users. This exploration offers insights into how the iPhone as an object, together with the metaphors and symbols that are incumbent with it, frame religious experience and participation.
Keywords: cell phone; Christianity; online religions

Networked individualism, discursive constructions of community and religious identity: The case of Australian Christian bloggers - Emerson Teusner, Paul (Networked Sociability and Individualism: Technology for Personal and Professional Relationships, 2011)
Keywords: Blogging; Christianity; emerging church; network

Constituents of a Theory of Media - Enzensberger, H.M. (Electronic Media and Technoculture, 2000)
Never before has the future been so systematically envisioned, aggressively analyzed, and grandly theorized as in the present rush to cyberspace and digitalization. In the mid-twentieth century, questions about media technologies and society first emerged as scholarly hand-wringing about the deleterious sweep of electronic media and information technologies in mass culture. Now, questions about new technologies and their social and cultural impact are no longer limited to intellectual soothsayers in the academy but are pervasive parts of day-to-day discourses in newspapers, magazines, television, and film. Electronic Media and Technoculture anchors contemporary discussion of the digital future within a critical tradition about the media arts, society, and culture. The collection examines a range of phenomena, from boutique cyber-practices to the growing ubiquity of e-commerce and the internet. The essays chart a critical field in media studies, providing a historical perspective on theories of new media. The contributors place discussions of producing technologies in dialogue with consuming technologies, new media in relation to old media, and argue that digital media should not be restricted to the constraining public discourses of either the computer, broadcast, motion-picture, or internet industries. The collection charts a range of theoretical positions to assist readers interested in new media and to enable them to weather the cycles of hardware obsolescence and theoretical volatility that characterize the present rush toward digital technologies.
Keywords: Constituents; electronic; media; media theory; theory

Prophetic Communities Online? Threat and promise for the church in cyberspace - Charles Ess (Listening: Journal of Religion and Culture, 1999)
Keywords: cyberspace; prophetic church; Prophetic Communities

Introduction: What is internet studies? - Ess, C; Consalvo, M (The Handbook of Internet Studies, 2011)
Keywords: communication research; Internet Histories Methods and Ethics; Internet Methodologies and the Online/Offline Divide; Internet Studies; Media studies; Online research

Critical Thinking and the Bible in the Age of New Media - Ess, Charles (University Press of America, 2004)
In Critical Thinking and the Bible in the Age of New Media, Charles Ess collects contemporary scholarship to address the question: What does critical thinking about the Bible mean as the Bible is _transmediated_ from print to electronic formats? This volume, the first of its kind, is made up of contributions originally developed for a conference sponsored by the American Bible Society. Ess provides a collection grounded in a wide diversity of religious traditions and academic disciplines--philosophy, biblical studies, theology, feminism, aesthetics, communication theory, and media studies. His introduction summarizes the individual chapters and develops their broader significance for contemporary debates regarding media, postmodernism, and the possible relationships between faith and reason
Keywords: Bible; New Media

SimChurch: Being the Church in the Virtual World - Estes, Douglas (Zondervan, 2009)
The meeting place for the church of tomorrow will be a computer screen. Don't laugh, and don't feel alarmed. The real-world church isn't going anywhere until Jesus returns. But the virtual church is already here, and it's poised for explosive growth. SimChurch invites you to explore the vision, the concerns, the challenges, and the remarkable possibilities of building Christ's kingdom online. What is the virtual church, and what different forms might it take? Will it be an extension of a real-world church, or a separate entity? How will it encourage families to worship together? Is it even possible or healthy to 'be' the church in the virtual world? If you're passionate about the church and evangelism, and if you feel both excitement and concern over the new virtual world the internet is creating, then these are just some of the vital issues you and other postmillennial followers of Jesus must grapple with. Rich in both biblical and current insight, combining exploration and critique, SimChurch opens a long-overdue discussion you can't afford to miss.
Keywords: Christianity; Church; Virtual

Materiality, Authority, and Digital Religion: The Case of a Neo-Pagan Forum - Evolvi, Giulia (Entangled Religions, 2020)
The study of material culture increasingly pays attention to digital religion, but there are certain aspects, such as religious authority, that remain underresearched. Some questions are still open for inquiry: What can a material approach contribute to the understanding of religious authority in digital venues? How can authority be materially displayed on the Internet? This article shows how religious authority is affected by material practices connected with digital media use through the qualitative analysis of a NeoPagan forum, The Celtic Connection. NeoPagans tend to hold a non traditional notion of authority, accord great importance to material practices, and extensively use the Internet. The analysis of the forum suggests that NeoPagans use digital venues to look for informal sources of authority and strategies to embed materiality in online narratives. The article claims that it is important to develop new frameworks to analyze nontraditional authority figures and new definitions of media that include both physical objects and communication technologies.

The Myth of Catholic Italy in Post-Fascist Newsreels - Evolvi, Giulia (Media History, 2018)
This article analyzes how Catholicism had a central role in the identity-creation process after the War. The study employs the online archive of the national agency ‘Istituto Luce’ to analyze 261 newsreels about religion released between 1946 and 1965. The article uses (i) Benedict Anderson’s work on imagined communities and (ii) Roland Barthes’ concept of mythology as theoretical frameworks. This study indicates that the majority of newsreels presented Catholicism as intertwined with Italian politics, and as a central element of both tradition and modernity. These findings suggest that the newly formed Italian democracy used the media to emphasize certain aspects of Catholicism, while overlooking others, such as its implications with the Fascist regime. In this way, the media contributed to create a post-war myth where Catholicism represented a moral resource for the country’s leaders and citizens. This historical process contributes to explain the contemporary pervasiveness of Catholicism in Italian media.

Hybrid Muslim identities in digital space: The Italian blog Yalla - Evolvi, Giulia (Social Compass, 2017)
Islam is often regarded as being incompatible with European values. In Italy, for example, anti-Islamic points of view reiterate the religion’s alleged inconsistency with Catholicism and secularism. This article argues that narrative practices can challenge this idea by articulating Muslim hybrid identities that are compatible with Italian culture and society. The second-generation blog Yalla Italia represents a ‘third space’ where young Italian Muslims contrast dominant media stereotypes, thereby creating ‘disruptive flows of dissent’. A textual analysis of the blog and interviews with some of the bloggers reveal that three main topics are employed to overcome marginalization: (1) critiques of mainstream media (2) narratives about family lives and the practice of Islam, and (3) advocacy of a quicker procedure for gaining Italian citizenship. The bloggers adopt a storytelling style to press for social and institutional change and explain how they succeed in adapting Islam to Italian society. Their religious diversity is thus perceived as providing a potential for Italy, rather than being a mark of marginalization.
Keywords: internet; Islam; Italy

Hate in a Tweet: Exploring Internet-Based Islamophobic Discourses - Evolvi, Giulia (Religions, 2018)
Islamophobia is the unfounded hostility against Muslims. While anti-Muslim feelings have been explored from many perspectives and in different settings, Internet-based Islamophobia remains under-researched. What are the characteristics of online Islamophobia? What are the differences (if any) between online and offline anti-Muslim narratives? This article seeks to answer these questions through a qualitative analysis of tweets written in the aftermath of the 2016 British referendum on European Union membership (also known as “Brexit”), which was followed by a surge of Islamophobic episodes. The analysis of the tweets suggests that online Islamophobia largely enhances offline anti-Islam discourses, involving narratives that frame Muslims as violent, backward, and unable to adapt to Western values. Islamophobic tweets also have some peculiar characteristics: they foster global networks, contain messages written by so-called “trolls” and “bots,” and contribute to the spreading of “fake news.” The article suggests that, in order to counteract online Islamophobia, it is important to take into account the networked connections among social media, news media platforms, and offline spaces.

#Islamexit: inter-group antagonism on Twitter - Evolvi, Giulia (Information, Communication & Society, 2019)
While analyses of Twitter have shown that it holds democratic potential, it can also provide a venue for hate speech against minorities. The articulation of opinion-based identities, the tendency to homophily, and the use of emotional discourses can indeed help spread verbal violence on Twitter. This paper discusses group polarization on Twitter through Mouffe's distinction of agonistic and antagonistic politics, as elaborated in the 2013 book “Agonistic: Thinking the World Politically”. The theory is supported by a practical example: a qualitative analysis of Islamophobic tweets sent in the aftermath of the 2016 British referendum on European Union membership, which is commonly referred to as ‘Brexit’. Following the UK’s decision to leave the EU, there was a surge of Islamophobic attacks on Twitter. My analysis reveals that anti-Islamic sentiments were articulated in terms of complex identities referring not only to religion but also to ethnicity, politics, and gender. The paper shows that these tweets are antagonistic in character because they prevent the dialogic participation of Muslims and propagate symbolic violence rather than engaging in constructive conflicts.

The veil and its materiality: Muslim women’s digital narratives about the burkini ban - Evolvi, Giulia (Journal of Contemporary Religion, 2019)
In the summer of 2016, around 30 French cities banned the burkini—swimwear used by Muslim women that covers the entire body and head—from public beaches. French authorities supported the ban by claiming that the burkini was unhygienic, a uniform of Islamic extremism, and a symbol of women’s oppression. Muslim head-coverings, including the burkini, are religious objects whose materiality points to complex semantic meanings often mediated in Internet discourses. Through a qualitative analysis of visual and textual narratives against the burkini ban circulated by Muslim women, this article looks at the way digital media practices help counteract stereotypes and gain control of visual representations. Muslim women focus on two main topics: 1) they challenge the idea of Muslims being ‘aggressors’ by describing the burkini as a comfortable swimsuit not connected with terrorism; 2) they refuse to be considered ‘victims’ by showing that the burkini holds different meanings that do not necessarily entail women’s submission. Muslim women’s digital narratives positively associate the materiality of the burkini with safety and freedom and focus on secular values rather than religious meanings.

Blogging My Religion: Secular, Muslim, and Catholic Media Spaces in Europe - Evolvi, Giulia (2018)
Religion in Europe is currently undergoing changes that are reconfiguring physical and virtual spaces of practice and belief, and these changes need to be understood with regards to the proliferation of digital media discourses. This book explores religious change in Europe through a comparative approach that analyzes Atheist, Catholic, and Muslim blogs as spaces for articulating narratives about religion that symbolically challenge the power of religious institutions. The book adds theoretical complexity to the study of religion and digital media with the concept of hypermediated religious spaces. The theory of hypermediation helps to critically discuss the theory of secularization and to contextualize religious change as the result of multiple entangled phenomena. It considers religion as being connected with secular and post-secular spaces, and media as embedding material forms, institutions, and technologies. A spatial perspective contextualizes hypermediated religious spaces as existing at the interstice of alternative and mainstream, private and public, imaginary and real venues.By offering the innovative perspective of hypermediated religious spaces, this book will be of significant interest to scholars of religious studies, the sociology of religion, and digital media.

Emotional Politics, Islamophobic Tweet. The Hashtags #Brexit and #chiudiamoiporti - Evolvi, Giulia (PARTECIPAZIONE E CONFLITTO, 2019)
Contemporary far-right politicians increasingly diffuse messages through social networks. This article argues that online communication may prove effective for political engagement because it can create emotional reactions against certain groups, in a process that I call "emotional antagonism." An example of emotional antagonism is online Islamophobia, which considers Islam as supposedly incompatible with democratic values and tends to conflate Muslims with migrants. Through qualitative observations and textual analyses of tweets, this article explores the following questions: How do certain online exchanges emotionally frame Muslims as the social "others" in relation to European culture? Why and how does the Internet facilitate the spread of emotional antagonism? What type of political propaganda and participation is connected to affective online Islamophobia? The article analyses two case studies: 1) Islamophobic tweets sent in the aftermath of the British referendum in 2016, with the hashtag #Brexit; 2) Anti-Muslim tweets that contain the hashtag #chiudiamoiporti (close the ports), launched by Italian Vice Prime Minister Matteo Salvini in 2018 to support anti-migration measures. The article shows that exploring emotional antagonism can add complexity to the current understanding of Islamophobic conflicts, of social media platforms' characteristics, and of political participation based on online communication.
Keywords: Brexit; Islamophobia; Matteo Salvini; migration; Twitter

Witchcraft: Changing Patterns of Participation in the Early Twenty-First Century - Douglas Ezzy; Berger, Helen (The Pomegranate, 2009)
There are indications that the phenomenal growth of Witchcraft and Paganism during the late twentieth and early twenty-first century may be slowing, based on statistics from selected search engines, websites, and blogs. In particular, inquisitive inquiry about contemporary Witchcraft— that is, those who are not Witches but are looking for information about it, such as seekers, dabblers, researchers, students doing term papers, and newspaper reporters—has declined since 2004. This decline, however, does not indicate that the religion is “dying out” because while the rate of increase has slowed it has not been eliminated; and of greater import, community networking appears to have remained stable, or possibly to have increased. Community networking can be seen in the use of Internet sites to share information about Witchcraft, upcoming rituals, or books and teachers, those participating in dialogue, or using the Internet as part of their spiritual work or for communications between coven meetings, or with coven members who are unable to attend. The statistics suggest that contemporary Witchcraft and Paganism may be in a period of change, in which there is a consolidation of membership with a slowing of the rate of new members, particularly among the young. Community building on the Internet continues to be important, but the intensity appears to be lessening, with indications of more people “posting” but doing so less frequently. We suggest that this indicates that Witchcraft is now entering a new phase of consolidation with less intense participation by members.
Keywords: alternative religion online; paganism online

The counterpublic of the J(ewish) Blogosphere: gendered language and the mediation of religious doubt among ultra‐Orthodox Jews in New York - Fader, A (Journal of the Royal Anthropological Institute, 2017)
While there have always been doubters and heretics among ultra‐Orthodox Jews, access to the Internet over the past fifteen years has amplified opportunities for anonymous expression and connection. An early key platform was the Jblogosphere (Jewish Blogosphere), which flourished between 2003 and 2009. This article focuses on four Hasidic bloggers (three men and a woman) who were part of a growing counterpublic of secret religious doubters. I trace how this counterpublic challenged the authority of the ultra‐Orthodox religious public sphere through gendered digital writing and reading in varieties of Yiddish and English. Linguistic resources for those engaging with the new medium of the blog became proxies for bodies that could not change without risk of expulsion. However, the counterpublic remained almost exclusively for men, reproducing the exclusion of women from the ultra‐Orthodox public sphere. The analysis focuses on dynamics between gendered languages and media/semiotic ideologies in order to highlight a historical moment when the mediation of religious doubt became publicly legible, with implications for religious change for individuals and their wider communities.
Keywords: Blogosphere; Jewish; language; mediation; religious; ultra Orthodox Jews

Ultra-Orthodox Jewish interiority, the Internet, and the crisis of faith - Fader, A (Journal of Ethnographic Theory, 2017)
This article argues for a recuperation of interiority. Rather than conflate interiority with belief, as immaterial and individualized, research with ultra-Orthodox Jews in New York reveals interiority to be as public and political as is the material. Over the past fifteen years, ultra-Orthodox Jews have been increasingly concerned with religious doubt. Many communal leaders have called the current moment “a crisis of faith,” with the perception that there are new challenges to ultra-Orthodoxy, especially from the Internet. In response, leaders have turned to explicit communal talk about interiority in their attempts to strengthen faith and therapeutically treat those with religious doubts. Public talk, where certain forms and locations of interiority are cultivated and others disciplined, shows efforts by ultra-Orthodox leadership to defuse the power of secular epistemologies, such as psychology and technologies, while harnessing their potentialities for religious authenticity
Keywords: digital media; interiority; Judaism; language; religion; technology; Ultra-Orthodox Jewish

Facebooking Religion and the Technologization of the Religious Discourse: A Case Study of a Botswana-based Prophetic Church - Faimau, Gabriel (Heidelberg Journal of Religions on the Internet, 2016)
Technologization of discourse is generally conceptualized as a process of influencing people’s way of thinking through the use of certain linguistic strategies. In this process, power is exercised through the use of linguistic strategies that shape the construction of identity as well as socio-religious vision. This study analyzes the ways in which certain linguistic strategies and religious discourses used in Facebook posts, reviews and comments on a religion-based Facebook page create and shape the narratives of religious authority, religious identity and religious community. Using the Facebook page of a popular prophetic Christian church in Botswana, Gospel of God’s Grace (3G Ministries), as a case study, this study examines the following questions: in what ways can an active religion-based Facebook page reconfigure and provide a platform for religious practice? To what extent does the use of various linguistic strategies inform and shape religious discourses found in various Facebook postings and comments? And how does a religious Facebook page provide a venue for the discursive interpretation of religious authority, the negotiation of religious identity and the development of socio-religious vision?
Keywords: Facebook; identity construction; religious authority; technologization

Religious testimonial narratives and social construction of identity: Insights from prophetic ministries in Botswana - Faimau, G. (Cogent Social Sciences, 2017)
Giving a testimony forms a central part of the religious practices among Pentecostal churches including prophetic ministries. Testimony links the understanding of one’s religious experience and the configuration of the divine intervention. Utilizing data collected through ethnographic observation among prophetic ministries in Botswana and digital ethnography of the testimonial narratives circulated online through various new media outlets of these ministries, this paper examines the ways in which religious identity is constructed and understood through the testimonial performance in various religious services. Informed by the premise that narrative is closely related to identity, the paper pays particular attention to the extent to which religious testimonies influence the dynamic relationship between individual, communal and institutional religious identity. The following questions are central to the analysis: In what ways does a religious testimony inform us about the construction and negotiation of religious identity? To what extent does a religious testimony influence the dynamic relationship between individual, communal and institutional religious identity? While suggesting that religious identity constructions and negotiations are embedded within the sharing of religious testimonies, I also argue that the sharing of a religious testimony has an agentive function of extending the social relationship between an individual believer, other believers and the religious community within which the testimony is shared.
Keywords: Facebook; identity; prophetic ministries; testimony

The dynamics and digitisation of religious testimonies: a case of prophetic ministries in Botswana - Faimau, Gabriel (Anthropology Southern Africa, 2017)
A major element in the religious practice of believers in prophetic Christianity is the sharing of religious testimonies. Focusing on prophetic ministries in Botswana, this paper examines the nature and function of religious testimonies and the dynamics of their digitisation and online circulation. It explores the ways in which religious testimonies mediate or extend the reach of prophetic ministries. Using data collected through fieldwork observation, in-depth interviews and digital ethnography, I argue that the sharing of testimony within Pentecostal Christian circles can be described as a system of institutional performance that aims to direct the spiritual development of believers, reinforce the central place and authority of a prophet and advance the institutional identity of a prophetic ministry.

The Divine Online: Civic Organizing, Identity Building, and Internet Fluency Among Different Religious Groups - Justin Farrell (Journal of Media and Religion, 2011)
The number of religious congregations with Web sites nearly tripled from 1998–2006, and each year another 10,000 congregations launch a Web site (Chaves & Anderson, 2008). Couple this with the fact that 79% of attendees are now in a congregation with a Web site. Scholars of media and religion know very little, however, about the content of these Web sites or what they tell us about the culture of different religious groups. The aim of this article, therefore, is to examine how congregations are constructing Web sites to advertise their identity, organize their followers to get involved in civic and political issues, and provide an interactive space for online participation in actual ministries. Extensive qualitative data were gathered from 600 individual congregation Web sites from nine denominations in 53 different cities across the United States. The results of the descriptive analysis of these data suggest that there is a strong correlation between the “off-line” characteristics of a particular congregation and the “on-line” characteristics of the same congregation. Evangelical congregations tend to have more complex, attractive, and interactive Web sites and fall into the “online religion” camp. Liberal-Protestant and Catholic congregations tend to create static “brochure” style Web sites that emphasize their denominational identity and thus fall into Hadden and Cowan's (2000) “religion online” camp. This study expands our theoretical knowledge about the proliferation of media into, and out of, religious congregations, and offers a broader understanding about how institutions negotiate their online identity in the digital age. [Supplemental materials are available for this article. Go to the publisher's online edition of the Journal of Media and Religion for the following free supplemental resource: Appendix II: Web Site Screen Shots.]
Keywords: Catholic; Catholic congregations; Catholics; Computer; Contemporary Religious Community; cyberspace; internet; Mass media; media and religion; network; New Media and Society; new media engagement; New Technology and Society; online communication; Online community; religion; religion and internet; Religion and the Internet; religiosity; religious engagement; religious identity; Religious Internet Communication; Religious Internet Communities; religious media research; sociability unbound; Sociology of religion; users’ participation; virtual community; virtual public sphere; “media research”; “online identity; “religion online”; “religious congregations”; “religious media research”

'You wince in agony as the hot metal brands you’: Religious behavior in an online pole-playing game - Feltmate, D. (Journal of Contemporary Religions, 2010)
Keywords: Online; religion; video games

Internet Ritual: A Case of the Construction of Computer-Mediated Neopagan Religious Meaning - Fernback, Jennifer (Practicing Religion in the Age of Media, 2002)
Increasingly, the religious practices people engage in and the ways they talk about what is meaningful or sacred take place in the context of media culture -- in the realm of the so-called secular. Focusing on this intersection of the sacred and the secular, this volume gathers together the work of media experts, religious historians, sociologists of religion, and authorities on American studies and art history. Topics range from Islam on the Internet to the quasi-religious practices of Elvis fans, from the uses of popular culture by the Salvation Army in its early years to the uses of interactive media technologies at the Simon Wiesenthal Center's Beit Hashoah Museum of Tolerance. The issues that the essays address include the public/private divide, the distinctions between the sacred and profane, and how to distinguish between the practices that may be termed "religious" and those that may not.
Keywords: internet ritual; Neopagan; religion

Religious Online Developments in a Secular Context - P. Fischer-Nielsen (Masaryk University Journal of Law and Technology, 2012)
Religious groups have conceived the internet as both a promising way of increasing interest in religious issues and a threat to the core religious values. This article deals with religious developments on the internet based on theoretical perspectives on secularization. Four relevant themes are listed, namely secularization as loss of religious institutional power and authority, secularization as adaption, secularization as decrease in individual religious engagement, These themes are investigated through an empirical analysis of results from two large surveys with 1,015 Danes and 1,040 Danish pastors and secularization as changed conditions for religious communication. The article concludes that the internet does not seem to have dramatically changed people’s religious orientation. As in offline contexts, religious institutions are under pressure on the internet. Though the internet has been viewed as a new direct channel to people, evidence suggests that people are difficult to reach and that other players than the religious institutions dominate the transmission of religious messages. Secularization does take place online, but the development is counteracted by deliberate attempts to use the internet in religious activities, for instance by pastors who engage in critical negotiation of the possibilities online.
Keywords: adaption; Authority; cyber church.; dialogue; discussion groups; individualization; internet; media sites; Negotiation; religion; search engines; secularization; Social Networking

Religion on the Internet: Community and Virtual Existence: - Foltz, Franz; Foltz, Frederick (Bulletin of Science, Technology & Society, 2016)
There is considerable controversy concerning the ability of the Internet to provide communal experiences. This article looks at the ability of the World Wide Web to foster religious community, particularly from a Christian perspective. It looks at the nature of religion and community and shows to what extent the Internet has and has not been successful in recreating religious community. It looks at the reaction of two particular groups of users and categorizes Web sites into five types: research sites, extensions of local community, independent sites, spiritual retreats, and online worship. Finally it discusses the limitations of disembodied experience and argues that most individuals use the media within these limitations.

The Subject and Power - Michel Foucault (The University of Chicago Press, 2000)

Discipline and punish - Foucault, M. (Journal of Management & Governance, 1977)

Thy Kingdom Connected - Friesen, Dwight J. (Baker Books, 2009)
Networks are everywhere. From our roads to our relationships, from our food supply to our power grids, networks are an integral part of how we live. Similarly, our churches, denominations, and even the kingdom of God are networks. Knowing how networks function and how to work with rather than against them has enormous implications for how we do ministry.In Thy Kingdom Connected, Dwight J. Friesen brings the complex theories of networking to church leaders in easy-to-understand, practical ways. Rather than bemoaning the modern disintegration of things like authority and structure, Friesen inspires hope for a more connective vision of life with God. He shows those involved in ministry how they can maximize already existing connections between people in order to spread the Gospel, get people plugged in at their churches, and grow together as disciples.
Keywords: Christianity; Connection; networking

Race, Religion, or Culture? Framing Islam between Racism and Neo-Racism in the Online Network of the French Far Right - Froio, Caterina (Perspectives on Politics, 2018)
When debates about Islam acquire importance in the public sphere, does the far right adhere to traditional racist arguments, risking marginalization, or does it conform to mainstream values to attain legitimacy in the political system? Focusing on the aftermath of the 2015 terrorist attacks in France, I explore the framing of Islam, discussing how the far right’s nativist arguments were reformulated to engage with available discursive opportunities and dominant conceptions of the national identity. By looking at actors in the protest and the electoral arenas, I examine the interplay between the choice of anti-Islam frames and baseline national values. I offer a novel mixed-method approach to study political discourses, combining social network analysis of the links between seventy-seven far-right websites with a qualitative frame analysis of online material. It also includes measures of online visibility of these websites to assess their audiences. The results confirm that anti-Islam frames are couched along a spectrum of discursive opportunity, where actors can either opt to justify opposition to Islam based on interpretations of core national values (culture and religion) or mobilize on strictly oppositional values (biological racism). The framing strategy providing most online visibility is based on neo-racist arguments. While this strategy allows distortion of baseline national values of secularity and republicanism, without breaching the social contract, it is also a danger for organizations that made “opposition to the system” their trademark. While the results owe much to the French context, the conclusions draw broader implications as to the far right going mainstream.

Internet use among religious followers: Religious postmodernism in Japanese Buddhism - Fukamizu, K. (Journal of Computer-Mediated Communication, 2007)
Strong sect organizations are a feature of traditional Buddhist denominations in Japan. Having long benefited from the protection of Japan's feudal society, these once strong organizations have been buttressed by factors of social change in the modern and post-modern eras, including modernization and the evolution of the media. The Internet is a rich source of information about innovations of religions adapting to social change. To examine these changes, I undertook a survey from 2002 to 2004 of 2,007 followers and religious specialists. The results highlight a critical attitude among followers: Sending and receiving messages in the interaction between a religious group and its followers results in followers expanding the scope of allowable subjects of criticism, and they have begun to entertain doubts regarding their faith systems. We may infer that in postmodern faith, horizontal interaction among religious followers will take on an increasingly important role in comparison with the vertical (top-down) structure of traditional doctrines.
Keywords: Buddhism; internet; Japanese; religion

Technology, ecology and spirituality: neopaganism and hybrid ontologies in technoculture - Susan Gallacher (Murdoch University, 2008)
This thesis considers three convergent issues pertinent to investigations of identity and agency in contemporary society: the proliferation of digital, network technologies, the rise of interest in secular — ‘new edge’ — spiritualities, and our growing awareness of impending ecological crises. I argue that these three issues necessitate a critical reconsideration of human agency, one that embodies a more sustainable and responsible ‘being-in-the-world’. With this goal in mind, I apply the insights of ecofeminism, feminist approaches to technology and science, and the philosophy of technology, to provide a critical analysis of the human-technology relation in the broader contexts of gender, ecology and spirituality. In particular, I highlight the strengths of ecofeminism, and then employ several alternative theories in order to attend to limitations I identify within ecofeminism; in particular, its uncompromising stance towards modern technology as wholly patriarchal and damaging to both nature and women. Against this position, I argue that technology is fully embedded in and central to our being-in-the-world, and thus must be accounted for in any consideration of contemporary agency. I then attend to both technophobic and technophilic approaches to technology and technoscience in feminism more generally, suggesting how these oppositional tensions are embodied in the figures of the ‘cyborg’ and the ‘goddess’. In search of more complex, hybridised ways to understand the human-technology relation, I then turn to three key theorists – Don Ihde, Donna Haraway and Bruno Latour. Synergising their approaches with the neopagan worldview, I propose a metaphorical and material identity which properly attends to and incorporates the treble issues of ecology, technology and spirituality into its worldview: the technopagan. At once nature-worshipper and digital dweller, the technopagan is a dynamic, multi-faceted and adaptable agent that can effectively challenge traditional humanist binaries between nature and technology, science and religion, and human and nonhuman.
Keywords: ecology; neopaganism; Spirituality; technology

Secularisation and de-institutionalised religion - Ganiel, G (Foundations and Futures in the Sociology of Religion, 2017)
Since the sociology of religion became recognised as a distinct sub-discipline over the last century, the dominance of approaches taking their inspiration from the sociological classics has increasingly been challenged. Empirical findings have brought the notion of secularisation into question; and theorists have sought to deconstruct how we think of ‘religion.’ This collection appraises the continuing influence of the foundational approaches and places these in relation to newly emerging directions in the field.
Keywords: de-institutionalized religion; Secular; Sociology of religion

Rhythms and Rhymes of Life: Music and identification processes of Dutch-Moroccan youth - Gazzah, Miriam (ISIM, 2008)
http://www.miriamgazzah.nl/uploads/4/5/7/7/4577982/rhythmsrhymesdissertation2008aup.miriamgazzah.pdf
Keywords: Dutch; identity; Music; Youth

What is apologetics? Baker encyclopedia of Christian apologetics - Norman L. Geisler (Baker Academic, 1999)
This comprehensive reference volume covers every key issue, person, and concept related to Christian apologetics from Anselm to Zen.

The Virtual Construction of the sacred–Representation and Fantasy in the Architecture of Second Life Churches - Gelfgren, S; Hutchings, T (Nordic Journal of Religion and Society, 2014)
This study aims to construct a typology of the visual style of Christian spaces in the online virtual world of Second Life (SL). Virtual worlds offer diverse new possibilities for architectural style, unrestricted by gravity, weather or scarcity of materials. These new regions also operate largely beyond the control and indeed awareness of established religious authorities, so they can also offer users new opportunities to reconsider the social structure of their communities. This research project aims to survey religious responses to these new potential freedoms. Research to date on religion in SL has focused on small samples of spaces or activity, but we found 114 Christian spaces. An overwhelming number of the locations we visited featured a Christian church building. 81 of 114 included a church building that reproduced a recognizable offline architectural style, and only 9 included a church with an entirely different style. Only 15 Christian locations had buildings that cannot be characterised as churches.
Keywords: Church; Sacred; Second Life Churches; Virtual

Why Does the Archbishop Not Tweet?: How Social Media Challenge Church Authorities - Gelfgren, Stefan (Nordicom Review, 2015)
In summer 2012, the Archbishop of the Church of Sweden appeared on Twitter. There was only one problem – it was not the Archbishop himself who was tweeting, but an anonymous person. A discussion then ensued on Twitter and in the blogosphere between those in favor of the Archbishop and his department and mainly social media proponents. The present article describes and analyzes the social media debate, and how authority and hierarchies are negotiated in and through social media. The analysis is based on Heidi Campbell’s “Religious-Social Shaping of Technology” model, and emphasizes the need to take into account not only the faith and tradition of the religious actor, but also the societal context in which the negotiating process takes place. In this case, the concepts of “media- tization” and “secularization” are used to understand the broader context of the process.

The Call to Jihad: Charismatic Preachers and the Internet - Gendron, A (Studies in Conflict & Terrorism, 2016)
A range of psychological, social, and environmental factors render some individuals more susceptible to militant Islam than others. Research also suggests that there are certain “triggers,” which help to explain why it is that only some individuals exposed to the same societal structural influences turn to violence. This article seeks to contribute to future empirical research in this area by studying the significance of certain “charismatic” preachers in this process and examining the role the Internet plays in strengthening the charismatic bond. Difficulties in defining and measuring “charisma” may help in part to explain the paucity of research on this aspect of radicalization but since charismatic authority derives from the bond between preacher and follower, an examination of the activities, strategies, and techniques used to build relationships and win adherents to Salafi-jihadism may provide valuable insights for countering radicalization.
Keywords: Digital Religion; internet; jihad; Preachers

Apocalyptic AI: Visions of Heaven in Robotics, Artificial Intelligence, and Virtual Reality - Robert M Geraci (Oxford University Press, 2010)
Apocalyptic AI, the hope that we might one day upload our minds into machines or cyberspace and live forever, is a surprisingly wide-spread and influential idea, affecting everything from the world view of online gamers to government research funding and philosophical thought. In Apocalyptic AI, Robert Geraci offers the first serious account of this "cyber-theology" and the people who promote it. Drawing on interviews with roboticists and AI researchers and with devotees of the online game Second Life, among others, Geraci illuminates the ideas of such advocates of Apocalyptic AI as Hans Moravec and Ray Kurzweil. He reveals that the rhetoric of Apocalyptic AI is strikingly similar to that of the apocalyptic traditions of Judaism and Christianity. In both systems, the believer is trapped in a dualistic universe and expects a resolution in which he or she will be translated to a transcendent new world and live forever in a glorified new body. Equally important, Geraci shows how this worldview shapes our culture. For instance, Apocalyptic AI has influenced funding agencies such as the National Science Foundation, helping to prioritize robotics and AI research. It has become the ideology of choice for online gamers, such as those involved in Second Life; it has had a profound impact on the study of the mind; and it has inspired scientists and theologians alike to wonder about the super robots of the future. Should we think of robots as persons? What kind of morality would intelligent robots espouse? Apocalyptic AI has become a powerful force in modern culture. This volume shines a light on this belief system, revealing what it is and how it is changing society.
Keywords: Apocalypticism; Artificial Intelligence; Robotics; Second Life; Singularity; virtual worlds

Emerging churches: Creating Christian community in postmodern cultures - Eddie Gibbs; Eddie Gibbs (Baker Academic, 2005)
The "emerging church" movement is perhaps the most significant church trend of our day. The emerging church offers and encourages a new way of doing and being the church. While it largely resonates with an eighteen-to-thirty-four-year-old audience--the first fully postmodern generation--it is also gaining popularity with older Christians and encompasses a broad array of traditional and contemporary churches. Emerging Churches explores this movement and provides insight into its success. Filled with the latest research and interesting, anecdotal testimonies from those on the cutting edge of ministry, this book provides pastors, church leaders, and interested readers with an insightful glimpse into the thriving churches of today--and tomorrow.

The presentation of self in everyday life - Goffman, E (Penguin, 1990)
A notable contribution to our understanding of ourselves. This book explores the realm of human behavior in social situations and the way that we appear to others. Dr. Goffman uses the metaphor of theatrical performance as a framework. Each person in everyday social intercourse presents himself and his activity to others, attempts to guide and cotnrol the impressions they form of him, and employs certain techniques in order to sustain his performance, just as an actor presents a character to an audience. The discussions of these social techniques offered here are based upon detailed research and observation of social customs in many regions.

The Making of contemporary papacy: manufactured charisma and Instagram - Golan, Oren; Martini, Michele (Information, Communication & Society, 2019)
Recent research highlights the growth of alternative religious leadership on a global scale. In response, social media have emerged as platforms to compete for religious primacy. Accordingly, the study asks how is online religious authority constructed, re-affirmed and implemented by religious organizations? We contend that through online means, religious organizations are nowadays working to construct a public image to spark charismatic attraction towards institutional leaders. To investigate, we developed a grounded study that captured the full Instagram production of Pope Francis’ official account (429 images). Drawing on construal theory, findings demonstrated the strategic management of social, spatial, affective and hypothetical distance, simultaneously corresponding with uncovered facets: hierarchical positioning; geographical locales, haptic engagement, and leaders’ visual focus. Thus, we suggest introducing a concept of image-mediated-charisma, and its theoretical framing through digital distance. Concepts that were observed in the religious realm yet can be extended and applied to political or cultural leaders.

Charting Frontiers of Online Religious Communities: The Case of Chabad Jews - Oren Golan (Digital Religion: Understanding Religious Practice in New Media Worlds, 2013)
Keywords: Chabad Jews; Jewish Community; Jewish religion; Jews; new media engagement; New Technology and Society; Online community; Religion and the Internet; religious engagement; Sociology of religion

Fundamentalist web journalism: Walking a fine line between religious ultra-Orthodoxy and the new media ethos - Golan, O; Mishol-Shauli, N (European Journal of Communication, 2018)
New media journalism has perturbed traditional reporting not only in mainstream-modern societies but also within religious-cum-insular communities. Focusing on the Jewish ultra-Orthodox community in Israel and in light of web journalists’ continuous struggle with leading clergy and an apprehensive public, this study grapples with the question, ‘How do ultra-Orthodox web journalists view their work mission as information brokers for an enclave culture?’ The study gleaned from 40 in-depth interviews with web journalists and discussions with community web activists. Results uncovered three major schemata that drive their praxis: (1) Communal-Haredi, (2) Western-Democratic and (3) Journalist Ecosystem. Findings suggest a rising archetype of fundamentalist web journalism that rests its professional ethos on writers’ practice, rather than on formalized training or communal dictums. Web journalists were found to strongly identify with their community, yet, often unintentionally, also act as a secondary form of authority and harbingers of change.
Keywords: fundamentalism; journalist motivations; new media and religion; online journalism; religion; religion and media; ultra-Orthodox; Ultra-Orthodox Jews; web journalism

Building the sacred community online: the dual use of the Internet by Chabad - Golan, O; Stadler, N (Media, Culture & Society, 2015)
Religious communities have ongoing concerns about Internet use, as it intensifies the clash between tradition and modernity, a clash often found in traditionally inclined societies. Nevertheless, as websites become more useful and widely accessible, religious and communal stakeholders have continuously worked at building and promoting them. This study focuses on Chabad, a Jewish ultra-Orthodox movement, and follows webmasters of three key websites to uncover how they distribute religious knowledge over the Internet. Through an ethnographic approach that included interviews with over 30 webmasters, discussions with key informants, and observations of the websites themselves, the study uncovered webmaster’s strategies to foster solidarity within their community, on one hand, while also proselytizing their outlook on Judaism, on the other. Hence, the study sheds light on how a fundamentalist society has strengthened its association with new media, thus facilitating negotiation between modernity and religious piety.
Keywords: Chabad; community; Digital Religion; fundamentalism; religion; religious communities

Strategic Management of Religious Websites: The Case of Israel’s Orthodox Communities - Golan, O; Campbell, H (Journal of Computer-mediated Communication, 2015)
This study investigates how webmasters of sites affiliated with bounded communities manage tensions created by the open social affordances of the internet. We examine how webmasters strategically manage their respective websites to accommodate their assumed target audiences. Through in‐depth interviews with Orthodox webmasters in Israel, we uncover how they cultivate 3 unique strategies ‐‐ control, layering, and guiding ‐‐ to contain information flows. We thereby elucidate how web strategies reflect the relationships between community, religion and CMC.
Keywords: fundamentalism; internet; Orthodox Judaism; religious communities online; websites

Religious live-streaming: constructing the authentic in real time - Golan, Oren; Martini, Michele (Information, Communication & Society, 2019)
From the Wailing Wall in Jerusalem to the Kaaba of Mecca, many religious sites are webcasting in live-streaming. This study inquires how religious institutions act to shape users’ worldviews and negotiate meanings via live-streaming-mediated communication. Ethnographic fieldwork accompanied a case study of 25 in-depth interviews of the Canção Nova and the Franciscan Order’s recent media operation in the Holy Land. Findings uncovered three facets: (1) Evangelizing youth. (2) Establishing affinity towards the Holy Land. (3) Maintaining constant presence of the transcendental. Drawing on Walter Benjamin, proximity between believers and the divine via live-streaming is discussed and its implication for transforming the religious experience, establishing secondary authority in the Catholic world and propelling religious change in the information society.

Digital pilgrimage: Exploring Catholic monastic webcasts - Golan, Oren; Martini, Michele (The Communication Review, 2018)
This study questions how religious webmasters view the objectives of their webcasting in relation to pilgrimage. Findings uncovered four facets: (1) mediation of the holy sites and experience; (2) bonding between Holy Land communities and global believers; (3) cultivating agents; (4) media experiences as a pilgrimage surrogate. Drawing on Walter Benjamin, the study elucidates how online videos evoke proximity to the sacred, thus connecting holy sites and believers, while affirming webmasters as secondary actors of religious authority.

Embedded digital creatives - Goldsmith, B. (Creative work beyond the creative industries: Innovation, employment and production, 2014)

Japanese Cybercultures - Nanette Gottlieb; Mark McLelland (Routledge, 2003)
Japan is rightly regarded as one of the most technologically advanced countries in the world, yet the development and deployment of Internet technology in Japan has taken a different trajectory compared with Western nations. This is the first book to look at the specific dynamics of Japanese Internet use. It examines the crucial questions: * how the Japanese are using the Internet: from the prevalence of access via portable devices, to the fashion culture of mobile phones * how Japan's "cute culture" has colonized cyberspace * the role of the Internet in different musical subcultures * how different men's and women's groups have embraced technology to highlight problems of harassment and bullying * the social, cultural and political impacts of the Internet on Japanese society * how marginalized groups in Japanese society - gay men, those living with AIDS, members of new religious groups and Japan's hereditary sub-caste, the Burakumin - are challenging the mainstream by using the Internet. Examined from a variety of interdisciplinary perspectives, using a broad range of case-studies, this is an exciting and genuinely cutting-edge book which breaks new ground in Japanese studies and will be of value to anyone interested in Japanese culture, the Internet and cyberculture.
Keywords: culture; cyber; internet; Japan

Religion, Media, and Social Change - Kennet Granholm; Marcus Moberg; Sofia Sjö (Routledge Research in Religion, Media and Culture, 2014)
In an era of heightened globalization, macro-level transformations in the general socioeconomic and cultural makeup of modern societies have been studied in great depth. Yet little attention has been paid to the growing influence of media and mass-mediated popular culture on contemporary religious sensibilities, life, and practice. Religion, Media, and Social Change explores the correlation between the study of religion, media, and popular culture and broader sociological theorizing on religious change. Contributions devote serious attention to broadly-defined media including technologies, institutions, and social and cultural environments, as well as mass-mediated popular culture such as film, music, television, and computer games. This interdisciplinary collection addresses important theoretical and methodological questions by connecting the study of media and popular culture to current perspectives, approaches, and discussions in the broader sociological study of religion.
Keywords: Digital Religion; Globalization; institutions; Online community; religious change; social change; socioeconomic modern societies; sociological study of religion; Technologies

Judaism on the Web - Green, Irving (MIS Press, 1997)
Surfing the Web for information on a particular subject can be both fun and daunting. It's easy to get overwhelmed when a simple Web search lists hundreds or even thousands of sites. Often times you're left with a case of information overload -- a feeling of helplessness that results from having too much data and too little idea where to start looking. Judaism is one such topic with a myriad of Web sites devoted to it. You can spend countless hours browsing the vast online resources on this religious and cultural community. Wouldn't it be great if there was a guide to the very best of these Web sites? Judaism on the Web is a highly focused collection of 500 first-class sites related to Judaica. Author Irving Green has done the bulk of the Web searching for you, assembling the cream of the crop and placing them into one of five categories: the Jewish world, the Jewish year, culture, intellectual life, and current issues. You find references to sites that offer 3D virtual synagogues, genealogy resources, Kosher recipes, Jewish comics, Yiddish culture, holiday calendars, Israeli Web sites, coverage of Jewish denominations, and much more. So don't get bogged down by information overload. Let Judaism on the Web make online learning a fun and enlightening experience.
Keywords: internet; Israel; Jewish; religion

Counter-Radicalization via the Internet - Greenberg, K (The Annals of the American Academy of Political and Social Science, 2016)
ISIS and other international terrorist organizations rely on the Internet to disseminate their extremist rhetoric and to recruit people to their cause, particularly through popular online social media applications. Any meaningful counterterrorism strategy must, therefore, account for the ways in which terrorist organizations use the Internet to prey on young, manipulable minds who are drawn to radical ideas and propaganda and to the desire to serve a cause larger than themselves. This article outlines the ways in which extremist organizations use the Internet to ensnare new recruits, analyzes the implications of cyber-recruitment on existing counterterrorism techniques, and suggests ways in which the U.S. government can work with Internet service providers and other major cyber corporations to better address this growing threat.
Keywords: countering violent extremism; CVE; Internet recruitment; ISIS; radicalization

Buddhism, the Internet, and Digital Media: The Pixel in the Lotus - Grieve, G.P; Veidlinger, D (Routledge Studies in Religion and Digital Culture, 2014)
Buddhism, the Internet and Digital Media: The Pixel in the Lotus explores Buddhist practice and teachings in an increasingly networked and digital era. Contributors consider the ways Buddhism plays a role and is present in digital media through a variety of methods including concrete case studies, ethnographic research, and content analysis, as well as interviews with practitioners and cyber-communities. In addition to considering Buddhism in the context of technologies such as virtual worlds, social media, and mobile devices, authors ask how the Internet affects identity, authority and community, and what effect this might have on the development, proliferation, and perception of Buddhism in an online environment. Together, these essays make the case that studying contemporary online Buddhist practice can provide valuable insights into the shifting role religion plays in our constantly changing, mediated, hurried, and uncertain culture.
Keywords: Buddhism; digital media; internet

Finding Liquid Salvation: Using The Cardean Ethnographic Method To Document Second Life Residents And Religious Cloud Communities - Grieve, Gregory (Virtual Worlds, Second Life, and Metaverse Platforms: New Communication and Identity Paradigms, 2011)
Keywords: religion; Salvation; Second Life; virtual communities

Religion - Grieve, Gregory (Digital Religion: Understanding Religious Practice in New Media Worlds, 2012)
Keywords: religion

Cyber Zen: Imagining Authentic Buddhist Identity, Community, and Practices in the Virtual World of Second Life - Grieve, G.P (Routledge, 2016)
Cyber Zen ethnographically explores Buddhist practices in the online virtual world of Second Life. Does typing at a keyboard and moving avatars around the screen, however, count as real Buddhism? If authentic practices must mimic the actual world, then Second Life Buddhism does not. In fact, a critical investigation reveals that online Buddhist practices have at best only a family resemblance to canonical Asian traditions and owe much of their methods to the late twentieth-century field of cybernetics. If, however, they are judged existentially, by how they enable users to respond to the suffering generated by living in a highly mediated consumer society, then Second Life Buddhism consists of authentic spiritual practices. Cyber Zen explores how Second Life Buddhist enthusiasts form communities, identities, locations, and practices that are both products of and authentic responses to contemporary Network Consumer Society. Gregory Price Grieve illustrates that to some extent all religion has always been virtual and gives a glimpse of possible future alternative forms of religion
Keywords: Buddhist; cyber zen; Virtual World; Zen

Buddha Machine - Grieve, Gregory (Buddha Machine, 2012)
The Buddha Machine was created by sampling found images form the Internet Internet Archive, a San Francisco based non-profit whose library includes texts, audio, moving images and archived WebPages. The video generates trsna (the Buddhist notion of desire) by visually embodying Gilles Deleuze and Félix Guattari’s notion of the desiring machine. By desire, Buddhists refer to craving pleasure, material goods, and immortality, all of which are wants that can never be satisfied, and lies at the root of suffering. Suffering, or duḥkha, literally means to be “stuck” or stopped. Similarly, for Deleuze and Guattari, desire is not to be identified with lack, with the law, or with the signifier, but rather with production, or really with the stoppage of production. As they write in Anti-Oedipus “a machine may be defined as a system of interruptions or breaks.” The Buddha Machine is connected visually to the viewer, and creates desire by breaking visual flow. However, simultaneously, it is at the same time also a flow itself, or the production of a flow.

Virtually Embodying The Field: Silent Online Buddhist Meditation, Immersion, and The Cardean Ethnographic Method - Grieve, Gregory (Online - Heidelberg Journal of Religions on the Internet, 2010)
This article sketches the Cardean Ethnographic research method that emerged from two years of study in Second Life’s Zen Buddhist cloud communities. Second Life is a 3D graphic virtual world housed in cyberspace that can be accessed via the Internet from any networked computer on the globe. Cloud communitiesare groups that are temporary, flexible, elastic and inexpensive in the social capital required to join or to leave. In our research, we found ourselves facing a two-sided methodological problem. We had to theorize the virtual and its relation to the actual, while simultaneously creating practices for an effective ethnographic method. Our solution, named after the Roman Goddess of the hinge, Cardea, was a method that uses the model of a hinge to theorize the virtual as desubtantialized and the worlds opened up by cyberspace as nondualistic. This understanding of the virtual worldscalled for a classic ethnographic methodbased on participant observation and thick description.
Keywords: Buddhism; Ethnography; Immersion; Meditation

Imagining a Virtual Religious Community: Neo-pagans on The Internet - Grieve, Gregory (Chicago Anthropology Exchange, 1995)
Keywords: community; internet; neo-pagan; religion; Virtual

An Ethnographic Method for the Study of Religion in Video Game Environments - Grieve, G.P. (Methods for Studying Video Games and Religion, 2017)
Focusing on the practice of Buddhism in Second Life, this chapter describes an ethnographic method for the study of religion in video game environments. Gregory Price Grieve argues that if one takes into consideration the narrative imagining of role-play, then Second Life can be considered a game and that its religion practice is authentic because its game play engages with what its users perceive as sacred. He then goes on to outline an ethnographic method based on the field of virtual game spaces, the methodological tool of participant observation, and the analytic instrument of thick description, as well as briefly touching on ethics. Finally, Gregory Price Grieve illustrates a case study by examining Second Life Zen Buddhist objects, places, avatars, groups, and events, as well as touching on the life cycle of the research project described.
Keywords: Ethnography; religion; video games

Digital Zen: Buddhism, Virtual Worlds and Online Meditation - Grieve, Gregory (Religion, Media and Culture, 2013)
Because it makes its practitioners mindful of desire, _Digital Zen_ argues that the primarily Western converts who practice Anglo-Buddhist digital religion offer a form of religion that allows them to flourish in a late capitalistic society. Much contemporary popular religion is a protest against, and also a product of, the suffering produced by the desires of living in late capitalism. Being mindful of desire is crucial for human flourishing in late capitalism, because while “solid” modernity was driven by need and production, the current “liquid” system is driven by desire and consumption. Digital Buddhism is an apt place to locate such desires because freed from the physical, digital media display the unhindered imagination of its users, and Buddhism, throughout its historical phases, has seen desire as the cause of suffering.
Keywords: Buddhism; Digital; Ethnography; Meditation; Second Life; Virtual World; Zen

There is no Spoon? The Matrix, Ideology, and The Spiritual logic of Late Capital - Grieve, Gregory (Teaching Religion and Film, 2009)
Keywords: Ideology; religion; spiritual

Studying Religion in Digital Gaming: A Critical Review of an Emerging Field - Grieve, G. P; Campbell, H (Heidelberg Journal of Religions on the Internet, 2014)
This article provides an overview of the study of religion and gaming by outlining the dominant approaches, development and themes in this new interdisciplinary field of inquiry. It highlights dominant thematic and methodological approaches currently within the field of religion and digital games studies including the study of religiously-themed games, the role religion plays in mainstream games, and how gaming can be seen as a form of “implicit religion". This critical review is contextualized in relation to the studies presented in a forthcoming book, Playing with Religion in Digital Games, which maps key theoretical approaches and interpretive trends related to how different expressions of religion and religiosity are manifested in various gaming genres and narratives. We show that digital games are an important site of exploration into the intersection of religion and contemporary culture helping us understand what religion is, does, and means in a changing contemporary society.
Keywords: digital games; game studies; Implicit religion; Narrative; play; video games

The Goddess Net. In Religion Online: Finding Faith on the Internet - Griffin, Wendy (Religion Online: Finding Faith on the Internet, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression. Religion Online provides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes the Pew Internet and American Life ProjectExecutiveSummary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-defining Cyberspace as SacredSpace.
Keywords: Faith; internet; Online; religion

Authority, power, influence and social control: A theoretical synthesis. Academy of Management Review - Grimes, A.J. (Academy of Management Review, 1978)
Authority and power are usually not conceptually distinct, but for clarification, they are considered extremes on a control continuum. Power is conceptualized as influence and social control, the former reducing and latter reinforcing authority. These constructs permit reexamination of authority and leadership.

The Soul in Cyberspace - Groothuis, Douglas (Hourglass Books/Baker Books, 1997)
This book evaluates the emerging technologies of cyberspace in relation to their effects on our society and souls, and deals especially with the potential pitfall of becoming informationally rich but spiritually deprived.
Keywords: cyberspace; information; Soul; spiritual deprivation

The Cyberchurch is Coming. National Survey of Teenagers shows Expectation of Substituting Internet for Corner Church - Barna Research Group (Barna Research Online, 1998)
Keywords: Church; Cyberchurch; internet; teenagers

More Americans Are Seeking Net-Based Faith Experiences - Barna Research Group (Barna Research Online, 2001)
You can buy books on the Internet, strike up relationships on the Internet and a growing proportion of the population are experiencing God in cyberspace, as well. A new study released by the Barna Research Group, of Ventura, California, indicates that among the growing number of Americans who use the Internet, millions are turning to the digital dimension to get them in touch with God and others who pursue faith matters. The report projects that within this decade as many as 50 million individuals may rely solely upon the Internet to provide all of their faith-based experiences. Among the findings of the studies described in the report is that born again and evangelical Christians are every bit as likely as non-Christians to use the digital superhighway. Catholics and mainline Protestants are slightly more likely to use the Internet than are Baptists and Protestants who attend non-mainline churches. Adults who are affiliated with a faith group other than Christianity have one of the highest concentrations of Net usage (85%). Adults use the Internet for a wide variety of activities, regardless of their faith commitments. The most universal value of the Internet is to find information, but other common uses include maintaining existing relationships, buying products, and previewing new media.
Keywords: Americans; Faith; internet

Discovering the Digital Authority: Twitter as Reporting Tool for Papal Activities - Guzek, Damian (Online - Heidelberg Journal for Religions on the Internet, 2015)
This article focuses on Pope Francis activities on Twitter and understanding the way of using this kind of social media by religious authorities. By examining Francis’s tweets from half a year of his pontificate (from September 13, 2013 to March 16, 2014), the author offers an in-depth overview of methods for studying the presence of religious authority in the digital world. In fact, he faces both the rapidly growing Heidi Campbell’s Religious Social-Shaping of Technology analytic frame and the grounded theory approach. Conducting the research the author shows that Pope Francis’s Twitter can be treated as a good example of ‘religion online’ based on specific strategy to extend religious authority from the real to the virtual world.

Interview with Rosalind I. J. Hackett on religion and digital media trends in Africa - Hackett, Rosalind I. J; Madore, F; Millet-Mouity, P (Émulations. Revue de sciences sociales, 2017)
On October 21st, 2017, the editors of this special issue conducted an interview with Rosalind I. J. Hackett, one of the pioneering scholars in the field of media and religion in Africa. The interview took place via Skype and consisted of five questions on the study of religion and digital media in the African context.
Keywords: Africa; digital media; religion

Religion and the Internet - Rosalind I. J. Hackett (Diogenes, 2006)
Emergent scholarship on the most radical technological invention of our time confirms what most of us know from first-hand experience – that the internet has fundamentally altered our perceptions and our knowledge, as well as our sense of subjectivity, community and agency (see for example Vries, 2002: 19). The American scholar of religion and communications, Stephen O’Leary, one of the first scholars to analyze the role of the new media for religious communities, claims that the advent of the internet has been as revolutionary for religious growth and dissemination as was the invention of the printing press (O’Leary, 1996). In the present essay, I consider the transformations of both religion, and by extension scholarship on religion, occasioned by computer-mediated communication (CMC) and information. I lay out a basic framework for analyzing the multifunctionality of the internet with regard to religion. I also briefly address the multidisciplinarity required to comprehend this multi-dimensional technological revolution. My primary focus is religious uses (Lawrence, 2000), but some reference is also made to religious perceptions of this new medium. In my broader research, I am particularly interested in some of the latest forms of internet applications by religious individuals and organizations, and their consequence for inter-religious conflict or harmony in what sociologist Manuel Castells calls our ‘global network society’ (Castells, 1997; Hackett, 2003, 2005). The information technology revolution and the restructuring of late capitalist economies have generated this new form of society. But as to whether the internet is predominantly utopian or dystopian is hard to discern, conclusions may be determined by one’s own interests and vantage-point.
Keywords: internet; religion

Religion on the Internet: Research Prospects and Promises - Hadden, Jeffery; Cowan, Douglas (JAI Press/Elsevier Science, 2000)
Religion on the Internet is the first systematic inquiry into the nature, scope and content of religion in cyberspace. Contributors to this volume include leading social scientists engaged in systematic studies of how organizations and individuals are presenting religion on the Internet. Their combined efforts provide a conceptual mapping of religion in cyberspace at this moment. The individual papers and collective insights found in this volume add up to a valuable agenda of research that will enrich understanding of this new phenomenon. Among the contributors are the founders of three of the most important scholarly religion web sites on the Internet: American Religion Data Archive, Religious Tolerance, and Religious Movements Homepage. Religion and the Internet is essential reading for all who seek to understand how religion is being presented on the Internet and how this topic is likely to unfold in the years ahead.
Keywords: internet; religion; Research

THE CONSUMER JIHAD: BOYCOTT FATWAS AND NONVIOLENT RESISTANCE ON THE WORLD WIDE WEB - Leor Halevi (International Journal of Middle East Studies, 2012)
This article deals with the origins, development, and popularity of boycott fatwas. Born of the marriage of Islamic politics and Islamic economics in an age of digital communications, these fatwas targeted American, Israeli, and Danish commodities between 2000 and 2006. Muftis representing both mainstream and, surprisingly, radical tendencies argued that jihad can be accomplished through nonviolent consumer boycotts. Their argument marks a significant development in the history of jihad doctrine because boycotts, construed as jihadi acts, do not belong to the commonplace categories of jihad as a “military” or a “spiritual” struggle. The article also demonstrates that boycott fatwas emerged, to a large degree, from below. New media, in particular interconnected computer networks, made it easier for laypersons to drive the juridical discourse. They did so before September 11 as well as, more insistently, afterward. Their consumer jihad had some economic impact on targeted multinationals, and it provoked corporate reactions.
Keywords: fatwa online; internet and religion; Islam; jihad

Network Sociality and Religion in the Digital Age - Halprin, E (Queen’s University Kingston)
The study of religion through a community-building paradigm has dominated sociology of religion, but does not account for changes to sociality and social spaces in the digital era which have influenced the ways individuals express their religiosity. A network sociality paradigm better explains increasingly personal and individualised approaches to religiosity in a contemporary social setting because of the de-hierarchized nature of computer mediated communication. Approaching religion, and digital religion through the lens of mediatised network sociality reveals the development of new groups and identities using the internet as an accessible translocal socio-cultural space.
Keywords: digital age; religion; sociality

Mediated Martyrs of the Arab Spring: New Media, Civil Religion, and Narrative in Tunisia and Egypt - Jeffry R. Halverson; Scott W. Ruston; Angela Trethewey (Journal of Communication, 2013)
This article analyzes the emergence of nationalist martyr narratives and their dissemination via new media as forces for social mobilization and political change. Situating them in the religio-historical contexts of North Africa, we trace martyr narratives in Tunisia and Egypt back to pre-Islamic periods and compare them to the contemporary stories of Mohamed Bouazizi and Khaled Saeed. This reveals the impact of new media on the region, evident in “virtual reliquaries,” and the role that martyr narratives play as catalysts in social mobilization. The trajectory of the martyr narrative from the traditional religious context to the state-driven concept of civil religion allows for the political dimension of narratives resident within the religious context to surface in the contemporary discursive moment.
Keywords: Civil Religion; Egypt; martyr narratives; Narrative; New Media; political change; Tunisia; virtual reliquaries

Mediated Martyrs of the Arab Spring: New Media, Civil Religion, and Narrative in Tunisia and Egypt - Jeffry R. Halverson; Scott W. Ruston; Angela Trethewey (Journal of Communication, 2013)
This article analyzes the emergence of nationalist martyr narratives and their dissemination via new media as forces for social mobilization and political change. Situating them in the religio-historical contexts of North Africa, we trace martyr narratives in Tunisia and Egypt back to pre-Islamic periods and compare them to the contemporary stories of Mohamed Bouazizi and Khaled Saeed. This reveals the impact of new media on the region, evident in “virtual reliquaries,” and the role that martyr narratives play as catalysts in social mobilization. The trajectory of the martyr narrative from the traditional religious context to the state-driven concept of civil religion allows for the political dimension of narratives resident within the religious context to surface in the contemporary discursive moment.
Keywords: Arab Spring; Civil Religion; Contemporary Religious Community; Mediated Martyrs; Narrative; network; New Media and Society; new media engagement; New Technology and Society; online communication

The Dot On the I In History: Of Gentiles and Jews—a Hebrew Odyssey Scrolling the Internet - Hammer, M.B (Lulu Press, 2017)
The inspiration author Michael B. Hammer received when speaking with others about the Israeli-Palestinian problem led to The Dot on the I in History: On Gentiles and Jews—Scrolling the Internet with the goal of helping others better understand the problem. When the issues involve intertribal, interracial, interreligious, and international human relationships lasting over several generations, they often become so complex one does not see the forest for trees, unless one knows where and when the seeds were planted. That is what history is all about. This book aspires to explain what Judaism, Christianity, and Islam have in common, how they differ, and how they have evolved. You’ll also learn how the Internet has affected and changed those involved in the Middle East conflict. With this information, you will have a better understanding of the real reasons for such world-changing events as what took place on 9/11.
Keywords: Hebrew; internet; Jews

thelordismyshepherd.com: Seeking God in Cyberspace - Hammerman, Joshua (Simcha Press., 2000)
thelordismyshepherd.com opens a new and necessary dialogue on the soul of cyberspace. It will change the way people think about their computers, about God, about the future and about the interconnected destiny of humanity in this ever-shrinking world. The author, a noted rabbi and journalist, alternates between analytic and experiential approaches to the subject, escorting the reader on a multi-dimensional quest for spiritual and intellectual growth - a "virtual pilgrimage" if you will. A pilgrimage that travels tens of thousands of miles in a matters of instants, from Jerusalem to Mecca, to Chartres, even to Kosovo, and provides a new means of utilizing the vast power of technology to connect us to God and to transcend the artificial boundaries that separate us.
Keywords: cyberspace; God; Seeking

Technologies of Religion: Spheres of the Sacred in a Post-secular Modernity - Han, Sam (Routledge, 2016)
Bringing together empirical cultural and media studies of religion and critical social theory, Technologies of Religion: Spheres of the sacred in a post-secular modernity investigates powerful entanglement of religion and new media technologies taking place today, taking stock of the repercussions of digital technology and culture on various aspects of religious life and contemporary culture more broadly. Making the argument that religion and new media technologies come together to create "spheres"—environments produced by an architecture of digital technologies of all sorts, from projection screens to social networking sites, the book suggests that prior social scientific conceptions of religious worship, participation, community and membership are being recast. Using the case of the strain of American Christianity called "multi-site," an emergent and growing church-model that has begun to win favor largely among Protestants in the last decade, the book details and examines the way in which this new mode of religiosity bridges the realms of the technological and the physical. Lastly, the book situates and contextualizes these developments within the larger theoretical concerns regarding the place of religion in contemporary capitalism. Technologies of Religion: Spheres of the sacred in a post-secular modernity offers an important contribution to the study of religion, media, technology and culture in a post-secular world.

Wear White: The mediatized politics of religious anti-LGBT activism in Singapore - Han, Samuel (Nordic journal of religion and society, 2018)
As a result of the perceived rise in LGBT visibility and acceptance in Singapore, a social media campaign started in 2014 called Wear White, which brought together both Muslim and Christian participants to counter the annual Pink Dot rally. This is Singapore's version of (gay) pride parades, which are held in major cities all across the world. This article aims to analyze this religious backlash against LGBT, paying attention to its “media logic,” a term borrowed from the “mediatization” literature, and presenting it as a framework to understand the politicization of religion in the context of the Singapore state. It asks: (1) What sorts of intellectual arguments and aesthetic techniques are deployed in Wear White's media discourse? (2) How does Wear White's media discourse balance its anti-LGBT message within the secular(ist) context of Singapore? (3) How does social media affect Wear White's message in its attempt to bring it to a larger audience? To this end, the article engages in a critical assessment of Wear White's media discourse of the campaign, including video logs (vlogs) and social media posts.

Disenchantment revisited: Formations of the ‘secular’ and ‘religious’ in the technological discourse of modernity - Han, Sam (Social Compass, 2015)
This article problematizes sociologist Max Weber’s famed notion of ‘disenchantment’ in order to explore the ways in which ‘technology’ and ‘religion’ operate in the discourse of ‘secular modernity’. It suggests that disenchantment is not simply epistemological, that is, synonymous with rationalization and intellectualization, but also ontological, and a description of the overhauling of what Bruno Latour calls the ‘modernist settlement’. It proceeds in following manner: (1) it presents an ‘interpretive genealogy’ of technological rationality in discourses about modernity, demonstrating an internal conflict, especially in how ‘religion’, ‘the secular,’ and ‘technology’ are conceptualized. It posits that the lack of consistency in the invocation of these terms is a symptom of a deeper unresolved ontological (or, onto-cosmological) tension. (2) After establishing this ontological aporia, the article proceeds to offer a rereading of Weber’s original concept of disenchantment. (3) Finally, the author teases out some of the implications of reading disenchantment ontologically for the understanding of religion and technology.

Bible Reading and Critical Thinking - Hardmier, Chris (Critical Thinking and the Bible in the Age of New Media, 2004)
In Critical Thinking and the Bible in the Age of New Media, Charles Ess collects contemporary scholarship to address the question: What does critical thinking about the Bible mean as the Bible is _transmediated_ from print to electronic formats? This volume, the first of its kind, is made up of contributions originally developed for a conference sponsored by the American Bible Society. Ess provides a collection grounded in a wide diversity of religious traditions and academic disciplines--philosophy, biblical studies, theology, feminism, aesthetics, communication theory, and media studies. His introduction summarizes the individual chapters and develops their broader significance for contemporary debates regarding media, postmodernism, and the possible relationships between faith and reason.
Keywords: Bible; Critical thinking; postmodernism

The representation of Islam within social media: a systematic review - Hashmi, Umair Munir; Rashid, Radzuwan Ab; Ahmad, Mohd Kamil (Information, Communication & Society, 2020)
This systematic review was carried out to provide insights into how Islam has been represented in social media; and the omissions and gaps in the synthesized literature on the topic. Two databases – Scopus and the Web of Science – were explored to collect data. Primary searches between 2010 and 2019, revealed more than 100 studies dealing with the topic of investigation. After scrutinizing abstracts and removing duplicates, 36 studies came within the research criteria and were retained for analysis. A thematic analysis was conducted for the derivation of themes. The themes that emerged were: (1) Islam as a liberal religion; (2) Islam as a religion of extremism and terrorism; (3) Islam as religion of gender discrimination; (4) Islam as a religion of collective identity; and (5) Islam as a humane religion. Although the representation of Islam in social media is wide-ranging, more empirical studies found that social media users represent Islam negatively than studies which revealed positive view of Islam by social media users.

IMPACT OF INTERNET OF THINGS ON DEVELOPMENT OF MUSLIMS - Hassan, A.M; Ripin, M.N; Haron, Z; Mohd Nor, N. H; Hehsan, A; Tahir, N; Dahlan, A. D (Al-Qanatir: International Journal of Islamic Studies, 2018)
The Internet of Things (IoT) is a modern technology that is expected to bring significant impact in the information technology world. IoT generally refers to all electronic devices communicating through the internet. IoT is expected to transform existing modern technology from smartphones to smart environments such as smart watches for health monitoring, smart electricity grid, smart cars and drones for agricultural automation and monitoring of progress at construction sites. IoT technology is expected to mature in 2020 where at that time 33 billion devices will connect and generate 40 Zetabyte data. The development of this IoT promotes active life routines as well as scraping the normal life of the Muslim ummah gradually. In addition to this great technology, it is worrying of the extent to which the preparation and readiness of Muslims to accept the presence of IoT in their daily activities. Hence, this paper will discuss on the preparation and effects of IoT's presence in the development of Islam in all aspects such as social, humanitarian and economics based on scientific materials and reliable source of reference. Methodology used was mixed method; quantitatively and qualitatively. First phase was conducted by collecting data from questionnaire which involved 30 respondents in Faculty of Electrical Engineering UTM. Qualitative data collected in second phase using document analysis, where the data was collected from books and journal articles. The result of this paper is expected to help and provide reference for Muslims to meet this great technology and be prepared with the great impact of this IoT in the daily lives of Muslims.
Keywords: Internet of Things; Modern Technology; Muslim World

Ultima IV: Simulating the Religious Quest - Mark Hayse (Halos and Avatars: Playing Video Games With God, 2010)
Keywords: Britannia; messianic figure; quest; religion; religious games; religious video games; Spirituality; Ultima; video games

Searching for Integrity: The Politics of Mindfulness in the Digital Economy - Healey, Kevin (Nomos Journal, 2013)
This essay examines the adaptation of meditation, yoga, and other “mindfulness” techniques by digital media companies like Google, Apple, and Facebook. This adaptation is ironic, considering that many critics and scholars suggest that the products and services offered by these companies undermine the achievement of mindfulness. In fact, some critics call for mindfulness training specifically to counter-act the cognitive impacts of smartphones, social media, and personalized search engines. I argue that we should understand this irony as an outgrowth of the process of externalization in market capitalism. In this case, Silicon Valley companies create “integrity bubbles” that allow employees and executives to reap the benefits of mindfulness, while externalizing the problems of distraction and fragmentation. The resolution of this tension would mean the reconfiguration of the digital economy as we know it, in the spirit of “digital humanism.” This goal requires a more holistic approach to the politics of mindfulness that examines both personal and civic mindfulness, the latter of which includes a contemplative approach to critical media studies and the revitalization of journalism as a public good.
Keywords: contemplative media studies; Edward Snowden; Google; integrity; journalism; mindfulness

Exploring the religious frameworks of the digital realm: Offline-Online-Offline transfers of ritual performance - Heidbrink , S (Masaryk University Journal of Law and Technology, 2007)
Looking at the constantly growing field of religion online, the shifts in and the new definition of religious frameworks become an increasingly important topic. In the field of religious rituals, it is not only the participant, location and conduction of the ritual that is affected by this shift; also the researchers have to overthrow their former theologically resp. systemic based definition of religiousness and spirituality due to the fact that on the Internet, religion is defined and realized in a completely different way by its participants. This is true even in the field of Christianity as the example of a ritual created by some British „Emerging Church“ groups shows. These loosely defined groups which span all denominational borders of the Christian spectrum have been established since the late 1980s mainly in the UK in order to organize church services they refer to as „Alternative Worship“. The Internet plays an important role as a platform of communication and (self-)organization of the members and as technically and aesthetically challenging means of (re)presentation. Some events that were conducted in real life, like the multimedia labyrinth installation in St Paul`s cathedral in 2000, have even been „reconstructed“ in virtual space , generating a new form of worship. Interestingly but not unexpectedly, these transfer processes entail consequences for spirituality in real life. What exactly happens during the transfer into the digital realm? What are the interdependencies between offline and online and how do they affect worship and worshippers? These questions will be followed, employing the results and ideas of modern Ritual and Religious Studies, sheding light on a new field of (post)modern Christianity.
Keywords: Communication; information; methodology; Ritual; study of religion; technology

Performing Rituals in Virtual Worlds – A Contested Field - Heidbrink , S; Radde-Antweiler, K.; Miczek, N (RItual, Media, and Conflict, 2011)
Rituals can provoke or escalate conflict, but they can also mediate it and although conflict is a normal aspect of human life, mass media technologies are changing the dynamics of conflict and shaping strategies for deploying rituals. This collection of essays emerged from a two-year project based on collaboration between the Faculty of Religious Studies at Radboud University Nijmegen in the Netherlands and the Ritual Dynamics Collaborative Research Center at the University of Heidelberg in Germany. An interdisciplinary team of twenty-four scholars locates, describes, and explores cases in which media-driven rituals or ritually saturated media instigate, disseminate, or escalate conflict. Each multi-authored chapter is built around global and local examples of ritualized, mediatized conflict. The book's central question is: "When ritual and media interact (either by the mediatizing of ritual or by the ritualizing of media), how do the patterns of conflict change?"
Keywords: ritualized media; Rituals; Virtual

Popular religion and the internet. a match made in (cyber)heaven - Helland, C (Religion Online: Finding Faith on the Internet, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression. Religion Online provides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes the Pew Internet and American Life Project Executive Summary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-defining Cyberspace as Sacred Space

Surfing for Salvation - Helland, Christopher (Religion, 2002)
I demonstrate that despite the enormous amount of religion on the Internet, a general classification can be developed based upon the religious participation occurring at the various websites. I recognise these classifications as ‘religion-online’ and ‘online-religion’. Religion-online presents information about religion. It is a controlled environment. The site has been structured to limit participation. In contrast, online-religion provides an interactive religious environment for the web practitioner. Because of this difference, individuals and organisations have different perceptions concerning how the Internet should be used for religious purposes. In many cases there is an active form of religious participation occurring. Rituals are conducted, prayers are posted and even communion is carried out on this medium. In other situations the Internet presents material concerning religion to a passively receptive audience. Despite these levels of control, the web surfer is exposed to an enormous number of belief systems and also varying levels of online religious participation.
Keywords: Classification; Participation; Perception; Purpose; religion online

Online religion as Lived Religion: Methodological Issues in the Study of Religious Participation on the Internet - Helland, Christopher (Online-Heidelberg Journal of Religions on the Internet, 2005)
In his article Christopher Helland proposes a more comprehensive framework for his theoretical distinction for online religion and religion online. When he developed this typology in 1999, Helland recognized a clear distinction between religious Web sites where people could act with unrestricted freedom and a high level of interactivity (online religion) versus the majority of religious Web sites, which seemed to provide only religious information and no interaction (religion online). He now advances the religion online / online religion framework by drawing from the ongoing critique of his earlier work. He concludes that many religious Web sites today provide both information and an area where this information can be lived and communicated. This occurs on the Internet where Web sites try to incorporate both an information zone and interaction zone in a single site or, more commonly, where popular unofficial Web sites provide the area for online religion, while the official religious Web site supplies religion online. In cases where institutional religious organizations do not support online religion he assumes that it may be due to their perception of the Internet as a tool for communicating rather than an extension of our social world.
Keywords: internet; Online; Participation; religion

Online religion as Lived Religion: Methodological Issues in the Study of Religious Participation on the Internet - Helland, Christopher (Online-Heidelberg Journal of Religions on the Internet, 2005)
In his article Christopher Helland proposes a more comprehensive framework for his theoretical distinction for online religion and religion online. When he developed this typology in 1999, Helland recognized a clear distinction between religious Web sites where people could act with unrestricted freedom and a high level of interactivity (online religion) versus the majority of religious Web sites, which seemed to provide only religious information and no interaction (religion online). He now advances the religion online / online religion framework by drawing from the ongoing critique of his earlier work. He concludes that many religious Web sites today provide both information and an area where this information can be lived and communicated. This occurs on the Internet where Web sites try to incorporate both an information zone and interaction zone in a single site or, more commonly, where popular unofficial Web sites provide the area for online religion, while the official religious Web site supplies religion online. In cases where institutional religious organizations do not support online religion he assumes that it may be due to their perception of the Internet as a tool for communicating rather than an extension of our social world.
Keywords: internet; Online; Participation; religion

Canadian Religious Diversity Online: A Network of Possibilities - Helland, Christopher (Religion and Diversity in Canada, 2008)
Canada officially prides itself on being a multicultural nation, welcoming people from all around the world, and enshrining that status in its Charter of Rights and Freedoms as well as in an array of laws and policies that aim to protect citizens from discrimination on various grounds, including race, cultural origin, sexual orientation, and religion. This volume explores the intersection of these diversities, foregrounding religion as the primary focus of analysis. Taking as their point of departure the contested meaning and implications of the term diversity, the various contributions address issues such as the power relations that diversity implies, the cultural context that limits the understanding and practical acceptance of religious diversity, and how Canada compares in these matters to other countries. Taken together the essays therefore elucidate the Canadian case while also having relevance for understanding this critical issue globally.
Keywords: Canada; culture; diversity; religion

Online religion as Lived Religion: Methodological Issues in the Study of Religious Participation on the Internet - Helland, Christopher (Online-Heidelberg Journal of Religions on the Internet, 2005)
In his article Christopher Helland proposes a more comprehensive framework for his theoretical distinction for online religion and religion online. When he developed this typology in 1999, Helland recognized a clear distinction between religious Web sites where people could act with unrestricted freedom and a high level of interactivity (online religion) versus the majority of religious Web sites, which seemed to provide only religious information and no interaction (religion online). He now advances the religion online / online religion framework by drawing from the ongoing critique of his earlier work. He concludes that many religious Web sites today provide both information and an area where this information can be lived and communicated. This occurs on the Internet where Web sites try to incorporate both an information zone and interaction zone in a single site or, more commonly, where popular unofficial Web sites provide the area for online religion, while the official religious Web site supplies religion online. In cases where institutional religious organizations do not support online religion he assumes that it may be due to their perception of the Internet as a tool for communicating rather than an extension of our social world.
Keywords: internet; Online; Participation; religion

Diaspora on the electronic frontier: Developing virtual connections with sacred homelands - Helland, Christopher (Journal of Computer-Mediated Communication, 2007)
This study demonstrates how diaspora religious traditions utilized the Internet to develop significant network connections among each other and also to their place of origins. By examining the early Usenet system, I argue that the religious beliefs and practices of diaspora religious traditions were a motivating factor for developing Usenet groups where geographically dispersed individuals could connect with each other in safe, supportive, and religiously tolerant environments. This article explores the new forms of religious practices that began to occur on these sites, focusing on the manner in which Internet technology and the World Wide Web were utilized for activities such as long-distance ritual practice, cyber pilgrimage, and other religiously-motivated undertakings. Through these new online religious activities, diaspora groups have been able to develop significant connections not only among people, but also between people and the sacred homeland itself.
Keywords: electronic frontier; Online; Sacred; virtual communities

Online-Religion/Religion-Online and Virtual Communities - Helland, Christopher (Religion on the Internet: Research prospects and promises, 2000)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression. Religion Online provides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes the Pew Internet and American Life ProjectExecutiveSummary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-defining Cyberspace as SacredSpace.
Keywords: Online-religion; religion-online; virtual communities

Online religion as Lived Religion: Methodological Issues in the Study of Religious Participation on the Internet - Helland, Christopher (Online-Heidelberg Journal of Religions on the Internet, 2005)
In his article Christopher Helland proposes a more comprehensive framework for his theoretical distinction for online religion and religion online. When he developed this typology in 1999, Helland recognized a clear distinction between religious Web sites where people could act with unrestricted freedom and a high level of interactivity (online religion) versus the majority of religious Web sites, which seemed to provide only religious information and no interaction (religion online). He now advances the religion online / online religion framework by drawing from the ongoing critique of his earlier work. He concludes that many religious Web sites today provide both information and an area where this information can be lived and communicated. This occurs on the Internet where Web sites try to incorporate both an information zone and interaction zone in a single site or, more commonly, where popular unofficial Web sites provide the area for online religion, while the official religious Web site supplies religion online. In cases where institutional religious organizations do not support online religion he assumes that it may be due to their perception of the Internet as a tool for communicating rather than an extension of our social world.
Keywords: internet; Online; Participation; religion

Game Cultures as Sub-Creations. Case Studies on Religion & Digital Play - Hemminger, Elke (Online - Heidelberg Journal of Religions on the Internet, 2014)
As online and ofﬂine spaces, digital and analogue worlds merge into each other and saturate our everyday lives, concepts of reality and its social construction need re-thinking. Digital game cultures, formerly often regarded as not only separate from reality, but also secondary in their importance for ,real lifeʻ, can give us insight into processes of cultural construction und re-construction, relevant for our mediatised society in general. This paper analyzes digital game cultures as sub-creations (Tolkien 1947) that are consistent, signiﬁcant and serve as comments on and additions to society. Focusing on religious elements in digital games, the paper states that game cultures reﬂect cultural practice in general and therefore contribute to the social construction of reality in essential ways. The paper is based on the results of several case studies on digital games during which a system to categorize digital games concerning the way they use religious elements was developed, going beyond existing game categories. The paper will introduce these classiﬁcations in order to support the assumption that religion in games can be seen not only as a key element in game cultures, but also as a reﬂection of social attitude towards and social status of religion in a wider prospect. Following this assumption, the paper will show how the analysis of digital games and their religious contents can help us observe and understand processes of social reality construction that might not be accessible or visible in other social contexts.

The Future of ARIL in the Information Age - Henderson, Charles. H (Cross Currents, 1996)

New Religions and the Internet: Recruiting In A New Public Sphere - Hennerby, Jennifer; Dawson, Lorne (Journal of Contemporary Religions, 1999)
The mass suicide of 39 members of Heaven's Gate in March of 1997 led to public fears about the presence of 'spiritual predators' on the world wide web. This paper describes and examines the nature of these fears, as reported in the media. It then sets these fears against what we know about the use of the Internet by new religions, about who joins new religious movements and why, and the social profile of Internet users. It is argued that the emergence of the Internet has yet to significantly change the nature of religious recruitment in contemporary society. The Internet as a medium of communi- cation, however, may be having other largely unanticipated effects on the form and functioning of religion, both old and new, in the future. Some of the potential perils of the Internet are discussed with reference to the impact of this new medium on questions of religious freedom, community, social pluralism, and social control.

Digital Traces in Context - An Introduction - Hepp, A; Breiter, A; Friemel, T (International Journal of Communication, 2018)
A consequence of living in a media-saturated world is that we inevitably leave behind digital traces of our media use. In this introduction to the International Journal of Communication’s thematic section, we argue for a need to put those digital traces in context. As a starting point, we outline our basic understanding of digital traces, generally defining them as numerically produced correlations of disparate kinds of data that are generated by our practices in a media environment characterized by digitalization. On this basis, we distinguish three contextual facets that are of relevance when considering digital traces: first, the context of the scientific discourse in which research on digital traces is positioned; second, the context of the methods being applied to researching them; and third, the aforementioned context of the empirical field. With reference to the articles in this thematic section, this introduction argues that, in a single study, all three contextual facets interact as the scientific discourse relates to the methods being used, which in turn relates to the entire field of research.
Keywords: big data; contextualization; datafication; deep mediatization; digital methods; digital traces

Rethinking Transforming Communications: An Introduction - Hepp, A; Breiter, A; Hasebrink, U (Communicative Figurations, 2018)
This chapter introduces the contributions to this volume in three stages. First, it is argued that when considering the present stage of deep mediatization, it is insufficient to concentrate solely on the media as such: one also has to consider how communication transforms with changing media. It is by virtue of the change in human communicative practices together with other social practices that processes of social construction change. This is what is called transforming communications. Second, the chapter outlines why it is helpful to take a figurational approach for researching such transforming communications. The term figuration goes back to Norbert Elias, who used it to describe structured interrelations between humans. However, for the analysis in question, it is extended to reflect questions of communication. Finally, this introduction provides an overview of the arguments presented in the following chapters.
Keywords: Communication; mediatization

Theorizing religion and media in contemporary societies: An account of religious ‘publicization’ - Herbert, David E. J. (European Journal of Cultural Studies, 2011)
This article argues that a combination of the rapid development and dissemination of media technologies, the liberalization of national media economies and the growth of transnational media spheres is transforming the relationship between religion, popular culture and politics in contemporary societies in ways not adequately accounted for in existing sociological theories of religion (secularization, neo-secularization and rational choice) and still largely neglected in sociological theories of media and culture. In particular, it points to a series of media enabled social processes (de-differentiation, diasporic intensification and re-enchantment) which mirror and counter processes identified with the declining social significance of religion in secularization theory (differentiation, societalization and rationalization), interrupting their secularizing effects and tending to increase the public presence or distribution of religious symbols and discourses, a process described as religious ‘publicization’. These processes have implications for religious authority, which is reconfigured in a more distributed form but not necessarily diminished, contrary to neo-secularization theory. Furthermore, contrary to rational choice theory, the increased public presence of religion depends not only on competition between religious ‘suppliers’, but also on the work done by religions beyond the narrow religious sphere ascribed by secular modernity to religion, in supposedly secular spheres such as entertainment, politics, law, health and welfare and hence has implications for the relationship between politics and popular culture central to cultural studies.
Keywords: media change

Virtual as Contextual: A Net news theology - Herring, Debbie (Religion and Cyberspace, 2004)
In the twenty-first century, religious life is increasingly moving from churches, mosques and temples onto the Internet. Today, anyone can go online and seek a new form of religious expression without ever encountering a physical place of worship, or an ordained teacher or priest. The digital age offers virtual worship, cyber-prayers and talk-boards for all of the major world faiths, as well as for pagan organisations and new religious movements. It also abounds with misinformation, religious bigotry and information terrorism. Scholars of religion need to understand the emerging forum that the web offers to religion, and the kinds of religious and social interaction that it enables. Religion and Cyberspace explores how religious individuals and groups are responding to the opportunities and challenges that cyberspace brings. It asks how religious experience is generated and enacted online, and how faith is shaped by factors such as limitless choice, lack of religious authority, and the conflict between recognised and non-recognised forms of worship. Combining case studies with the latest theory, its twelve chapters examine topics including the history of online worship, virtuality versus reality in cyberspace, religious conflict in digital contexts, and the construction of religious identity online. Focusing on key themes in this groundbreaking area, it is an ideal introduction to the fascinating questions that religion on the Internet presents.

What Scripture Tells me: Spontaneity and Regulation within the Catholic Charismatic Renewal - Hervieu-Leger, D (Lived Religion in America: Toward a History of Practice, 1997)
Keywords: Catholic; Charismatic Renewal; Christianity; Lived religion; religious participation

Cyberpilgrimage: The (Virtual) Reality of Online Pilgrimage Experience - Hill-Smith, C (Religion Compass, 2011)
Cyberpilgrimage is the practice of undertaking pilgrimage on the internet. Such pilgrimages may be performed for a host of reasons, ranging from idle curiosity to the need to ready oneself, psychologically or informationally, for a ‘real’ (terrestrial) pilgrimage. For some web-users, these experiences may amount to little more than interesting diversions, mildly intriguing ripples in a sea of information and possibility, to be paused upon and pondered briefly before surfing onward to other things. Depending on individual motivations and circumstances, however, they can be deeply charged, transformative, enlightening and profoundly fulfilling on both emotional and spiritual levels. As new as the internet is, cyberpilgrimage is newer; and it seems clear we are witnessing the birth of one of a number of largely uncharted ways by which people are beginning to experience themselves spiritually on the internet. Such experiences tend to be perceived as more self-mediated and, thus, more individualised, liberated and radical than terrestrial experiences of a similar sort (though this is not necessarily the case). This article is intended to explain what cyberpilgrimage can entail, to survey the input to-date of contemporary scholars to the study of cyberpilgrimage; and to offer insight into some of the major debates and questions it raises, in particular with regard to the authenticity of computer-based ‘experience’.
Keywords: Online; pilgrimage; Ritual

Cyberpilgrimage: A Study of Authenticity, Presence and Meaning in Online Pilgrimage Experiences - Connie Hill-Smith (Journal of Religion and Popular Culture, 2009)
The idea of cyberpilgrimage may be met with scepticism. There may be a sense that pilgrimage via the Internet intrinsically cannot be authentic, that without any physical depth, it can only be an affectation, even a caricature, of “proper” (terrestrial) pilgrimage. This “authenticity issue” is crucial, and failure to address it will undermine academic attempts at its study, even while Internet religion becomes increasingly central to understanding contemporary religious expression. This article explores various aspects of the new phenomenon of cyberpilgrimage, framed by a discussion of the potential authenticity of cyberpilgrimage.

Flickering Pixels: How Technology Shapes Your Faith - Hipps, Shane (Zondervan, 2009)
Flickering pixels are the tiny dots of light that make up the screens of life---from TVs to cell phones. They are nearly invisible, but they change us. In this provocative book, author Shane Hipps takes readers beneath the surface of things to see how the technologies we use end up using us. Not all is dire, however, as Hipps shows us that hidden things have far less power to shape us when they aren't hidden anymore. We are only puppets of our technology if we remain asleep. Flickering Pixels will wake us up---and nothing will look the same again.

EXPERIMENTS IN DEVOTION ONLINE: THE YOUTUBE KHUṬBA - Charles Hirschkind (International Journal of Middle East Studies, 2012)
This paper explores what I call “online experiments in ethical affect” through an analysis of one popular Islamic genre: the short video segments of Friday sermons (khuṭub, s. khuṭba) placed on the video-sharing website YouTube. In my discussion of this media form, I give particular attention to the kind of devotional discourse and ethical socius that is enacted online around these taped performances: notably, the practices of appending written comments to specific videos, offering responses to comments left by others or criticisms directed at either the preacher or other commentators, and the act of creating links between khuṭba pages and other web-based content. In examining these practices, I want to look at the way some of the norms of ethical and devotional comportment associated with the khuṭba in the mosque carry over to the Internet context of khuṭba listening/viewing while also engendering novel forms of pious interaction, argument, and listening.
Keywords: ethics; internet; Islam; Sermons; YouTube

The Logics of the Media and the Mediatized Conditions of Social Interaction - Hjarvard, S (Media Logic(s) Revisited, 2018)
The notion of ‘media logics’ is useful for understanding the processes of mediatization and the ways in which media come to influence communication and social interaction in various domains of society. Media logics are the combined technological, aesthetic, and institutional modus operandi of the media and logics may in a general sociological vocabulary be understood as the rules and resources that govern a particular institutional domain. Media logics do‚ however‚ rarely exert their influence in isolation. We need to consider the media’s influence on an aggregate level and not only at the level of the individual media and its particular logics. Mediatization involves cultural and social processes in which logics of both media and other institutions are interacting and adapting to each other and through these processes a particular configuration of logics are established within an institutional domain. Such configurations condition, but do not determine communication and social interaction. Within a particular institution such as politics or education‚ the available media repertoire inserts various dynamics to communication and social interaction‚ and these dynamics represent the mediatized conditions of communication and social interaction.
Keywords: media; mediatized; social interaction

The Mediatization of Culture and Society - Hjarvard, Stig (Routledge, 2013)
Mediatization has emerged as a key concept to reconsider old, yet fundamental questions about the role and influence of media in culture and society. In particular the theory of mediatization has proved fruitful for the analysis of how media spread to, become intertwined with, and influence other social institutions and cultural phenomena like politics, play and religion.

The mediatisation of religion: Theorising religion, media and social change - Hjarvard, Stig (Culture and Religion, 2011)
Drawing on recent advances in mediatisation theory, the article presents a theoretical framework for understanding the increased interplay between religion and media. The media have become an important, if not primary, source of information about religious issues, and religious information and experiences become moulded according to the demands of popular media genres. As a cultural and social environment, the media have taken over many of the cultural and social functions of the institutionalised religions and provide spiritual guidance, moral orientation, ritual passages and a sense of community and belonging. Furthermore, the article considers the relationship between mediatisation and secularisation at three levels: society, organisation and individual. At the level of society, mediatisation is an integral part of secularisation. At the level of organisation and the individual, mediatisation may both encourage secular practices and beliefs and invite religious imaginations typically of a more subjectivised nature.

Dimensionalizing cultures: The Hofstede model in context - Hofstede, G (Online Readings in Psychology and Culture, 2011)
This article describes briefly the Hofstede model of six dimensions of national cultures: Power Distance, Uncertainty Avoidance, Individualism/Collectivism, Masculinity/Femininity, Long/Short Term Orientation, and Indulgence/Restraint. It shows the conceptual and research efforts that preceded it and led up to it, and once it had become a paradigm for comparing cultures, research efforts that followed and built on it. The article stresses that dimensions depend on the level of aggregation; it describes the six entirely different dimensions found in the Hofstede et al. (2010) research into organizational cultures. It warns against confusion with value differences at the individual level. It concludes with a look ahead in what the study of dimensions of national cultures and the position of countries on them may still bring.

Cultures and Organizations: Software of the Mind - Geert Hofstede; Gert Jan Hofstede; Michael Minkov (McGraw-Hill Education, 2010)
The revolutionary study of how the place where we grew up shapes the way we think, feel, and act-- with new dimensions and perspectives Based on research conducted in more than seventy countries over a forty-year span, Cultures and Organizations examines what drives people apart—when cooperation is so clearly in everyone’s interest. With major new contributions from Michael Minkov’s analysis of data from the World Values Survey, as well as an account of the evolution of cultures by Gert Jan Hofstede, this revised and expanded edition: Reveals the “moral circles” from which national societies are built and the unexamined rules by which people think, feel, and act Explores how national cultures differ in the areas of inequality, assertiveness versus modesty, and tolerance for ambiguity Explains how organizational cultures differ from national cultures—and how they can be managed Analyzes stereotyping, differences in language, cultural roots of the 2008 economic crisis, and other intercultural dynamics

The Immanent Internet Redux - Bernie Hogan; Barry Wellman (Digital religion, social media and culture: Perspectives, Practices and Futures, 2012)
Keywords: cyber; distopia; fantasy; internet; Networked individualism; transcendence; utopia; Virtual

Religion and Cyberspace - Hojsgaard, Morten; Warburg, Margit (Routledge, 2005)
In the twenty-first century, religious life is increasingly moving from churches, mosques and temples onto the Internet. Today, anyone can go online and seek a new form of religious expression without ever encountering a physical place of worship, or an ordained teacher or priest. The digital age offers virtual worship, cyber-prayers and talk-boards for all of the major world faiths, as well as for pagan organisations and new religious movements. It also abounds with misinformation, religious bigotry and information terrorism. Scholars of religion need to understand the emerging forum that the web offers to religion, and the kinds of religious and social interaction that it enables. Religion and Cyberspace explores how religious individuals and groups are responding to the opportunities and challenges that cyberspace brings. It asks how religious experience is generated and enacted online, and how faith is shaped by factors such as limitless choice, lack of religious authority, and the conflict between recognised and non-recognised forms of worship. Combining case studies with the latest theory, its twelve chapters examine topics including the history of online worship, virtuality versus reality in cyberspace, religious conflict in digital contexts, and the construction of religious identity online. Focusing on key themes in this groundbreaking area, it is an ideal introduction to the fascinating questions that religion on the Internet presents.

Introduction: waves of research - Hojsgaard, Morten; Warburg, Margit (Religion and Cyberspace, 2005)
In the twenty-first century, religious life is increasingly moving from churches, mosques and temples onto the Internet. Today, anyone can go online and seek a new form of religious expression without ever encountering a physical place of worship, or an ordained teacher or priest. The digital age offers virtual worship, cyber-prayers and talk-boards for all of the major world faiths, as well as for pagan organisations and new religious movements. It also abounds with misinformation, religious bigotry and information terrorism. Scholars of religion need to understand the emerging forum that the web offers to religion, and the kinds of religious and social interaction that it enables. Religion and Cyberspace explores how religious individuals and groups are responding to the opportunities and challenges that cyberspace brings. It asks how religious experience is generated and enacted online, and how faith is shaped by factors such as limitless choice, lack of religious authority, and the conflict between recognised and non-recognised forms of worship. Combining case studies with the latest theory, its twelve chapters examine topics including the history of online worship, virtuality versus reality in cyberspace, religious conflict in digital contexts, and the construction of religious identity online. Focusing on key themes in this groundbreaking area, it is an ideal introduction to the fascinating questions that religion on the Internet presents.

Cyber Religion: On the Cutting Edge Between the Virtual and the Real - Hojsgaard, Morten (Religion and Cyberspace, 2005)

The Relationship Between Religiosity and Internet Use - Greg G. Armfield & R. Lance Holbert (Journal of Media and Religion, 2003)
With the solidifying of the Internet as an influential form of mediated communication has come a surge of activity among media scholars looking into what leads individuals to use this emerging technology. This study focuses on religiosity as a potential predictor of Internet activity, and uses a combination of secularization theory and uses and gratifications theory as a foundation from which to posit a negative relation between these 2 variables. Religiosity is found to retain a significant negative relation with Internet use at the zero order, and remains a robust negative predictor of the criterion variable even after accounting for a host of demographic, contextual, and situational variables. Ramifications for these findings are discussed and an outline for future research building on our analyses is provided.
Keywords: Computer; Contemporary Religious Community; cyberspace; internet; Mass media; network; New Media and Society; new media engagement; New Technology and Society; online communication; Online community; religion; religion and internet; Religion and the Internet; religiosity; religious engagement; religious identity; Religious Internet Communication; Religious Internet Communities; secularization theory; Sociology of religion; users’ participation; uses and gratifications; virtual community; virtual public sphere; “media research”; “religion online”; “religious media research”

New confession app is no substitution for the sacrament Vatican says - Holdren, A (). Catholic News Agency Online, 2011)

“@God please open your fridge!” A content analysis of Twitter messages to @God - Holmberg, K; Bastubacka, J.J.M; Thelwall, M (Journal of Religion, Media and Digital Culture, 2016)
This study investigates religious communication in social media by analyzing messages sent to God on Twitter. More specifically, the goal of this research is to map and analyze the various contexts in which God is addressed on Twitter, and how the tweets may reflect religious beliefs, ritual functions, and life issues. Using content analysis techniques and phenomenography, tweets addressing God were investigated. The results of this descriptive and indicative study show that religion and religiosity are communicated on Twitter in a manner that creates a unique sphere in which praise and profanities coexist. The tweets in the sample vary a great deal in their content and communicative function, ranging from profanities to prayers and from requests to win the lottery to conversations with and comments about God. Some tweets address God as a form of humour or satire, cursing, or otherwise without any deeper religious intention, while other tweets are apparently genuine messages directed to the transcendent, prayers, with which the senders want to show and share their belief with their followers on Twitter.
Keywords: Apps; digitial; God; Twitter

Mass Media Religion: The Social Sources of the Electronic Church - Hoover, Stewart (SAGE Publications, Incorporated, 1988)
Mass Media Religion considers and explores the implications of the evergrowing religious broadcasting media in terms of their social and political contexts. The author reviews both the historical origins of fundamentalist and neo-evangelical responses to the crisis of modernity and the historical development of the electronic church. He includes a series of interviews with representative viewers, discussing their beliefs, experiences, worldviews, and the role electronic religion plays in other aspects of their lives. Finally, the development of the electronic church in its wider context and its implications for American culture in general are considered.

Religion in the Media Age - Hoover, Stewart (Routledge, 2006)
Looking at the everyday interaction of religion and media in our cultural lives, Hoover's new book is a fascinating assessment of the state of modern religion. Recent years have produced a marked turn away from institutionalized religions towards more autonomous, individual forms of the search for spiritual meaning. Film, television, the music industry and the internet are central to this process, cutting through the monolithic assertions of world religions and giving access to more diverse and fragmented ideals. While the sheer volume and variety of information travelling through global media changes modes of religious thought and commitment, the human desire for spirituality also invigorates popular culture itself, recreating commodities, film blockbusters, world sport and popular music as contexts for religious meanings. Drawing on research into household media consumption, Hoover charts the way in which media and religion intermingle and collide in the cultural experience of media audiences. Religion in the Media Age is essential reading for everyone interested in how today mass media relates to contemporary religious and spiritual life.

Media, Home and Family - Hoover, Stewart M.; Clark, Lynn Schofield; Alters, Diane F. (Routledge, 2003)
Based on extensive fieldwork, this book examines how parents make decisions regulating media use, and how media practices define contemporary family life.

Religion in the News: Faith and Journalism in American Public Discourse - Hoover, Stewart (SAGE Publications, Inc, 1998)
Since the 1970s, more and more religious stories have made their way to headline news: the Islamic Revolution in Iran, televangelism and its scandals, and the rise of the Evangelical New Right and its role in politics, to name but a few. Media treatment of religion can be seen as a kind of indicator of the broader role and status of religion on the contemporary scene. To better understand the relationship between religion and the news media, both in everyday practice and in the larger context of American public discourse, author Stewart P. Hoover gives a cultural-historical analysis in his book, Religion in the News. The resulting insights provide important clues as to the place of religion in American life, the role of the media in cultural discourse, and the prospects of institutional religion in the media age. This volume is highly recommended to media professionals, journalists, people in the religious community, and for classroom use in religious studies and media studies programs.

The "Third Spaces" of Digital Religion - S. Hoover; N. Echchaibi (Finding Religion in the Media: Work in Progress on the Third Spaces of Digital Religion, 2012)
The emergence of new modes of digital communicative practice has had both lay and scholarly discourses struggling to adapt. The descriptive challenge is, indeed, a formidable one as the range and depth of emergent implications in technology, society, culture, and practice continues to develop. The trajectories that flow out of "the digital" into individual, social, and cultural space seem nearly limitless in extent and scope, at the same time that many voices are urging caution in expecting or claiming too much for these practices
Keywords: Digital; Digital Religion; Negotiation; New Media; power; Research; Third Spaces

Religious Meaning in the Digital Age: Field Research on Internet/Web Religion. - Hoover, S.; Park, J.K. (Belief in Media: Cultural Perspective on Media and Christianity)
Keywords: Christianity; culture; field research; media; religious; Religious Media

Rethinking Media, Religion, and Culture - Hoover, Stewart M.; Lundby, Knut (Sage Publications, Incorporated, 1997)
The growing connections between media, culture, and religion are increasingly evident in our society today but have rarely been linked theoretically until now. Beginning with the decline of religious institutions during the latter part of this century, Rethinking Media, Religion, and Culture focuses on issues such as the increasing autonomy and individualized practice of religion, the surge of media and media-based icons that are often imbued with religious qualities, and the ensuing effect on cultural practices. Editors Stewart M. Hoover and Knut Lundby examine each of these issues and the implications of major recent findings of religious, media, and cultural studies as they pertain to one another. In a primary effort, the leading class of contributors to this work effectively triangulate these three separate areas into a coherent whole. The book explores phenomena like rallies, rituals, and resistance as they are distinct expressions of religion often transmogrified into different mediated or cultural expressions. This collection should benefit the work of scholars and researchers in communication, media, cultural, and religious studies who seek a broader understanding of the two-sided relationships between religion and media, media and culture, and culture and religion.

Media, Public Scholarship and Religious Controversy: Notes from Trump’s America - Hoover, Stewart M (journal of religion in Europe, 2019)
The persistence of religion in the twenty-first century has renewed the importance of scholarships devoted to it. At the same time, the digital age has re-positioned and recentered the affordances of mediated circulations around "the religious." This increasing presence and significance of media and religion suggests that substantive scholarships of religion must necessarily articulate media as well. Religious controversies therefore present a special challenge and a special opportunity to scholarships of media and religion. New ways of doing scholarship, and doing so publicly, present themselves. All scholarships of mediated religion must necessarily be public, so scholarship is articulated into these circulations, and at the same time can build on and benefit from knowledge-building that occurs outside the formal boundaries of the academy. This paper explores emerging theories of digital mediation and proposes a circulation-focused understanding of the role, place, and potentials of scholarships today.

Media and the imagination of religion in contemporary global culture - Hoover, Stewart M. (European Journal of Cultural Studies, 2011)
This article argues for an invigorated scholarship of religion within cultural studies. It suggests that this is justified both on its own terms and because there is evidence that the interaction of media and religion is creating entirely new forms of the religious in contemporary public life. Religion persists in history, but it persists in part because of its mediation and this persistent, mediated religion constitutes a new evolution. The article presents a range of contexts where this can be seen to be happening, not least those contexts most involved in contemporary cultural globalization.

Personal Religion Online - Stewart Hoover; Lynn Schofield Clark (2004)
Paper presented at Internet Research 5.0, University of Sussex, England.
Keywords: American Life Project; internet; Pew Internet; religion; spiritual religious; survey

The Media and Religious Authority - Hoover, Stewart M (Penn State University Press, 2016)
As the availability and use of media platforms continue to expand, the cultural visibility of religion is on the rise, leading to questions about religious authority: Where does it come from? How is it established? What might be changing it? The contributors to The Media and Religious Authority examine the ways in which new centers of power and influence are emerging as religions seek to “brand” themselves in the media age. Putting their in-depth, incisive studies of particular instances of media production and reception in Asia, Africa, Latin America, and North America into conversation with one another, the volume explores how evolving mediations of religion in various places affect the prospects, aspirations, and durability of religious authority across the globe.

Faith Online: 64% of Wired Americans Have Used the Internet for Spiritual or Religious Information - Hoover, Stewart; Rainie, Lee; Clark, Lynn. S (Pew Internet and American Life Project, 2004)

Does God Make the Man?: Media, Religion, and the Crisis of Masculinity - Hoover, Stewart M.; Coats, Curtis D. (NYU Press, 2015)
Many believe that religion plays a positive role in men’s identity development, with religion promoting good behavior, and morality. In contrast, we often assume that the media is a negative influence for men, teaching them to be rough and violent, and to ignore their emotions. In Does God Make the Man?, Stewart M. Hoover and Curtis D. Coats draw on extensive interviews and participant observation with both Evangelical and non-Evangelical men, including Catholics as well as Protestants, to argue that neither of these assumptions is correct. Dismissing the easy notion that media encourages toxic masculinity and religion is always a positive influence, Hoover and Coats argue that not only are the linkages between religion, media, and masculinity not as strong and substantive as has been assumed, but the ways in which these relations actually play out may contradict received views. Over the course of this fascinating book they examine crises, contradictions, and contestations: crises about the meaning of masculinity and about the lack of direction men experience from their faith communities; contradictions between men’s religious lives and media lives, and contestations among men’s ideas about what it means to be a man. The book counters common discussions about a “crisis of masculinity,” showing that actual men do not see the world the way the “crisis talk” has portrayed it—and interestingly, even Evangelical men often do not see religion as part of the solution.

The media and religious authority - Hoover, S (Pennsylvania State University, 2016)
As the availability and use of media platforms continue to expand, the cultural visibility of religion is on the rise, leading to questions about religious authority: Where does it come from? How is it established? What might be changing it? The contributors to The Media and Religious Authority examine the ways in which new centers of power and influence are emerging as religions seek to “brand” themselves in the media age. Putting their in-depth, incisive studies of particular instances of media production and reception in Asia, Africa, Latin America, and North America into conversation with one another, the volume explores how evolving mediations of religion in various places affect the prospects, aspirations, and durability of religious authority across the globe. An insightful combination of theoretical groundwork and individual case studies, The Media and Religious Authority invites us to rethink the relationships among the media, religion, and culture.

Finding Religion in the Media: Work in Progress on the Third Spaces of Digital Religion - Stewart M. Hoover; Nabil Echchaibi (2012)
Keywords: Digital Religion; Internet Studies; media and religion; networked society; online identity; religion online; Third Spaces; users’ participation; virtual community; virtual public sphere

Practicing Religion in the Age of the Media: Explorations in Media, Religion, and Culture - Stewart M. Hoover; Lynn Schofield Clark (Columbia University Press, 2013)
increasingly, the religious practices people engage in and the ways they talk about what is meaningful or sacred take place in the context of media culture—in the realm of the so-called secular. Focusing on this intersection of the sacred and the secular, this volume gathers together the work of media experts, religious historians, sociologists of religion, and authorities on American studies and art history. Topics range from Islam on the Internet to the quasi-religious practices of Elvis fans, from the uses of popular culture by the Salvation Army in its early years to the uses of interactive media technologies at the Simon Wiesenthal Center's Beit Hashoah Museum of Tolerance. The issues that the essays address include the public/private divide, the distinctions between the sacred and profane, and how to distinguish between the practices that may be termed “religious” and those that may not.
Keywords: Beit Hashoah; popular culture; quasi-religious practices; Sacred; Salvation Army; Secular

The Anthropology of Religious Meaning Making in The Digital Age - Hoover, Stewart; Park, Jin (Media Anthropology, 2005)
Media Anthropology represents a convergence of issues and interests on anthropological approaches to the study of media. The purpose of this reader is to promote the identity of the field of study; identify its major concepts, methods, and bibliography; comment on the state of the art; and provide examples of current research. Based on original articles by leading scholars from several countries and academic disciplines, Media Anthropology provides essays introducing the issues, reviewing the field, forging new conceptual syntheses.

Forward: practice, autonomy and authority in the digitally religious and digitally spiritual - Hoover, S (Digital Religion, Social Media and Culture: Perspectives, Practices and Rituals, 2012)
This anthology - the first of its kind in eight years - collects some of the best and most current research and reflection on the complex interactions between religion and computer-mediated communication (CMC). The contributions cohere around the central question: how will core religious understandings of identity, community and authority shape and be (re)shaped by the communicative possibilities of Web 2.0? The authors gathered here address these questions in three distinct ways: through contemporary empirical research on how diverse traditions across the globe seek to take up the technologies and affordances of contemporary CMC; through investigations that place these contemporary developments in larger historical and theological contexts; and through careful reflection on the theoretical dimensions of research on religion and CMC. In their introductory and concluding essays, the editors uncover and articulate the larger intersections and patterns suggested by individual chapters, including trajectories for future research.
Keywords: Digital Religion; spiritual

A mediated religion: historical perspectives on Christianity and the Internet - Horsfield, P. G.; Teusner, P. (Studies in World Christianity, 2007)
Keywords: Christianity; media; religion

From Jesus to the Internet: A History of Christianity and Media - Peter Horsfield (Wiley Blackwell, 2015)
Keywords: Christianity; Digital; internet; intersection; media; religion

From Jesus to the Internet: A History of Christianity and Media - Horsfield, Peter (Wiley Blackwell, 2015)
From Jesus to the Internet examines Christianity as a mediated phenomenon, paying particular attention to how various forms of media have influenced and developed the Christian tradition over the centuries. It is the first systematic survey of this topic and the author provides those studying or interested in the intersection of religion and media with a lively and engaging chronological narrative. With insights into some of Christianity s most hotly debated contemporary issues, this book provides a much-needed historical basis for this interdisciplinary field.

A Mediated Religion: Historical perspectives on Christianity and the Internet - Horsfield, P; Teusner, P. (Studies in World Christianity, 2007)
Keywords: Christianity; history; internet and religion; media

The media and religious authority from ancient to modern - Horsfield, P (The Media and Religious Authority, 2016)

Digital Islamophobia: The Swedish woman as a figure of pure and dangerous whiteness - Horsti, Karina (New Media & Society, 2017)
This article addresses the digital culture of Islamophobic bloggers, focusing on the online circulation of a forensic photograph of a Swedish woman who was assaulted. The analysis shows how through appropriating this image, the bloggers created a unifying, imagined whiteness in the transnational Islamophobic network. The empirical analysis clarifies how this one image migrated and transformed in the blogosphere and legitimated the recurrent discursive trope of “Muslim rape.” This image became a subcultural “memory freeze frame” crystallizing the contemporary Islamophobic ideologies articulated in connection to race, ethnicity, nation, gender, and sexuality. The viral circulation of this image constructed a cultural, gendered, and racial Swedish whiteness, imagined to have become victimized by both Islam and liberal feminism, and therefore requiring global protection.

Virtual Morality: Christian Ethics in the Computer Age - Houston, Graham (Apollos, 1998)

Digital Jesus. The Making of a New Christian Fundamentalist Community on the Internet - Howard, Robert G (New York University Press, 2011)
In the 1990s, Marilyn Agee developed one of the most well-known amateur evangelical websites focused on the "End Times", The Bible Prophecy Corner. Around the same time, Lambert Dolphin, a retired Stanford physicist, started the website Lambert's Library to discuss with others online how to experience the divine. While Marilyn and Lambert did not initially correspond directly, they have shared several correspondents in common. Even as early as 1999 it was clear that they were members of the same online network of Christians, a virtual church built around those who embraced a common ideology. Digital Jesusdocuments how such like-minded individuals created a large web of religious communication on the Internet, In essence developing a new type of new religious movement - one without a central leader or institution. Based on over a decade of interaction with figures both large and small within this community, Robert Glenn Howard offers the first sustained ethnographic account of the movement as well as a realistic and pragmatic view of how new communication technologies can both empower and dis-empower the individuals who use them. By tracing the group's origins back To The email lists and "Usenet" groups of the 1980s up To The online forums of today, Digital Jesusalso serves as a succinct history of the development of online group communications.

Online Ethnography Of Dispensationalist Discourse: Revealed Verses Negotiated Truth - Howard, Robert G (Religion on the Internet: Research Prospects and Promises, 2000)
Religion on the Internet is the first systematic inquiry into the nature, scope and content of religion in cyberspace. Contributors to this volume include leading social scientists engaged in systematic studies of how organizations and individuals are presenting religion on the Internet. Their combined efforts provide a conceptual mapping of religion in cyberspace at this moment. The individual papers and collective insights found in this volume add up to a valuable agenda of research that will enrich understanding of this new phenomenon. Among the contributors are the founders of three of the most important scholarly religion web sites on the Internet: American Religion Data Archive, Religious Tolerance, and Religious Movements Homepage. Religion and the Internet is essential reading for all who seek to understand how religion is being presented on the Internet and how this topic is likely to unfold in the years ahead.

Media - Hughes-Freeland, F. (Theorizing Rituals: Issues, Topics, Approaches, Concepts, 2006)

Creating Church Online - Tim Hutchings (Routledge, 2017)
Creating Church Online constructs a rich ethnographic account of the diverse cultures of online churches, from virtual worlds to video streams. This book also outlines the history of online churchgoing, from its origins in the 1980s to the present day, and traces the major themes of academic and Christian debate around this topic. Applying some of the leading current theories in the study of religion, media and culture to this data, Tim Hutchings proposes a new model of religious design in contexts of mediatization, and draws attention to digital networks, transformative third spaces and terrains of existential vulnerability. Creating Church Online advances our understanding of the significance and impact of digital media in the religious and social lives of its users, in search of new theoretical frameworks for digital religion.
Keywords: Church; Online

“The Light of a Thousand Stories”: - Hutchings, Tim (Online - Heidelberg Journal of Religions on the Internet, 2019)
Open access and free to read online: https://heiup.uni-heidelberg.de/journals/index.php/religions/article/view/23952 Understanding a videogame requires attention to the social dimensions of its production, its material form and its reception. Games are produced in communities of designers, played by communities of gamers, and accepted into families, households, and other communal settings. Christian games have often been designed with this wider community context in mind, advertised to families and churches as products that can help attract and retain new audiences. This article focuses on the children’s videogame Guardians of Ancora (GoA), produced by the Christian organization Scripture Union in 2015. We will use an interview with the product developer to explore the intent behind the game, and we will use an interview with a British volunteer at ‘St. George’s Church’ to discover how the game has been used within a Christian community. GoA incorporates a degree of procedural rhetoric (Bogost 2007) into its design, but St. George’s invites children to engage with the game’s story and world in the context of a week of crafts, songs and other volunteer-led activities. Scholars of digital religion have long been fascinated by the relationship between online and offline religion, and the study of the social context of religious gaming offers a new way to approach this classic theme.

Contemporary Religious Community and the Online Church - Hutchings, T. (Information, Communication & Society, 2011)
‘Online churches' are Internet-based Christian communities, seeking to pursue worship, discussion, friendship, support, proselytism and other key religious practices through computer-mediated communication. This article introduces findings of a four-year ethnographic study of five very different ‘online churches’, focusing on the fluid, multi-layered relationship between online and offline activity developed by Christian users of blogs, forums, chatrooms, video streams and virtual worlds. Following a review of online church research and a summary of methods, this article offers an overview of each of the five groups and identifies clear parallels with earlier television ministries and recent church-planting movements. A new model of online and offline activity is proposed, focused on two pairs of concepts, familiarity/difference and isolation/integration, represented as the endpoints of two axes. These axes frame a landscape of digital practice, negotiated with great care and subtlety by online churchgoers. These negotiations are interpreted in light of wider social changes, particularly the shift from bounded community towards ‘networked individualism’.
Keywords: Christianity; Cyberchurch

Materiality and the Study of Religion: The Stuff of the Sacred - Hutchings, Tim; McKenzie, Joanne (Routledge, 2016)
Material culture has emerged in recent decades as a significant theoretical concern for the study of religion. This book contributes to and evaluates this material turn, presenting thirteen chapters of new empirical research and theoretical reflection from some of the leading international scholars of material religion. Following a model for material analysis proposed in the first chapter by David Morgan, the contributors trace the life cycle of religious materiality through three phases: the production of religious objects, their classification as religious (or non-religious), and their circulation and use in material culture. The chapters in this volume consider how objects become and cease to be sacred, how materiality can be used to contest access to public space and resources, and how religion is embodied and performed by individuals in their everyday lives. Contributors discuss the significance of the materiality of religion across different religious traditions and diverse geographical regions, paying close attention to gender, age, ethnicity, memory and politics. The volume closes with an afterword by Manuel Vásquez.

Religion and the Digital Humanities: New Tools, Methods and Perspectives - Hutchings, T. (Annual Review of the Sociology of Religion, 2012)
From the editors' introduction: "Tim Hutchings believes that the emerging research field of "digital humanities" seeks to generate and explore intersections between the questions and commitments of the traditional humanities disciplines and the opportunities, challenges and social transformations associated with digital media. This article maps the possibilities and challenges offered by the diverse landscape of new research, drawing on the author's own research experience as one of several sociologists of "cyber" and "cyborg" religion working at HUMlab, a digital humanities study laboratory in Umea, Sweden. Three of the author's own research projects - studies of cyberchurches, digital evangelism and Christian music festivals - will be used as case studies to demonstrate the development and application of digital research methodologies."
Keywords: Digital humanities; methodology

Considering religious community through online churches - Hutchings, T (Digital religion: Understanding religious practice in new media worlds, 2013)
Digital Religion offers a critical and systematic survey of the study of religion and new media. It covers religious engagement with a wide range of new media forms and highlights examples of new media engagement in all five of the major world religions. From cell phones and video games to blogs and Second Life, the book provides a detailed review of major topics and includes a series of case studies to illustrate and elucidate the thematic explorations. It also considers key theoretical, ethical and theological issues raised within Digital Religion studies.
Keywords: online church; religious

Global Perspectives on Religion, Media and Public Scholarship - Hutchings, Tim; Asamoah-Gyadu, Kwabena; Evolvi, Giulia; Han, Sam (Journal of Religion, Media and Digital Culture, 2020)
This article encourages researchers of religion, media and culture to develop new, global, comparative conversations about the meaning and purpose of public scholarship. Key terms like “religion”, “media”, “publicness” and “scholarship” can be understood and articulated differently in different social, cultural and geographical locations, and dialogue across our academic contexts is needed to help explore these parallels and divergences. This article shares three reflections from scholars who have lived and worked in west Africa, southern Europe and south-east Asia. Each contributor has been asked to address two questions: How do religious communities engage public audiences? And how can (or should) scholars communicate with the public? The conclusion to the article identifies some of the central themes of their responses: secularity, colonial legacies, globalization, power, vulnerability, and the intended audience of our public interventions.

Online Christian Churches: Three Case Studies - Hutchings, T. (Australian Religious Studies Review, 2010)
Online churches are Internet-based Christian communities, pursuing worship, proselytism and other ecclesial activities through digital media. This article is based on three case studies of online churches: i-church, the Anglican Cathedral of Second Life, and LifeChurch.tv Church Online. Seven key themes emerge from these case studies and are used here as a framework for comparative analysis: mass appeal, spiritual experience, community, reliance on the familiar, local church attendance, internal control and external oversight.

'The Politics of Familiarity: Visual, Liturgical and Organisational Conformity in the Online Church - Hutchings, T. (Special Issue on Aesthetics and the Dimensions of the Senses, 2010)
“Online churches” are Internet-based Christian communities, pursuing worship, education, support, proselytisation and other religious goals through computer-mediated communication. This paper draws on three years of participant observation and 50 interviews to investigate reliance on the familiar in the aesthetics and sensory experience of online religion, a trend that previous researchers have noticed but not fully explained. I use two ethnographic studies to explore the range of motivations that can guide this common strategy and consider visual design, use of sound, avatar gestures, awareness of co-presence and the physical activity of the computer user. Key factors include the desire to “frame” participant expectations, “ground” online experience, demonstrate theological “authenticity” and encourage participatory leadership, and these achievements are used to validate experimentation in other areas. This strategy is not uncontested, however: “outsiders” are frequently deterred by styles that “insiders” consider “normal”, and both churches have begun to explore new forms of architecture, ritual and communication with no clear offline parallels. New blends of familiarity and innovation are emerging, indicating some of the future directions of online churchmanship. My two case studies, the Anglican Cathedral of Second Life and LifeChurch.tv Church Online, reflect two key trends among online churches: the proliferation of small-scale independent congregations and the increasing involvement of wealthy institutions. The empirical and theoretical dimensions of this paper are innovative and timely, drawing attention to the professionalization and domestication of online religion and the rise of the “online campus”, key developments that deserve considerable scholarly attention.

Design and the digital Bible: persuasive technology and religious reading - Hutchings, Tim (Journal of Contemporary Religion, 2017)
This article analyses two ‘digital Bibles’, products that allow the user to engage with the Bible through the screen and speakers of his/her mobile phone, tablet or computer. Both products, ‘YouVersion’ and ‘GloBible’, have been created by Evangelical Christian companies. I argue that both are designed to train the user in traditional Evangelical Christian understandings of the work of reading. Digital media offer new opportunities to guide and influence the user, and this article applies the concepts of ‘persuasive technologies’ and ‘procedural rhetoric’ to analyse the design intentions of the two digital Bibles. This approach helps us to appreciate the significance of the material form of a sacred text as a vehicle for religious socialisation and raises important questions about the potential for digital media to re-shape traditional relationships of power in Evangelical Christian communities.

I Am Second: Evangelicals and Digital Storytelling - Hutchings, T. (Australian Journal of Communication, 2012)
This article explores the use of online video as a medium for spiritual autobiography through a case study of the Christian movement I am Second (IaS). IaS has published 74 short films, focused primarily on evangelical Christian celebrities. In each case, the video subject overcomes struggles or achieves fulfilment only by surrendering their lives to God and becoming ‘Second’. These stories are shared through fan blogs, Facebook, YouTube, and offline study groups. Analysis of the design, circulation, and response to these films indicates that digital media are fostering significant shifts in the production and reception of religious storytelling.
Keywords: Christianity; digital storytelling; evangelism; social media

Contemporary religious community and the online church - Hutchings, T (Information, Communication & Society, 2011)
‘Online churches' are Internet-based Christian communities, seeking to pursue worship, discussion, friendship, support, proselytism and other key religious practices through computer-mediated communication. This article introduces findings of a four-year ethnographic study of five very different ‘online churches’, focusing on the fluid, multi-layered relationship between online and offline activity developed by Christian users of blogs, forums, chatrooms, video streams and virtual worlds. Following a review of online church research and a summary of methods, this article offers an overview of each of the five groups and identifies clear parallels with earlier television ministries and recent church-planting movements. A new model of online and offline activity is proposed, focused on two pairs of concepts, familiarity/difference and isolation/integration, represented as the endpoints of two axes. These axes frame a landscape of digital practice, negotiated with great care and subtlety by online churchgoers. These negotiations are interpreted in light of wider social changes, particularly the shift from bounded community towards ‘networked individualism’.
Keywords: online church; religious

The Internet and the Church: An Introduction - Hutchings, T. (Expository Times, 2010)
The Internet is connecting people and organisations around the world in important new ways, changing the way we relate to one another, find resources, share information and form communities. These changes have very important implications for Christians and their churches. This article offers an overview of online activity, including websites, blogs, forums, social network sites, virtual worlds and online evangelism, and introduces theoretical work on the importance of online social networking, the role of the user in shaping technology, and the balance between control and participation in online activity.

The Dis/Embodied Church: Worship, new media and the body - Tim Hutchings (Christianity in the Modern World: Changes and Controversies)
Keywords: New Media; online church

Wiring death: dying, grieving and remembering on the internet - Hutchings, T. (Emotion, Identity and Death: Mortality Across Disciplines, 2012)
Keywords: Death

Network Theology: Christian Understandings of New Media - Hutchings, T. (Journal of Religion, Media and Digital Culture, 2012)
Review article considering three recent works of popular Christian theology: Dwight J. Friesen, Thy Kingdom Connected: What the Church Can Learn from Facebook, the Internet, and Other Networks (Grand Rapids: Baker Books, 2009); Shane Hipps, Flickering Pixels: How Technology Shapes Your Faith (Grand Rapids: Zondervan, 2009); and Jesse Rice, The Church of Facebook: How the Hyperconnected Are Redefining Community (Colorado Springs: David C. Cook, 2009).

Creating Church Online: Ritual, Community and New Media - Hutchings, Tim (Routledge, 2017)
Online churches are internet-based Christian communities, pursuing worship, discussion, friendship, support, proselytization, and other key religious goals through computer-mediated communication. Hundreds of thousands of people are now involved with online congregations, generating new kinds of ritual, leadership, and community and new networks of global influence. Creating Church Online constructs a rich ethnographic account of the diverse cultures of online churches, from virtual worlds to video streams. This book also outlines the history of online churchgoing, from its origins in the 1980s to the present day, and traces the major themes of academic and Christian debate around this topic. Applying some of the leading current theories in the study of religion, media and culture to this data, Tim Hutchings proposes a new model of religious design in contexts of mediatization, and draws attention to digital networks, transformative third spaces and terrains of existential vulnerability. Creating Church Online advances our understanding of the significance and impact of digital media in the religious and social lives of its users, in search of new theoretical frameworks for digital religion.

Creating Church Online: A Case-Study Approach to Religious Experience - Hutchings, T. (Studies in World Christianity, 2007)
Keywords: Church; Experience; Online; religion

REAL VIRTUAL COMMUNITY - Tim Hutchings (Word and World, 2015)
Virtual community can be real community. An example is the Church of Fools (now St Pixels), launched as an experiment eleven years ago, meant to last but three months. However, that experiment created a congregation that is still alive today, one in which people carry on public discussions with sufficient human feelings to form webs of personal relationships online.
Keywords: virtual community

Creating Church Online: Networks and Collectives in Contemporary Christianity - Hutchings, T. (Digital Religion, Social Media and Culture: Perspectives, Practices and Futures, 2012)
Keywords: Christianity; Cyberchurch

Considering Religious Community Through Online Churches - Tim Hutchings (Digital Religion: Understanding Religious Practice in New Media Worlds, 2013)
Keywords: Christian Churches; Contemporary Religious Community; New Media and Society; new media engagement; online Christianity; online church; Religion and the Internet; religious engagement; Sociology of religion; “religion online”

“In-Line Religion”: Innovative Pastoral Applications of the New Information and Communication Technologies (NICTS) by the Catholic Church in Nigeria - Walter C. Ihejirka (Politics and Religion, 2008)
This paper joins the growing corpus of literature on the relationship between religion and the new information and communication technologies in Africa. However, the case I will be presenting may not fall neatly into the two afore-mentioned categories. That is why I termed it innovative, and would classify it as an in-line religion, ‘in’ standing for indirect religious application of NICT. This paper thus advances a new perspective in studying the application of new information and communication technologies in religious belief and praxis in Africa.

Message of the Holy Father for the XXIV World Communications Day: The christian message in a computer culture - Pope John Paul II (1990)

Message of the Holy Father for the 36TH World Communications Day -- Internet: A New Forum for Proclaiming the Gospel - Pope John Paul II (2002)

Facebook as a Site for Inter-religious Encounters: A Case Study from Finland - Illman, Ruth; Sjö, Sofia (Journal of Contemporary Religion, 2015)
The aim of this article is to analyse the social networking site Facebook as a possible platform for inter-religious dialogue. Building on a case study—an attack on a Buddhist temple in Turku, Finland, and the consequent interaction that took place online immediately following the attack—the article investigates the strengths and limitations of social networking sites such as Facebook for encountering and connecting with religious others. The ethnographic material—consisting of both Internet material and interviews with concerned parties—is discussed in close connection with current research on religion, social media, and discussions online. Themes that are highlighted include stereotypes and superficiality as assumed aspects of online conversations, the role of power in dialogue—both offline and online, and symbolic communicative actions and social networking sites.

The New Arab Man: Emergent Masculinities, Technologies, and Islam in the Middle East - Marcia C. Inhorn (Princeton University Press, 2012)
Middle Eastern Muslim men have been widely vilified as terrorists, religious zealots, and brutal oppressors of women. The New Arab Man challenges these stereotypes with the stories of ordinary Middle Eastern men as they struggle to overcome infertility and childlessness through assisted reproduction. Drawing on two decades of ethnographic research across the Middle East with hundreds of men from a variety of social and religious backgrounds, Marcia Inhorn shows how the new Arab man is self-consciously rethinking the patriarchal masculinity of his forefathers and unseating received wisdoms. This is especially true in childless Middle Eastern marriages where, contrary to popular belief, infertility is more common among men than women. Inhorn captures the marital, moral, and material commitments of couples undergoing assisted reproduction, revealing how new technologies are transforming their lives and religious sensibilities. And she looks at the changing manhood of husbands who undertake transnational "egg quests"--set against the backdrop of war and economic uncertainty--out of devotion to the infertile wives they love. Trenchant and emotionally gripping, The New Arab Man traces the emergence of new masculinities in the Middle East in the era of biotechnology.
Keywords: Arab; Islam; male; Masculinities; men; Middle East; Muslim; stereotypes; Technologies

Niches in the Islamic Religious Market and Fundamentalism: Examples from Turkey and Other Countries - Introvigne, Massimo (Interdisciplinary Journal of Research of Religion, 2005)
The article applies the theory of religious niches to the intra-Islamic religious markets, with a special focus on Turkey. In normal conditions, these niches conform to general principles of religious economy. The ultrastrict and strict niches are smaller than the “central” moderate and conservative niches. Distortions in religious economies occur in what the article calls “religious war economies” (i.e., military conflicts perceived as religious) and “economies of war against religion” (i.e., governmental intervention against all organized religious groups). In the first case (e.g., Palestine, Iraq), there is in fact a war-caused modification of religious demand, with an expanded demand for ultrastrict religion. In the second case (e.g., Algeria, Turkey before 2002), the state effectively prevents moderate and conservative religious supply to meet the demand, with the unintended effect that in part this demand is captured by the ultrastrict groups, which are much more accustomed to operating illegally or against state pressure. Data about Turkey after the 2002 and 2004 elections confirm that when conservative and moderate religious supply is free to operate, ultrastrict alternatives enjoy only limited success.

So Many Evil Things: Anti-Cult Terrorism via the Internet - Introvingne, Massimo (Religion on the Internet: Research prospects and promises, 2000)
Religion on the Internet is the first systematic inquiry into the nature, scope and content of religion in cyberspace. Contributors to this volume include leading social scientists engaged in systematic studies of how organizations and individuals are presenting religion on the Internet. Their combined efforts provide a conceptual mapping of religion in cyberspace at this moment. The individual papers and collective insights found in this volume add up to a valuable agenda of research that will enrich understanding of this new phenomenon. Among the contributors are the founders of three of the most important scholarly religion web sites on the Internet: American Religion Data Archive, Religious Tolerance, and Religious Movements Homepage. Religion and the Internet is essential reading for all who seek to understand how religion is being presented on the Internet and how this topic is likely to unfold in the years ahead.

A symbolic universe. Information terrorism and new religions in cyberspace - Introvingne, Massimo (Religion and Cyberspace, 2005)
In the twenty-first century, religious life is increasingly moving from churches, mosques and temples onto the Internet. Today, anyone can go online and seek a new form of religious expression without ever encountering a physical place of worship, or an ordained teacher or priest. The digital age offers virtual worship, cyber-prayers and talk-boards for all of the major world faiths, as well as for pagan organisations and new religious movements. It also abounds with misinformation, religious bigotry and information terrorism. Scholars of religion need to understand the emerging forum that the web offers to religion, and the kinds of religious and social interaction that it enables. Religion and Cyberspace explores how religious individuals and groups are responding to the opportunities and challenges that cyberspace brings. It asks how religious experience is generated and enacted online, and how faith is shaped by factors such as limitless choice, lack of religious authority, and the conflict between recognised and non-recognised forms of worship. Combining case studies with the latest theory, its twelve chapters examine topics including the history of online worship, virtuality versus reality in cyberspace, religious conflict in digital contexts, and the construction of religious identity online. Focusing on key themes in this groundbreaking area, it is an ideal introduction to the fascinating questions that religion on the Internet presents.

Baraetika suru shūkyō バラエティ化する宗教 (Religion transformed into entertainment) - Kenji Ishii (Seikyūsha, 2010)

Communicating Hinduism in a Changing Media Context - Jacobs, Stephen (Religion Compass, 2012)
New media forms have a range of implications for the way in which the Hindu community is conceived and Hinduism is practiced. Oral modes of communication continue to have a significant role in the communication of Hinduism, however, Hindus have also made effective, and often innovative, use of all media forms. The use of print made by Hindu reformers, such as Rammohun Roy, was an important feature in the conceptualization of Hinduism as a ‘world religion’. Print technology also made possible the proliferation of visual images, which have now become incorporated into the devotional practices of many Hindus. Hindus have also developed unique genres in film and television, drawing on the rich narrative traditions of Hindu mythology. Hinduism can also be found in cyberspace. Online darśan, online pūjā services and other uses of the Internet have enabled Hindus, both in India and in diaspora, to maintain a connection with gurus, sacred places and other aspects of tradition. These developments in communication technologies are important in understanding Hinduism today, and the way in which it has evolved in a global context.
Keywords: Communication; Hindu; media

Virtually Sacred: The Performance of Asynchronous Cyber-RItuals in Online Spaces - Jacobs, S (Journal of Computer-Mediated Communication, 2007)
This article explores how the design of sacred spaces and ritual performance are transformed in the move from offline to online contexts. A semiotic analysis of two websites—a Christian Virtual Church and a Hindu Virtual Temple—suggests the potential for demarcating distinct online sacred spaces, in a Durkheimian sense, in which devotees can engage in ritual activity. The article focuses on the performance of cyberpuja in the Virtual Temple and the posting of prayers in the Virtual Church. Interviews with the Web designers and an analysis of the sites suggest that the virtual is primarily conceived in terms of a simulation of the "real." Consequently these sites are envisaged in terms of conventional notions of sacred space and ritual performance, rather than as something radically new.
Keywords: cyberspace; Performance; Ritual; Sacred

Authority in the Virtual Sangat : Sikhism, Ritual and Identity in the Twenty-First Century - Jakobsh, Doris R (Online – Heidelberg Journal of Religions on the Internet, 2006)
In her paper Authority in the Virtual Sangat. Sikhism, Ritual and Identity in the Twenty-First Century, Doris Jakobsh analyses the change of authority based on her research on Sikhs on the Internet. She stresses the Web as a ‘third place’ of communication among the Sikhs as well as the phenomenon of new authorities online. However, this does not imply the replacement of the traditional seats of authority, the Akal Takht, SGPC, or gurdwara managements, but one can recognize a significant shift away from these traditional sites of authority toward the ‘new authorities’, the intermediaries of cyberspace. Her analysis shows that this aspect of the Sikh experience brings with it the most profound challenges and, most importantly, a need to bridge the post-modern individual, i.e. ‘Sikh tradition’ intertwined and legitimated by the metanarrative, and the proliferation of new authorities who have become intermediaries of Sikhism online by virtue of their expertise within the digital domain.
Keywords: Akal Takht; Authority; Digital Religion; identity; online communication; Ritual; Sangat; Sikhism; Sociology of religion; third place

Feminizing the Khalsa - Jakobsh, Doris R. (Sikh Formations, 2015)
The ‘marked body’ of the Sikh male has long been the normative means for understanding Sikhism at large. The highly visible Khalsa Sikh male, complete with external signifiers known as the 5Ks, and the accompanying turban, tend to characterize the Sikh community at large, both in the Indian homeland as well as within Sikh diasporic contexts. This paper examines processes of negotiation of Sikh female identity, in essence the religious particularization of Sikh women that is taking place through varied means on the WWW. The far-reaching effects of instant, ‘authoritative’ transmission of information, whether through interpretations of historical and/or sacred texts, access to personal narratives on a global/local scale, as well as the construction of identity through online images will be examined.

Why Bill was killed. Understanding social interaction in virtual worlds' - Jakobsson, M. (Interactions in Virtual Worlds. Proceedings of the fifteenth Tewnte Workshop on language technology, 1999)
This paper deals with how we should approach the sociology of virtual worlds on the Internet. I argue for the importance of establishing an inside view based on direct experiences of the phenomenon, to avoid the risks of drawing erroneous conclusions about virtual worlds based on the physical world, and not realizing that virtual worlds are full of real people engaged in real interaction. I present an incident from a world based on the Palace technology to examplify the following points: The social interaction is fundamentally different from interaction in the physical world. The interaction is real. The social structures are hierarchical. People are not anonymous.

Searching for salvation: An analysis of U.S. religious searching on the World Wide Web - Bernard Jansen; Andrea Tapia; Amanda Spink (Religion, 2010)
The goals of this research were to answer three questions. How predominant is religious searching online? How do people interact withWeb search engines when searching for religious information? How effective are these interactions in locating relevant information? Specifically, referring to a US demographic, we analyzed five data sets from Web search engine, collected between 1997 and 2005, of over a million queries each in order to investigate religious searching on the Web. Results point to four key findings. First, there is no evidence of a decrease in religious Web-searching behaviors. Religious interest is a persistent topic of Web searching. Second, those seeking religious information on the Web are becoming slightly more interactive in their searching. Third, there is no evidence for a move away from mainstream religions toward non-mainstream religions since the majority of the search terms are associated with established religions. Fourth, our work does not support the hypothesis that traditional religious affiliation is associated with lower adoption of or sophistication with technology. These factors point to the Web as a potentially usefully communication medium for a variety of religious organizations.
Keywords: online religions; religious related searching; religious searching; web religious searching

Erving Goffman: A major theorist of power? - Jenkins, R (Journal of Power, 2008)
This article argues that Erving Goffman’s interactional sociology offers many useful insights into what power is and how it actually works, and that in addition to his other reputations we ought to think of Goffman as a significant theorist of power. A critical Goffmanian approach potentially allows us to comprehend the normal, diffuse ubiquity of power while according full recognition to the practices of individuals, whether self‐conscious or habitual, rule‐observant or improvisational. How Goffman’s understanding of power may help us to understand the contemporary realities of the early twenty‐first century is also discussed.

Convergence culture: Where old and new media collide - Jenkins, H (New York University Press, 2006)
Convergence Culture maps a new territory: where old and new media intersect, where grassroots and corporate media collide, where the power of the media producer and the power of the consumer interact in unpredictable ways. Henry Jenkins, one of America’s most respected media analysts, delves beneath the new media hype to uncover the important cultural transformations that are taking place as media converge. He takes us into the secret world of Survivor Spoilers, where avid internet users pool their knowledge to unearth the show’s secrets before they are revealed on the air. He introduces us to young Harry Potter fans who are writing their own Hogwarts tales while executives at Warner Brothers struggle for control of their franchise. He shows us how The Matrix has pushed transmedia storytelling to new levels, creating a fictional world where consumers track down bits of the story across multiple media channels.Jenkins argues that struggles over convergence will redefine the face of American popular culture. Industry leaders see opportunities to direct content across many channels to increase revenue and broaden markets. At the same time, consumers envision a liberated public sphere, free of network controls, in a decentralized media environment. Sometimes corporate and grassroots efforts reinforce each other, creating closer, more rewarding relations between media producers and consumers. Sometimes these two forces are at war. Jenkins provides a riveting introduction to the world where every story gets told and every brand gets sold across multiple media platforms. He explains the cultural shift that is occurring as consumers fight for control across disparate channels, changing the way we do business, elect our leaders, and educate our children.

Rituals and Pixels. Experiments in Online Church - Jenkins, Simone (Heidelberg Journal of Religions on the Internet, 2008)
Simon Jenkins, the founder of the famous “Church of Fools”, writes about his experiences of turning Christian rituals into virtual reality. In his article “Rituals and Pixels. Experiments in Online Church” he describes from an emic perspective the beginnings and the formation of the ”Church of Fools” as an experiment of a 3D-Faith-Environment, its development and his latest project, “St Pixels".
Keywords: Reality; Ritual; Virtual

My iPod, My iCon: How and Why Do Images Become Icons? - Eric Jenkins (Critical Studies in Media Communication, 2008)
This paper engages the cultic following of Apple computer through an examination of their brand image, here represented by the famous iPod silhouette commercials. I argue that Apple employs the techniques of the Orthodox icon, constructing a mode of seeing known as symbolical realism. This mode cues the reader to see with their divine eye, recognizing neither a realistic portrayal of an actual event nor a symbolic representation. Instead, the viewer sees the advertisements as a hypostasis of the immersion in music. This mode of seeing deflects attention from Apple's ideological gain and invites viewer participation in a cult celebrating the immersive experience. In short, the ads construct a visual enthymeme whose missing element is the user. By participating in the ritual of seeing through symbolic realism and thereby completing the enthymeme, the iPod is transformed into my iCon, bestowing the commodity, and by extension the corporation, with cult value.
Keywords: Cult Value; Icons; Ipod; Symbolic Realism; Visual Rhetoric

Religious authority and autonomy intertwined: The case of converts to Islam in Denmark - Jensen, T. G. (The Muslim World, 2006)

Waving a "Hi": Religion Among Facebook Users - Johns, M.D. (Association of Internet Researchers 9.0, 2008)
Keywords: Facebook; religion; social media; user

Ethical Issues in the Study of Religion and New Media - Mark Johns (Digital Religion: Understanding Religious Practice in New Media Worlds, 2012)
Keywords: ethics; Internet Studies

The church is flat: The relational ecclesiology of the emerging church movement - Jones, T (The JoPa Group, 2011)
The Church Is Flat is the first significant, researched study into the ecclesiology of the emerging church movement. Research into eight congregations is put into conversation with the theology of Jürgen Moltmann, concluding with pragmatic proposals for the the practice of a truly relational ecclesiology. Tony Jones visited eight emerging church congregations (Cedar Ridge Community Church, Pathways Church, Vintage Faith Church, Journey Church, Solomon's Porch, House of Mercy, Church of the Apostles, and Jacob's Well), facilitating interviews, focus groups, and surveys. After interpreting the data, Jones pulls out the most significant practices of these congregations and judges them relative to the relational ecclesiology of Jürgen Moltmann. Finally, Jones proposes a way forward for the emerging church movement, and the Protestant church writ large.

A better atonement: Beyond the depraved doctrine of original sin - Jones, T (The JoPa Group, 2012)
In A Better Atonement, theologian Tony Jones debunks the traditional doctrine of Original Sin and shows how that doctrine has polluted our view of the atonement. In an intriguing interlude, Jones distances himself from other progressive theologians and biblical scholars by strongly defending the historical crucifixion and physical resurrection of Jesus. Jones then summarizes various understandings of the atonement, from the ancient church to today, ultimately proposing a view that both takes into account a realistic view of sin and maintains an robust belief in the Trinity.

The new Christians: Dispatches from the emergent frontier - Jones, T (Jossey-Bass, 2008)
Following on the questions raised by Brian McLaren in A New Kind of Christian, Tony Jones has written an engaging exploration of what this new kind of Christianity looks like. Writing "dispatches" about the thinking and practices of adventurous Emergent Christians across the country, he offers an in-depth view of this new "third way" of faith-its origins, its theology, and its views of truth, scripture and interpretation, and the Emergent movement's hopeful and life-giving sense of community. With the depth of theological expertise and broad perspective he has gained as a pastor, writer, and leader of the movement, Jones initiates readers into the Emergent conversation and offers a new way forward for Christians in a post-Christian world. With journalistic narrative as well as authoritative reflection, he draws upon on-site research to provide fascinating examples and firsthand stories of who is doing what, where, and why it matters.

Pixelated Stained Glass: A Fantasy Theme Analysis of Online and Face-to-Face Christian Community - Elizabeth B. Jones (Ball State University, 2007)
This thesis investigates how two Christian communities – differentiated primarily by their medium of communication – characterize and cast Christian community. The method of fantasy theme analysis was used to explore this thesis’s central research question; namely, are content differences present in the ways in which face-to-face and digital communication systems characterize and cast the Christian sense of community? After an analysis of St. Pixels Church of the Internet (digital communication) and St. Luke’s United Methodist Church (face-to-face communication) it was found that the online community demonstrated a rhetorical vision of koinonia, while the face-to-face community demonstrated a rhetorical vision of ekklesia.

Doing Internet Research: Critical Issues and Methods for Examining the Net - Steve Jones (Sage Publishing, 1999)
The Internet is a medium with great consequences for social and economic life. This book is written to help people discern in what ways it has commanded the public imagination, and the methodological issues that arise when one tries to study and understand the social processes occurring within it. The contributors offer original responses in the search for, and critique of, methods with which to study the Internet and the social, political, economic, artistic, and communicative phenomena occurring within and around it.

Postmodern youth ministry - Jones, T (Zondervan, 2001)
The rules have changed. Everything you believe is suspect. The world is up for grabs. Welcome to the emerging postmodern culture. A "free zone" of rapid change that places high value on community, authenticity, and even God--but has little interest in modern, Western-tinged Christianity. Postmodern Youth Ministry addresses these enormous philosophical shifts and shows how they’re affecting teenagers.

Internet in the Monastery - Jonveaux, isabelle (Online - Heidelberg Journal of Religions on the Internet, 2019)
Monasticism is characterized by community life in a specific place (stabilitas loci), but also by local and translocal networks that correspond to different functions of the monastery (religious, cultural, commercial, etc.). Although Max Weber describes monasteries as out-of-the-world institutions, most monastic communities (at least male ones) have Internet access and an online presence now. The use of digital media in monastic life raises a number of questions: What impact does it have on the community life of monks and nuns? Can it jeopardize the quality of community life? Regarding the external communication of the monastery, does its online presence allow the monks to extend the community beyond the cloister? This paper analyzes the role played by digital media in monastic life on the individual and community levels, and on the monastery’s outside communication with various audiences.

Une retraite de Carême sur Internet - Jonveaux, isabelle (Archives de Sciences Sociales des Religions, 2007)

Le jeûne d'Internet. Réduction et abstinence des médias numériques au service de l’expérience spirituelle / Internet fast. Reduction and abstinence from digital media and spiritual experience - Isabelle Jonveaux (RESET - Revue en Sciences Sociales sur Internet, 2020)
The use of digital media for the religious practice is no longer the exception, but seems to have become a common practice. Parallel to this, we observe more and more forms of total or partial renouncement of use of the Internet during a particular period of reintensification of the religious or spiritual life. Taking the examples of asceticism of religious virtuosi with Catholic monks and nuns, Christian Lent and fasting and hiking weeks that are part of a holistic spirituality approach, this article shows with the help of empiric data how actors consciously reduce their use of the Internet for religious purposes. Some even speak of an Internet fast which would be an indispensable counterpart to the food fast. However, in many cases, disconnection appears to be more difficult than food fasting and is then seen as a new type of virtuosity. Re-examining the classical categories of the sociology of religions that are fasting and asceticism, this article shows how they are redefined today with new objects of application. For the institutional Church, it is also an opportunity to restore plausibility to practices - especially the Lenten fast - which had gradually fallen into disuse.
Keywords: abstinence; fast; internet; religious practice

L’autre Internet : les moines et le web - Jonveaux, isabelle (Terrain et Travaux, 2009)

Gott online - Mönche und Gläubige im Internet - Jonveaux, isabelle (Handbuch der Religionen, 2014)

Facebook as a monastic place? The new use of internet by Catholic monks - Jonveaux, isabelle (Digital Religion)
Although Catholic monasteries are theoretically out of the world, monks and nuns more and more use the internet, both for religious and non-religious reasons. While society at large often takes it for granted that monks are out of modernity, monastic communities have been adopted this media from relatively early on, and we cannot say that they have come late to its use. The internet can offer monasteries a lot of advantages because it allows monks to be in the world without going out of the cloister. Nevertheless, the introduction of this new media in monasteries also raises a lot of questions about the potential contradictions it poses with other aspects of monastic life. The paper does not deal with online religious practices, but seeks to research the use of the medium by monks and nuns even in their daily lives, and attempts especially to investigate the potential changes it brings to monastic life.

When Church and Cinema Combine: Blurring Boundaries through Media-Savvy Evangelicalism - D Justice (Journal of Religion, Media and Digital Culture, 2014)
The use of social media presents new religious groups with opportunities to assert themselves in contrast to established religious institutions. Intersections of church and cinema form a central part of this phenomenon. On one hand, many churches embrace digital media, from Hollywood clips in sermons to sermons delivered entirely via video feed. Similarly and overlapping with this use of media, churches in cinemas have emerged around the world as a new form of Sunday morning worship. This paper investigates intersections of church and cinema through case studies of two representative congregations. CityChurch, in Würzburg, Germany, is a free evangelical faith community that meets in a downtown Cineplex for Sunday worship. LCBC (Lives Changed by Christ) is one of the largest mult-sited megachurches on the American East Coast. While LCBC’s main campus offers live preaching, sermons are digitally streamed to the rest. Both CityChurch and LCBC exemplify growing numbers of faith communities that rely on popular musical and social media to 1) redefine local and global religious relationships and 2) claim identity as both culturally alternative and spiritually authentic. By engaging with international flows of worship music, films, and viral internet sensations, new media-centered faith communities like CityChurch and LCBC reconfigure established sacred soundscapes. CityChurch’s use of music and media strategically differentiates the congregation from neighboring traditional forms of German Christianity while strengthening connections to the imagined global evangelical community. LCBC creates what cultural geographer Justin Wilford dubs a “postsuburban sacrality” that carves out meaning from the banality of strip-mall-stubbed suburban existence. Analyzing the dynamics of music and media in these new worship spaces assumes growing importance as transnational music and media choices play an increasingly a central role in locally differentiating emergent worship communities from historically hegemonic religious neighbors.
Keywords: Church; Cinema; Cineplex; CityChurch; Evangelicalism; Germany; Media-Savvy

Mediatized lives: Autobiography and assumed authenticity in digital storytelling - Kaare, H.; Lundby, K. (Digital Storytelling, Mediatized Stories. Self-representations in New Media, 2009)
Recent years have seen amateur personal stories, focusing on «me, flourish on social networking sites and in digital storytelling workshops. The resulting digital stories could be called «mediatized stories. This book deals with these self-representational stories, aiming to understand the transformations in the age-old practice of storytelling that have become possible with the new, digital media. Its approach is interdisciplinary, exploring how the mediation or mediatization processes of digital storytelling can be grasped and offering a sociological perspective of media studies and a socio-cultural take of the educational sciences. Aesthetic and literary perspectives on narration as well as questioning from an informatics perspective are also included.

"Let's Meet in Holy Land": The Pilgrimage in Virtual Worlds - Emil R. Kaburuan; Chen, Chien-Hsu; Jeng, Tay-Sheng (International Conference on Religion and Spirituality in Society, 2011)
Keywords: 3D Virtual Environment; Avatar; pilgrimage; Virtual Pilgrim; virtual worlds

Isn’t it Real? – Experiencing the Virtual Church in Second Life® - Emil R. Kaburuan; Chen, C. H.; Jeng, T. S. (Handbook of Research on Practices and Outcomes in Virtual Worlds and Environments, 2012)
Keywords: religion online; Second Life; Users' Experience; virtual worlds

Internet Use in Wired Religious Community: Communication Behavior Among Asia-Pacific Nazarene Theological Seminary (APNTS) Residential Students - Emil R. Kaburuan (VDM Verlag Publishing, 2010)
Keywords: Communication Behavior; internet; Wired Religious Community

Service Design Model of the Online Virtual Church in Second Life® - Emil R. Kaburuan; Chen, Chien-Hsu; Jeng, Tay-Sheng (13th Annual Conference on Human Computer Interaction, 2009)

Marketing of Religion in Cyberspace - Sudhir Kale; Rajeev Kamineni (Australian and New Zealand Marketing Academy Conference Proceedings, 2003)
The Internet has begun to play a significant role in people’s lives, albeit in the lives of people living on the ‘right’ side of the digital divide. Yet, the nexus between religion and the Internet has seldom been discussed in the marketing context. This paper investigates the effect of the Internet on how people use the new technology to fulfill their spiritual and religious needs. The marketing implications of this nascent but widely spreading phenomenon are discussed since this trend has a significant impact on the providers of spiritual and religious services.

Going on Pilgrimage Online : the Representation of Shia Rituals on the Internet - Sabine Kalinock (Online – Heidelberg Journal of Religions on the Internet, 2006)
In her article Going on Pilgrimage Online. The Representation of Shia Rituals on the Internet, Sabine Kalinock gives an overview of the representation of Shia ritual in the Internet and discusses the relation between innovations and traditional discourses. Emphasis is laid on the possibilities that the Internet offers and which are especially important in the Muslim and Iranian context: the mixing of the sexes, exchange with believers in other parts of the world and the free expression of critical ideas. Kalinock thereby concentrates on case studies from Iranian religious websites set up by various Shiite communities, official institutions as well as private persons. These Websites are usually presented in at least three languages: Arab, Persian, and English, and deal with religious regulations and rituals, hagiographies and recent miracle stories that are recorded with modern technology and confirmed by physicians. Pictures, video films and audio records supplement the texts. Via email believers can seek the guidance of a leading clergyman of their choice (marja at-taqlid) while various books and online resources provide further advice. In chat rooms men and women discuss, affirm or question the meaning and validity of certain religious rules and rituals.
Keywords: analyzing rituals; communication within the Internet; media and religion; New Technology and Society; Online community; Pilgrimage Online; Practicing Faith in Cyberspace; religion; religious practice; Shia

Religious Discourse and Cyberspace - Anastasia Karaflogka (Religion, 2002)
This article explores the evolution and development of a typology of cyberspatial religious discourse over the course of a few years. The vast quantity of information published on the Net requires the creation of a typology in order to identify and classify the different approaches, attitudes, applications and functions of religion on and in cyberspace. The three different typologies indicate, on the one hand, the versatile character of cyberspace, and on the other hand, the ever-expanding nature of its perimeters. They show that cyberspatial discourse, religious or not, cannot be confined within restricted boundaries but must be perceived as a changeable and unforeseen structure, having the capacity to adapt itself according to the visions, fantasies, ingenuities and inventiveness of the users. They also suggest that despite the rhizomatic construction of cyberspace, the information published on the innumerable religious sites can be systematised in a ‘logical’ formation.
Keywords: Attitude; cyberspace; religion; Typology

Vaishnava cyber-puja: Problems of purity and novel ritual solutions - Karapanagiotis, N. (Heidelberg Journal of Religions on the Internet, 2010)
In this article, I examine Vaishnava Hindu views on cyber-pūjā to Vishnu (the ritual worship of Vishnu online). Based on ethnographic interviews with Vaishnava devotees in the New Jersey tri-state area, I argue that although these devotees have nothing against the online worship of Vishnu in theory (they believe that Vishnu is ontologically present in cyberspace and available there for worship), they nonetheless have reservations about performing such worship in practice. These reservations, I argue, stem from concerns about violations of two types of purity: spatial purity (the purity of the sacred cyber-altar space in which Vishnu resides) and mental purity (the purity of the mental state of the devotee who is performing the cyber-pūjā). However, although devotees have concerns over the violations of purity that stem from cyber-pūjā, many have come up with novel, medium specific, ritual practices that can help overcome or at least mitigate these purity violations. I discuss these ritual practices—which include actions such as lighting incense in front of the computer, clearing one's private data (browsing history, etc.,) and moving the computer to a separate part of the desk—and the ways that they enhance both the computer as a space for worshipping Vishnu and devotees' mental purity while doing so. Finally, I conclude the article with a discussion of the importance that Vaishnavas place on purity of intention, and show that for many devotees, pure devotional intention is all one needs in order to overcome any seemingly problematic aspect of cyber-pūjā.

Swipe Left to Pray. Analyzing Authority and Transcendence in Prayer Apps - Karis, Tim (Entangled Religions, 2020)
This paper centers on a fairly new phenomenon in digital religion: prayer apps. After an overview of their typical features, the paper will present a number of analytical perspectives on such apps, arguing that investing in theoretical work is needed, particularly in a young research field. Starting points are provided by Heidi Campbell’s four-layer model of religious authority, Michel Foucault’s concept of “technologies of the self,” Birgit Meyer’s understanding of religion as a practice of mediation, and by the conceptualization of the transcendence/immanence distinction developed at the Käte Hamburger Kolleg Dynamics of the History of Religions Between Asia and Europe at the Center for Religious Studies, Ruhr-Universät Bochum. With regards to authority, it will be pointed out that prayer apps employ highly different strategies of authorization. These include the evocation of traditional authority, building trust through the use of familiar design language (often borrowed from outside the religious field), and self-imposed strategies aimed at the ‘improvement’ of the individual believer. As for the transcendence/immanence-distinction, it will be argued that it is important to differentiate between prayer apps that have a more auxiliary character, helping users to prepare their offline praying practice, and those apps that allow users to pray directly on their phone – which has significant implications for the understanding of transcendence.

Religious beings in fashionable bodies: the online identity construction of hijabi social media personalities - Kavakci, Elif; Kraeplin, Camille R (Media, Culture & Society, 2016)
A ‘hijabista’ – from the terms hijabi and fashionista – is a Muslim woman who dresses ‘stylishly’ while still adhering to the rules governing ‘modest’ apparel that coincides with Islamic dress code. A handful of these digitally savvy young women have established an online presence, becoming social media personalities with hundreds of thousands, even millions, of ‘followers’ who avidly consume (read) their personal blogs and/or social media posts. This study examines new media, faith, and fragmentation online, where virtual spaces facilitate the construction (re-construction) of a digital identity or persona. We employ an approach that combines netnography and case study to examine the content generated by three high-profile hijabistas, or hijabi fashion and lifestyle bloggers, and build upon identity theory to determine how each has negotiated an online persona that privileges her religious or fashionable self.

Gendai Shūkyō tokushū: Media ga umidasu kamigami 現代宗教2008 特集：メディアが生み出す神々 (Contemporary Religion 2008 Special Issue: Gods Born out of the media) - Kokusai Shūkyō Kenkyūjo (Akiyama shoten, 2008)

Online Buddhist Community: An Alternative Religious Organization in the Information Age - Kim, M-C. (Religion and Cyberspace, 2005)
In the twenty-first century, religious life is increasingly moving from churches, mosques and temples onto the Internet. Today, anyone can go online and seek a new form of religious expression without ever encountering a physical place of worship, or an ordained teacher or priest. The digital age offers virtual worship, cyber-prayers and talk-boards for all of the major world faiths, as well as for pagan organisations and new religious movements. It also abounds with misinformation, religious bigotry and information terrorism. Scholars of religion need to understand the emerging forum that the web offers to religion, and the kinds of religious and social interaction that it enables. Religion and Cyberspace explores how religious individuals and groups are responding to the opportunities and challenges that cyberspace brings. It asks how religious experience is generated and enacted online, and how faith is shaped by factors such as limitless choice, lack of religious authority, and the conflict between recognised and non-recognised forms of worship. Combining case studies with the latest theory, its twelve chapters examine topics including the history of online worship, virtuality versus reality in cyberspace, religious conflict in digital contexts, and the construction of religious identity online. Focusing on key themes in this groundbreaking area, it is an ideal introduction to the fascinating questions that religion on the Internet presents.

Communities of (Digital) Practice: Preparing religious leaders for lively online engagement - Lisa Kimball; Kyle Oliver (Religious Education Association, 2013)
The digital revolution has expanded the skill set needed for leadership in faith communities. Theological education has adapted slowly. We chronicle the transformation of a teaching and learning center at a denominational seminary from static resource-lending enterprise into a dynamic learning lab for digital engagement. Convening communities of digital media practice in an action research setting, the center equips religious educators to be substantial contributors to online conversations about faith. Using situated learning theory, we discuss our research with faith formation practitioners and seminarians.
Keywords: Christian education; digital literacy; evangelism; faith formation; social media; theological education

Religious Identity, Expression, and Civility in Social Media: Results of Data Mining Latter‐Day Saint Twitter Accounts - Kimmons, R; McGuire, K; Stauffer, M; Jones, J.E.; Gregson, M; Austin, M (Journal for the Scientific Study of Religion, 2017)
This study explores religious self‐identification, religious expression, and civility among projected Latter‐Day Saint Twitter accounts (201,107 accounts and 1,542,229 tweets). Novel methods of data collection and analysis were utilized to test hypotheses related to religious identity and civility against social media data at a large scale. Results indicated that (1) projected LDS Twitter accounts tended to represent authentic (rather than anonymous or pseudonymous) identities; (2) local minority versus majority status did not influence users’ willingness to religiously self‐identify; (3) isolation stigma did not occur when users religiously self‐identified; (4) participants exhibited much lower degrees of incivility than was anticipated from previous studies; and (5) religious self‐identification was connected to improved civility. Results should be of interest to scholars of religion for better understanding participation patterns and religious identity among Latter‐Day Saints and for exploring how these results may transfer to other groups of religious people.
Keywords: civility; data mining; Later-Day Saint; religious identity; social media; Twitter

Alternative Worlds: Metaphysical Questing and Virtual Community amongst the Otherkin - Kirby, Danielle; Di Lauro, Frances (… Through a Glass Darkly: Reflections on the Sacred. Collected Essays. With an Introduction by Victoria Barker, 2006)
Keywords: alternative religion online; Otherkin

Thinking critically about and researching algorithms - Kitchin, R. (Information, Communication & Society, 2017)
More and more aspects of our everyday lives are being mediated, augmented, produced and regulated by software-enabled technologies. Software is fundamentally composed of algorithms: sets of defined steps structured to process instructions/data to produce an output. This paper synthesises and extends emerging critical thinking about algorithms and considers how best to research them in practice. Four main arguments are developed. First, there is a pressing need to focus critical and empirical attention on algorithms and the work that they do given their increasing importance in shaping social and economic life. Second, algorithms can be conceived in a number of ways – technically, computationally, mathematically, politically, culturally, economically, contextually, materially, philosophically, ethically – but are best understood as being contingent, ontogenetic and performative in nature, and embedded in wider socio-technical assemblages. Third, there are three main challenges that hinder research about algorithms (gaining access to their formulation; they are heterogeneous and embedded in wider systems; their work unfolds contextually and contingently), which require practical and epistemological attention. Fourth, the constitution and work of algorithms can be empirically studied in a number of ways, each of which has strengths and weaknesses that need to be systematically evaluated. Six methodological approaches designed to produce insights into the nature and work of algorithms are critically appraised. It is contended that these methods are best used in combination in order to help overcome epistemological and practical challenges.

Social informatics. In Encyclopaedia of Lis - Kling, R. (Kluwer Publishing, 2001)

“I Type the Amens and Think the Rest”: An Ethnographic Look at Religion in Virtual Reality - Madeline LeNore Klink (Reed College, 2008)
In 2003, a company called Linden Labs launched the first widely-accessible virtual reality: Second Life. Religious groups have been among the first to take advantage of this new frontier, but they have thus far garnered no attention from the academy. This thesis explores the new phenomenon of religious activity in virtual reality through a three-month ethnographic study of a Bible study at the Campivallensis Catholic Meditation,Center in Second Life. I supplement the study with six interviews with Bible study attendees. I also review scholarly research and Catholic theology that relates to religious activity in virtual reality. My thesis concludes that Campivallensians value individualism and theological diversity { values which are supported and reinforced by the medium of Second Life. I speculate that these values will cause friction between virtual reality participants and religious authorities in years to come.

The Internet and Religion in Singapore: A National Survey - Kluver, Randolph; Detenber, Benjamin H.; Shahiraa Sahul Hameed; Pauline Hope Cheong; Lee Wainpeng (Singapore Internet Research Centre, 2005)
Singapore has one of the highest Internet penetration rates in the world (60.2%) and 85% of Singaporeans claim to have a religious affiliation to one of the main religious traditions within the country, including Buddhism, Taoism, Christianity, Islam, Hinduism, or traditional Chinese religions. International surveys have shown the use of the Internet for religious purposes is growing significantly, and that in the future, the Internet could be a primary source for religious information for users around the world. The main aim of this project was to investigate and better understand how Singaporeans used the Internet for religious purposes. A national survey with 711 respondents was conducted from 21st to 26th of November 2004 to measure the extent to which Singaporeans used the Internet in a religious context, their perceptions of the religious impact of the Internet and the most common online religiously oriented online activities among Singaporeans.

Technological modernization, the Internet, and religion in Singapore - Kluver, Randy (Journal of Computer-Mediated Communication, 2007)
This study critically examines the ways in which technological modernization and religion co-exist and mutually reinforce one another within the Singaporean context. Interviews with religious leaders of a diverse set of faiths in Singapore about how they understand the role of information technology in religious practice reveal a broad-based acceptance of the Internet and other information technologies and little sense of a danger to religious faith. Contrary to the proposals of secularization theory, these findings suggest that various religious communities have adopted and in some cases embrace the Internet as part of their contemporary religious mission and strategy for growth. The findings further contribute to historical research on the social construction of technology and lend support to emergent research on the spiritual shaping of Internet technology by religious communities seeking to integrate the Internet into their everyday social and religious practices in wired contexts such as Singapore.
Keywords: Faith; Singapore; Technologies

The relationship between problematic Internet use, God attachment, and psychological functioning among adults at a Christian university - Knabb, J.J; Pelletier, J (Mental Health, Religion and Culture, 2014)
In the present study, we utilised structural equation modelling (SEM) to investigate the relationship between God attachment and problematic Internet use, mediated by emotional distress. Findings supported the proposed hypothesis that anxious God attachment (i.e., anxiety about God's abandonment) predicts both problematic Internet use (i.e., obsessing about the Internet, neglecting tasks and relationships due to the Internet, struggling to control Internet use) and psychological distress (i.e., depression, anxiety, stress, worry). In addition, weak-to-moderate correlations emerged between depression, anxiety, stress, and worry and problematic Internet use. Further research is needed to generalise and replicate these preliminary results.
Keywords: addiction; attachment; distress; God; internet; problematic Internet use

Excess, Artifice, Sentimentality: Almodóvar’s Camp Cinema as a Challenge for Theological Aesthetics - S Knauss (Journal of Religion, Media and Digital Culture, 2014)
Camp is defined as a style that is characterised by excess, artificiality, theatricality, exaggeration, sentimentality. What could this possibly contribute to Christian theological aesthetics, the study of God and theological issues through the aesthetic, art, beauty? This paper proposes, through a discussion of camp in its “incarnation” in Pedro Almodóvar’s cinema, that it has several aspects to offer. Camp uncovers and challenges the categories of truth and reality in theological aesthetics as well as the artforms in which this truth can be discovered. Its embrace of the superficial and material can be seen, in theological terms, as an incarnational aesthetics that offers redemption through the affirmation of the material, not its disruption or negation. Camp underlines the subversive power of pleasure and laughter against tendencies that dismiss pleasure as escapism, and challenges theological aesthetics to acknowledge the wisdom that lies in emotions and affects. It criticizes by fostering solidarity and empathy, rather than antagonism. Thus camp represents a challenge to self-critically reflect on processes of exclusion on an aesthetic and a social level, and challenges us to imagine a different world, a world of beauty, love and passion
Keywords: Camp Cinema; Christianinty; religion; Sentimentality; Theological Aesthetics

The changing faces of media and religion - Knott, Kim.; Mitchell, Jolyon (Religion and Change in Modern Britain, 2012)
This book offers a fully up-to-date and comprehensive guide to religion in Britain since 1945. A team of leading scholars provide a fresh analysis and overview, with a particular focus on diversity and change. They examine: relations between religious and secular beliefs and institutions the evolving role and status of the churches the growth and settlement of non-Christian religious communities the spread and diversification of alternative spiritualities religion in welfare, education, media, politics and law theoretical perspectives on religious change. The volume presents the latest research, including results from the largest-ever research initiative on religion in Britain, the AHRC/ESRC Religion and Society Programme. Survey chapters are combined with detailed case studies to give both breadth and depth of coverage. The text is accompanied by relevant photographs and a companion website.
Keywords: media; religion

Symbol of the cross in popular culture. The analysis of the use and transformation of the symbol in the “Machina” magazine - Marta Kolodziejska (Polish Sociological Review, 2013)
The article focuses on the use and transformation of religious symbols in popular culture. The Polish popculture “Machina” magazine was chosen as a case study. Popular culture, based strongly on visual communication, has fluid canons and is of an (auto)ironic nature. Symbols from different domains are transformed within this culture so that they fit its rules of communication. Religious symbols have been used extensively in “Machina” in a conventional, humorous, and deriding manner. According to the results of the analysis, the use of religious symbols in popular culture is inevitably connected to the overlapping of religious communication and popcultural communication, which creates a particular ambivalence of the meaning of the symbol. One should ask if resulting adaptations of religious symbols by popular culture might be considered to be a process of desacralisation. On the basis of the above-mentioned case study, one cannot give an unequivocal answer. Although popcultural communication may lead to simplification and deconstruction of symbols, one cannot claim it is de-symbolised as such. Desymbolisation and desacralisation are ongoing processes, but they are parallel to the process of creation and transformation of symbols as well. The research may be an inspiration for further analysis of the way religious symbols function within the realm of popular culture.

RELIGION ON CATHOLIC INTERNET FORUMS IN POLAND. A MEMORY MEDIATED - Kolodziejska, Marta (Nordic Journal of Religion and Society, 2014)
The following article aims to show that on Catholic Internet forums in Poland, religion—in this case Roman Catholicism—serves as a mediated chain of memory fulfilling two main functions simultaneously: an integrating function and a differentiating function. The analysis will be based on Hervieu-Léger’s concept of religion as a chain of memory (2000, 2006) and Davie’s modified concept of religion as memory that mutates (2000, 2006).A thread from 2011 on one of the most popular Catholic forums in Poland—forum.wiara.pl—will be used as a case study. It will be shown that through voicing various notions of the meaning of religion, faith, the institutional Church, and the connection between science and religion, users both distinguish themselves from and integrate themselves with other users, as well as with their representation of ‘average’ Catholics in Poland.
Keywords: Catholicism; forums; internet; memory; religion

The electronic frontier of Catholicism in Poland- the answer to the crisis of religious community? - Marta Kolodziejska (2014 Volume of Religion and the Social Order: Religion in Times of Crisis, 2014)

Online Catholic Communities: Community, Authority, and Religious Individualization - Marta Kolodziejska (Routledge Studies in Religion and Digital Culture, 2018)
The Catholic Church has been moving into a new phase, one where its congregation can choose to meet and practice elements of their own version of their faith on online forums. This new form of congregating allows for an individualised faith to manifest itself outside of the usual church authority structures. Online Catholic Communities provides insight into how religious and non-religious internet forum users interact and form groups during interactions; it also discusses the transformation of religious authority and its emanations in these digital contexts. Using the top three online forums used by Polish Catholics as a case study, this project explores the formation of these online communities. It then looks at the alternative authority structures that emerge online and how these lead to an individualised form of religious engagement that can develop independently of mainstream doctrine. Through highlighting how religious discourse in Poland is appropriated and creatively modified by users in fulfilling their own spiritual needs, this work reveals the constant interplay between online and offline religious contexts. This monograph includes cutting edge research on online expressions of religious community, authority and individualisation and as such will be of keen interest to scholars of religious studies and the sociology of religion, as well as communication studies.
Keywords: Catholic Church; digital environments; individualization; religious authority

Religion and technology: refiguring place, space, identity and community - Lily Kong (Area, 2001)
This paper reviews the literature on the religion–technology nexus, drawing up a research agenda and offering preliminary empirical insights. First, I stress the need to explore the new politics of space as a consequence of technological development, emphasizing questions about the role of religion in effecting a form of religious (neo)imperialism, and uneven access to techno-religious spaces. Second, I highlight the need to examine the politics of identity and community, since cyberspace is not an isotropic surface. Third, I underscore the need to engage with questions about the poetics of religious community as social relations become mediated by technology. Finally, I focus on questions about the poetics of place, particularly the technological mediation of rituals.
Keywords: community; cyberspace; place; religion; space; technology

Christian Evangelizing Across National Boundaries: Technology, Cultural Capital and the Intellectualization of Religio - Lily Kong (Religion and Place, 2013)
Christian evangelical work across national boundaries is often associated with missionary work. In this chapter, I focus on other strategies used in Christian evangelizing, particularly the widespread international dissemination and replication of courses about Christianity for the unconverted using standardized material and approaches. I examine how religious globalization (i.e. the convergence and conformity of religious practice across national boundaries) through such courses takes place, with the aid of technology, the tapping of shared cultural capital and the “intellectualization” of religion. I argue that such forms of evangelization work for certain audiences better than for others. Using the case of the Alpha course, an evangelical Christian course originating in London and replicated in different parts of the world, and focusing on its dissemination and effects in Singapore, I demonstrate how the evangelical material works best with a transnational elite audience with a shared cultural and intellectual capital
Keywords: Alpha course; audience; Christianity; cultural capital; evangelical; intellectual capital; intellectualization; London; religion; Singapore

Between individualisation and tradition: transforming religious authority on German and Polish Christian online discussion forums - Kołodziejska, Marta; Neumaier, Anna (Religion, 2017)
The aim of this paper is to connect the debates on individualisation and mediatisation of religion and transformations of religious authority online on theoretical and empirical basis. The classical and contemporary concepts of individualisation of religion, rooted in the secularisation debate, will be connected with Campbell’s [2007. “Who’s Got the Power? Religious Authority and the Internet.” Journal of Computer-Mediated Communication 12 (3): 1043–1062] concept of four layers of religious authority online. The empirical material consists of a joint analysis of German Christian and Polish Catholic Internet forums. In a transnational comparison, the findings show similar tendencies of individualisation and emerging communities of choice, as well as a lasting significance of textual religious authorities, although different levels of authority are negotiated and emphasised to a varying extent. However, in both cases critique of the Church and religion usually emerges offline, and is then expressed online. While the forums do not have a subversive potential, they facilitate adopting a more independent, informed, and reflexive approach to religion.

The projectilic image: Islamic State’s digital visual warfare and global networked affect - Kraidy, Marwan M (Media, Culture & Society, 2017)
Islamic State’s (IS) image-warfare presents an auspicious opportunity to grasp the growing role of digital images in emerging configurations of global conflict. To understand IS’ image-warfare, this article explores the central role of digital images in the group’s war spectacle and identifies a key modality of this new kind of warfare: global networked affect. To this end, the analysis focuses on three primary sources: two Arabic-language IS books, Management of Savagery (2004) and O’ Media Worker, You Are a Mujahid!, 2nd Edition (2016), and a video, Healing the Believers’ Chests (2015), featuring the spectacular burning of a Jordanian air force pilot captured by IS. It uses the method of ‘iconology’ within a case-study approach. I analyze IS’ doctrine of image-warfare explained in the two books and, in turn, examine how this doctrine is executed in IS video production, conceptualizing digital video as a specific permutation of moving digital images uniquely able to enact, and via repetition, to maintain, visual and narrative tension between movement and stillness, speed and slowness, that diffuses global network affect. Using a theoretical framework combining spectacle, new media phenomenology, and affect theory, the article concludes that global networked affect is projectilic, mimicking fast, lethal, penetrative objects. IS visual warfare, I argue, is best understood through the notion of the ‘projectilic image’.
Keywords: digital image; digital video

The House of Netjer: A New Religious Community Online - Krogh, Marilyn C.; Pillfant, Ashley (Religion Online: Finding Faith on the Internet, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression. Religion Online provides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes the Pew Internet and American Life ProjectExecutiveSummary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-defining Cyberspace as SacredSpace.

The Media World of ISIS - Krona, Michael; Pennington, Rosemary (Indiana University Press, 2019)
From efficient instructions on how to kill civilians to horrifying videos of beheadings, no terrorist organization has more comprehensively weaponized social media than ISIS. Its strategic, multiplatformed campaign is so effective that it has ensured global news coverage and inspired hundreds of young people around the world to abandon their lives and their countries to join a foreign war. The Media World of ISIS explores the characteristics, mission, and tactics of the organization's use of media and propaganda. Contributors consider how ISIS's media strategies imitate activist tactics, legitimize its self-declared caliphate, and exploit narratives of suffering and imprisonment as propaganda to inspire followers. Using a variety of methods, contributors explore the appeal of ISIS to Westerners, the worldview made apparent in its doctrine, and suggestions for counteracting the organization's approaches. Its highly developed, targeted, and effective media campaign has helped make ISIS one of the most recognized terrorism networks in the world. Gaining a comprehensive understanding of its strategies―what worked and why―will help combat the new realities of terrorism in the 21st century.

Media logic and the mediatization approach: A good partnership, a mésalliance, or a misunderstanding? - Krotz, F. (Media logic(s) revisited. Transforming communications—Studies in cross-media research, 2018)

The Internet as a Mirror and Distributor of Religious and Ritual Knowledge - Krueger, Oliver (Asian Journal of Social Sciences, 2004)
Since the early 1990s, religious movements appeared on the Internet and introduced new forms of communication in ritual and dogma. Their Internet sites present different dogmatic, institutional, and other aspects of their religion; provide interactive communications and religious services; or simply sell religious items. This paper puts forth the argument that the gaining of ritual and dogmatic knowledge is losing its dependence on direct social interaction in a spatial community, and increasingly relies on Internet-based discourse in religious newsgroups and other discussion forums. Nevertheless, for migrant communities in the diaspora (Zoroastrians, Hindus, and adherents of Afro-American religions), the Internet appears to be offering a new opportunity for re-establishing the spatial bonds of the lost religious community. In other cases such as that of the Wicca religion, this greater independence of traditional religious and social hierarchies encourages the development of fragmentary and syncretic forms of religion.

Methods and Theory for Studying Religion on the Internet: Introduction to the Special Issue on Theory and Methodology - Oliver Krüger (Heidelberg Journal of Religions on the Internet, 2005)
Religious Internet research is just beginning and some of these questions have provoked initial answers – but most of the questions have stimulated even more issues with regard to substantial and methodological demands. The social aspects and consequences of religious Internet use, particularly, still have to be considered in further research. Immanent Internet research offers many new perspectives for religious studies. While traditional media like books, magazines, and television enable us to see only the supplier and the supplies on the religious market, the Internet – as an interactive medium – now makes it possible to be aware of the consumer’s perspective as well. By observing Internet chat rooms, guest books, frequently asked questions (FAQs), and discussion forums and discussion lists (which are normally archived) on religion-related Web sites in particular, we can observe the way religious knowledge is spread in an online community in detail. We can recognize that these new processes of communication create new hierarchies among users in discussion forums. This new diffusion of ritual knowledge, which is nowadays accessible to every Internet user, also signifies changes in the traditional structure of religious communities. However, we still know very little about what people are actually doing with the ritual and religious knowledge that they gain from Internet use. Thus, on the one hand we need to discuss new methodological and theoretical approaches in Internet research but we also have to consider the shortcoming of past approaches.

Discovering the Invisible Internet: Methodological Aspects of Searching Religion on the Internet - Kruger, Oliver (Online: Heidelberg Journal of Religion on the Internet, 2005)

Power vs. influence: Knowing the difference could make or break your company - Kuhel, B. (Forbes.com, 2017)
Beth Kuhel writes about leadership strategies and tips for rising up in the workplace. Connect with Beth on LinkedIn and Twitter @BethKuhel

Starting a Northland house church - Lacich, D. (Northland Wb Log, 2008)

Existential media: Toward a theorization of digital thrownness - Lagerkvist, Amanda (New Media & Society, 2017)
Our digitally enforced lifeworld is an existential and ambivalent terrain. Questions concerning digital technologies are thus questions about human existence. This theoretical essay employs key concepts from existential philosophy to envision an existential media analysis that accounts for the thrownness of digital human existence. Tracing our digital thrownness to four emergent fields of inquiry, that relate to classic themes (death, time, being there, and being-in-and-with-the-world), it encircles both mundane connectivity and the extraordinary limit-situations (online) when our human vulnerability is principally felt and our security is shaken. In place of a savvy user, this article posits the “exister” as the principal subject in media studies and inhabitant of the digital ecology—a stumbling, hurting, and relational human being, who navigates within limits and among interruptions through the torrents of our digital existence, in search for meaning and existential security.

The netlore of the infinite: death (and beyond) in the digital memory ecology - Lagerkvist, Amanda (New Review of Hypermedia and Multimedia, 2015)
In an era that celebrates instantaneity and hyper-connectivity, compulsions of networked individualism coexist with technological obsolescence, amounting to a sense of fragmentation and a heightened tension between remembering and forgetting. This article argues, however, that in our era of absolute presence, a netlore of the infinite is emerging, precisely in and through our digital memory practices. This is visible in the ubiquitous meaning-making practices of for instance personal digital archiving through the urges for self-perpetuation; it is evident at sites where the self may be saved for posterity; it is discernible in the techno-spiritual practices of directly speaking to the dead on digital memorials, as well as in the tendency among some users to regard the Internet itself as a manifestation of eternity, “heaven” and the sacred. This article shows that by approaching digital memory cultures existentially, and by attending to the complexities of digital time, we may gain insights into important and paradoxical aspects of our existential terrains of connectivity. This makes possible an exploration into how people navigate and create meaning in the digital memory ecology—in seeking to ground a sense of the eternal in the ephemeral.

Relational authority and legitimacy in international relations - Lake, D. (American Behavioral Scientist, 2009)
This article develops a theory of relational authority in the most unpromising setting of international relations. Relational authority locates legitimacy in a social contract between a ruler, who provides a social order of value to the ruled, and the ruled, who comply with the ruler’s commands necessary to the production of that order. International politics are nearly universally assumed to be an anarchy devoid of authority. Through the lens of relational authority, however, one sees that relations between states are better described as a rich variety of hierarchies in which dominant states legitimately rule over greater or lesser domains of policy in subordinate states. After contrasting alternative approaches to authority, the article identifies international hierarchies and summarizes a suite of measures that capture variations between the United States and other states. The article then deduces a set of international behaviors that follows from relational authority and demonstrates that (a) the United States is more likely to join international disputes in which its subordinates are involved and (b) subordinates acknowledge the authority of the dominant state by engaging in actions of symbolic obeisance, of which the most costly and salient form is following the United States into war.

Christian Web Sites: Usage and Desires - Laney, Michael (Religion and Cyberspace, 2005)
In the twenty-first century, religious life is increasingly moving from churches, mosques and temples onto the Internet. Today, anyone can go online and seek a new form of religious expression without ever encountering a physical place of worship, or an ordained teacher or priest. The digital age offers virtual worship, cyber-prayers and talk-boards for all of the major world faiths, as well as for pagan organisations and new religious movements. It also abounds with misinformation, religious bigotry and information terrorism. Scholars of religion need to understand the emerging forum that the web offers to religion, and the kinds of religious and social interaction that it enables. Religion and Cyberspace explores how religious individuals and groups are responding to the opportunities and challenges that cyberspace brings. It asks how religious experience is generated and enacted online, and how faith is shaped by factors such as limitless choice, lack of religious authority, and the conflict between recognised and non-recognised forms of worship. Combining case studies with the latest theory, its twelve chapters examine topics including the history of online worship, virtuality versus reality in cyberspace, religious conflict in digital contexts, and the construction of religious identity online. Focusing on key themes in this groundbreaking area, it is an ideal introduction to the fascinating questions that religion on the Internet presents.

CyberFaith: How Americans Pursue Religion Online - Larsen, Elena (2001)
The 25% of Internet users who have searched online for religious information parallel the profile of the American population at large. However, the intensity of religious devotion of “Religion Surfers” distinguishes them from the general population. Some 81% of online Religion Surfers describe their commitment to faith as “very strong,” compared to only 19% of the population as a whole. The top uses of the Internet by Religion Surfers are simply to find information on their own faith or another one. Old-fashioned face-to-face socializing is much more appealing to Religion Surfers than tech-aided interactions with others that are related to faith. In our sample of 500 Religion Surfers, 9% of them had looked for religious or spiritual information via the Internet on the same day we reached them, 26% had gone online for such information within the past week, 29% had made the search within the past month, 26% had made the search in the past six months and 9% had performed the search more than six months ago.

CyberFaith: How Americans Pursue Religion Online - Larsen, Elena (Religion Online: Finding Faith on the Internet, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression. Religion Online provides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes the Pew Internet and American Life Project Executive Summary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-defining Cyberspace as SacredSpace.

Wired Churches, Wired Temples: Taking Congregations and Missions into Cyberspace - Larsen, E. (Pew Internet and American Life Project, 2000)
Keywords: churches; congregations; internet; Missions; temples; wired

5 considerations for digital age leaders - Larson, L.; Miller, T.; Ribble, M. (Learning and Leading with Technology, 2009)

The Death of a Virtual Muslim Discussion Group: Issues and Methods in Analysing Religion on the Net - Larsson, G. (Heidelberg Journal of Religions on the Internet, 2005)
In his article, Göran Larsson analzyes Islamic online discussion group. All the suggested approaches are tested against data taken from the largest Swedish Muslim discussion group, Sveriges Förenade CyberMuslimer (SFCM).
Keywords: communication technology; forum; information; methodology; Muslim minorities; Sweden

Cyber-Islamophobia? The case of WikiIslam - Göran Larsson (Contemporary Islam, 2007)
A large amount of academic research has analysed and documented the fact that Muslims are often presented in a negative or stereotypical way in Western media and popular culture. This article focuses on how the Internet can also be used in spreading and publishing anti-Islamic and anti-Muslim opinions. Although the Internet is significant in the development of contemporary society, no studies have focused on the importance of information and communication technologies in spreading Islamophobic opinions. However, the new technologies can also be used for monitoring and combating Islamophobia, and many Muslim organisations are today using the Internet for these purposes. The article is based on an indepth analysis of both anti-Muslim and pro-Muslim homepages that can be related to the debate over Islamophobia.
Keywords: internet; Islam; Islamophobia; Reactive identities

God on the Internet - Jonathan V. Last (First Things, 2005)
This article discusses the use of blogging by Catholics—both clergy and laity members alike—as a means to express affection for the Pope, dedication to the Magisterium and devotion of God. The author discusses the advantages and shortcomings of the use of such technology for these purposes.

#AmplifyWomen: the emergence of an evangelical feminist public on social media - Laughlin, Corrina (Feminist Media Studies, 2020)
This study conceptualizes the Twitter response to a Christianity Today article that challenged the role of female Christian bloggers as authoritative figures and centered around the hashtag #AmplifyWomen, as an “affective public”. It employs the method of “hashtag ethnography” to investigate it. The article argues that this public points to the beginnings of a connective feminist movement in evangelicalism brought about by the affordances of digital media and makes two moves in service to this assertion. First, it explains that it is through a reliance on the tropes of postfeminism that Christian celebrity bloggers have achieved the level of charismatic authority that they have. And second it tracks how the affective public that emerged to defend them mobilized a tactical rhetoric to resist the dominant patriarchal structures of the traditionally conservative culture of white evangelicalism.

Allah On-Line: The Practice of Global Islam in the Information Age - Lawrence, Bruce. F (Practicing Religion in the age of Media, 2002)
Increasingly, the religious practices people engage in and the ways they talk about what is meaningful or sacred take place in the context of media culture—in the realm of the so-called secular. Focusing on this intersection of the sacred and the secular, this volume gathers together the work of media experts, religious historians, sociologists of religion, and authorities on American studies and art history. Topics range from Islam on the Internet to the quasi-religious practices of Elvis fans, from the uses of popular culture by the Salvation Army in its early years to the uses of interactive media technologies at the Simon Wiesenthal Center's Beit Hashoah Museum of Tolerance. The issues that the essays address include the public/private divide, the distinctions between the sacred and profane, and how to distinguish between the practices that may be termed "religious" and those that may not.

Cultivating the Self in Cyberspace: The Use of Personal Blogs among Buddhist Priests - Lee, J. (Journal of Media and Religion, 2009)
This research attempts to understand the Internet religious practices from the immanent perspective. Since previous research on this subject has been mainly transcendental, this study offers a challenging view using a different perspective. The exploration of cultivating the self in cyberspace revealed that the degree of self-cultivation varies contingent upon the given conditions and the technologies that the priests practice to interact with them. This research has a potential to further the exploration of the interaction of cyberspace and the inner self, expanding the boundary of the study beyond online religious practices. When cyberspace and the self are understood in the plane of consistency, the range of the study about the engagement of the self in the new media can be opened out. Understanding the notions of the process of territorializing intensities and technologies of the self, the engagement of the self in cyberspace can be more specifically developed.
Keywords: blogs; cyberspace; Self

Ritualwell.Org -- Loading the Virtual Canon, or: The Politics and Aesthetics of Jewish Women's Spirituality - Lefkovitz, Lori. H; Shapiro, Rona (Nashim: A Journal of Jewish Women's Studies & Gender Issues, 2005)
Keywords: Jewish; Politics; Women

Holy Pirates: Media, Ethnicity and Religious Renewal in Israel - Lehamann, David; Siebzehner, Batia (Religion, Media & the Public Sphere, 2006)
"... one of those rare edited volumes that advances social thought as it provides substantive religious and media ethnography that is good to think with."—Dale Eickelman, Dartmouth College Increasingly, Pentecostal, Buddhist, Muslim, Jewish, Hindu, and indigenous movements all over the world make use of a great variety of modern mass media, both print and electronic. Through religious booklets, radio broadcasts, cassette tapes, television talk-shows, soap operas, and documentary film these movements address multiple publics and offer alternative forms of belonging, often in competition with the postcolonial nation-state. How have new practices of religious mediation transformed the public sphere? How has the adoption of new media impinged on religious experiences and notions of religious authority? Has neo-liberalism engendered a blurring of the boundaries between religion and entertainment? The vivid essays in this interdisciplinary volume combine rich empirical detail with theoretical reflection, offering new perspectives on a variety of media, genres, and religions.

The Guide to the Jewish Internet - Levin, Michael (No Starch Press, 1996)
Prepare to enter a cyber-neighborhood—a vast community of Jewish cooks, singles, kids, writers, musicians, sports lovers, travelers, history buffs, Holocaust survivors, religious students and families. Acclaimed novelist Michael Levin is your affable guide to the Jewish Internet, adding bits of Jewish culture and commentary to over 800 insightful reviews of Jewish oriented Internet resources, including webpages, gopher menus, FTP sites, and mailing lists.

Prayer, Pop and Politics: Researching Religious Youth in Migration Society - Limacher, Katharina; Mattes, Astrid; Novak, Christoph (V&r Unipress, 2019)
This interdisciplinary volume presents research at the intersection of religion, age and race and tackles the question what it is like to be young and religious in a migration society. The chapters' foci range from digital and offline activism of religious youth to participatory action research projects on radicalisation prevention. The authors present research on various religious traditions, and apply an array of different theoretical angles including feminist, post- and de-colonial perspectives. In going one step further, the volume engages in the debate over novel conceptual frameworks attuned to investigate contemporary manifestations of youth religiosity, for example in digital spaces. The methodological chapters strongly advocate for reflexivity in the context of empirical research on religion in migration society. In discussing the implications of insider and outsider positions in research, as well as researchers' privileges and the challenges in concept operationalization, it promotes a self-evaluative assessment of researchers' positionalities.

Authority: Construction and corrosion - Lincoln, B. (University of Chicago Press, 1994)
What is authority? How is it constituted? How ought one understand the subtle (and sometimes not-so-subtle) relations between authority and coercion? Between authorized and subversive speech? In this fascinating and intricate analysis, Bruce Lincoln argues that authority is not an entity but an effect. More precisely, it is an effect that depends for its power on the combination of the right speaker, the right speech, the right staging and props, the right time and place, and an audience historically and culturally conditioned to judge what is right in all these instances and to respond with trust, respect, and even reverence. Employing a vast array of examples drawn from classical antiquity, Scandinavian law, Cold War scholarship, and American presidential politics, Lincoln offers a telling analysis of the performance of authority, and subversions of it, from ancient times to the present. Using a small set of case studies that highlight critical moments in the construction of authority, he goes on to offer a general examination of "corrosive" discourses such as gossip, rumor, and curses; the problematic situation of women, who often are barred from the authorizing sphere; the role of religion in the construction of authority; the question of whether authority in the modern and postmodern world differs from its premodern counterpart; and a critique of Hannah Arendt's claims that authority has disappeared from political life in the modern world. He does not find a diminution of authority or a fundamental change in the conditions that produce it. Rather, Lincoln finds modern authority splintered, expanded, and, in fact, multiplied as the mechanisms for its construction become more complex—and more expensive.

Internet and Religion. The Making of Meaning, Identity And Community Through Computer Mediated Communication - Linderman, Alf; Lövheim, Mia (Mediating Religion: Conversations in Media, Culture and Religion, 2003)
This is the first book to bring together many aspects of the interplay between religion, media and culture from around the world in a single comprehensive study. Leading international scholars provide the most up-to-date findings in their fields, and in a readable and accessible way. 37 essays cover topics including religion in the media age, popular broadcasting, communication theology, popular piety, film and religion, myth and ritual in cyberspace, music and religion, communication ethics, and the nature of truth in media saturated cultures.

Discursive legitimation of a controversial technology: Ultra-Orthodox Jewish women in Israel and the Internet - Livio, o.; Tenenboim Weinblatt, K. (The Communication Review, 2007)
The introduction of the internet to ultra-Orthodox Jewish society has presented an acute dilemma. While seen as a potential carrier of secular values and officially banned, the internet also presents significant socio-economic opportunities for a community in which women are often the sole providers. This research focuses on the discursive strategies ultra-Orthodox women internet users employ to legitimate their use of this controversial technology. A glaring disparity was observed between these women's actual, subversive technology-related practices and the rhetorical construction of the same practices, which attempted to portray them as congruent with community values. We suggest that when investigating the domestication of new technologies, examining technology-related discourse may be no less important than the more common to date focus on practice.

Web of meanings: Dilemmatic aspects of ultra-orthodox Jewish women’s discourse concerning the Internet - Oren Livio; Keren Tenenboim (2004)
Paper presented at Internet Research 5.0, University of Sussex, England.
Keywords: GENDER; internet; Israeli society; Jews; Modernity; Ultra-Orthodox Jewish

Shifting Realities: Information Technology and the Church - Lochhead, David (WCC Publications, 1997)
Information technology is changing the world in ways that profoundly affect us whether or not we ever use a computer. While some Christians greet these developments with enthusiasm and others with alarm, most seem to regard them with uncertainty and ambivalence. The author describes how churches are discovering ecumenical applications of new technologies, and explores the relation between Christian understandings of the "Word" and contemporary information technologies; the "underside" of information technology (threats to privacy and the availability of hate literature and pornography on the Internet); and what all this does to our perceptions of reality and the way the Christian gospel is communicated today.
Keywords: Church; information; technology

A Voice of Their Own. Young Muslim Women, Blogs and Religion - Lövheim, M (Mediatization and Religion: Nordic Perspectives, 2012)
Keywords: blogs; Internet Mediatization of Religion; Islam; Media studies; mediatization of religion; Muslim Women and media; New Media and Society; new media research; Nordic perspective; religion and culture

Identity - Lövheim, M. (Digital Religion: Understanding Religious Practice in New Media Worlds, 2012)
Digital Religion offers a critical and systematic survey of the study of religion and new media. It covers religious engagement with a wide range of new media forms and highlights examples of new media engagement in all five of the major world religions. From cell phones and video games to blogs and Second Life, the book: provides a detailed review of major topics includes a series of case studies to illustrate and elucidate the thematic explorations considers the theoretical, ethical and theological issues raised. Drawing together the work of experts from key disciplinary perspectives, Digital Religion is invaluable for students wanting to develop a deeper understanding of the field.
Keywords: Digital; identity; religion

The mediatisation of religion debate: an introduction - Lövheim, M; Lynch, G (Culture and Religion, 2011)
Within the growing literature on religion and media, a more specific debate has recently developed in relation to the mediatisation of religion. The Danish scholar, Stig Hjarvard, has undertaken leading work in articulating a detailed theory of the mediatisation of religion, arguing that contemporary religion is increasingly mediated through secular, autonomous media institutions and is shaped according to the logics of those media. This special issue is the first extended discussion of Hjarvard's thesis by researchers working across different disciplines and areas of study. This introduction sets out the background and key concepts for this debate, discusses why the mediatisation of religion debate is important for sociological and cultural understandings of contemporary religion, and provides a brief summary of the arguments of the individual articles within this collection.
Keywords: mediatisation; religion

Virtually boundless? Youth negotiating tradition in cyberspace - Lövheim, M. (Everyday Religion. Observing Modern Religious Lives, 2007)
Social scientists sometimes seem not to know what to do with religion. In the first century of sociology's history as a discipline, the reigning concern was explaining the emergence of the modern world, and that brought with it an expectation that religion would simply fade from the scene as societies became diverse, complex, and enlightened. As the century approached its end, however, a variety of global phenomena remained dramatically unexplained by these theories. Among the leading contenders for explanatory power to emerge at this time were rational choice theories of religious behavior. Researchers who have spent time in the field observing religious groups and interviewing practitioners, however, have questioned the sufficiency of these market models. Studies abound that describe thriving religious phenomena that fit neither the old secularization paradigm nor the equations predicting vitality only among organizational entrepreneurs with strict orthodoxies. In this collection of previously unpublished essays, scholars who have been immersed in field research in a wide variety of settings draw on those observations from the field to begin to develop more helpful ways to study religion in modern lives. The authors examine how religion functions on the ground in a pluralistic society, how it is experienced by individuals, and how it is expressed in social institutions. Taken as a whole, these essays point to a new approach to the study of religion, one that emphasizes individual experience and social context over strict categorization and data collection.

A Space Set Apart? Young People Exploring The Sacred On The Internet - Lövheim, Mia (In Implications of the Sacred in (Post)Modern Media, 2006)

Mediatization: analyzing transformations of religion from a gender perspective - Lövheim, M (Media, Culture & Society, 2016)
This book presents new research on the changing relationship between the media, religion and culture from a Nordic perspective, while engaging with the theory of the mediatization of religion. In contemporary society, news journalism, film and television series, as well as new digital media, provide critical commentary on religion while also enabling new forms of religious imagery and interaction. Religious leaders, communities and individuals reflexively negotiate their presence within this new mediatized reality. In an increasingly globalized Nordic context, the media have also come to play an important role in the performance of both individual and social identities, and in the representation and development of social and religious conflicts. Through empirical analysis and theoretical discussions, scholars from film and media studies, the sociology of religion, and theology contribute to the development of the theory of the mediatization of religion as well as to the broader research field of media, religion and culture.
Keywords: GENDER; mediatization; public sphere; religion

The Mediatized Conditions of Contemporary Religion: Critical Status and Future Directions - Lövheim, Mia; Hjarvard, Stig (Journal of Religion, Media and Digital Culture, 2019)
During the last decade the framework of mediatization theory has been introduced in the field of media, religion and culture as a parallel perspective to the “mediation of religion” approach, allowing new questions to be posed that align with religious change within Europe. This article provides a critical review of existing research applying mediatization of religion theory, focusing on key issues raised by its critics as well as how the theory have moved the research field forward. These issues concern the concept of religion, institution and social change, religious authority, and the application of mediatization theory outside the North-Western European context where it originated. The article argues that an institutional approach to mediatization is a relevant tool for analyzing change as a dynamic process in which the logics of particular forms of media influence practices, values and relations within particular manifestations of religion across various levels of analysis.

Intersecting Identities: Young People, Religion and Interaction on the Internet - Lövheim, Mia (Uppsala University, 2004)
The growth of the Internet gave rise to many anticipations and apprehensions of how the new medium would affect the construction of meaning, individual identities, and social interaction. As humanity’s oldest expression of existential meaning, religion provides a challenging case for such studies. This study approaches these issues through an analysis of how 15 young Swedish men and women experience and use a particular web community, the Site, in constructing religious identities. The study took place during the year 2000, through a combination of online observations, offline interviews and text analysis. Starting from Ammerman’s concept of religious “autobiographies” - the individual self as constructed in interactions with religious discourses throughout life - the study argues that the Internet can become a significant resource in this process, but that this possibility is structured by certain conditions. An analysis of the ”repertoire of possibilities” of the Site – formed by the range of discourses, social relations, rules of interaction, and mode of communication – shows that these conditions contribute to polarized interactions and stereotyped identities, which restrict possibilities to further explore, question or reassess convictions and boundaries. The analysis of individual strategies for negotiating these conditions shows that intentions, dilemmas and competences in the individual’s repertoire of experiences affect when, how and for whom the Internet can become this resource. Finally, the study points to some significant conditions in the offline context which affect the process. The study outlines a framework, based on Linderman’s model of social semeiology, Slevin’s theory of the Internet and cultural transmission, and Fairclough’s discourse analysis, for the analysis of particular cases of meaning construction on the Internet. Furthermore, this framework suggests ways in which a case of religious identity construction on the Internet can be related to theories about transformation of religion and identities in late modern society.

Young People, Religious Identity and the Internet - Lövheim, Mia (Religion Online: Finding Faith on the Internet, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression. Religion Online provides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes the Pew Internet and American Life Project Executive Summary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-defining Cyberspace as SacredSpace.

Rethinking cyberreligion? Teens, religion and the Internet in Sweden - Mia Lovheim (Nordicom Review, 2008)
Since the coming of the Internet scholars have been discussing its implications for the future of religion. With its high levels of Internet use and low levels of religious practice Sweden represents an interesting case for studying these issues. This article presents findings from the first online survey of Swedish teenager’s use of the Internet for religious purposes, conducted at one of the largest social networking sites LunarStorm. The results show that more young people seem to come into contact with religion via the Internet than through local religious communities. However, the findings also challenge several early expectations about the Internet as a new arena for religion in contemporary society. Thus the article initiates a critical discussion of what conclusions may be drawn from these results, and where future research on young people, religion and the Internet should be directed.
Keywords: internet; religious change; social networking sites; Sweden; teenagers

Young People and the Use of the Internet as Transitional Space - Mia Lovheim (Online: Heidelberg Journal of Religion on the Internet, 2005)
Keywords: internet; Transition; Young

Gender, religion & authority in digital media - Lövheim, M. (Ruhr University-Bochum, Germany, 2019)

Media, Religion and Gender: Key Issues and New Challenges - Lövheim, Mia (Routledge, 2013)
Media, Religion and Gender presents a selection of eminent current scholarship that explores the role gender plays when religion, media use and values in contemporary society interact. The book: surveys the development of research on media, religion and culture through the lens of key theoretical and methodological issues and debates within gender studies. includes case studies drawn from a variety of countries and contexts to illustrate the range of issues, theoretical perspectives and empirical material involved in current work outlines new areas and reflects on challenges for the future. Students of media, religion and gender at advanced level will find this a valuable resource, as will scholars and researchers working in this important and growing field.

Constructing Religious Identity on the Internet - Lövheim, Mia; Linderman, Alf G (Religion and Cyberspace, 2005)
In the twenty-first century, religious life is increasingly moving from churches, mosques and temples onto the Internet. Today, anyone can go online and seek a new form of religious expression without ever encountering a physical place of worship, or an ordained teacher or priest. The digital age offers virtual worship, cyber-prayers and talk-boards for all of the major world faiths, as well as for pagan organisations and new religious movements. It also abounds with misinformation, religious bigotry and information terrorism. Scholars of religion need to understand the emerging forum that the web offers to religion, and the kinds of religious and social interaction that it enables. Religion and Cyberspace explores how religious individuals and groups are responding to the opportunities and challenges that cyberspace brings. It asks how religious experience is generated and enacted online, and how faith is shaped by factors such as limitless choice, lack of religious authority, and the conflict between recognised and non-recognised forms of worship. Combining case studies with the latest theory, its twelve chapters examine topics including the history of online worship, virtuality versus reality in cyberspace, religious conflict in digital contexts, and the construction of religious identity online. Focusing on key themes in this groundbreaking area, it is an ideal introduction to the fascinating questions that religion on the Internet presents.

Media and religion: Bridging ‘incompatible agendas’ - Lövheim, M (Foundations and Futures in the Sociology of Religion, 2018)
This chapter addresses the challenge of finding adequate theories for understanding the growing complexity of the religious situation in Europe and the rest of the world through discussing the insights that can be gained through engagement with theories of the role of media in contemporary society. Various forms of media have become pivotal arenas for the new visibility of religion in Europe. While sociologists of religion are becoming more sensitive to these developments, they continue to lack the conceptual tools to adequately analyse what this means for the role and presence of religion in contemporary society. Following Grace Davie’s (2000) exploration of the incompatible agendas between sociologists of religion on the one hand and media scholars on the other, the aim of this chapter will be to highlight the changes currently taking place and the emerging potential for closer dialogue between these two factions in the future.
Keywords: media; religion

Considering Critical Methods and Theoretical Lenses in Digital Religion Studies - Lövheim, M; Campbell, H (New Media and Society, 2017)
This article introduces a special issue on critical methods and theoretical lenses in Digital Religion studies, through contextualising them within research trajectories found in this emerging field. By starting from the assertion that current “fourth-wave of research on religion and the Internet,” is focused on how religious actors negotiate the relationships between multiple spheres of their online and offline lives, article authors spotlight key theoretical discussions and methodological approaches occurring within this interdisciplinary area of inquiry. It concludes with notable methodological and theoretical challenges in need of further exploration. Together it demonstrates how religion is practiced and reimagined within digital media spaces, and how such analysis can contribute to broader understanding of the social and cultural changes new media technologies are facilitating within society.
Keywords: Digital Religion; internet; media technologies; methodology; religion; theory

Theoretical Framework for Approaching Religion and New Media - Lundby, Knut (Digital Religion: Understand Religious Practice in New Media Worlds, 2012)
Keywords: method; theory

Mediatization of Communication - Lundby, Knut (De Gruyter Mouton, 2014)
This handbook on Mediatization of Communication uncovers the interrelation between media changes and changes in culture and society. This is essential to understand contemporary trends and transformations. "Mediatization" characterizes changes in practices, cultures and institutions in media-saturated societies, thus denoting transformations of these societies themselves.This volume offers 31 contributions by leading media and communication scholars from the humanities and social sciences, with different approaches to mediatization of communication. The chapters span from how mediatization meets climate change and contribute to globalization to questions on life and death in mediatized settings.The book deals with mass media as well as communication with networked, digital media. The topic of this volume makes a valuable contribution to the understanding of contemporary processes of social, cultural and political changes.The handbook provides the reader with the most currentstate of mediatization research.

Dreams of Church in Cyberspace - Knut Lundby (Digital religion, social media and culture: Perspectives, Practices and Futures, 2012)
Keywords: Blogging; Church; cyberspace; mission; Networked individualism; social networks; virtual community; Virtual environments; Virtual World; virtuality

Digital Storytelling, Mediatized Stories. Self-representations in New Media - Lundby, K. (Peter Lang, 2008)
Recent years have seen amateur personal stories, focusing on «me, flourish on social networking sites and in digital storytelling workshops. The resulting digital stories could be called «mediatized stories. This book deals with these self-representational stories, aiming to understand the transformations in the age-old practice of storytelling that have become possible with the new, digital media. Its approach is interdisciplinary, exploring how the mediation or mediatization processes of digital storytelling can be grasped and offering a sociological perspective of media studies and a socio-cultural take of the educational sciences. Aesthetic and literary perspectives on narration as well as questioning from an informatics perspective are also included.

Transforming Faith-based Education in the Church of Norway: Mediation of Religious Traditions and Practices in Digital Environments - Knut Lundby (Studies in World Christianity, 2006)
The mediated life-world of children and youth in contemporary, media-rich societies raises challenges for Christian education. The specific 'digital environments' of communication and social interaction with digital devices on digital networks make a critical context as well as new opportunities for religious education. In 2003 the parliament in Norway decided upon a reform of religious education outside the schools. The Christian churches, other religious communities and organised humanists were invited to make their own training programmes, to be funded by the government. In the white book to the parliament the government stated that use of digital technology and the Internet would be 'a natural part' of the new faith-based education reform in the country. Digital environments challenge and transform the faith-based education. However, this new programme itself transforms religious education in Norway.
Keywords: Christian Churches; Christian education; digital environments; faith-based education; government; media societies

Contested Communication. Mediating the Sacred - Lundby, Knut. (Implications of the Sacred in (Post)Modern Media, 2006)
In recent years, there has been growing awareness across a range of academic disciplines of the value of exploring issues of religion and the sacred in relation to cultures of everyday life. Exploring Religion and the Sacred in a Media Age offers inter-disciplinary perspectives drawing from theology, religious studies, media studies, cultural studies, film studies, sociology and anthropology. Combining theoretical frameworks for the analysis of religion, media and popular culture, with focused international case studies of particular texts, practices, communities and audiences, the authors examine topics such as media rituals, marketing strategies, empirical investigations of audience testimony, and the influence of religion on music, reality television and the internet.Both academically rigorous and of interest to a wider readership, this book offers a wide range of fascinating explorations at the cutting edge of many contemporary debates in sociology, religion and media, including chapters on the way evangelical groups in America have made use of The Da Vinci Code and on the influences of religion on British club culture and electronic dance music.
Keywords: Communication; media; Sacred

Religion between Politics and Media: Conflicting Attitudes towards Islam in Scandinavia - Lundby, K; Hjarvard, S; Lövheim, M; Jernsletten, H.H (Journal of Religion in Europe, 2017)
Based on a comparative project on media and religion across Denmark, Norway, and Sweden, this article analyzes relationships between religiosity and political attitudes in Scandinavia and how these connect with attitudes regarding the representation of Islam in various media. Data comes from population-wide surveys conducted in the three countries in April 2015. Most Scandinavians relate ‘religion’ with conflict, and half of the population perceives Islam as a threat to their national culture. Scandinavians thus perceive religion in terms of political tensions and predominantly feel that news media should serve a critical function towards Islam and religious conflicts. Finally, the results of the empirical analysis are discussed in view of the intertwined processes of politicization of Islam and mediatization of religion.
Keywords: Islam; media; Politics; religion; Scandinavia

Media and transformations of religion - Lundby, K (Religion across Media: From Early Antiquity to Late Modernity, 2013)
Keywords: media; religion

Unorganized atheism and the secular movement: reddit as a site for studying ‘lived atheism’ - Lundmark, Evelina; LeDrew, Stephen (Social Compass, 2019)
This article examines discussions on the reddit.com forum r/atheism in comparison with rhetoric found in contemporary atheist organizations and among leading figures within the atheist movement. We demonstrate how the culture of r/atheism converges with that of formal atheist cultures, most importantly regarding understandings of rationality and how religious people deviate from it, while highlighting areas of tension regarding how to relate to religion and religious people. We conclude that the social experience of community and belonging appears to be as important as other more instrumental goals commonly adopted by secular activists, and that tensions regarding the practice of atheism and the purpose of the forum correspond to tensions found in formal institutional contexts. We thus argue that while r/atheism is not directly or explicitly affiliated with atheist activism, overlap in the nature of discussion and debates is sufficient to consider the forum another window into the development of a general atheist culture practiced in institutional contexts and at the everyday level of ‘lived’ atheism.

Algorithmic authority: The ethics, politics, and economics of algorithms that interpret, decide, and manage - Lustig, C.; Pine, K.; Nardi, B.; Irani, L.; Lee, M. K.; Nafus, D.; Sandvig, C. (2016)
CHI 2016 is the premier world-wide conference for Human-Computer Interaction (HCI) and this year took place in the heart of Silicon Valley, San Jose, California. The Proceedings and Extended Abstracts represent today's most innovative, novel and creative work in HCI. These Proceedings and Abstracts have added over one-thousand documents in the ACM Digital Library. Across all tracks, CHI received nearly 5000 submissions and accepted over 1000 that can be seen today. These include almost 600 rigorously reviewed papers and notes selected from over 2200 submissions. These Proceedings and Abstracts also document two days of workshops, symposia and meetings involving over 800 participants, a record number for CHI conferences. The CHI 2016 conference includes two days of focused workshops and four days of technical content, including CHI's prestigious technical program, with 16 parallel sessions of rigorously reviewed research Papers, engaging Panels, Case Studies and Special Interest Groups (SIGs), Conference highlights also include student research, design, and game competitions, and last-minute SIGs for discussing current topics. The popular alt.chi forum enters its eleventh year of provocation within the HCI community. The conference also showcases Interactivity and Interactivity Research Demos, which are hands-on demonstrations of the best in technology and innovation. And we're particularly proud this year to include documents from our new Art Exhibition, held at the Works/San Jose Gallery in conjunction with the CHI conference. We began our conference planning process with three core ideas: "CHI in Silicon Valley": emphasizing local engagement in this vibrant community, "#chiforgood": HCI in the community, both during the workshop time and at appropriate points during the conference, and a "More Humane Conference and Planning Process": lots of transparency, early planning, no surprises, data-driven decisions and taking into account the importance of families, work/life balance, and the like. From this, the overall theme of the conference emerged, #chi4good: addressing issues of social good through the innovation and creativity of the CHI community. To this end we held a Day of Service on the Saturday before the conference with hundreds of CHI attendees working on projects for non-profit and area arts organizations, and we have continued that theme throughout the conference by hosting the Diversity and Inclusion Lunch, brought childcare back to the conference for the first time in many years, and introduced the lunch@chi program to facilitate small group lunches on the first day of the conference. We've introduced CHI's first Diversity & Inclusion Statement, and our keynote speakers, represent the vibrancy, diversity and excitement of the wide field of HCI with particular emphasis on #chi4good. This year's speakers were chosen from among crowd-sourced suggestions from the CHI community and they are: Dayo Olopade, (Journalist and author of The Bright Continent); Kimberly Bryant (Founder, Black Girls Code), in conversation with Sarah Guthals, (Co-Founder of ThoughtSTEM); Marissa Meyer (President & CEO of Yahoo), in conversation with Terry Winograd (Professor Emeritus, Stanford University); Vishal Sikka (CEO of Infosys), in conversation with computing pioneer Alan Kay (Viewpoints Research Institute); and Salman Khan (founder, Khan Academy). With careful consultation from the community, we have enhanced the CHI conference experience from submission and review processes, to more participation possibilities at the conference. Peer-reviewed papers have more space for references and will receive a wider range of better-matched reviews. There are more curated venues and more input into the selection of keynote speakers.

Algorithmic authority: The case of bitcoin - Lustig, K.; Nardi, B. (2015)

Digital Catholicism: The Internet and the Vatican - Lynch, A.P. (Global Catholicism in the Twenty-first Century, 2018)
This chapter argues that the Catholic Church’s presence on the Internet contributes to the formation of “digital Catholicism”, an engagement by the Church with the users of the digital domain through online technologies in a post-secular world. The Vatican’s website includes a wide range of information, from papal encyclicals to the latest feed from the Pope’s Twitter account. The website poses a number of questions relevant to the study of religion in a digital age: How is the website’s construction modelled on the corporate structure of the real-world Church? How does the website’s design reflect the Church’s geographic relationship to its members? And to what degree does the website encourage interaction with its users? The chapter critically assesses these questions, and how the Vatican website contributes to the Catholic Church’s concern, especially since the aggiornamento of Vatican II, to keep the Church relevant in the context of secularisation. Furthermore, how the website reflects the Church’s awareness of the importance of new communication technologies in a post-secular landscape, as expressed in the Vatican II documents Inter Mirifica and Communio et Progressio, and more recently “The Church and Internet”, is assessed. Finally, unofficial Catholic websites, those run by laypeople seeking to raise awareness about issues important to them, will be analysed as examples of Internet use for religious purposes that lies outside of the control of religious organisations such as the Catholic Church.
Keywords: Catholicism; Digital Religion; internet; Vatican

The Sacred in the Modern World: A Cultural Sociological Approach - Lynch, Gordon (Oxford University Press, 2014)
The central aim of this book is to provide a theoretical framework for using the concept of the sacred as a tool for social and cultural analysis. It differentiates between ontological theories of the sacred which locate the sacred in the essence of the cosmos or the human person, and a cultural sociological approach which understands the sacred as culturally constructed. Adopting the latter, a critical re-reading is given of Emile Durkheim’s understanding of the sacred, and of later theoretical contributions made by Edward Shils, Robert Bellah, and Jeffrey Alexander. Using this framework, the intersection of multiple sacred forms is used to analyse the cultural meanings surrounding the systemic abuse and neglect of children within the Irish industrial school system. The role of public media in circulating sacred meanings is also discussed, and the case of the BBC’s refusal to air a humanitarian appeal for Gaza in 2009 is explored to demonstrate the tensions between the sacred function of public media and journalistic notions of impartiality. The book concludes by examining whether human society without sacred forms is possible, and argues that the communicative structure of the sacred underlies the very notion of moral, human society. A critical approach to the sacred is required which involves both a recognition of the harm that can be done through the pursuit of sacred commitments, and the development of critical practices that make it possible to understand the significance of the sacred in social life.
Keywords: child abuse; cultural sociology; Edward Shils; Emile Durkheim; industrial schools; Jeffrey Alexander; media; Robert Bellah; Sacred

Would God Use Email? - Lyon, D. (Zadok Perspectives, 2001)
Email is an ever-present tool of communication. It is used in business, among community groups, between friends and within families. But what is appropriate use? Are there occasions when email is inappropriate? David Lyon suggests a framework for answering these questions.
Keywords: email; God; religion

Techno-Ritualization : the Gohozon Controversy on the Internet - Marc MacWilliams (Online – Heidelberg Journal of Religions on the Internet, 2006)
In Techno-Ritualization – The Gohozon Controversy on the Internet, Mark MacWilliams describes the case of the “Gohonzon”, Nichiren’s sacred mandala consisting of the title of the Lotus Sutra that is used for worship in the various Nichiren Buddhist sects. Whereas this mandala is generally considered as extremely sacred and it is demanded that it should be housed in the home altar and only displayed privately for devotional chanting, it can nowadays be found on the Internet as a “prayer Gohonzon” from the American Independent Movement, a Buddhist group unaffiliated with the official authority Sôka Gakkai International (SGI). The Internet site offers a virtual altar with a fully displayed Gohonzon, twinkling lighted candles before it, and the chant, “Namu Myoho Renge Kyo,” flashing syllable by syllable on the screen. MacWilliam underlines the power of the Internet to transform religious practice with the example of the virtual prayer and to challenge real life ecclesiastical organizations: the way the Internet is being used is transforming the way people “do” religion.
Keywords: Digital Religion; Gohonzon; Lotus Sutra; Nichiren; Nichiren Buddhist sects; religion; Ritual; sacred mandala; Sôka Gakkai; worship

Introduction to the Symposium - MacWilliams, Mark (Religion, 2002)

Virtual Pilgrimage to Ireland’s Croagh Patrick - MacWilliams, M (Religion Online: Finding Faith on the Internet, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression. Religion Online provides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes the Pew Internet and American Life Project Executive Summary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-defining Cyberspace as Sacred Space.

Techno-Ritualization: The Gohozon Controversy on the Internet - MacWilliams, Marc (Heidelberg Journal of Religions on the Internet, 2006)

New media and Islamism in the Arab Winter: A case study of Huda TV in pre-revolutionary Egypt - Maguire, Thomas E. R. (Journal of Arab & Muslim Media Research, 2012)
Although Islam promises to play an increasing role in the public life of Muslim societies, scholarly analysis often falls short in comprehending the complex and diverse nature of this revival. As Middle Eastern societies open to wider public participation, the emergence of an active Muslim polity seems irrepressible. Yet onlookers from afar worry that Islam will only find political expression through narrow and intolerant ideologies that subvert democratic principles. This article seeks to understand the complex evolution of Islamism, and explain how its restricted and often superficial expression through media may reflect a stunted beginning rather than a permanent state of regressive fundamentalism. Through a case study of Huda TV in the era immediately preceding the rise of social media, this article shows how the powerfully repressive context of Middle Eastern media ensured the enduring stagnation of a nascent political discourse.
Keywords: Arab Winter; Islam; New Media

Religion and Media - Jeffrey Mahan (Religion Compass, 2012)
This essay describes the emerging field of religion and media and outlines key issues at play in the field. The field focuses both on the media and their content and on the reception of media among various publics as ways to examine the location of religion, the nature of religious practice and the complexity of religious identity and authority. On the one hand, studies reveal how religious institutions and leaders use traditional and new media, and command of emerging media grants some institutions and leaders increased voice and authority. On the other, we find evidence that in the emerging media culture, authority shifts from traditional locations such as sacred writings, traditions and religious authorities to the individual internal authority of religious consumers involved in religious self-construction. Those in the field typically argue that religion has always been mediated and that studying the mediation of religion is necessary to the understanding of religion. There is a great deal of religion, or something that looks a great deal like religion, to be found online and in modern media. Students in a Colorado bible college celebrate communion online, leading to online discussion by their denomination’s theologians of whether this is appropriate (J. Dulce, personal conversation). In Ghana Christian videographers create popular melodramas that portray traditional African religious practice as spiritually powerful but evil (Mitchell in Mitchell & Plate 2007). American Mormons use media to correct what they see as media misrepresentations of their faith. In the cyberspace environment of “Second Life” it is possible to worship online at Temple Beit Israel (Crabtree 2007) while in Israel Orthodox Jews create web browsers that block material inappropriate for religious Jews (Campbell 2010). And, Elvis fans make seemingly religious pilgrimage to his home (Doss 1999). In these examples what seem to be “two ontologically distinct spheres – the spiritual and the technological – collide” (Meyer 2009, p. 1). This activity has not gone unnoticed by scholars. There is vibrant interdisciplinary conversation about religion and media in fields including religious and theological studies, cultural studies, media studies, art history, anthropology and sociology. The conversation considers what attention to media and mediation tells us about the nature of religion itself. Methodologically, social scientific and cultural study approaches predominate. The conversation emerged out of research in quite varied cultural contexts and has found location in scholarly associations including the Society for the Scientific Study of Religion, the American Academy of Religion and the Society for Biblical Literature. It began to find independent organizational structure with an invitational meeting held in Uppsala, Sweden, in 1994. This led to the establishment of the International Study Commission on Religion, Media and Culture (1996–2005) whose work has continued in a series of international conferences with meetings in Boulder (1996), Edinburgh (1999), Louisville (2004), Sigtuna (2006), Sao Paulo (2008) and Toronto (2010). Work is underway to establish the International Society for Media, Religion and Culture at the conference scheduled to be held in Eskisehir, Turkey (2012). Key areas of study include: • How religious practitioners, movements and institutions use media and are shaped by their adoption or rejection of new forms of media• The interpretation of the way they are portrayed in media and• How they attempt to control media content.But, also • The appearance of religious themes and images in popular entertainment• The ritual use of seemingly secular entertainment and• The fetishization and consumption of religious images and objects.We know that “religion” is a complex phenomenon uniting diverse practices and beliefs. The same can be said about “media”. We ought not to talk too easily about “the media” in the singular as though there were a single media message, impact or interaction with religion. While together the various media may constitute media cultures, our examples are of a particular form of religion and a particular medium in cultural context. Many of the participants in this conversation are located in media studies departments and they are likely to define their work as being about “Media and Religion”. This reversal of the terms is worth noting. Just as religion scholars argue that the connection helps them to understand and define religion, colleagues in media studies suggest that it helps them understand media more clearly. They argue that media does not simply treat religion as a subject; but carry out some of religion’s ritual and interpretive functions. With the establishment of the regular study of religion and media within the guilds and the launching of a scholarly society, it becomes appropriate to recognize “religion and media” as a distinct interdisciplinary field. This essay identifies the field and points to some key figures, concerns and insights while recognizing that, as with any emerging field, much remains in flux.

The Irish Catholic Church and the Internet - Catherine Maignant (New Hibernia Review, 2017)
Nevertheless, in spite of resistances and initial smiles, the internet has become more than a key communication channel for the Catholic church; it has, in the minds of many, become a potential transformational force. Numerous commentators have suggested that the impact of the digital age on religion is likely to be as revolutionary as the invention of the printing press.6 The medium is in a position to influence the language of the church, the nature of its interactions with the faithful, and its very understanding of time and space. The official discourse remains that regardless of the medium in which the church delivers its message, the fundamental message does not change. But this question, too, is up for discussion, especially as the church is unable to control the matrix of online culture. For now, it appears that the Catholic church is merely seeking to seize the opportunities provided by the new digital age and respond to its challenges, while continuing to carry out out its traditional mission and trying to restore confidence in itself as an institition.
Keywords: Catholic Church; internet

The Irish Catholic Church and the Internet - Maignant, C (New Hibernia Review, 2017)
In an article about the current state of the Catholic church in Ireland published in an Italian Jesuit magazine in 2017, the former Irish provincial Gerry O'Hanlon wrote that the challenge for the Irish church today was "to re-awaken the need for salvation and the Good News of the Gospels within a culture which experiences no such need."1 Back in 2004, another Jesuit, writing in the Review of Ignatian Spirituality, had already warned that "effective advertising and marketing" were crucial" to "develop a fresh image" of the Catholic church, one that would be more likely to "capture the imagination of [its] customers."2 The emergence and growth of the church's digital strategy in Ireland must be understood against this background, as one of many attempts to avoid becoming what Archbishop Diarmuid Martin once called "an irrelevant minority culture.
Keywords: Catholic Church; internet; Irish

User need and experience of Hajj mobile and ubiquitous systems: Designing for the largest religious annual gathering - Majrashi, K; Borsci, S (Cogent Engineering, 2018)
The Hajj pilgrimage is one of the largest annual events in the world. Each year, millions of Muslims visit the holy sites in Makkah. While Hajj mobile applications that help pilgrims perform Hajj activities efficiently are gaining popularity, little has been done to investigate pilgrims’ needs and their experiences of these applications. During the 2017 Hajj season, we conducted a study to investigate the needs and experiences of Hajj mobile service users. We used a questionnaire to investigate the need for 20 Hajj mobile features and found that maps (particularly offline maps) were the most needed feature. We also interviewed 16 pilgrims to investigate user experience (UX) of Hajj mobile applications. Three major themes emerged from our qualitative analysis of the perceptions reported by our participants: UX problems with the current mobile applications, the importance level of application features, and opportunities for improving the UX of applications. We relate these themes to specific implications for designing a better UX of mobile applications used for Hajj and its related domain (religion) and to applications for use in similar contexts (e.g., crowd and movement situations).
Keywords: crowd; hajj; HCI; mobile applications; mobility; religion; ubiquity; usability; user experience

Internet Communication and Qualitative Research - Chris Mann; Fiona Stewart (Sage Publishing, 2000)
Communication and Qualitative Research is the first textbook to examine the impact of Internet technology on qualitative research methods. Drawing on many pioneering studies using computer-mediated communication (CMC), the authors show how online researchers can employ Internet-based qualitative methods to collect rich, descriptive, contextually-situated data. They discuss the methodological, practical and theoretical considerations associated with such methods as in-depth online interviewing, virtual focus groups, and participant observation in virtual communities.

Goffman on organizations - Manning, P. K. (Organization Studies, 2008)
This paper has two linked objectives: the first is to select those aspects of Goffman's immense body of work which continue, in my mind, to have a bearing/relevance for the organization studies field. The second is to offer one condensed empirical illustration, drawing upon an earlier published study which took purchase/inspiration from Goffman.

The Language of New Media - Manovich, Lev (MIT Press, 2001)
In this book Lev Manovich offers the first systematic and rigorous theory of new media. He places new media within the histories of visual and media cultures of the last few centuries. He discusses new media's reliance on conventions of old media, such as the rectangular frame and mobile camera, and shows how new media works create the illusion of reality, address the viewer, and represent space. He also analyzes categories and forms unique to new media, such as interface and database. Manovich uses concepts from film theory, art history, literary theory, and computer science and also develops new theoretical constructs, such as cultural interface, spatial montage, and cinegratography. The theory and history of cinema play a particularly important role in the book. Among other topics, Manovich discusses parallels between the histories of cinema and of new media, digital cinema, screen and montage in cinema and in new media, and historical ties between avant-garde film and new media.

La Chiesa in Internet. La sfida dei media digitali - Marchetti, Rita (Carocci, 2015)
Il volume offre un contributo per pensare criticamente il ruolo della rete e dei media digitali nella vita quotidiana in rapporto alle istituzioni tradizionali, in particolare alla Chiesa cattolica in Italia. I rapporti della Chiesa con i processi di modernizzazione sono stati spesso controversi e caratterizzati da un’alternanza di intuizioni e chiusure, di accettazione e cautela, tanto da rendere legittima, inizialmente, l’ipotesi di un atteggiamento di resistenza nei confronti dei mutamenti creati dalla diffusione di internet. Al contrario, il mondo ecclesiale in rete si è dimostrato una realtà estremamente e inaspettatamente ricca, con migliaia di utenti anche tra le persone e i parroci più anziani, come mostra l’importante mole di dati e informazioni raccolte sul campo di cui il volume rende conto.

Let’s Talk about Sex: Australian Muslim Online Discussions - Roxanne D. Marcotte (Contemporary Islam: Dynamics of Muslim Life, 2015)

Fatwa Online: Novel Patterns of Production and Consumption in "Political Islam and Global Media: The Boundaries of Religious Identity", ed. by Noha Mellor and Khalil Rinnawi - Marcotte, Roxanne; Mellor, Noha; Rinnawa, Khahil (Routledge, 2016)
The development of new and social networking sites, as well as the growth of transnational Arab television, has triggered a debate about the rise in transnational political and religious identification, as individuals and groups negotiate this new triad of media, religion and culture. This book examines the implications of new media on the rise of political Islam and on Islamic religious identity in the Arab Middle East and North Africa, as well as among Muslim Arab Diasporas. Undoubtedly, the process of globalization, especially in the field of media and ICTs, challenges the cultural and religious systems, particularly in terms of identity formation. Across the world, Arab Muslims have embraced new media not only as a source of information but also as a source of guidance and fatwas, thereby transforming Muslim practices and rituals. This volume brings together chapters from a range of specialists working in the field, presenting a variety of case studies on new media, identity formation and political Islam in Muslim communities both within and beyond the MENA region.

The ‘Religionated’ Body: Fatwas and Body Parts - Roxanne D Marcotte (Medicine, Religion, and the Body, 2010)
This chapter looks at some of the issues that arise with meanings that are associated with Muslim bodies to illustrate the importance of the body in Islam as a reflection of social meanings and its significance as the object of power relations. In order to investigate how the body is imagined in Islam, it may be useful, for our purpose, to resurrect an obsolete mid-17th century verb in order to discuss the specific religious ontological statuses that are attributed to persons and bodies: to 'religionate' literally means 'to make religious'. Ethico-religious, social and physical segregation of 'religionated' bodies often finds its religious justification in the theological or religiolegal realms. The chapter focuses on the 'religionated' meaning of bodies. Bodies still often retain their 'religionated' constructions in contemporary fatwas on such issues as blood and organ donation, organ transplant, or dissection of cadavers for medical training.
Keywords: body parts; fatwas; Islam; organ donation; religionated bodies

Gender and Sexuality Online on Australian Muslim Forums - Roxanne D. Marcotte (Contemporary Islam: Dynamics of Muslim Life, 2010)

Life Online. Researching Real Experience in Virtual Space - Markham, A. (AltaMira, 1998)
Alienating for some, yet most intimate and real for others, emerging communications technologies are creating a varied array of cyberspace experiences. Nowhere are the new and old more intertwined, as familiar narratives of the past and radical visions of the future inform our attempts to assess the impact of cyberspace on self and society. Amidst the dizzying pace of technological innovation, Annette N. Markham embarks on a unique, ethnographic approach to understanding internet users by immersing herself in on-line reality. The result is an engrossing narrative as well as a theoretically engaging journey. A cast of characters, the reflexive author among them, emerge from Markham's interviews and research to depict the complexity and diversity of internet realities. While cyberspace is hyped as a disembodied cultural arena where physical reality can be transcended, Markham finds that to understand how people experience the internet, she must learn how to be embodied there ”a process of acculturation and immersion which is not so different from other anthropological projects of cross-cultural understanding. Both new and not-so-new, cyberspace provides a context in which we can ask new sorts of questions about all cultural experience.

S(l)Pirituality. Immersive Worlds as a Window to Spirituality Phenomena - Martinez-Zárate, Pablo; Corduneanu, Isabela; Martinez, Luiz M (Heidelberg Journal of Religions on the Internet, 2008)
This paper focuses on several conceptual and methodological considerations for studying spirituality in Massive Multiuser Online Environments (MMOEs), taking Second Life (SL) as our main case study. This inquiry represents the follow-up of two previous research lines, one related with pop-esoteric products and operational belief system, and the other with communication patterns and social networks within online environments. Hence, our current objective pretends to highlight how operational belief articulates, or acquires meaning, through users’ interaction inside online environments.
Keywords: Phenomena; Spirituality

Fundamentalisms Comprehended - ARTIN E. MARTY; R. SCOTT APPLEBY (The Fundamentalism Project, 1995)
In this fifth volume of the Fundamentalism Project, Fundamentalisms Comprehended, the distinguished contributors return to and test the endeavor's beginning premise: that fundamentalisms in all faiths share certain "family resemblances." Several of the essays reconsider the project's original definition of fundamentalism as a reactive, absolutist, and comprehensive mode of anti-secular religious activism. The book concludes with a capstone statement by R. Scott Appleby, Emmanuel Sivan, and Gabriel Almond that builds upon the entire Fundamentalism Project. Identifying different categories of fundamentalist movements, and delineating four distinct patterns of fundamentalist behavior toward outsiders, this statement provides an explanatory framework for understanding and comparing fundamentalisms around the world.
Keywords: activism; anti-secular; family resemblances; religion

Virtual Religion in Context - Maxwell, P (Religion, 2002)
This article explores the notion of ‘virtual religion’ in various ways. In part, it is a response to a number of ideas found in the articles by Philip P. Arnold, Shawn Arthur, Christopher Helland, Anastasia Karaflogka and Mark MacWilliams which appear in this issue of Religion, but it also discusses religion in online contexts in relation to various important themes such as the character of cyberspace both present and future, the multimedia Web and its alleged postmodern orientations, virtual identity, the dynamics of virtual community, and the controversies concerning the positive and negative ramifications of online life and experience, as discussed by technomystics, technophobes and others who hold more moderate views. The article ends by raising some questions about the future character of religion and spirituality in cyberspace.
Keywords: Context; religion; Virtual

Virtual Religion in Context - Maxwell, P (Religion, 2002)
This article explores the notion of 'virtual religion' in various ways. In part, it is a response to a number of ideas found in the articles by Philip P. Arnold, Shawn Arthur, Christopher Helland, Anastasia Karaflogka and Mark MacWilliams which appear in this issue of Religion, but it also discusses religion in online contexts in relation to various important themes such as the character of cyberspace both present and future, the multimedia Web and its alleged postmodern orientations, virtual identity, the dynamics of virtual community, and the controversies concerning the positive and negative ramifications of online life and experience, as discussed by technomystics, technophobes and others who hold more moderate views. The article ends by raising some questions about the future character of religion and spirituality in cyberspace
Keywords: community; Context; religion; Spirituality; Virtual

Mashup Religion: Pop Music and Theological Invention - John S. McClure (Baylor University Press, 2011)
Popular music artists are intentionally unoriginal. Pop producers find their inspiration by sampling across traditions and genres; remix artists compose a pastiche of the latest hits. These"mashup"artists stretch the boundaries of creativity by freely intermingling old sounds and melodies with the newest technologies. Using this phenomenon in contemporary music-making as a metaphor, John McClure encourages the invention of new theological ideas by creating a mashup of the traditional and the novel. What emerges are engaging ways of communicating that thrive at the intersection of religion and popular culture yet keep alive the deepest of theological truths.
Keywords: artists; digital audio; digital media; Popular music; religious life; singers; songwriters; Theological Invention; theology; traditional communities

Training Catholic youth ministry leaders using Web 2.0 tools - McCorquodale, Charlotte; Leigh Sterten (Journal Of Youth Ministry, 2010)
Keywords: Roman Catholic Church; Training; Web 2.0; Youth Ministry

Lived Religion: Faith and Practice in Everyday Life - McGuire, Meredith B (Oxford University Press, 2008)
How can we grasp the complex religious lives of individuals such as Peter, an ordained Protestant minister who has little attachment to any church but centers his highly committed religious practice on peace-and-justice activism? Or Hannah, a devout Jew whose rich spiritual life revolves around her women's spirituality group and the daily practice of meditative dance? Or Laura, who identifies as Catholic but rarely attends Mass, and engages daily in Buddhist-style meditation at her home altar arranged with symbols of Mexican American popular religion? Diverse religious practices such as these have long baffled scholars, whose research often starts with the assumption that individuals commit, or refuse to commit, to an entire institutionally framed package of beliefs and practices. Meredith McGuire points the way forward toward a new way of understanding religion. She argues that scholars must study religion not as it is defined by religious organizations, but as it is actually lived in people's everyday lives. Drawing on her own extensive fieldwork, as well as recent work by others, McGuire explores the many, seemingly mundane, ways that individuals practice their religions and develop their spiritual lives. By examining the many eclectic and creative practices -- of body, mind, emotion, and spirit -- that have been invisible to researchers, she offers a fuller and more nuanced understanding of contemporary religion.
Keywords: Embodied Practices for Healing and Wholeness; Gendered Spiritualities; Popular Religions in Practice; Popular Religious Expressions; Religious Commitment; Religious Hybridity; religious identity; religious lives; Sociology of religion; Spirituality and Materiality

Give Me That Online-Time Religion: The Role Of The Internet in Spiritual Life - McKenna, Katelyn Yael; West, Kelly J (Computers in Human Behavior, 2005)
Online religious forums allow individuals to meet and interact with others who share their faith, beliefs, and values from the privacy of their homes. Active membership in traditional religious organizations has been shown to fulfill important social needs and to be associated with a number of benefits for the individuals involved. The survey study we report here found that many of the self and social benefits derived from participation in local religious institutions also accrue for those who take part in virtual religious forums. These interactive online forums were found to attract both those who are actively engaged in their local religious organizations and those who are unaffiliated. (c) 2005 Published by Elsevier Ltd.

Understanding media - McLuhan, M. (Signet Books)
You’ve heard the expression, “The medium is the message.” But what does that really mean? “The medium is the message” is a term coined by Marshall McLuhan in his book, Understanding Media: Extensions of Man. More than fifty years after it was published – in 1964 – Understanding Media reads as if it’s from the future. In this Understanding Media summary, I’ll break down – in my own words – why “The medium is the message,” as well as other key ideas within this media theory classic.

The Virtual Pagan: Exploring Wicca and Paganism through the Internet - McSherry, Lynn (Weiser Books, 2002)
Here is a practical manual on craft and technology for anyone interested in joining an on-line coven.

The Gospel in Cyberspace: Reflections on Virtual Reality - Meadows, P. R. (Epworth Review, 1995)
Keywords: cyberspace; Gospel

Researching Individuals Religious in the Context of the Internet - Meier, Gernot (Online: Heidelberg Journal of Religion on the Internet, 2005)
Keywords: Individuals; internet; Research

Aesthetic Formations: Media, Religion, and the Senses - Meyer, Birgit (Palgrave Macmillan, 2010)
This book examines the incorporation of newly accessible mass media into practices of religious mediation in a variety of settings including the Pentecostal Church and Islamic movements, as well as the use of religious forms and image in the sphere of radio and cinema.

Online Rituals in Virtual Worlds: Christian Online Services between Dynamix and Stability - Miczek, N (Online-Heidelberg Journal of Religions on the Internet, 2008)
Keywords: Christianity; Online; Ritual; Virtual

Digital faiths: An analysis of the online practices of Muslim women in the Netherlands - Midden, Eva; Ponzanesi, Sandra (Women's Studies International Forum, 2013)
In response to current debates in Western Europe around Islam, gender equality and emancipation, this article aims to develop a new perspective on conceptualising ‘emancipation’ in feminist theory and practice. Our case study of how Muslim women in the Netherlands use digital media to negotiate their religious affiliations and multiple belongings shows that faith and religious practices are important markers of Muslim women's agency, both emancipatory and submissive. Theoretically, the article integrates classical feminist standpoint theory and situated knowledges with current debates on agency and subjectivity. Methodologically, our virtual ethnography draws on both online and offline data: postings on four websites for Muslims living in the Netherlands as well as focus group interviews with their editors/bloggers and women active in Dutch Muslim women's organisations. The data were analysed through Critical Discourse Analysis.

Faith in the Age of Facebook: Exploring the Links Between Religion and Social Network Site Membership and Use - Brian J. Miller (Sociology of Religion, 2013)
This study examines how religiousness influences social network site (SNS) membership and frequency of use for emerging adults between 18 and 23 years old utilizing Wave 3 survey data from the National Study of Youth and Religion (NSYR). Independent of religion promoting a prosocial orientation, organizational involvement, and civic engagement, Catholics and Evangelical Protestants are more likely than the “not religious” to be SNS members, and more Bible reading is associated with lower levels of SNS membership and use. We argue there are both sacred and secular influences on SNS involvement, and social behaviors, such as being in school and participating in more non-religious organizations, generally positively influence becoming a SNS member, yet certain more private behaviors, such as Bible reading, donating money, and helping the needy, lessen SNS participation. We also suggest four areas for future research to help untangle the influence of religiousness on SNS use and vice versa.
Keywords: adolescents/youth; civic participation; internet; personal religiousity; social networks; technology

Blogging as social action: a genre analysis of the weblog - Miller, C. R.; Shepherd, D. (Into the Blogosphere: Rhetoric, Community, and Culture of Weblogs, 2004)

Faith in the Age of Facebook: Exploring the Links Between Religion and Social Network Site Membership and Use - Brian J. Miller; Peter Mundey; Jonathan P. Hill (Sociology of Religion, 2013)
This study examines how religiousness influences social network site (SNS) membership and frequency of use for emerging adults between 18 and 23 years old utilizing Wave 3 survey data from the National Study of Youth and Religion (NSYR). Independent of religion promoting a prosocial orientation, organizational involvement, and civic engagement, Catholics and Evangelical Protestants are more likely than the “not religious” to be SNS members, and more Bible reading is associated with lower levels of SNS membership and use. We argue there are both sacred and secular influences on SNS involvement, and social behaviors, such as being in school and participating in more non-religious organizations, generally positively influence becoming a SNS member, yet certain more private behaviors, such as Bible reading, donating money, and helping the needy, lessen SNS participation. We also suggest four areas for future research to help untangle the influence of religiousness on SNS use and vice versa.
Keywords: adolescents; civic participation; emerging adulthood; internet; personal religiosity; social networks; technology; Youth

The Internet: An Ethnographic Approach - Miller, D.; Slater, D. (Berg, 2000)
An examination of Internet culture and consumption. The Internet is increasingly shaping, and being shaped by, users' lives. From cybercafes to businesses, from middle class houses to squatters settlements, the authors have gathered material on subjects as varied as personal relations, commerce, sex and religion. Websites are also analyzed as new cultural formations acting as aesthetic traps. At every point, email chat and surfing are found to be exploited in ways that bring out both unforeseen attributes of the Internet and the contradictions of modern life. The material, taken from ethnographic work in Trinidad, adds depth to earlier discussions about the Internet as an expansion of space, the changes it effects to time and personhood, and the new political economy of the information age. A tie-in with the book's own website provides further illustrations.

The presentation of self in electronic life: Goffman on the Internet - Miller, H. (1964)
Paper presented at Embodied Knowledge and Virtual Space Conference, Goldsmiths' College, University of London.

Aspects of Christian Exegesis: Hermeneutics, the Theological Virtues, and Technology - Mitcham, C..; Grote, J (Theology and Technology: Essays in Christian Analysis and Exegesis, 1984)

Posting images on the web: the creative viewer and non-violent resistance against terrorism - Mitchell, Jolyon (Material Religion, 2006)
In this article I investigate how the web was used for expressing non-violent resistance in the wake of the July 2005 bombings in London. I first describe how one website, entitled "We are not afraid," became a space for displaying and viewing responses to these attacks. My contention is that, to describe this phenomenon either as the creation of a fully fledged online community or simply as an electronic noticeboard is to oversimplify what is both a fluid and a social network. Indeed, the phenomenon is better described as a diverse collective representation in the face of shared trauma. In order to test this thesis out, I develop a taxonomy of postings showing the uses that these images are put to, including to console, to encourage, to explain and to exhort. Second, I look at the communicative ripples caused by this site, including the development of other sites that accepted the posting of satirical pictures and more explicit religious imagery. Third, I examine written responses to this web phenomenon, showing how these sites became catalysts for further interaction. On the basis of this analysis I make a number of observations, including that this represents a visually dominated, highly original and largely transitory network of resistance against terrorism.

Young People, Technoculture and Embodied Spirituality - Mitchell, Craig D (Interface: A Forum for Theology in the World, 2011)

Promoting Peace, Inciting Violence: The Role of Religion and Media - Jolyon Mitchell (Routledge, 2013)
This book explores how media and religion combine to play a role in promoting peace and inciting violence. It analyses a wide range of media - from posters, cartoons and stained glass to websites, radio and film - and draws on diverse examples from around the world, including Iran, Rwanda and South Africa. Part One considers how various media forms can contribute to the creation of violent environments: by memorialising past hurts; by instilling fear of the ‘other’; by encouraging audiences to fight, to die or to kill neighbours for an apparently greater good. Part Two explores how film can bear witness to past acts of violence, how film-makers can reveal the search for truth, justice and reconciliation, and how new media can become sites for non-violent responses to terrorism and government oppression. To what extent can popular media arts contribute to imagining and building peace, transforming weapons into art, swords into ploughshares?

Virtual Space, Real Religion: Using the Internet for Adult Faith Formation - Terri Miyamoto (Seton Hall University, 2007)
At the Church of St. Clare, we have embraced information technology across many ministries, and have several years of experience in using web pages and email. In 2003 we began a major effort to plan and implement a culture of Adult Faith Formation, which has opened up new challenges and fresh ideas. Chapter 1 describes the parish and some of the questions related to technology use as we look at the possibilities that the Web 2.0 provides us as parish ministers. Before making technology decisions, we have to understand how adults grow in faith. Chapter 2 summarizes some recent work in that area. Chapter 3 addresses the culture of communications technology in the United States, drawing on surveys and personal experience to understand how Americans use the Internet, both in general and specifically for activities related to faith and spirituality. The Church is not unaware of these technologies; Chapter 4 brings together some Church documents and theological reflection on the opportunities and dangers of modern methods of communication. Given the volatile nature of information technology, it is more important to understand guidelines and objectives than to choose specific technologies. Chapter 5 offers a set of principles that can be used to evaluate proposed technology uses and to spark creative thinking around areas where we might discover shortfalls. In Chapter 6 I attempt to test these principles by applying them to some web sites, both our own and others that appear to be recognized as “best in class” examples.

Locating the “Internet Hindu”: Political Speech and Performance in Indian Cyberspace - Mohan, S (Television & New Media, 2015)
The article seeks to offer an understanding of the politics and presence of this increasingly visible, informal online political formation in India, whose members are referred to as the Internet Hindus. Used to describe young, often urban, middle-class/upper-middle-class followers of Hinduism residing in India (and abroad), the term has come to be associated almost entirely with those who aggressively voice their right-wing political views and support for Narendra Modi on social media platforms. The article explores the politics espoused by some of these “Internet Hindus” and frames them vis-à-vis the larger themes foregrounded by the electoral victory of the Hindu nationalist political outfit, the Bharatiya Janata Party (BJP). In doing so, the article attempts to locate “Internet Hindus” in a democracy, which has the third largest Internet user base in the world, and seeks to deconstruct their ethno-nationalistic online posturing, while reflecting on what this may mean for the online collective itself.
Keywords: digital politics; Hindu nationalism; Hindutva; Internet Hindu; political speech; social media

The Language of Islamophobia in Internet Articles - Haja Mohideen; Shamimah Mohideen (INTELLECTUAL DISCOURSE, 2008)
Islamophobia, the hatred for and fear of Islam and Muslims, manifests itself in physical, political, cultural, linguistic and other forms. From the linguistic perspective, many words have been coined to perpetuate prejudices against Muslims and their religion. Expressions are freely used to associate Islam, which means “peace” in Arabic, with concepts and actions which the religion and practising Muslims do not approve of, much less condone. Expressions such as Islamic terrorism, Islamic fanaticism, Muslim extremists, Islamist and political Islam have been used pejoratively. To strike fear and misgivings in the minds of many Europeans, the British capital has even been mischievously called “Londonistan” by anti-Muslim elements. Known Islamophobic items taken from Internet articles need to be analysed to respond objectively to linguistic Islamophobia
Keywords: internet; Islamophobia; language; Muslims; political Islam; religion

Computer-Mediated Communication and Theology: A Missional Analysis of Digital Media - Josh Mohland (Humboldt State University, 2006)
As a primary goal, this paper will serve to develop a critical understanding of how computer-mediated communication is shaping modern theology. Since this question encompasses very broad areas of study, I will narrow my focus to frameworks where this shift can be analyzed in a concise way, as well as provide insight into where I think contemporary theology is going.

Responsible Technology: A Christian Perspective - Monsma, S. V. (Eerdmans, 1986)

Researching theo(b)logy: Emerging Christian communities and online construction of identity, theology and society - Katharine Sarah Moody (UK Research Network for Theology, Religion and Popular Culture Conference, 2007)
In this paper I will present two Internet technologies, blogs and open source programming, which are being used by emerging Christian communities in their construction of identity, theology and society. I am in the preliminary stages of data collection for my PhD thesis, and so this paper addresses several methodological issues that are raised when conducting research on blogs. This paper reflects on the use emerging Christian communities are making of the Internet and argues for a participatory research methodology for the blogosphere.

Cybersociality: Connecting Digital Fun to the Play of God - John W. Morehead (Halos and Avatars: Playing Video Games With God, 2010)
Keywords: cyber; cybersociality; Digital Religion; digital technologies; Digital Worlds; Immersion; popular culture; theology; transcendentalize secularity; video games

Mediation or mediatisation: The history of media in the study of religion - Morgan, David (Culture and Religion, 2011)
Several different accounts of ‘mediatisation’ and ‘mediation’ circulate in the literature of media studies. This paper begins with a parsing of them, considering their conceptual distinctions and similarities. The argument developed here is for a general theory of mediation and a more particular view of mediatisation. Although developing a critical assessment of a prevailing notion of mediatisation, the paper does not dismiss it, but regards it as exhibiting a limited usefulness. In order to make its case, the paper relies on the case study of Evangelical ephemeral print in Britain circa 1800, examining the production and circulation of tracts in order to show that arguments for mediatisation need to be strongly qualified by historical evidence. Greater reliance on historical precedents will strengthen studies of mediatisation by chastening the often exorbitant and ahistorical claims made for it.

Religion and media: A critical review of recent developments - Morgan, David (Critical Research on Religion, 2013)
This article considers recent changes in the definition of religion and of media as the basis for framing the study of their relation to one another and recent research in the intersection they have come to form over the last two decades or so. The history, materiality, and reception of each have colored scholarly work, and made ethnography, practice, material culture, and embodiment key aspects of scholarship. A new paradigm for some scholars for studying mediation is aesthetics—no longer understood as the “philosophy of the beautiful,” but as the study of perception in the mediated practices that make up lived religion.

Religion and Material Culture: The Matter of Belief - Morgan, David (Routledge, 2009)
Religious belief is rooted in and sustained by material practice, and this book provides an extraordinary insight into how it works on the ground. David Morgan has brought together a lively group of writers from religious studies, anthropology, history of art, and other disciplines, to investigate belief in everyday practices; in the objects, images, and spaces of religious devotion and in the sensations and feelings that are the medium of experience. By avoiding mind/body dualism, the study of religion can break new ground by examining embodiment, sensation, space, and performance. Materializing belief means taking a close look at what people do, how they feel, the objects they exchange and display, and the spaces in which they perform whether spontaneously or with scripted ceremony. Contributions to the volume examine religions around the world—from Korea and Brazil to North America, Europe, and Africa. Belief is explored in a wealth of contexts, including Tibetan Buddhism, the hajj, American suburbia and the world of dreams, visions and UFOs.

Key Words in Religion, Media and Culture - Morgan, David (Routledge, 2008)
'From The Passion of the Christ to the presumed 'clash of civilizations', religion's role in culture is increasingly contested and mediated. Key Words in Religion, Media, and Culture is a welcome and interdisciplinary contribution that maps the territory for those who aim to make sense of it all. Highlighting the important concepts guiding state-of-the-art research into religion, media, and culture, this book is bound to become an important and frequently consulted resource among scholars both seasoned and new to the field.' –Lynn Schofield Clark 'David Morgan has assembled here a fine team of scholars to prove beyond a doubt that the intersections of religion, media, and culture constitute one of the most stimulating fields of inquiry around today...This highly useful and theoretically sophisticated text will likely assume 'ritual' status in this emergent field.' – Rosalind I. J. Hackett, University of Tennessee, US 'This volume is a major intervention in the literature on religion, media and culture. Drawing together leading international scholars, it offers a conceptual map of the field to which students, teachers and researchers will refer for many years to come. The publication of Key Words in Religion, Media and Culture is a significant moment in the formation of this area of study, and sets a standard for cross-disciplinary collaboration and theoretical and methodological sophistication for future work in this area to follow.' – Gordon Lynch, Birkbeck College, University of London, UK

What's “home” got to do with it? Contradictory dynamics in the domestication of technology and the dislocation of domesticity. - Morley, D. (European Journal of Cultural Studies, 2003)
This article focuses on how we can understand the contradictory dynamicsthrough which communications technologies have been domesticated at the same time that domesticity itself has been dislocated. The article addresses questions of historical periodization and the need for a more developed historical perspective on the futurological debates about the new technologies with which so much of media and cultural studies is concerned today.

Group identity and social closeness: Secular and Ultra-Orthodox Jews in Israeli academic institutions - Moskovich, Y; Liberman, I (International Journal of Sociology and Social Policy, 2018)
The purpose of this paper is to study examine the social identity of Ultra-Orthodox students enrolled in institutions of higher learning in Israel, and specifically the ways in which the identity of Ultra-Orthodox students who interact with other groups on campus compares to the identity of self-segregated Ultra-Orthodox students. Traditionally, Ultra-Orthodox students have preferred self-segregated educational institutions. Today, however increasing numbers of Ultra-Orthodox Jews are enrolling in regular academic institutions. Although they study in separate, homogeneous classrooms, they interact with secular students within the framework of the institution.
Keywords: identity; Israeli society; Secular; Ultra-Orthodox Jews

Online Buddhist Community: An Alternative Organization In The Information Age - Kim. Mun-Cho (Religion and Cyberspace, 2005)
In the twenty-first century, religious life is increasingly moving from churches, mosques and temples onto the Internet. Today, anyone can go online and seek a new form of religious expression without ever encountering a physical place of worship, or an ordained teacher or priest. The digital age offers virtual worship, cyber-prayers and talk-boards for all of the major world faiths, as well as for pagan organisations and new religious movements. It also abounds with misinformation, religious bigotry and information terrorism. Scholars of religion need to understand the emerging forum that the web offers to religion, and the kinds of religious and social interaction that it enables. Religion and Cyberspace explores how religious individuals and groups are responding to the opportunities and challenges that cyberspace brings. It asks how religious experience is generated and enacted online, and how faith is shaped by factors such as limitless choice, lack of religious authority, and the conflict between recognised and non-recognised forms of worship. Combining case studies with the latest theory, its twelve chapters examine topics including the history of online worship, virtuality versus reality in cyberspace, religious conflict in digital contexts, and the construction of religious identity online. Focusing on key themes in this groundbreaking area, it is an ideal introduction to the fascinating questions that religion on the Internet presents.

Muslim Political Activism or Political Activism by Muslims? Secular and Religious Identities Amongst Muslim Arab Activists in the United States and United Kingdom - Nagel, Caroline R.; Staeheli, Lynn A. (Identities, 2011)
Scholarship on Muslim political mobilisation in the West has developed as an important counterpoint to public discourse, which has tended to cast Muslims as a threat to social cohesion, liberal democracy, and national security. But even as scholarly literature has shed light on civic participation among Muslims, it has sidelined the diversity of political identities and values that motivate them. Most, if not all, Muslims in the West find their identities politicised in some way, but the question of whether this leads to a consensus amongst Muslims about the role of religion in public life often remains unexamined. In this article we draw on interviews with seventy-eight activists in Britain and the United States who are both Muslim and Arab to complicate ideas about the political mobilisation of Muslims in the West. Respondents, we show, are far from unified in their views on religion as a basis for political action and mobilisation. Some are keen to place Islam squarely in mainstream political spaces; most, however, are insistent that Islam should remain a private faith and identity and that political mobilisation should take place under the aegis of Arabness or other ‘secular’ identities. Using theoretical perspectives on the public sphere, we explain the complexity of our respondents' political identities and activism. Our overall aim is to broaden perspectives on the ways in which people from Muslim backgrounds participate in public, political life in Western contexts.

Digital leadership, Twitter and Pope Francis - Narbona, Juan (Church, Communication and Culture, 2016)
The Internet reproduces and strengthens our model of social dialog. Just as in the physical world, the online public conversation and, above all, the ideological debate, requires leaders who can be a point of reference to either foster values or contradict them. The concept of leadership has drawn the attention of several studies concerning communication management. Leaders are neither all equal nor do they exercise leadership by means of the same tools. This article studies both the concept of digital leadership as a guide for online conversation and the use that microblogs, such as Twitter, can provide for this purpose. Among several public figures using Twitter, we have focused our study on the @Pontifex account to have an insight into the type of leadership exercised by the Holy Father and the impact of his teaching. The analysis shows that the Pope uses Twitter for catechetical purposes and that he is aware that his message can reach a large audience. Moreover, although interaction between the Pope and his followers on this platform is a fact already known, we have further found that some messages arouse followers’ interest more than others do.

religion@home? Religionsbezogene Online-Plattformen und ihre Nutzung: Eine Untersuchung zu neuen Formen gegenwärtiger Religiosität - Neumaier, Anna (Ergon, 2016)
Uber den Wandel gegenwartiger Religion und Religiositat ist in Debatten rund um Sakularisierung und Re-Sakralisierung viel diskutiert worden. Die Bedeutung neuer Medien wurde dabei aber noch wenig berucksichtigt. An diese Debatten anschliessend widmet sich die vorliegende Studie deshalb religioser Online-Nutzung, ihren Bedingungen, Formen und Konsequenzen: Was sind Ausloser fur den Einstieg, Themen des Online-Austauschs, und in welchem Zusammenhang steht die Online-Nutzung mit der Einbettung in die lokale Gemeinde? Dem geht die Arbeit mit Blick auf christliche Online-Foren nach. Sie beschrankt sich dabei nicht auf Analysen der Online-Diskussionen, sondern stellt mit uber 30 qualitativen Interviews und einer quantitativen Erhebung die Perspektive der Nutzer dieser Foren in den Mittelpunkt. Insgesamt zeigt sich: Forennutzung ist vor allem als Strategie der Restabilisierung individueller Religiositat zu verstehen. Ihr Ausgangspunkt sind weniger mediale Eigenschaften des Internets, sondern vielmehr Defizite traditioneller religioser Angebote, die zu anhaltender Unzufriedenheit oder dem Abbruch der Gemeindeeinbettung fuhren. Durch die Aneignung individueller religioser Expertise und Wiedereinbettung in einen Kontext kollektiver Legitimierung von Religiositat vermag die Online-Nutzung hier Ausgleich zu schaffen. Die erarbeiteten Nutzungsmuster und Typen online entstehender Gemeinschaften zeigen Details dieser Prozesse.

Witchcraft and the Web: Weaving Pagan Traditions Online - Nightmare, M. Macha (ECW Press, 2001)
Witchcraft is one of the most popular and fastest growing spiritual paths in the US. it is also one of the busiest topics on the Web as once isolated communities find making connections a breeze with the advent of internet technology. M. Macha NightMare, a practicing with for 30 years, takes an unconventional look at the cultural effects of the internet on the ancient-future spirituality that is contemporary witchcraft. A new web is being woven with the threads of tradition and technology intertwined.

Creative and Lucrative Daʿwa: The Visual Culture of Instagram amongst Female Muslim Youth in Indonesia - Nisa, E.F (Asiascape: Digital Asia, 2018)
Social media have become part of the private and public lifestyles of youth globally. Drawing on both online and offline research in Indonesia, this article focuses on the use of Instagram by Indonesian Muslim youth. It analyzes how religious messages uploaded on Instagram through posts and captions have a significant effect on the way in which Indonesian Muslim youth understand their religion and accentuate their (pious) identities and life goals. This article argues that Instagram has recently become the ultimate platform for Indonesian female Muslim youth to educate each other in becoming virtuous Muslims. The creativity and zeal of the creators of Instagram daʿwa (proselytization), and their firm belief that ‘a picture is worth a thousand words’, has positioned them as social media influencers, which in turn has enabled them to conduct both soft daʿwa and lucrative daʿwa through business.
Keywords: culture; Da'wa; fashion; Indonesia; Instagram; Muslim youth; veiling

The Religion of Technology: The Divinity of Man and the Spirit of Invention - David Noble (Penguin, 1999)

Catholic, protestant and holistic spiritual appropriations of the internet - Noomen, I; Aupers, S; Houtman, D (Information, Communication & Society, 2011)
This article relies on in-depth qualitative interviews with 21 web designers, active in the fields of Catholicism, Protestantism and holistic spirituality in the Netherlands, to study religious appropriations of the Internet. The authors found that these different religious groups embraced the medium of the Internet motivated by a common desire to make oneself heard in the cacophony of voices that has resulted from processes of secularization and religious change. In doing so, Catholic web designers struggle with the dilemma of either following Roman orthodoxy or creating room for dialogue and diversity, whereas their Protestant counterparts feel forced to either let a thousand flowers bloom or surrender to a highly compromised image of their faith. Holistic spirituality, finally, struggles with neither of these problems and appropriates the Internet as its virtually natural habitat for sharing and connecting. The authors conclude that, consistent with theories about cultured technology and spiritualizing of the Internet, offline religious heritages matter a lot when religions seek to appropriate the Internet through web design. These appropriations tend not to be smooth transpositions of coherent and conflict-free offline religious heritages to online environments, however, but conflict-ridden processes stirring long-standing struggles over authority and identity.
Keywords: Catholic; internet; Protestant; religion; spiritual

Utopian and Dystopian Possibilities of Networked Religion in the New Millennium - O'Leary, S (Religion and Cyberspace, 2005)
In the twenty-first century, religious life is increasingly moving from churches, mosques and temples onto the Internet. Today, anyone can go online and seek a new form of religious expression without ever encountering a physical place of worship, or an ordained teacher or priest. The digital age offers virtual worship, cyber-prayers and talk-boards for all of the major world faiths, as well as for pagan organisations and new religious movements. It also abounds with misinformation, religious bigotry and information terrorism. Scholars of religion need to understand the emerging forum that the web offers to religion, and the kinds of religious and social interaction that it enables. Religion and Cyberspace explores how religious individuals and groups are responding to the opportunities and challenges that cyberspace brings. It asks how religious experience is generated and enacted online, and how faith is shaped by factors such as limitless choice, lack of religious authority, and the conflict between recognised and non-recognised forms of worship. Combining case studies with the latest theory, its twelve chapters examine topics including the history of online worship, virtuality versus reality in cyberspace, religious conflict in digital contexts, and the construction of religious identity online. Focusing on key themes in this groundbreaking area, it is an ideal introduction to the fascinating questions that religion on the Internet presents.

Cyberspace as Sacred Space. Communicating Religion on Computer Networks - O'Leary, Stephen.D. (Journal of the American Academy of Religion, 1996)
Keywords: Communication; Computer; cyberspace; networks

Online Ultra-Orthodox Religious Communities as a Third Space: A Netnographic Study - Okun, S; Nimrod, G (International Journal of Communication, 2017)
This research applies a netnographic approach to explore the extent to which online communities function as a third space that supports a networked religion. Five months of observation at a leading online ultra-Orthodox Jewish forum revealed four chief characteristics: religious–secular discussion—the forum served as a platform for religious discourse as well as a sphere for discussing a wide range of subjects unrelated to religion; identity game—members constantly played two types of identity games: personal and group; intense activity—the forum was characterized by rather intense activity patterns; and a unique religious expressiveness—this was reflected in textual and visual representations and exhibited in online debates. Findings indicate that the forum offers its members a third space of digital religion that is hybrid in any possible sense and reinforces a lively networked religion. While it aims at enabling serious discussion of religious matters, it also serves members as a social sphere in which they can communicate about extrareligious issues; express their personalities, skills and opinions; and even play with their anonymous peers.
Keywords: Judaism; netnography; networked religion; online communities; Spirituality; third space; ultra-Orthodox

The Essentiality of “Culture” in the Study of Religion and Politics - Laura R. Olson (Journal for the Scientific Study of Religion, 2011)
This article reviews various theoretical approaches political scientists employ in the analysis of religion and politics and posits culture as a conceptual bridge between competing approaches. After coming to the study of religion slowly in comparison with other social science disciplines, political science finally has a theoretically diverse and thriving religion and politics subfield. However, political scientists’ contributions to the social scientific study of religion are hampered by a lack of agreement about whether endogenous or exogenous theoretical approaches ought to dominate our scholarship. I assert that the concept of culture—and more specifically, subculture—might help create more connections across theoretical research traditions. I emphasize how the concept of religion-based subculture is inherent in psychological, social psychological, social movement, and contextual approaches to religion and politics scholarship, and I explore these theoretical connections using the example of religion-based “us versus them” discourses in contemporary American politics.
Keywords: analysis; culture; Politics; religion; Research; Sociology of religion; study of religion; theoretical approaches

Cyberethics: New challenges or old problems - Ottmar, J. (Concilium, 2005)
Keywords: cyberspace; ethics

Media, Religion and Gender: Key Issues and New Challenges - Mia L övheim (Routledge, 2014)
Media, Religion and Gender presents a selection of eminent current scholarship that explores the role gender plays when religion, media use and values in contemporary society interact. The book: surveys the development of research on media, religion and culture through the lens of key theoretical and methodological issues and debates within gender studies. includes case studies drawn from a variety of countries and contexts to illustrate the range of issues, theoretical perspectives and empirical material involved in current work outlines new areas and reflects on challenges for the future. Students of media, religion and gender at advanced level will find this a valuable resource, as will scholars and researchers working in this important and growing field.

Vatican warning on danger of “online confession.” - Owen, R. (The Sunday Times Online, 2003)

Cyberspace as Sacred Space: Communicating Religion on Computer Networks - O’Leary, Stephen (Journal of the American Academy of Religion, 1996)

The Unknown God of the Internet - O’Leary, Stephen; Brasher, Brenda (Philosophical Perspectives on Computer-Mediated Communication, 1996)

Religious Leaders, Mediated Authority and Social Change - Cheong P.H. (Journal of Applied Communication Research, 2012)
This essay discusses the relationships between mediated religious authority and social change, in terms of clergy's social media negotiation and multimodal communication competence, with implications for attracting attention and galvanizing active networks and resources for social initiatives.
Keywords: Authority; Leaders; religion; social media

Miracles or Love? How Religious Leaders Communicate Trustworthiness through the Web - Pace, Stefano (Journal of Religion and Popular Culture, 2004)
A religious organization should communicate trustworthiness by attempting correctly to interpret its message and by recruiting new members. Modern communication involves new means of communication like the Internet, which has become an important medium capable of spreading a complex message to a large audience. Religious movements are a growing social and organizational force that employ modern communication methods and criteria. This paper addresses the convergence of religious communication and the Internet, by focusing on trust, a fundamental element of any type of communication, especially of a religious kind. Two main drivers can elicit trust: capabilities (the skill to realize what is promised) and benevolence (the lack of any opportunistic or egoistic goal). This paper employs the content analysis method to analyze the biographies of religious leaders posted on the their official web-sites, in order to verify the existence of these two trust drivers, i.e., leader’s capabilities and benevolence. The results demonstrate the different stress placed on each.
Keywords: Communication; Love; religion

Digital religion and Hinduism in the United States - Pandharipande, Rajeshwari V. (World Englishes, 2018)
As religions migrate from their native contexts, they adopt new languages for their communication. Additionally, in the 21st century, digital media is being used for religious practices such as ritual worship, sermons and discourses. This article focuses on the case of Hinduism in the US diaspora where the Hindu community (unlike its native counterpart in India) uses the English language and the digital media for the Hindu religious practices. In particular, this article discusses the ways in which the use of the English language and digital media is more conventionalized in the context of discussion about religion (in the discourses of satsang), as opposed to the experience of religion (for example, in puja ‘worship ritual’).

Do you believe in magic? Computer Games in Everyday Life - Pargman, Daniel; Jakobsson, Peter (European Journal of Cultural Studies, 2008)
Huizinga's concept of a 'magic circle' has been used to depict computer games and gaming activities as something separate from ordinary life. In this view, games are special (magical) and they only come to life within temporal and spatial borders that are enacted and performed by the participants. This article discusses the concept of a 'magic circle' and finds that it lacks specificity. Attempts to use the concept of a magic circle create a number of anomalies that are problematic. This is not, as has been suggested earlier, primarily a matter of the genre of the game, or a discussion of what an appropriate definition of a 'game' might be. Rather, in this study with hardcore gamers, playing computer games is a routine and mundane activity, making the boundary between play and non-play tenuous to say the least. This article presents an alternative theoretical framework which should be explored further.

Religion and Media: No Longer a Blindspot in Korean Academia - Park, Jin Kyu; Cho, Kyuhoon; Han, Sam (Journal of Korean Religions, 2017)
In contemporary social life, religion and media cannot be said to be separated. Contrary to the long-lasting understanding that the two are independent from each other, the spheres of religion and media are closely intertwined. Dynamic and increasing connections have been observed and reported by a range of scholars. Indeed, the scholarly interest in the relationship is a fairly recent one. Only thirty years ago, religion was just a blindspot within media studies (Hoover and Venturelli 1996). Similarly, media were an overlooked issue in religious studies. However, the new millennium witnessed a fast-growing attention to the interactions in both fields, demonstrated by two simultaneously released pieces of literature. On the one hand, Journal of Media and Religion was launched in 2002 by a community of media scholars who had investigated the religious dimension of media-related phenomena. In the preface to the inaugural issue, the respected media scholar James Carey noted that ‘‘[N]one of these religious phenomena can be understood without reference to media that organize religious community, transcribe and embed religious belief, and create both collective memory and modern politics’’ (Carey 2002, 3). On the other hand, a year earlier, a group of religion researchers collected twenty-five articles in an edited volume entitled Religion and Media. Hent de Vries and Samuel Weber, the volume’s editors, summarized their efforts as confronting ‘‘the conceptual, analytical, and empirical possibilities and difficulties involved in addressing the complex issue of religion in relation to ‘media,’ that is to say, ancient and modern forms of mediatization such as writing, confession, ritual performance, film, and television, not to mention the ‘new technological media,’ of which the Internet is the most telling example’’ (de Vries and Weber 2001, vii).

"Making MOOsic”: the development of personal relationships online and a comparison to their offline counterparts - Parks, M. R.; Roberts, L. D. (Journal of Social and Personal Relationships, 1998)
Despite the rapid development of the Internet over the past decade and the associated media hyperbole about cyberspace relationships, there is a paucity of systematic research examining the prevalence, type and development of personal relationships in on-line settings. This research examines relational topography in real-time text-based virtual environments known as MOOs (Multi-User Dimensions, Object Oriented). Current users of MOOs (235) completed a survey on MOO relationships, with 155 also completing a survey on offline relationships. Almost all survey respondents (93.6%) had formed ongoing personal relationships on MOOs. The most commonly reported types of relationships were close friendships, friendships and romances. The majority of relationships formed (83.6%) was with members of the opposite sex. Levels of relational development (interdependence, depth, breadth, code change, commitment, predictability/understanding, network convergence) were typically moderate to high. Most relationships had migrated to other virtual environments, and a third had resulted in face-to-face meetings. On average, MOO relationships were found to be more developed than newsgroup relationships, but less developed than off-line relationships. It was concluded that MOOs provide an inherently social and powerful context for the formation of personal relationships, many of which will transfer to other settings.

Religion and Views on Reproductive Technologies: A Comparative Study of Jews and Non-Jews - Harriet L. Parmet; Judith N. Lasker (Shofar: An Interdisciplinary Journal of Jewish Studies, 1991)
New developments in reproductive technology have proliferated throughout the last decade and received enormous attention from the public. In vitro fertilization, artificial insemination, and surrogate motherhood have all been the subject of controversy at the same time as they are becoming more widely
Keywords: children; education; Jews; Non-Jews; religion; technology; Youth

Digital Apocalypse: The Implicit Religiosity of the Millennium Bug Scare - Karen Pärna; Aupers, Stef; Houtman, Dick (Religions of Modernity: Relocating the Sacred to the Self and the Digital, 2010)
Keywords: Implicit religion; millennium bug

Believing in the Net: Implicit Religion and the Internet Hype, 1994-2001 - Karen Pärna (Leiden University Press, 2010)
Starting with Weber’s disenchantment thesis, a sociological tradition has developed that associates modernity with a crisis of meaning. The de-mystification of our worldview and the decreasing influence of religious traditions in specific are seen as obstacles for making sense of human existence. But in fact, modern societies are full of meaning and they continue to be religious. This study shows that, in an implicit form, religion can be found everywhere in our culture. The Internet hype of the 1990s was a particularly effervescent example of implicit religiosity. The hopeful discourse about the Internet that typified this hype drew on religious ideas and language, and it inspired strong belief. This dissertation explores the appeal of the Internet as an object of faith and it looks at how it could serve as a source of meaning.
Keywords: Anomie; Disenchantment; Giving meaning; Hypes; ICT; Implicit religion; internet; Modernity; Sociology of religion; Technophilia

Some methodological reflections about the study of religions on video sharing websites - Pasche, Florence (Marburg Journal of Religion, 2008)
Keywords: filming; religion and internet; sharing; video

Religious Rituals on Video Sharing Websites - Pasche Guignard, Florence (Reflexivity, Media and Visuality)
Keywords: religion and internet; Ritual; video sharing website

Mediatisation of Catholicism in Croatia: A Networked Religion? - Pavić, Z; Kurbanović, F; Levak, T (Revija za sociologiju, 2017)
This paper deals with the topic of mediatisation of religion. It is seen as a process wherein the structural logic and communicative characteristics of the media play a significant role in religious communication, thus exerting an influence on the success of the transmission of such messages and on religion as a whole. Consequently, it is argued that contemporary social transformations of religion cannot be properly analysed and understood without the acknowledgement of the increasing mediatisation of religion and its effects. Having in mind the overarching importance of the Internet as a communication platform, the authors investigated whether the Internet presence of Catholicism in Croatia can be identified as a networked religion with its main components (networked communities, storied identities, shifting authority, convergent practice and multisite reality). Media content analysis using a sample (N = 200) of various categories of Catholic websites and Facebook pages was employed. Even though noteworthy differences were found between the sites affiliated, semi-affiliated and non-affiliated with the Catholic Church in Croatia, as well as between such websites and Facebook pages, the findings suggest that in the case of Catholicism in Croatia, Internet religious communication bears close connections to the offline world, does not challenge formal religious authorities, nor does it lead to new interpretations of religious doctrines and texts. The authors concluded that the Internet presence of Catholicism in Croatia leads to the re-affirmation and deepening of the existing forms of religion in the new media environments.
Keywords: Catholicism; Croatia; mediatisation; networked religion; religion

The new class of digital leaders - Peladue, P.; Herzog, M.; Acker, O. (Strategy+Business, 2017)

Social media as third spaces? Exploring Muslim identity and connection in Tumblr - Pennington, Rosemary (International Communication Gazette, 2018)
Third spaces have been imagined as sites of resistance, where hegemonic and normative understandings of the world may be challenged. New media are often imagined to have this liberatory potential as well, particularly for those individuals who experience social, cultural, or political marginalization. This research considers whether social media might help facilitate third spaces. It takes as a case for exploring this topic the experience of 188 Muslim bloggers in social networking site Tumblr. Many of these individuals live in non-Muslim majority countries and say they sometimes feel stuck between identities. The qualitative analysis of their blogs, as well as interviews with 30 of the bloggers, seeks to understand how Tumblr can facilitate third spaces where these bloggers can explore the hybrid nature of their identities while connecting to others who share that experience.

Making Space in Social Media: #MuslimWomensDay in Twitter - Pennington, Rosemary (Journal of Communication Inquiry, 2018)
At the end of Women’s History Month 2017, social media sites were filled with posts using the hashtag #MuslimWomensDay. Muslim women have often been framed in media as either victims of a violent faith and its believers or enablers of that violence, rarely are they given the space to tell their own stories. The #MuslimWomensDay hashtag was designed to draw attention to the stories and experiences of Muslim women. This qualitative textual analysis of approximately 300 tweets explores how Twitter users deployed the #MuslimWomensDay hashtag in their posts in order to understand the story users told of what it means to be a Muslim woman as well as what narratives of Islam they had to fight against.

The playful world: how technology is transforming our imaginationms - Pesce, M. (Ballantine Books, 2000)
As you read these words, the architects of the new virtual reality are inventing a world you never imagined: call it the playful world. It's a world of interactive Web-based toys that instantly collapse the gulf between wish and existence, space and time, animate and inanimate. It's a world where the entire fabric of the material world becomes manipulable, programmable, mutable. Situated at the crossroads of high technology and popular culture, the playful world is taking shape at the speed of electronic creativity. Are you ready for it? Your kids are. In this spellbinding new book, Mark Pesce, one of the pioneers in the ongoing technological revolution, explores how a new kind of knowing and a new way of creating are transforming the culture of our time. It started, bizarrely enough, with Furbys, the first toys that had the "will" to grow and interact intelligently with their environment. As Pesce argues, Furbys, for all their cloying cuteness, were a vital sign of a new human endeavor--the ability to copy part of our own intelligence into the physical world. But engineers of the playful world have already gone much further into considerably stranger virtual realms. Pesce takes us inside the world's cutting-edge research facilities where the distinction between bits and atoms is rapidly dissolving. We meet the creators of LEGO Mindstorms, a snap-together plastic device that intelligently controls motors and processes data from sensors. We watch technological geniuses like Marvin Minsky and Eric Drexler turn the theoretical breakthroughs of Nobel laureate Richard Feynman into "nanites"-- tiny ultra-high-speed computers that replicate intelligent life. We observe the launch of the amazing and much-anticipated Sony Playstation 2, a platform that will allow us to bring synthetic worlds into the home and create a gateway to the living planet. Web-based toys are only the beginning--the first glimmer of a new reality that is transforming our entire culture with incredible speed and power. After all, thanks to the computer revolution and the Internet, all of us already command powers that just a generation ago would have been described as magical. Magic is about to take on a whole new dimension. In this dazzling book, Mark Pesce offers a mind-bending preview of the incredible future that awaits us all in The Playful World.

Introduction Essay: Special Issue of RMDC on Public Scholarship, Media and Religion - Peterson, Kristin M.; Campbell, Heidi A. (Journal of Religion, Media and Digital Culture, 2020)
Keywords: Digital media; religion; public scholarship

Pushing boundaries and blurring categories in digital media and religion research - Peterson, Kristin M. (Sociology Compass, 2020)
As religious identity and spiritual practices transform and expand in the digital media moment, this article advocates for more critical scholarship on media and religion that examines the complex ways that individuals make meaning in the digital age. First, I present an overview of foundational media and religion theories that analyze the interactions between these ever‐changing fields, such as the culturalist tradition, mediatization theory, and the social shaping of technology approach. Furthermore, this essay highlights insightful research trends that blur distinctions between media spaces and complicate definitions of religion. Finally, a discussion of gaps in the scholarship will justify an argument for more theories centered in international contexts, as well as analysis of the relationships between media technologies, aesthetics, affect, identity and religious expression. These emerging approaches provide more in‐depth discussions of how the fast‐changing and ever‐complex digital culture is deeply connected to the evolving nature of religion and human existence.

Beyond Fashion Tips and Hijab Tutorials: The Aesthetic Style of Islamic Lifestyle Videos - Peterson, Kristin M. (Film Criticism, 2016)
Among young women, lifestyle videos have become extremely popular on YouTube, and a similar trend has emerged among young Muslim women who share modest fashion tips and discuss religious topics. This paper examines the videos of two prominent Muslim women on YouTube, Amena Khan and Dina Torkia, in an effort to understand how they engage with aesthetic styles in order to work against Western stereotypes of Muslim women as oppressed and lacking individuality. Islamic lifestyle videos might appear to simply promote a vacuous focus on appearances, but I argue that it is through the aesthetics and affects of these videos that Amena and Dina do political work to redistribute the sensible and shift what is considered attractive, beautiful and pleasurable in Western society. Additionally, the hybrid aesthetic styles and affects of authenticity and pleasure, which are possible in digital spaces like YouTube, offer Amena and Dina the chance to control their own visual images and to resist being coopted as icons of Western freedom or Islamic piety.

The Unruly, Loud, and Intersectional Muslim Woman: Interrupting the Aesthetic Styles of Islamic Fashion Images on Instagram - Peterson, Kristin M (2020)
This article explores the concept of a social media interrupter, one who engages with the visual style and discourse of social media influencers while incorporating a subversive critique of the ways that social media spaces perpetuate injustices and marginalize voices. This concept of social media interrupter is discussed through an analysis of Islamic fashion iconoclast Leah Vernon, a self-identified fat, Black Muslim woman who uses her position as a fashionista on Instagram to insert her biting critique of both Islamic fashion and social media influencers. Instead of standing outside, she interrupts and disrupts Islamic fashion on Instagram by constantly bringing up concerns of body image, fatphobia, colorism, racism, economic inequality, and mental health. Leah’s intersectional feminist critique, I argue, gains power and visibility because of how she effectively interrupts the aesthetic style of Instagram by inserting her unruly body and her concern for social injustices.
Keywords: body image; influencers; Instagram; intersectional feminism; Islamic fashion

Webs of reality: social perspectives on science and religion - Petry, Y.; Stahl, W. A.; Campbell, R. A.; Diver, G. (Rutgers University Press, 2002)
Science and religion are often thought to be advancing irreconcilable goals and thus to be mutually antagonistic. Yet in the often acrimonious debates between the scientific and religious communities, it is easy to lose sight of the fact that both science and religion are systems of thought and knowledge that aim to understand the world and our place in it.Webs of Reality is a rare examination of the interrelationship between religion and science from a social science perspective, offering a broad view of the relationship, and posing practical questions regarding technology and ethics. Emphasizing how science and religion are practiced instead of highlighting the differences between them, the authors look for the subtle connections, tacit understandings, common history, symbols, and implicit myths that tie them together. How can the practice of science be understood from a religious point of view? What contributions can science make to religious understanding of the world? What contributions can the social sciences make to understanding both knowledge systems? Looking at religion and science as fields of inquiry and habits of mind, the authors discover not only similarities between them but also a wide number of ways in which they complement each other.
Keywords: religion; science; social perceptions; Webs

Webs of reality: social perspectives on science and religion - Petry, Y.; Stahl, W. A.; Campbell, R. A.; Diver, G. (Rutgers University Press, 2002)
Science and religion are often thought to be advancing irreconcilable goals and thus to be mutually antagonistic. Yet in the often acrimonious debates between the scientific and religious communities, it is easy to lose sight of the fact that both science and religion are systems of thought and knowledge that aim to understand the world and our place in it.Webs of Reality is a rare examination of the interrelationship between religion and science from a social science perspective, offering a broad view of the relationship, and posing practical questions regarding technology and ethics. Emphasizing how science and religion are practiced instead of highlighting the differences between them, the authors look for the subtle connections, tacit understandings, common history, symbols, and implicit myths that tie them together. How can the practice of science be understood from a religious point of view? What contributions can science make to religious understanding of the world? What contributions can the social sciences make to understanding both knowledge systems? Looking at religion and science as fields of inquiry and habits of mind, the authors discover not only similarities between them but also a wide number of ways in which they complement each other.
Keywords: religion; science; social perceptions; Webs

Beyond the traditional-modern binary: faith and identity in muslim women’s online matchmaking profiles - Piela, A. (CyberOrient, 2011)
Finding a suitable partner in both diasporic and non-diasporic settings proves increasingly challenging for young Muslims, especially those unable or not wanting to search within their kinship networks. At the same time, religious matchmaking websites are becoming increasingly common especially among Muslim women. As studies of Muslim matchmaking sites tend to focus on the ever-popular topic of the headscarf and its associations in the matchmaking context, a much more comprehensive study of the specificity of the online religious identities and self-representation is required. This paper examines a number of profiles of young Muslim women using online matchmaking sites and discusses broad themes of faith, ethnicity and identity that emerge in the analysis.
Keywords: identity; information and communication technology; matchmaking; Muslim women; social aspects; websites

Claiming Religious Authority: Muslim Women and New Media - Anna Piela (Media, Religion and Gender Key Issues and New Challenges, 2013)
Keywords: Authority; Digital Religion; GENDER; Islam; Muslim; New Media

How do Muslim women who wear the niqab interact with others online? A case study of a profile on a photo-sharing website - Piela, Anna (New Media & Society, 2017)
This article identifies a gap in extant literature on women who wear the niqab and their representations in ‘traditional’ media: there are few academic sources that draw from these women’s own narratives. In order to address this gap, this article highlights niqabis’ self-representations in the form of photographic self-portraits published in new media and demonstrates a variety of positive ways in which these self-portraits are received by the audiences. The article is based on a case study of a profile of a prolific author who posts and discusses her work on a popular photo-sharing website. It throws light on contextualised and relational interpretations of the niqab and its meaning and at the same time challenges a common perception that non-Muslim audiences are uniformly critical of women who wear the niqab. Data analysis of the data so far indicates that women who wear the niqab exercise their agency by making visual references to the everyday and successfully establish dialogue and intimacy with their audiences. It is suggested that new media settings are particularly important in researching ‘niqab experiences’, as they foster a variety of relevant data types and narratives driven by participants, rather than researchers.

Seeking For Truth. Plausibility on a Baha’i Email List - Piff, David; Warburg, Margit (Religion and Cyberspace, 2005)
In the twenty-first century, religious life is increasingly moving from churches, mosques and temples onto the Internet. Today, anyone can go online and seek a new form of religious expression without ever encountering a physical place of worship, or an ordained teacher or priest. The digital age offers virtual worship, cyber-prayers and talk-boards for all of the major world faiths, as well as for pagan organisations and new religious movements. It also abounds with misinformation, religious bigotry and information terrorism. Scholars of religion need to understand the emerging forum that the web offers to religion, and the kinds of religious and social interaction that it enables. Religion and Cyberspace explores how religious individuals and groups are responding to the opportunities and challenges that cyberspace brings. It asks how religious experience is generated and enacted online, and how faith is shaped by factors such as limitless choice, lack of religious authority, and the conflict between recognised and non-recognised forms of worship. Combining case studies with the latest theory, its twelve chapters examine topics including the history of online worship, virtuality versus reality in cyberspace, religious conflict in digital contexts, and the construction of religious identity online. Focusing on key themes in this groundbreaking area, it is an ideal introduction to the fascinating questions that religion on the Internet presents.

The Invisible technologies of Goffman's sociology from the merry-go-round to the Internet - Pinch, T. (Technology and Culture, 2010)
Erving Goffman is not usually thought of as sociologist of technology. In this paper I argue that Goffman's early studies are replete with materiality and technologies. By paying more attention to mundane and invisible technologies, such as merry-go-rounds, surgical instruments, and doors, I argue that Goffman's interaction order can be shown to be materially and technologically framed, staged, and mediated. Important notions such as "role distance," "front stage," and "backstage" turn out to depend crucially upon materiality and technologies. When it comes to studying the internet there is thus, in principle, no fundamental distinction to be drawn between online and off-line interaction; both are forms of performed, staged, and mediated interaction. I show how Goffman's notion of copresence can be extended to the study of the internet and speculate as to what a sociology of material performativity, which combines interactional sociology with the insights of Social Construction of Technology, might look like.

Streetbook: How Egyptian and Tunisian youth hacked the Arab Spring - John Pollock (Technology Review, 2011)
Keywords: Arab Spring; social media

Contesting #StopIslam: The Dynamics of a Counter-narrative Against Right-wing Populism - Poole, Elizabeth; Giraud, Eva; Quincey, Ed de (Open Library of Humanities, 2019)
This paper sets out quantitative findings from a research project examining the dynamics of online counter-narratives against hate speech, focusing on #StopIslam, a hashtag that spread racialized hate speech and disinformation directed towards Islam and Muslims and which trended on Twitter after the March 2016 terror attacks in Brussels. We elucidate the dynamics of the counter-narrative through contrasting it with the affordances of the original anti-Islamic narrative it was trying to contest. We then explore the extent to which each narrative was taken up by the mainstream media. Our findings show that actors who disseminated the original hashtag with the most frequency were tightly-knit clusters of self-defined conservative actors based in the US. The hashtag was also routinely used in relation to other pro-Trump, anti-Clinton hashtags in the run-up to the 2016 presidential election, forming part of a broader, racialized, anti-immigration narrative. In contrast, the most widely shared and disseminated messages were attempts to challenge the original narrative that were produced by a geographically dispersed network of self-identified Muslims and allies. The counter-narrative was significant in gaining purchase in the wider media ecology associated with this event, due to being reported by mainstream media outlets. We ultimately argue for the need for further research that combines ‘big data’ approaches with a conceptual focus on the broader media ecologies in which counter-narratives emerge and circulate, in order to better understand how opposition to hate speech can be sustained in the face of the tight-knit right-wing networks that often outlast dissenting voices.

Media, religion and the marketplace in the information economy: evidence from Singapore - Jessie Poon; Shirlena Huang; Pauline Hope Cheong (Environment and Planning, 2012)
In this paper we suggest that the exchange of communication in a mediatized environment is transforming the nature of transactions in the religious marketplace. In this economy of religious informational exchanges, digitalization facilitates a process of mediatization that converts religious performance into forms suitable for commodifi cation and commoditization. The intersection of digital media, religion, and the marketplace is demonstrated in the context of mega Protestant and Buddhist organizations in Singapore. We show how these large organizations embed media relations in their sacred spaces through a process of hybridization. In turn, hybrid spaces are converted into material outputs that may be readily transacted in real and virtual spaces. Hybridization attends to a postmodern audience and consumers who value experience and sensorial stimulations. It integrates retail, entertainment, and the aesthetics into a space of ascetic performance that is digitally transportable. Digital transactional spaces thrive on the abundance of information, and information multiplies when communication is unfettered by the absence of proprietary safeguards. The religious marketplace may therefore be understood as a medially driven performance space where points of interaction are digitally
Keywords: Buddhism; Computer; Contemporary Religious Community; cyberspace; digital media; hybridization; information economy; internet; Mass media; network; New Media and Society; new media engagement; New Technology and Society; online communication; Online community; Protestantism; religion; religion and internet; Religion and the Internet; religiosity; religious engagement; religious identity; Religious Internet Communication; Religious Internet Communities; Singapore; sociability unbound; Sociology of religion; users’ participation; virtual community; virtual public sphere; “digital religion”; “Internet Studies”; “media and religion”; “media research”; “networked society”; “online identity”; “religion online”; “religious congregations”; “religious media research”; “religious practice online”

Alternative spiritualities, new religious movements and Jediism in Australia - Adam Possamai (Australian Religion Studies Review, 2003)
Perhaps the first academic article to discuss the hyper-real/fiction-based religion Jediism which is based on the Star Wars movies and primarily organised online.
Keywords: alternative religion online; hyper-real religion; Jediism

Religion and Popular Culture. A Hyper-Real Testament - Adam Possamai (Gods, Humans and Religions, 2005)

Authority and liquid religion in cyber-space: the new territories of religious communication - Possamai, Adam; Turner, Bryan S. (International Social Science Journal, 2012)
This article considers three case studies of forms of authority within new cyber-territories. We first deal with the example of a traditional religion, Islam, by exploring new social issues that this religious system encounters in cyber-space. Second, we turn to a social movement that is by definition less traditional and less established, namely neo-paganism; and finally, we examine the new phenomenon of hyper-real religion (Possamai 2005b, 2012) to discover whether, even in free-floating religions where in principle everything is permitted and where the individual has full autonomy to decide on the specific constructions of his/her religion, forms of authority and social/religious distinctions are paradoxically present.

The Cybersangha: Buddhism on the Internet - Prebish, C.D. (Religion Online: Finding Faith on the Internet, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression. Religion Online provides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes the Pew Internet and American Life Project Executive Summary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-defining Cyberspace as Sacred Space.
Keywords: Buddhism; Cybersangha; cyberspace; internet; Online; religion

The Cybersangha: Buddhism on the Internet - Prebish, Charles (Religion Online: Finding Faith on the Internet., 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression. Religion Onlineprovides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes the Pew Internet and American Life ProjectExecutiveSummary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-defining Cyberspace as SacredSpace.

Shofar: An Interdisciplinary Journal of Jewish Studies - Purdue University Press
Shofar, a quarterly, interdisciplinary journal of Jewish studies, is the official journal of the Midwest and Western Jewish Studies Associations. Under the editorship of Zev Garber and Peter Haas and a distinguished editorial board, Shofar ranges far and wide in a multidisciplinary world that spans four thousand years. It publishes original, scholarly work for a general university audience and reviews a wide range of recent books in Judaica.
Keywords: diaspora; history; Jewish Community; Jewish studies; Jews; journal; Judaica; popular culture

What is a thought leader? - Prince, R. A.; Rogers, B. (Forbes.com, 2012)

Information Technology and Cyberspace: Extra-connected Living - Pullinger, D. (Longman and Todd, 2001)

Methods for analyzing let’s plays: Context analysis for gaming videos on YouTube - Radde-Antewler, K; Zeilier, X (Gamenvironments, 2015)
Let's Plays, gaming videos distributed on video platforms such as YouTube, became immensely popular during the last years. As a new research field they offer a huge new pool of research data for the study of video games/gaming and religion. But how to adequately analyze these data? We here propose a matrix for the initial section of analyzing Let's Plays, namely context analysis which then of course needs to be followed by content analysis. Based on the six wh-questions as applied especially also in the classical historical-critical method, we here propose a structured, step by step procedure analyzing specified and clearly defined components. Each step in this context analysis takes up one specific component of the Let's Play and provides context information for it. As such, we present and discuss a sequence of steps which is applicable not only in the study of Let's Plays and religion, but in research on Let's Plays in general.
Keywords: Beyond: Two Souls; context analysis; gamevironments; Let’s Play; YouTube

How to Study Religion and Video Gaming - A Critical Discussion - Radde-Antweiler, K (Methods for Studying Video Games and Religion, 2017)
Game studies has been an understudied area within the emerging field of digital media and religion. Video games can reflect, reject, or reconfigure traditionally held religious ideas and often serve as sources for the production of religious practices and ideas. This collection of essays presents a broad range of influential methodological approaches that illuminate how and why video games shape the construction of religious beliefs and practices, and also situates such research within the wider discourse on how digital media intersect with the religious worlds of the 21st century. Each chapter discusses a particular method and its theoretical background, summarizes existing research, and provides a practical case study that demonstrates how the method specifically contributes to the wider study of video games and religion. Featuring contributions from leading and emerging scholars of religion and digital gaming, this book will be an invaluable resource for scholars in the areas of digital culture, new media, religious studies, and game studies across a wide range of disciplines.
Keywords: religion; video games

Introduction: Religious Authority: Ascribing Meaning to a Theoretical Term - Radde-Antweiler, Kerstin; Grünenthal, Hannah (Journal of Religion, Media and Digital Culture, 2018)
Critical voices in the press argue that with digital media religious authority is weakened or endangered. Moreover, not only the press, but also academic researchers are convinced that the way the construction of religious authority is changing is crucial because it is the base and the backbone of religious organizations and their structures and function. However, there is by no means consensus on the definition of the term authority. Not only religious actors, but researchers as well ascribe different meanings to academic terms such as authority. Therefore, we have to ask critically what actually authority is. In other words, what meaning is ascribed to the concept or term author by the different researchers in their respective disciplines? Based on these reflections, the aim of this report is to analyze how the term authority is 'filled' with meaning in the academic discourse.

Virtual Religion. An Approach to a Religious and Ritual Topography of Second Life - Radde-Antweiler, Kerstin (Heidelberg Journal of Religions on the Internet, 2008)
Kerstin Radde-Antweiler gives an overview or a cross section about the religious and ritualistic settings within “Second Life” and explores the question why studies in and around Virtual Worlds represent an important issue in the Study of Religions. In her article about “Virtual Religion. An Approach to a Religious and Ritual Topography of Second Life” she introduces the theoretical concept of an “actor-related religious historiography” which tries to take into account the religiousness of the individual actor.
Keywords: Actor; religion; Second Life

Rituals Online : Transferring and Designing Rituals - Kerstin Radde-Antweiler (Online – Heidelberg Journal of Religions on the Internet, 2006)
Kerstin Radde-Antweiler stresses the aspect of ritual construction by the individual believers in her paper Rituals Online. Transferring and Designing Rituals. In addition to the potential of the Internet to offer interaction and new processes of communication in the context of rituals – the so called "Online-Rituals" –, this medium also offers much information about rituals and instructions how to perform a ritual, in and outside the Internet. This varies from the publication of – at first glance - fixed ritual prescripts to texts on how to design a ritual by him- or herself. These fixed texts are often identified as old traditional scripts, whereas critical analyses show explicit or implicit transfers and receptions of various religious traditions. In the paper, different ritual prescripts presented on Wicca- and Solitaire Homepages, which are often seen as continuation of pre-Christian, matriarchal, Celtic and Germanic cults and mythologies, are analysed and their transfer processes are exemplified. Instances that show the processes of ritual transfer are the choice of the owner-names, the mixture of deities of different religions, the integration of different feasts and festivals etc. The assertion of perpetual continuity from the insider perspective seems contradict those texts which encourage the believers to develop their own individual ritual. Therefore, the elements of newness and invention as well as the phenomenon of Ritual Design in their processes of gaining legitimacy and authority has to be examined
Keywords: Authority; Digital Religion; Hexe; Hexenglaube; internet; Online-Rituals; Patchwork; religion; Ritual; Wiccakult

‘Blogging Sometimes Leads to Dementia, Doesn’t It?’ The Roman Catholic Church in Times of Deep Mediatization - Radde-Antweiler, K; Grünenthal, H; Gogolok, S (Communicative Figurations, 2018)
The chapter analyzes religious authorities in Catholicism in times of deep mediatization. Like few other organizations, the Catholic Church seems to be caught between the general tendency of deep mediatization and its own reluctance to adapt to a mediatized world and society. One topic that is directly connected to media change is the construction of religious authority. Unlike earlier perspectives on the relation of religious authority and media, the figurational perspective offers the possibility to look at changes in the construction of religious authority and their interrelation with media change on different levels. Those different levels refer to different actor constellations and different media ensembles, as well as to different levels of authority, in other words local and translocal authority. In this chapter, we will explore how official religious authorities in the Catholic Church, namely priests in different positions, deal with deep mediatization. This includes the question concerning how they use media themselves, in which situations they use or don’t use media, how and why they are reluctant; but also how they define their own and other’s authority in a mediatized society and how all of this effects the organization as a whole. We will find out that there are different scopes in which authority is constructed differently: while the degree of mediatization is relatively low on the local scope, religious authorities are expected to go with mediatization in a translocal and global scope.
Keywords: Blogging; dementia; mediatization; Roman Catholic Church

Ritual is becoming digitalised". Introduction to the Special Issue on Rituals on the Internet - Kerstin Radde-Antweiler (Online – Heidelberg Journal of Religions on the Internet, 2006)
Keywords: analysing rituals; communication within the Internet; media and religion; New Technology and Society; Online community; Practicing Faith in Cyberspace; religion; religious practice; RITUALS ON THE INTERNET; Techno-Ritualization

Wedding Design. Online: Transfer and Transformation of Ritual Elements in the Context of Wedding Rituals - Radde-Antweiler, K. (Ritual Matters. Dynamic Dimensions in Practice, 2010)
This book explores the interaction of rituals and ritualised practices utilising a cross-cultural approach. It discusses whether and why rituals are important today, and why they are possibly even more relevant than before.

Mediatized Religion in Asia: Studies on Digital Media and Religion - Radde-Antweiler, Kerstin; Zeiler, Xenia (Routledge, 2018)
This edited volume discusses mediatized religion in Asia, examining the intensity and variety of constructions and processes related to digital media and religion in Asia today. Individual chapters present case studies from various regions and religious traditions in Asia, critically discussing the data collected in light of current mediatization theories. By directing the study to the geographical, cultural and religious contexts specific to Asia, it also provides new material for the theoretical discussion of the pros and cons of the concept mediatization, among other things interrogating whether this concept is useful in non-’Western’ contexts."

Rituals-Online: Transferring and Designing Rituals - Radde-Antwiler, K. (Online-Heidelberg Journal of Religion on the Internet, 2006)
“(1) We acquire knowledge today from the Internet. (2) Searching and finding information in the Internet is an independent element of our culture – in the future, children will learn how to count, read, write, and google at school. (3) The ability to acquire information and integrate it into our personal corpus of knowledge is more important than the knowledge itself. (4) Search engines like Google always provide a surplus of information: Users find answers to questions that they haven’t even asked (yet). Google generates an entire universe of questions and in the process ultimately changes the basic operation of knowledge acquisition.”
Keywords: Design; Online; Ritual

Exploring the Meanings of Hijab through Online Comments in Canada - Rahman, Osmud; Fung, Benjamin; Yeo, Alexia (Journal of Intercultural Communication Research, 2016)
Controversies surrounding ethnic dress such as hijab have increased public awareness about cultural diversity. The number of comments posted on online media make it evident that many people are concerned about ethnic attire, cultural differences and social cohesion. Although researchers have examined the meanings of veiling, the relationships between hijab and public opinion have seldom been investigated. The overarching objective of this study was to understand the relationships between Islamic attire and online readers’ opinion. In light of the limitations in the previous studies on this topic, this study attempts to fill the gap by studying posters’ opinions toward hijab through publicly available online information in the form of posted comments.

Digital religion, the supermarket and the commons - Rähme, Boris (Sociétés, 2018)
The aim of this article is to highlight an intersection between recent research on contemporary spiritualities and work in the field of digital religion. The concept of commons-based peer production, developed in the areas of social digital technologies and networked collaboration, offers an alternative to the widely used analogy of the spiritual supermarket when it comes to describing and explaining the eclecticism at work in some contemporary spiritualities.

Divergent Attitudes within Orthodox Jewry Toward Mass Communication - Rashi, T (Review of Communication, 2011)
This paper examines the divergent attitudes toward mass media among the streams of Orthodox Jewry. According to most Ultra-Orthodox Jewish leaders, media spread blasphemy, provoke gossip and slander, and steal time from religious studies, but Rabbi M. Schneerson, late leader of the Chabad movement, believed that the media should be exploited to spread the tenets of Judaism. Modern Orthodox rabbis generally favor limited access to media*filtering out its negative aspects, embracing its positive features, and using it to impart religious knowledge. Understanding these various attitudes may help media professionals deal with religion-based criticism and encourage media-borne moderate religious dialogue.
Keywords: Communication; Jewish; Jews; Orthodox

The bases of social power - Raven, B. H.; French, J. (Studies in social power)
5 types of social influence, leading to various research hypotheses, are distinguished: referent power, expert power, reward power, coercive power, and legitimate power. Referent power, involving identification of P with O, will tend to have the broadest range. Coercion will produce decreased attraction of P toward O and high resistance. Reward will result in increased attraction and low resistance. "The more legitimate the coercion the less it will produce resistance and decreased attraction." 42 refs. (PsycINFO Database Record (c) 2016 APA, all rights reserved)

Practically Religious: Worldly Benefits and the Common Religion of Japan - Reader, Ian; Tanabe, George J. (University of Hawai’i Press, 1998)

Virtual worlds: culture and imagination - Reid, E (Cybersociety, 1995)
The culture of computer and network- mediated communication is growing both in size and sophistication. Cyberspace is the new frontier where new worlds, meanings and values are developed. CyberSociety focuses on the construction, maintenance and mediation of community in electronic networks and computer-mediated communication. Leading scholars representing the range of disciplines involved in the study of cyberculture lay out the definitions, boundaries and approaches to the field, as they focus on the social relations that computer-mediated communication engenders.

Hierarchy and power: social control in cyberspace - Reid, E (Communities in Cyberspace, 1999)
This wide-ranging introductory text looks at the virtual community of cyberspace and analyses its relationship to real communities lived out in today's societies. Issues such as race, gender, power, economics and ethics in cyberspace are grouped under four main sections and discussed by leading experts: * identity * social order and control * community structure and dynamics * collective action. This topical new book displays how the idea of community is being challenged and rewritten by the increasing power and range of cyberspace. As new societies and relationships are formed in this virtual landscape, we now have to consider the potential consequences this may have on our own community and societies. Clearly and concisely writtenwith a wide range of international examples, this edited volume is an essential introduction to the sociology of the internet. It will appeal to students and professionals, and to those concerned about the changing relationships between information technology and a society which is fast becoming divided between those on-line and those not.

Clothed With Strength And Dignity: How Evangelical Women are Re-Claiming and Re-Constructing the Evangelical Church in the Blogosphere - Vanessa Reimer (The World Social Science Forum, 2013)
Much has been written on the significance of the religious web log or “blog” in the past decade, especially as its growing popularity among authors and readers alike has coincided with the continued decline in institutional church attendance in the West (see Cheong et al, Corrigon et al, Campbell, and West). However, much less has been written on the significance of religious blogs authored by women, and particularly those that are written from a standpoint of cultivated ambivalencei toward the doctrines and practices of their religious traditions; a phenomenon that is especially poignant for feminist scholars to consider given the historical tendency for patriarchal religious institutions to marginalize and delegitimize women's voices (Bammert 155; Gallagher 215; Steiner-Aeschliman and Mauss 248). To that end, it is further pertinent to consider the growing popularity of religious blogs authored by women in North America who identify as evangelical Protestant—a Christian tradition that remains largely (albeit not exclusively) committed to the value of patriarchal authority within and outside the institutional church, even (and especially) while some mainline Protestant denominations have been adopting the value of gender equality both at the institutional and doctrinal levels (Steiner-Aeschliman and Mauss 248; Keller and Ruether xxxviii-xxxix). This exploratory study accordingly employs feminist Critical Discourse Analysis to investigate a purposive selection of religious blogs that are authored by evangelical women and written from a standpoint of cultivated ambivalence.
Keywords: Blogosphere; Christianity; Digital Religion; Evangelical Church; female; GENDER; Women

Witches on Facebook: Mediatization of Neo-Paganism - Renser, Berit; Tiidenberg, Katrin (Social Media + Society, 2020)
This article investigates the mediatization of neo-Paganism by analyzing how Estonian witches use Facebook groups and Messenger and how Facebook’s affordances shape the neo-Paganism practiced in those spaces. This is a small-scale exploratory study based on ethnographic interviews and observational data. To understand the mediatization of neo-Paganism, we use the communicative figurations model which suggests three layers of analysis: framing, actors, and communicative practices. For a more granular understanding of these three on social media, we rely on the framework of affordances. We found that social media neo-Paganism is (1) characterized by networked eclecticism; (2) enacted by witches who amass authority by successfully using social media affordances; and (3) consists of practices and rituals that are preferred by seekers, easily transferable to social media settings and validated by Facebook algorithms. Social media neo-Paganism thus is a negotiation between authoritative witches, seekers, and platform affordances that validate some practices over others.

Cybernauts Awake!: Ethical and Spiritual Implications of Computers, Information Technology and the Internet - Church of England Board for Social Responsibility (Church Publishing House, 1999)

The New Media Frontier: Blogging, Vlogging, and Podcasting for Christ - Reynolds, John Mark; Overton, Roger; Hewitt, Hugh (Crossway Books, 2008)
Study reports that only 2% of America's twelve millionbloggers claim "religion, spirituality or faith" as their maintopic. This leaves a great mission field in cyberspace, saycontributors to The New Media Frontier, because the latestforms of communication present so many opportunities to promote thecause of Christ in other topics and fields. Before blindly jumpingin, however, Christians need to weigh the possibilities against theconsequences, and then proceed with the practical discernment andgrace this book provides. With a foreword by national radio host Hugh Hewitt-who has beenat the forefront of the new media movement among Christians-editorsRoger Overton and John Mark Reynolds (along with an impressive listof other new media experts) survey the current landscape andexplore specific areas in which God's people can creatively expandtheir reach to a lost world. By stressing the urgency for Christianinvolvement, unearthing the dangers, and advising readers on how touse this media with different audiences, this book equips believersto advance, demonstrate, and utilize the Christian worldview inthis exciting realm.

The Virtual Community - Rheingold, H. (Harper Perennial, 1993)
"When you think of a title for a book, you are forced to think of something short and evocative, like, well, 'The Virtual Community,' even though a more accurate title might be: 'People who use computers to communicate, form friendships that sometimes form the basis of communities, but you have to be careful to not mistake the tool for the task and think that just writing words on a screen is the same thing as real community.'" - HLR
Keywords: community; Computer; culture; internet; media; Virtual

The Church of Facebook: How the Hyperconnected Are Redefining Community - Rice, Jesse (David C. Cook, 2007)
A revolution is taking place, one profile at a time. Online social networks are connecting people like never before. And with millions of users, they’re creating a virtual world that erases all boundaries. It’s a movement that’s changing how we form relationships, perceive others, and shape our identity. Yet at their core, these sites reflect our need for community. Our need for intimacy, connection, and a place to simply belong. Are we seeing the future of the church? Do these networks help or hurt relationships? And what can these sites teach us about God and each other? The Church of Facebook explores these ideas and much more. Author Jesse Rice offers a revealing look at the wildly popular world of online social groups. From profiles, to The Wall, to status updates, to “poking,” Jesse shares what Facebook reveals about us, and what it may mean for the church.

New media/Internet research topics of the association of Internet researchers - Rice, R (The Information Society: An International Journal, 2005)
This study summarizes prior reviews of new media and Internet research, and the growth of the term Internet in academic publications and online newsgroups. It then uses semantic network analysis to summarize the interests and concepts of an interdisciplinary group of Internet researchers, as represented by session titles and paper titles and abstracts from the 2003 and 2004 Association of Internet Researchers conferences. In both years, the most frequent words appearing in the paper abstracts included Internet, online, community, social, technology, and research. The 2003 papers emphasized topics such as the social analysis/ research of online/Internet communication, community, and information, with particular coverage of access, individuals, groups, digital media, culture; role and process in e-organizations; and world development. The 2004 papers emphasized topics such as access; news and social issues; the role of individuals in communities; user-based studies; usage data; and blogs, women, and search policy, among others.
Keywords: access; AoIR; communication technology; internet research; new media research; Online community; semantic network analysis

The Twible: All the chapters of the Bible in 140 characters Or Less . . . Now with 68% more humor - Riess, J (Jana Riess, 2013)
You've wanted to read the Bible, but it's uber-long and, let's face it, sometimes boring. You're a busy person with stuff to do. You want the Bible, only funnier. Enter The Twible, which brings you every chapter as tweeted in 140 characters or less, from Genesis to Revelation! Find out what the Bible says you're supposed to do if a friend starts worshiping another god, your child disrespects you in public, or you break the Sabbath. (The answers to those dilemmas are to stone your friend, stone your child, and stone yourself. In that order.) Learn where Paul swears in the New Testament, and why Jeremiah could benefit from antidepressants. Inside The Twible you'll find: A tweet for each of the 1,189 chapters of the Bible A summary of every book of the Bible in seven words or less Dozens of informative sidebars (print edition only) More than 50 original cartoons A glossary telling you who's who in the Bible Unicorns From start to finish, The Twible brings the Bible to wonderful, wicked, weird life. The Twible adapts the Old Testament to the light-hearted quipping familiar in everyday Tweets.-- The Guardian, The Twible is the most entertaining version of my dad's book I've read in the last two millennia! -- Jesus Christ The Twible is the best example I have ever seen of the reverence of irreverence. Only those who love deeply and securely can bring this kind of humor to the telling of the family's stories. Don't read it, unless you are prepared to fall in love with them again. -- Phyllis Tickle, author of The Divine Hours and The Great Emergence I wouldn't object if Twibles were in every hotel room. If they're using this book, I look forward to the next time Christians attempt to proselytwize -- Hemant Mehta, The Friendly Atheist blogger; author of The Young Atheist's Survival Guide Forget about reading the Bible in a year. Now you can read it in an hour, thanks to the subversive, somewhat disturbed, mind of Jana Riess. -- Peter Enns, author of Genesis for Normal People The perfect (surreptitious) iPad or Tablet companion for draggy Sunday (or Saturday) morning services. Caution: Not to be used for congregational Scripture reading. -- Mark I. Pinsky, author of The Gospel According to the Simpsons Whatever you think of Twitter, there can be no speedier or funnier way to read through the Bible than with Riess's Twible providing spot-on interpretation chapter by chapter. On a jet stream of solid scholarship, it'll keep you thinking long after the hashtags have burned away. -- Kristin Swenson, author of Bible Babel: Making Sense of the Most Talked-about Book of All Time The Twible is an indelible book that reads like an oddly religious comedy but has the impact of a brilliant jingle that sticks in your brain to the point of madness. Read it and drive yourself pleasantly nuts. -- Frank Schaeffer, author of And God Said, Billy! This is brilliant stuff;hilariously accurate summaries of complex material. Riess is a very funny, charmingly masterful guide. -- Debbie Blue, pastor; author of Consider the Birds: A Provocative Guide to the Birds of the Bible This is absolutely the funniest and most fun Bible translation ever. Yet, throughout the ensuing hilarity there is a wisdom here that challenges and provokes. -- Steven L. Peck, author of A Short Stay in Hell and The Scholar of Moab

Medios digitales y religión: investigar la mediatización de la fe en la era digital - Riezu,Xabier (Crisis y cambio: propuestas desde la sociología)
Keywords: Mediatización; medios digitales; podcasting; Rezandovoy

Uses and Gratifications of a Spanish Digital Prayer Project: Rezandovoy - Riezu,Xabier (Trípodos, 2014)
This article attempts to make a contribution, from a sociology and communication sciences perspective, about the knowledge of religion in digital media. The results of a case study about Rezandovoy, a digital prayer service of the Society of Jesus, are exposed here. The service was created in Valladolid (Spain) in 2011 and it is used by 40,000 Spanish-speakers from around the world daily. The theoretical framework used is the paradigm of uses and gratifications, a consolidated framework in mass media research that is also applied to new digital media. This theoretical framework helps to explain the reasons why believers from all over the world use digital media in relation to their faith. In the current case study, through a methodology consisting in focus groups, interviews and virtual ethnography, it is concluded that there are a variety of gratifications that encourage users to utilise Rezandovoy. By taking into account what the users themselves say about the satisfactions that they obtain from the service, six categories of gratifications are defined: “Spiritual”, “Prayer School”, “Guidance”, “Social Utility”, “Diversion” and “Emotional”.
Keywords: audio prayer; digital prayer; Jesuits; Rezandovoy; uses and gratifications theory

Money, God, and SMS: Explorations in Supporting Social Action Through a Bangladeshi Mosque - Rashidujjaman Rifat, M; Chen, J; Toyama, K (CHI Conference, 2017)
Religious institutions hold a significant place in daily life for the vast majority of people in the world, especially in developing countries. Yet despite their social prominence, and despite HCI's emphasis on the social context of technology, organized religion is neglected in both the HCI and ICTD literature. This paper explores the relationship that mosques in Bangladesh have with their constituencies and with technology, with an eye toward the integration of technology with existing religious institutions as a way to achieve positive social ends. We first describe a qualitative exploration of several mosque communities in Bangladesh, where we find that skepticism and pragmatism about modern technology interact in a complex way that nevertheless leaves room for technical interventions. We then describe a randomized controlled trial to study the relative value of SMS messages infused with overtly religious or secularly altruistic frames for the purpose of mosque fundraising. We find that SMS messages increase donations overall, but that their framing is significant. Messages with secular altruistic framing increased donations by 9.5%, while those with religious sentiment increased donations by 57.3%. Our findings demonstrate how technologies like SMS amplify underlying religious forces and suggest the possibility of working with religious institutions in applying positive ICT interventions.
Keywords: Bangladeshi Mosque; God; money; SMS; social action

The Beast Within: Anthrozoomorphic Identity and Alternative Spirituality in the Online Therianthropy Movement - Venetia Laura Delano Robertson (Nova Religio: The Journal of Alternative and Emergent Religions, 2013)
Keywords: NRMs; popular occulture; shape-shifters; Therianthropy

Virtual Warfare: The Internet as the New Site for Global Religious Conflict - Robinson, Rowena (Asian Journal of Social Science, 2004)
This paper explores the ways in which a resurgent Hindu fundamentalism (Hindutva) is redefining Hinduism and Hindu identities in a transnational, global context. The global project of Hindutva makes use of new global communication channels, including the Internet, and is apparently espoused by influential sections of the transnational Hindu middle class, especially in the United States. This paper examines a selected sample of Internet sites devoted to the spread of religious and fundamentalist beliefs and ideas particularly relevant to India and transnational Hinduism, and explores the ways in which the Internet is changing the shape of communities and the ways in which they represent one another. The paper puts forth the argument that in the context of globalization, the Net has become an important space for the creation of transnational religious identities. The Net is shaping religion, specifically Hinduism, in distinct ways and is the newest expression of religion's changing face. The battle for souls is being fought on Internet sites. The questions of this paper relate to the modes of representation of "other religions" as revealed particularly by Hindu sites, the ways in which Internet sites garner audiences, and the strategies they adopt to link themselves with both global audiences and local groups. A sociological analysis will reveal the shape of these discourses and link their popularity with the social and political context of globalization, a liberalized economy, and the organization of religious practice in post 1990s India.
Keywords: Communication; Globalization; Hindu; religion

Enhancing the Spiritual Relationship: The Impact of Virtual Worship on the Real World Church Experience - Robinson-Neal, Andreé (Heidelberg Journal of Religions on the Internet, 2008)
In her article “Enhancing the Spiritual Relationship: The Impact of Virtual Worship on the Real World Church Experience” Andreé Robinson-Neal discusses her experiences as a virtual churchgoer in “Second Life“ and describes the relationship between online worship and her offline faith experience. The article centres around the reality of experience in virtual worship and how can both enhance and hinder the “real-life faith walk.

Goffman on power, hierarchy, and status - Rogers, M. F. (The View from Goffman, 1980)
Among the most commonly overlooked set of insights offered by Erving Goffman is his commentary, comprised of both explicit and implicit elements, on the interrelationship among power, hierarchy, and status in everyday life. In fact, Goffman has been subject to criticism for his apparent failure to treat these sorts of stratification-related phenomena. To date the most detailed critique of Goffman along these lines is Alvin Gouldner’s analysis.1

The Jewish Guide to the Internet - Romm, Diane (Jason Aronson Publishers, 1996)
This is the only current and comprehensive guide to Jewish sites on the Internet. Completely rewritten, this volume contains more than 1500 sites arranged in 136 subject areas. This is a new and updated edition of the popular reference guide to the Jewish electronic universe. Included is an alphabetical listing of the Jewish sources found on the internet.

The Talmud and the Internet: A Journey between Worlds - Rosen, Jonathan (Farrar, Straus and Giroux, 2000)
The Talmud and the Internet, in which Jonathan Rosen examines the contradictions of his inheritance as a modern American and a Jew, is a moving and exhilarating meditation on modern technology and ancient religious impulses. Blending memoir, religious history and literary reflection Rosen explores the remarkable parallels between a page of Talmud and the homepage of a web site, and reflects on the contrasting lives and deaths of his American and European grandmothers. Jonathan Rosen is the author of the novels Joy Comes in the Morning and Eve's Apple. His essays have appeared in The New York Times and The New Yorker, among other publications. He is the editorial director of Nextbook. The Talmud and the Internet, in which Jonathan Rosen examines the contradiction of his inheritance as an American and a Jew, is a moving and exhilarating mediation on modern technology and ancient religious impulses. Blending memoir, religious history, and literary reflection, Rosen explores the remarkable parallels between a page of Talmud and the home page of a website and reflects on the contrasting lives and deaths of his American and European grandmothers.

TV : Satan or Savior? : Protestant responses to television in the 1950s - Michele Ann Rosenthal (University of Chicago, 1999)
Keywords: 1950; communication research; Mass media; media and religion; Protestant; Television

On Pomegranates and Etrogs: Internet Filters as Practices of Media Ambivalence among National Religious Jews in Israel - Rosenthal, M; Ribak, R (Digital Judaism: Jewish Negotiations with Digital Media and Culture, 2015)
In the contemporary environment of media saturation, users are continually making choices about the types and kinds of media technologies to employ or avoid at different moments and places in their everyday lives. Some of these choices are based on simple technical or practical criterion (i.e., my smartphone is easy to access during my daily commute), while others are informed by a sense of decorum (i.e., one should not text during a funeral) or the idea that self-imposed limits of media use will lead to a more balanced lifestyle (i.e., no e-mail after work hours). Among such abundance, it is nearly impossible to be an early adopter or enthusiastic user of all media-users are constantly making choices (i.e., to text rather than telephone, to invest in a laptop but not in a smartphone, etc.), and through these choices they express ambivalence about certain media and enthusiasm about others. Users’ deliberations and discussions about these choices and practices are increasingly employed as identity markers (Hoover, Clark and Alters, 2004; Seiter, 2003). Media consumption and avoidance of specific contents or technologies are not only practical choices but also are expressions of identification with a specific class, ethnic, religious or spiritual community.
Keywords: internet filters; Israel; Jews; religious

The Dynamics of Religion, Media, and Community - Rota, Andrea; Kruger, Oliver (Online - Heidelberg Journal of Religions on the Internet, 2019)
This article introduces the special issue, “The Dynamics of Religion, Media, and Community”. It examines the shifting faith in the concept of religious community in the social studies of religion and calls attention to the normative expectations connected to the rise of new forms of communities in the age of the Internet. Against this backdrop, it discusses strengths and weakness of selected approaches in the study of media and religion and suggests future research pathways to which the articles in the special issue provide important contributions.

“Electronic Jihad”: The Internet as Al Qaeda's Catalyst for Global Terror - Rudner, M (Studies in Conflict & Terrorism, 2016)
The Internet has emerged as a key technology for Al Qaeda and other jihadist movements waging their so-called electronic jihad across the Middle East and globally, with digital multiplier effects. This study will examine the evolving doctrine of “electronic jihad” and its impact on the radicalization of Muslims in Western diaspora communities The study describes Internet-based websites that served as online libraries and repositories for jihadist literature, as platforms for extremist preachers and as forums for radical discourse. Furthermore, the study will then detail how Internet connectivity has come to play a more direct operational role for jihadi terrorist-related purposes, most notably for inciting prospective cadres to action; for recruiting jihadist operatives and fighters; for providing virtual training in tactical methods and manufacture of explosives; for terrorism financing; and for actual planning and preparations for specific terror attacks. Whereas contemporary jihadist militants may be shifting from the World Wide Web to social media, such as Facebook, YouTube, and Twitter for messaging and communications, nevertheless the Internet-based electronic jihad remains a significant catalyst for promoting jihadist activism and for facilitating terrorist operations.
Keywords: Al Qaeda; electronic; internet; jihad

Ethnic Revival, and the Reappearance of Indigenous Religions in the ROC : the Use of the Internet in the Construction of Taiwanese Identities - Michael Rudolph (Online – Heidelberg Journal of Religions on the Internet, 2006)
Michael Rudolph’s article Nativism, Ethnic Revival, and the Reappearance of Indigenous Religions in the ROC: The Use of the Internet in the Construction of Taiwanese Identities deals with rituals presented on Taiwanese Websites in the context of identity construction. Since the mid-nineties, long abandoned and very un-Chinese ritual practices suddenly seemed to become popular again in China’s runaway-province Taiwan: in spite of the fact that most of the island’s 2% of indigenous population had been Christianized for half a century, intellectual elites of different aboriginal groups now referred to ancestor-gods, tattooing and even headhunting again as essential parts of their own traditional repertoire, often making abundant use of the Internet in order to propagate these convictions to a broader Chinese speaking public. This contribution not only scrutinises the political context that made such a development possible, but also assesses this practice in terms of the identity construction of the specific ethnic groups.
Keywords: aboriginal groups; Digital Religion; Ethnic; identity; Indigenous Religions; internet; online communication; religion online; Ritual; Taiwan

Virtual Spirituality: The Negotiation and (Re)-Presentation of Psychic-Spiritual Identity on the Internet - Ryan, Tamlyn (University of York, 2012)
This research is an examination of how people engaged in psychic and spiritual interests use the internet to participate as a group through social media. Exploring how individuals take advantage of the opportunities afforded by the internet to pursue their interest in psychic spirituality reveals different ways of participating and interacting online. The ways in which individuals present their psychic-spiritual selves online, how they negotiate their online identities and make sense of their culture, is also examined. Using an eclectic methodological approach, this research used a combination of ethnographic methods and autoethnography to explore online psychic-spiritual culture. Documentary analysis of website text and images, together with participant observation, both covert and overt, were used to examine websites. Facebook interaction and psychic readings in online discussion board forums based on psychic-spiritual interests were analysed using discourse analysis. Autoethnographic self-reflections were also collected and analysed in order to capture an intrapsychic perspective of psychic reading culture. It was found that psychic practitioners use their websites to communicate the message that they are credible psychic readers whilst Facebook was found to be a site in which, through a delicate interplay of activity and performance, identity is constructed through interaction between the psychic reader and their Facebook friends. Psychic-spiritual discussion board forums meanwhile are sites of situated learning in which learner psychic readers learn to become appropriate members of the psychic-spiritual milieu. Also, although the sociological analytic mind does not easily accommodate the nature of psychic reading, the study did manage to obtain an intrapsychic perspective on psychic readings. Thus, members of the psychic-spiritual milieu have taken full advantage of the internet to pursue their interest in psychic reading culture.
Keywords: communities of practice; Facebook; online forums; psychic practices; psychic spirituality; virtual spirituality

Holy mavericks: evangelical innovators and the spiritual marketplace - Lee S.L.; Sinitiere P.L. (New York University Press, 2009)
Joel Osteen, Paula White, T. D. Jakes, Rick Warren, and Brian McLaren pastor some the largest churches in the nation, lead vast spiritual networks, write best-selling books, and are among the most influential preachers in American Protestantism today. Spurred by the phenomenal appeal of these religious innovators, sociologist Shayne Lee and historian Phillip Luke Sinitiere investigate how they operate and how their style of religious expression fits into America's cultural landscape. Drawing from the theory of religious economy, the authors offer new perspectives on evangelical leadership and key insights into why some religious movements thrive while others decline. Holy Mavericksprovides a useful overview of contemporary evangelicalism while emphasizing the importance of "supply-side thinking" in understanding shifts in American religion. It reveals how the Christian world hosts a culture of celebrity very similar to the secular realm, particularly in terms of marketing, branding, and publicity. Holy Mavericksreaffirms that religion is always in conversation with the larger society in which it is embedded, and that it is imperative to understand how those religious suppliers who are able to change with the times will outlast those who are not.

Media, Racism and Islamophobia: The Representation of Islam and Muslims in the Media - Saeed, Amir (Sociology Compass, 2007)
This article examines the representation of Islam and Muslims in the British press. It suggests that British Muslims are portrayed as an ‘alien other’ within the media. It suggests that this misrepresenatation can be linked to the development of a ‘racism’, namely, Islamphobia that has its roots in cultural representations of the ‘other’. In order to develop this arguement, the article provies a summary/overview of how ethnic minorities have been represented in the British press and argues that the treatment of British Muslims and Islam follows these themes of ‘deviance’ and ‘un-Britishness’.

The Effects of Religiousity on Internet Consumption - Ozlem Hesapci Sanaktekina; Yonca Aslanbayb; Vehbi Gorguluc (Information, Communication & Society, 2012)
The relationship between technology adoption and religion has received scant research attention. The complicated process of Internet use among contemporary religious people is affected by the tension between technological developments and religious beliefs. The current research aims to explore the effects of religiosity on Internet consumption in a newly industrialized Muslim country, Turkey. The study utilized a cross-sectional design based on data from 2,698 subjects, selected by stratified random sampling, covering all 12 regions of the country. By offering an exploratory approach, this study sheds light on how various interpretations of religion enable culture-specific observations on Internet consumption patterns, and its relation with different levels of religiosity. The findings revealed that the level of religiosity has a significant effect on the patterns of Internet consumption.
Keywords: Internet use; religion; religiousity; social media

Tweeting Prayers and Communicating Grief over Michael Jackson Online - Sanderson, James; Pauline Hope Cheong (Bulletin of Science, Technology, & Society, 2010)
Death and bereavement are human experiences that new media helps facilitate alongside creating new social grief practices that occur online. This study investigated how people’s postings and tweets facilitated the communication of grief after pop music icon Michael Jackson died. Drawing upon past grief research, religion and new media studies, a thematic analysis of 1,046 messages was conducted on three mediated sites (Twitter, TMZ.com, and Facebook). Results suggested that social media served as grieving spaces for people to accept Jackson’s death rather than denying it or expressing anger over his passing. The findings also illustrate how interactive exchanges online helped recycle news and “resurrected” the life of Jackson. Additionally, as fans of deceased celebrities create and disseminate web-based memorials, new social media practices like “Michael Mondays” synchronize tweets within everyday life rhythms and foster practices to hasten the grieving process.
Keywords: blogs; celebrity; internet; microblogging; popular culture; religion; social media

Tweeting Prayers and Communicating Grief over Michael Jackson Online - Sanderson, Jimmy; Pauline Hope Cheong (Bulletin of Science Technology & Society, 2010)
Death and bereavement are human experiences that new media helps facilitate alongside creating new social grief practices that occur online. This study investigated how people’s postings and tweets facilitated the communication of grief after pop music icon Michael Jackson died. Drawing on past grief research, religion, and new media studies, a thematic analysis of 1,046 messages was conducted on three mediated sites (Twitter, TMZ.com, and Facebook). Results suggested that social media served as grieving spaces for people to accept Jackson’s death rather than denying it or expressing anger over his passing. The findings also illustrate how interactive exchanges online helped recycle news and “resurrected” the life of Jackson. Additionally, as fans of deceased celebrities create and disseminate web-based memorials, new social media practices such as “Michael Mondays” synchronize tweets within everyday life rhythms and foster practices to hasten the grieving process.
Keywords: Communication; Death; Grief; Social Practices

La reconstrucción de lo “religioso” en la circulación en redes socio-digitales - Moisés Sbardelotto (La Trama de la Comunicación, 2014)
En este artículo, se presenta una reflexión sobre la mediatización digital de la religión, fenómeno socio-comunicacional en que se sitúa la actual reconstrucción de lo religioso. En sitios católicos brasileños, se analiza el desvío de la práctica de la fe al ambiente online a partir de lógicas mediáticas, los llamados rituales online, que complejizan el fenómeno religioso y las procesualidades comunicacionales. Se describen tres modalidades de oferta y apropiación de lo sagrado: la inter faz interaccional, las interacciones discursivas y las interacciones rituales. A partir de esas nuevas modalidades de percepción y de expresión de lo sagrado, se analizan las prácticas de instituciones sociales como la Iglesia y la sociedad en general al hablar públicamente sobre lo religioso en las redes digitales – en este caso, lo “católico”, es decir, constructos simbólicos que la sociedad considera como vinculados a la doctrina y tradición de la Iglesia Católica-. Se analizan, entonces, los conceptos de reconexión y dispositivos conexiales. Como conclusión, se afirma que, en esa reconstrucción de lo “católico”, surge una religiosidad en experimentación marcada por e-rejías, o sea, nuevos sentidos simbólicos de lo religioso en red, “bricolajes de la fe” en el ambiente digital. This article presents a reflection on the digital mediatization of religion, socio-communicational phenomenon in which stands the current reconstruction of the religious. In Brazilian Catholic sites, it analyzes the displacement of the practice of the faith to the online environment based on mediatic logics, the so-called rituals online, that turn the religious phenomena and the communication processualities more complex. It describes three forms of of fer and appropriation of the sacred: the interactional inter face, the discursive interactions and the ritual interactions. From these new modes of perception and expression of the sacred, it analyses practices of social institutions as the Church and society in general to speak publicly about religion in digital networks – in this case, the “Catholic”, ie symbolic constructs that society considers as linked to the doctrine and tradition of the Catholic Church. It then discusses the concepts of reconnection and connectial devices. In conclusion, it is stated that in the reconstruction of the “Catholic” arises a religiosity in experimentation marked by e-resies, ie new symbolic meanings of the networked religious, “bricolages of faith” in the digital environment.
Keywords: Catholic Church; Catholicism; circulation; connectial dispositifs; mediatization; mediatization of religion; reconnections; socio-digital networks

The Sacred in Bits and Pixels: An Analysis of the Interactional Interface in Brazilian Catholic Online Rituals - Moisés Sbardelotto (Journal of Religion, Media and Digital Culture (JRMDC), 2014)
Through digital technologies, a new form of communicational interaction between the user and the sacred occurs in an online religious experience. This phenomenon is illustrated in practice by numerous religious services present in the online Catholic environment, which manifest new modes of discourse and religious practices, beyond the scope of the traditional church – what I term here “online rituals” – marked by a process of mediatization of religion. In this paper, from a corpus of four Brazilian websites, I analyze key concepts for the understanding of this phenomenon, including digital mediatization and interface. I examine, in these Brazilian Catholic websites, the communicational configurations of the religious experience from five areas of the interactional interface: the screen; peripherals; the organizational structure of content on websites; the graphic composition of the webpages; and possible interface failures. Finally, I examine a shift in the communicational dynamics of religion today, marked by new materialities present in online religious rituals.
Keywords: Brazil; Catholic Church; Catholicism; Interaction; interface; internet; mediatization; mediatization of religion; online rituals; religion; technology

'E o Verbo se fez bit': Uma análise da experiência religiosa na internet - Moisés Sbardelotto (2011)
Com a manifestação de um fenômeno de apropriação da Internet por parte das instituições religiosas católicas, este texto busca analisar o funcionamento das interações entre fiel-Igreja-Deus para a vivência, a prática e a experiência da fé nos rituais online do ambiente digital católico brasileiro. Examina-se particularmente, por meio de uma metodologia analítica qualitativa, fundamentada nas contribuições do pensamento sistêmico e complexo, um corpus de pesquisa de quatro sites católicos: CatolicaNet, Irmãs Apóstolas do Sagrado Coração de Jesus – Província do Paraná, A12 e Pe. Reginaldo Manzotti. Perscruta-se, assim, que religião resulta dessa manifestação de práticas religiosas a partir do emprego e da atividade dos meios digitais, com o objetivo de colaborar com a análise das primeiras consequências diretas que esse fenômeno está trazendo para a religião e, particularmente, para a Igreja Católica como a conhecemos hoje. A partir de uma leitura de alguns estudos que abordam a interface entre comunicação e fenômeno religioso na Internet, reflete-se sobre alguns conceitos e perspectivas de análise para a investigação dos sites católicos institucionais brasileiros, como a midiatização digital do sistema religioso; a questão da técnica transformada em meio; novas modalidades de experienciação; e novas configurações de tempo-espaço-materialidades na experiência religiosa do fiel-internauta. Em seguida, descrevem-se três modalidades de estratégias de oferta de sagrado por parte do sistema e de apropriação por parte do fiel nos sites católicos brasileiros, a partir de inferências obtidas em nosso corpus de pesquisa: os níveis tecnológico e simbólico da interface interacional; quatro fluxos de interações discursivas; e dois fluxos, com dois subfluxos cada, de interações rituais. Como pistas de conclusão, aponta-se que, por meio dessas estratégias interacionais, a religião que nasce no ambiente online é vivenciada, praticada e experienciada por meio de novas temporalidades, novas espacialidades, novas materialidades, novas discursividades e novas ritualidades marcadas pelos protocolos e processualidades da Internet.
Keywords: Interaction; internet; mediatization; religion; system

Close Ties, Intercessory Prayer, and Optimism Among American Adults: Locating God in the Social Support Network - Markus H. Schafer (Journal for the Scientific Study of Religion, 2013)
Prayer is often an interpersonal phenomenon. It represents not only a form of social support shared between or among people, but also a means of embedding an unobservable actor (God) within a conventionally observable social network. This study considers whether the receipt of intercessory prayer from close network ties is associated with future-oriented well-being. Analyses use social network module data from the Portraits of American Life Study (PALS), a nationally representative study of American adults containing a breadth of information not available in prior studies of networks, prayer, and well-being. Despite experiencing more instances of recent adversity (mental or physical health problem, financial trouble, and unemployment), prayed-for PALS respondents report the highest levels of optimism. Furthermore, the association between network prayer and optimism is robust to inclusion of individual-level indicators of religiosity. Finally, other forms of social support that an individual receives from his or her close ties do not explain the benefits of intercessory prayer.
Keywords: intercession; offline; optimism; Prayer; religion; social networks; social support; well-being

Conceptualising Hinduism - Heinz Scheifinger (Asia Research Institute, National University of Singapore, 2009)
There is not a homogenous religion that can be referred to as Hinduism. Instead, ‘Hinduism’ encompasses a diverse range of practices, beliefs, and groups that can be subsumed under the term ‘Hindu.’ Despite this, Hinduism is often used in both popular and academic works to refer to a religion that is comparable to, for example, Christianity or Islam. This is clearly highly problematic. In this paper I show that although there is certainly not a homogenous religion that can be referred to as Hinduism, the use of the term is still acceptable. However, use of the term demands that it is adequately conceptualized. With such a conceptualization, the term can be used with confidence. After I have shown that the term ‘Hinduism’ should be retained, I want to briefly consider aspects of Hinduism in the light of key ideas in the work of Baudrillard. The reason for this is that Baudrillard has interesting things to say regarding the nature of images and the image is of extreme importance within Hinduism. Furthermore, it is worthwhile considering Baudrillard’s ideas in the light of Hindu images because in his work ‘Simulacra and Simulations’ he makes specific reference to religious images. I will argue that his conclusions regarding religious images are not universal and are highly questionable when applied to Hinduism. Finally, despite my reservations concerning the applicability of Baudrillardian ideas to Hinduism, I consider online images of Hindu deities in the light of the theory of simulacra. This is because there does not appear to be a strong link between the medium of the Internet and Baudrillard’s notion of hyper-real simulacra. However, I can conclude that replicated images of Hindu deities on the WWW are no more hyper-real than their original counterparts.

The Significance of Non-Participatory Digital Religion - Scheifinger, H (Digital Hinduism: Dharma and Discourse in the Age of New Media, 2017)
This edited volume seeks to build a scholarly discourse about how Hinduism is being defined, reformed, and rearticulated in the digital era and how these changes are impacting the way Hindus view their own religious identities. It seeks to interrogate how digital Hinduism has been shaped in response to the dominant framing of the religion, which has often relied on postcolonial narratives devoid of context and an overemphasis on the geopolitics of the Indian subcontinent post-partition. From this perspective, this volume challenges previous frameworks of how Hinduism has been studied, particularly in the West, where Marxist and Orientalist approaches are often ill-fitting paradigms to understanding Hinduism. This volume engages with and critiques some of these approaches while also enriching existing models of research within media studies, ethnography, cultural studies, and religion.
Keywords: Digital Religion; Hinduism; non-participatory

Hindu Worship Online and Offline - Heinz Scheifinger (Digital Religion: Understanding Religious Practice in New Media Worlds, 2013)
Keywords: cyberspace; Hindu; New Media and Society; New Technology and Society; Religion and the Internet; religious engagement; Sociology of religion

Internet Threats to Hindu Authority: Puja Ordering Websites and the Kalighat Temple - Heinz Scheifinger (Asian Journal of Social Science, 2009)
This article investigates threats to authority within Hinduism as a result of the Internet. It focuses upon websites which allow for pujas (devotional rituals) to be ordered to be carried out at the important Kalighat Temple in Kolkata. The two groups which currently exercise authority at the temple are identified, along with the specific forms of authority which they exercise. The processes which are occurring as a result of the puja ordering websites and the activities of those responsible for them are then demonstrated. The argument put forward is that, in addition to the puja ordering services being a threat to both the authority of the temple administration and the priests working there, they also have the potential to affect the relationship between these two groups. Findings from the Kalighat Temple case study further suggest that the effects at temples of online puja ordering services are dependent upon the current situation at respective temples.
Keywords: Authority; Hinduism; internet; Kalighat Temple; Puja ordering websites; Pujas

Israel: Chutzpah and Chatter in the Holy Land - Schejter, Amit; Cohen, Akiba (Perpetual Contact. Mobile Communication Private Talk, Public Performance, 2002)

Religion and the information society - Schement, J.R; Stephenson H.C. (Religion and Mass Media: Audiences and Adaptations, 1996)
How do religious audiences react to and use the media? How do institutional religious influences and expectations affect how they experience media news and entertainment? Drawing on theory and empirical research, contributors to Religion and Mass Media explore these questions from Jewish, Roman Catholic, Evangelical, Protestant, Fundamentalist and Mormon audience perspectives. The book looks at recent theoretical developments in the sociology of religion and communication theory; offers an overview of specific religious beliefs; examines audience behaviour; and describes specific case studies including the use of gospel rap and contemporary music in black religious communities.

Listening Communities? Some Remarks on the Construction of Religious Authority in Islamic Podcasts - Scholz, J.; Selge, T.; Stille, M.; Zimmerman, J. (Die Welt des Islams, 2008)
n the context of the vivid activity of Muslim individuals and groups on the Internet and the recent technological developments in the field of computer mediated communication, podcasts offering a wide range of religious information and/or advice to Muslim (and non-Muslim) listeners play an increasingly important role. Being an integral part of the Web 2.0's online landscape and presenting, at the same time, many characteristics of more “traditional” audio media such as cassette recordings, podcasts cannot only be located at the intersection between virtual space and “real world”, but represent, as a medium, also a direct continuation of older forms of Muslim media usage for da'wa-purposes and propagandistic aims. This article attempts to analyze in how far the use of podcasts (and to a smaller extent of videocasts) by Muslim groups and individuals contributes to the emergence of a Muslim online “counter public” sometimes challenging, sometimes reinforcing existing authority structures. Special attention is paid to the question which means and features specific to this new medium Muslim podcasters use to legitimize their religious authority, and to the question in how far established symbol systems commonly relied upon in the Muslim community are used as instruments for the construction of religious online authority and the redistribution of Definitionsmacht. Furthermore, it discusses to what extent questions of “right belief” and “correct religious practice” play a role in these processes. For this purpose, style and content of four selected podcasts (Zaytuna Institute Knowledge Resource Podcast, MeccaOne Media Podcast, Ahmadiyya Podcast, Alt.muslim Review) are analyzed in order to illustrate different ways in which this new medium is used by Muslim groups today. It is shown that podcasts—as part of the overall media spectrum—are used by Muslim groups for internal and external da'wa-purposes, as well as for the reinforcement of existing power and authority structures (e.g. by projecting the presence of the group's leader both into time and into space) and as a means to cope with institutional and communal crisis. They might also become an important instrument not for the (re-)construction, but for the deconstruction of religious authority.
Keywords: community; Islam; Podcast

The Sacred and the Virtual: Religion in Multi-User Virtual Reality - Schroeder, Ralph; Heather, Noel; Lee, Raymond M. (Journal of Computer Mediated Communication, 1994)
This paper explores the social interaction among participants in a church service in an online multi-user virtual reality (VR) environment. It examines some of the main features of prayer meetings in a religiously-oriented virtual world and also what sets this world apart from other virtual worlds. Next, it examines some of the issues of research ethics and methods that are raised in the study of online behavior in virtual worlds. The paper then analyzes the text exchanges between participants in a virtual church service and some of the ways in which these compare with the content of a conventional church service. Finally, the paper draws out some implications for our understanding of the relation between interaction in the virtual and in the “real” world.
Keywords: Church; Interaction; Sacred; Virtual

Christianity and the mass media in America : toward a democratic accommodation - Quentin J Schultze (Rhetoric and public affairs series., 2003)
Demonstrates how religion and the media in America have borrowed each other's rhetoric. In the process, they have also helped to keep each other honest, pointing out respective foibles and pretensions. Christian media have offered the public as well as religious tribes some of the best media criticism - better than most of the media criticism produced by mainstream media themselves. Meanwhile, mainstream media have rightly taken particular churches to task for misdeeds as well as offered some surprisingly good depictions of religious life
Keywords: America; Christian media; communication research; media; media criticism; religion; religious life; Religious sociology; rhetoric

Habits of the High-Tech Heart. - Schultze, Quentin (Baker Academic, 2002)

Muslims and New Media in West Africa: Pathways to God - Schulz, D.E. (Indiana University Press, 2011)

Algorithmic Absolution: The Case of Catholic Confessional Apps - Scott, Sasha A. Q. (Online - Heidelberg Journal of Religions on the Internet, 2016)
This article explores the Catholic ritual of confession as practiced through the use of mobile apps. Confession is a surprisingly persistent social form and in this article I begin by contextualising the relationship between society, confession and technology before presenting a case study of Catholic confessional apps that covers their design, marketing, and user feedback from review forums. This throws up a series of important questions about how we understand religious authenticity and authority in practices of faith that have a computational agent taking moral deviations as ‘data input’. How should we conceptualise these applications when an algorithm imparts absolution, when penance is assigned by computational code? Observing that most people do not question the automation of the confessional ritual and that users feel their use of confessional apps as entirely legitimate forms of religious practice, I argue that questions of authenticity are secondary to those of authority. In the traditional Sacrament of Penance a priest, acting in persona Christi as the minister of Christ’s mercy and drawing upon canonical law, recites the Rites of Penance, thereby performing the transition from the state of ‘penitent’ to ‘absolved’. The replacement of a priest with the silent logics of algorithmic automation has profound implications for the authoritative power of confession as a transformative ritual.

Gender, religion and new media: attitudes and behaviors related to the internet among Ultra-Orthodox women employed in computerized environments - Shahar, RNB; Lev-On, A (International Journal of Communication System, 2011)
This article focuses on the interface between gender, religion, and new technology, and examines the attitudes and behaviors pertaining to the Internet among ultra-Orthodox (Haredi) women working in designated “technological hothouses.”
Keywords: GENDER; internet; New Media; religion; ultra Orthodox; Women

The Bible on the Internet - Kathryn Shellnutt (Washington and Lee University, 2008)
For centuries, different groups have read the Bible as a closed system or as open system. The “closedness” or “openness” of the Bible depends on how different religious communities treat, approach, and use the Bible. Churches that apply many of the characteristics of stable systems to the Bible promote or favor less open readings; churches with many of the characteristics of complex systems allow for more open readings. The Internet, itself a complex system, seems to favor an open reading of the Bible, offering the ability to move instantly from passage to passage or passage to commentary, an overwhelming amount of additional information and context, and a sense of interactivity all at once. In this paper, the author will discuss each of instance in the history of the Bible that gave rise to a more open perspective of on the text as well as use web sites to demonstrate how the digitalization of the Bible relates back historical movements towards open reading. It will also include exceptions to the openness the Internet invites, showing how digital technology can also be used to maintain hierarchical, stable systems and keep the Bible closed. Though the digital Bible may share characteristics with the previous versions, it ultimately marks a unique setting for biblical text and readers. Because the Bible serves as Christianity’s central text, reading it online could have broader implications for Christians. The sacred experience or sacred mystery associated with the physical book of the Bible, as a holy object, may be lost in the Internet’s timelessness and placelessness, which makes biblical text universally accessible. Or, this sense of sacred may be enhanced by the infiniteness the Internet, where meaning can emerge out of individual choices made within a complex system.

The Technology of Religion: Mapping Religious Cyberscapes - Shelton, Taylor (The Professional Geographer, 2012)
This article combines geographical studies of both the Internet and religion in an analysis of where and how a variety of religious practices are represented in geotagged Web content. This method provides needed insight into the geography of virtual expressions of religion and highlights the mutually constitutive, and at times contradictory, relationship between the virtual and material dimensions of religious expression. By using the spatialities of religious practice and contestation as an example, this article argues that mappings of virtual representations of material practices are important tools for understanding how online activities simultaneously represent and reproduce the material world.
Keywords: cyberscapes; geography; internet; religion

The People of the Nook: Jewish Use of the Internet - Sheskin, I; Liben, M (The Changing World Religion Map, 2015)
Considered both an ethnic group and a religious group, there are about 13–14 million Jews worldwide (0.2 % of the population). The 6.7 million Jews in the U.S. constitute about 2 % of the American population. Internet usage by the American Jewish community is significant as an educational resource and a communication tool. As early as 2000, the National Jewish Population Survey found that 40 % of Jewish adults used the internet for Jewish-related information in 1999, a remarkable figure given that the internet only really entered the public domain in a significant way in the mid-1990s. Thus, the “People of the Book” have embraced technology to become the “People of the Nook.” First, we examine those using the internet both for general information about Jewish-related items and their local Jewish communities. The extent to which various demographic and religious subgroups of American Jews use the internet is also explored. Second, internet uses are examined, including educational purposes, ritual obligations (z’manim, counting the Omer, eruvim, electronic Yahrtzeit boards), convening a minyan, and conducting research. From the proliferation of mobile applications and web-based communication tools to the ever-growing storehouse of information, modern technology has made a significant imprint upon Jewish religious practice. The internet continues to play an important and positive role in Jewish religious life, as both an educational medium and a tool for performing religious tasks. Judaism, like other faiths, puts significant emphasis on community and physical proximity. The use of the internet to form a community by overcoming geographic space at almost no cost is an exciting opportunity allowing people to participate who might otherwise be unable because of time and cost constraints or physical limitations. But does this community downplay the physical proximity that allows one to comfort a mourner by a hug or a pat on the back?
Keywords: internet; Jewish

Algorithmic culture - Shifas, T. (European Journal of Cultural Studies, 2015)
Over the last 30 years or so, human beings have been delegating the work of culture – the sorting, classifying and hierarchizing of people, places, objects and ideas – increasingly to computational processes. Such a shift significantly alters how the category culture has long been practiced, experienced and understood, giving rise to what, following Alexander Galloway, I am calling ‘algorithmic culture’. The purpose of this essay is to trace some of the conceptual conditions out of which algorithmic culture has emerged and, in doing so, to offer a preliminary treatment on what it is. In the vein of Raymond Williams’ Keywords, I single out three terms whose bearing on the meaning of the word culture seems to have been unusually strong during the period in question: information, crowd and algorithm. My claim is that the offloading of cultural work onto computers, databases and other types of digital technologies has prompted a reshuffling of some of the words most closely associated with culture, giving rise to new senses of the term that may be experientially available but have yet to be well named, documented or recorded. This essay, though largely historical, concludes by connecting the dots critically to the present day. What is at stake in algorithmic culture is the gradual abandonment of culture’s publicness and the emergence of a strange new breed of elite culture purporting to be its opposite.

Algorithmic culture - Shifas, T. (European Journal of Cultural Studies, 2015)
Over the last 30 years or so, human beings have been delegating the work of culture – the sorting, classifying and hierarchizing of people, places, objects and ideas – increasingly to computational processes. Such a shift significantly alters how the category culture has long been practiced, experienced and understood, giving rise to what, following Alexander Galloway, I am calling ‘algorithmic culture’. The purpose of this essay is to trace some of the conceptual conditions out of which algorithmic culture has emerged and, in doing so, to offer a preliminary treatment on what it is. In the vein of Raymond Williams’ Keywords, I single out three terms whose bearing on the meaning of the word culture seems to have been unusually strong during the period in question: information, crowd and algorithm. My claim is that the offloading of cultural work onto computers, databases and other types of digital technologies has prompted a reshuffling of some of the words most closely associated with culture, giving rise to new senses of the term that may be experientially available but have yet to be well named, documented or recorded. This essay, though largely historical, concludes by connecting the dots critically to the present day. What is at stake in algorithmic culture is the gradual abandonment of culture’s publicness and the emergence of a strange new breed of elite culture purporting to be its opposite.

Speculative post on the idea of algorithmic authority - Shirky, C. A. (2009)

Design & domestication of ICTs: Technical change and everyday life - Silverstone, R. H. L. (Communicating by design: The politics of information and communication technologies, 1996)

Information and communication technologies and the moral economy of the household - Silverstone, R.; Hirsch, E.; Morley, D. (Consuming technologies: Media and information, 1992)
This paper, which draws on ongoing empirical work in the UK, considers the particular dynamics of time within domestic settings. It situates those dynamics within arguments that have drawn attention to the power of the new information and communication technologies to transform our perceptions of, and relations to, time (and space). It suggests that an understanding of the patterns of everyday life, both inside and outside the home, provides a basis for a more sensitive awareness of the complex patterns of temporality which emerge around the consumption of new media technologies.

Lost in translation? The emergence of the digital Guru Granth Sahib - Singh, Jasjit (Sikh Formations, 2018)
This article explores the impact of the digital online environment on the religious lives of Sikhs with a particular focus on the emergence of the ‘Digital Guru’, i.e. digital versions of the Guru Granth Sahib. Using data gathered through interviews and an online survey, I examine how the ‘Digital Guru’ is impacting on the transmission of the Sikh tradition and on Sikh religious authority. I then explore some of the issues faced in engaging with the ‘Digital Guru’ and the consequences of the emergence of online translations. Given that ‘going online’ has become an everyday practice for many, this article contributes to understandings of the impact of the online environment on the religious adherents in general, and on Sikhs in particular.

Global Sikh-ers: Transnational Learning Practices of Young British Sikhs - Singh, Jasjit (Sikhs Across Borders Transnational Practices of European Sikhs, 2012)

Young Sikhs religious engagement online - Singh, J (Digital methodologies in the sociology of religion, 2016)
This volume considers the implementation difficulties of researching religion online and reflects on the ethical dilemmas faced by sociologists of religion when using digital research methods.
Keywords: Online; religious; Sikhs

Identity and Community in the Weblogs of Muslim Women of Middle Easter n and North African Descent Living in the United States - Ashley Dyess Sink (xxxx, 2006)
In recent years, media attention in the United States increasingly has turned to Arabs and Muslims. But few of the voices speaking are those of the people in question. Muslim women, especially, are seldom heard in the mainstream. However, many of them are speaking, telling their stories to audiences large and small through new technology on the Internet. Weblogs, online personal journals, allow anyone with access to the Internet to become a published author. These sites of dialogue and intimate revelation offer unique insights into their authors’ lives. In this thesis, in-depth qualitative textual analysis was used to examine the weblogs of six Muslim women of Middle Eastern or North African descent (MMENA) living in the United States and writing in English to understand how they use their blogs to negotiate identity and create community. Intercultural communication theories (specifically Ting-Toomey’s identity negotiation theory, Hofstede’s cultural dimensions, and Tajfel’s social identity theory), computer-mediated communication theories, and existing literature on Muslim women were all incorporated. The women addressed identity within several different areas, in each one displaying a “paradox of identity”: what Edward Said also called “plurality of vision” or “a constant contest between cultures.” They were aware of more than one culture (that of mainstream United States and the culture of their heritage), were fully part of neither of them, and fully felt the dissonances between them. This conflict was strengthened by their membership in a culture currently faced with prejudice from United States culture as a whole. Their blogs seemed to be a kind of identity workshop, a fluid space between the different aspects of who they are. Within them, they negotiated personal identity, gender identity, and cultural/ethnic identity. They built two kinds of community through their blogs: that which was based on face-to-face relationships and was an extension of everyday interactions, and that which was based primarily on computer-mediated interactions. The blogs all displayed, to some extent, a "sense of community" involving feelings of membership, the fulfillment of needs, and a shared emotional connection. This is the first study to address MMENA women in relation to their use of blogs. The paradox of identity the women experienced is important to understand in the context of today’s society in the US. It appears that outsiders’ perceptions of MMENA Americans have a great impact on these women, perhaps greater than they would have on women of different backgrounds, because of their high level of communalism and their status as female members of a non-dominant group within the US.

Creating a Place of Prayer for the 'Other': A Comparative Case Study in Wales Exploring the Effects of Re-shaping Congregational Space in an Anglican Cathedral - ap Siôn, T (Journal of Empirical Theology, 2017)
Provision of spaces for personal prayer and reflection has become a common phenomenon within historic churches and cathedrals in England and Wales, offering an example of devotional activity that operates largely outside that of traditional gathered congregations, but also in relationship with them. Over the past decade, the apSAFIP (the ap Siôn Analytic Framework for Intercessory Prayer) has been employed to examine the content of personal prayer requests left in various church-related locations, mapping similarities and differences in pray-ers’ concerns. Building on this research tradition, the present study examines whether changes to physical environment in an Anglican cathedral in Wales has an effect on the personal prayer activity occurring within it, with a particular focus on intercessory prayer requests.
Keywords: Anglican Cathedral; Prayer; theology; World Christianity

Video Games, Video Clips, and Islam: New Media and the Communication of Values - Sisler, Vit (Muslim Societies in the Age of Mass Consumption, 2009)
In the course of the 20th century, hardly a region in the world has escaped the triumph of global consumerism. Muslim societies are no exception. Globalized brands are pervasive, and the landscapes of consumption are changing at a breathtaking pace. Yet Muslim consumers are not passive victims of the homogenizing forces of globalization. They actively appropriate and adapt the new commodities and spaces of consumption to their own needs and integrate them into their culture. Simultaneously, this culture is reshaped and reinvented to comply with the mechanisms of conspicuous consumption. It is these processes that this volume seeks to address from an interdisciplinary perspective. The papers in this anthology present innovative approaches to a wide range of issues that have, so far, barely received scholarly attention. The topics range from the changing spaces of consumption to Islamic branding, from the marketing of religious music to the consumption patterns of Muslim minority groups. This anthology uses consumption as a prism through which to view, and better understand, the enormous transformations that Muslim societies Middle Eastern, South-East Asian, as well as diasporic ones have undergone in the past few decades.

Representation and Self-Representation: Arabs and Muslims in Digital Games - Sisler, Vit (Gaming Realities: A Challenge for Digital Culture, 2006)
This paper presents the ways in which Muslims and Arabs are represented in mainstream European and American digital games. It analyzes how games — particularly of the action genre — construct the Arab or Muslim ‘Other.’ Within these games, one finds the diverse ethnic and religious identities of the Islamic world reconstructed into a series of flat social typologies, often presented within the framework of hostility and terrorism. The second part of the paper deals with selected digital games created in the Middle East, whose authors are knowingly working with the topic of self-representation. Recent digital games originating in the Middle East can be perceived as examples of an ongoing digital emancipation taking place through the distribution of media images and their corresponding meanings. A key part of this ongoing digital emancipation involves the construction of Arab and Islamic heroes, a process accomplished by exploiting distinctive narrative structures and references to Islamic cultural heritage.

Digital Arabs: Representation in Video Games - Sisler, Vit (European Journal of Cultural Studies, 2008)
This article presents the ways in which Muslims and Arabs are represented and represent themselves in video games. First, it analyses how various genres of European and American video games have constructed the Arab or Muslim Other. Within these games, it demonstrates how the diverse ethnic and religious identities of the Islamic world have been flattened out and reconstructed into a series of social typologies operating within a broader framework of terrorism and hostility. It then contrasts these broader trends in western digital representation with selected video games produced in the Arab world, whose authors have knowingly subverted and refashioned these stereotypes in two unique and quite different fashions. In conclusion, it considers the significance of western attempts to transcend simplified patterns of representation that have dominated the video game industry by offering what are known as 'serious' games.

Procedural religion: Methodological reflections on studying religion in video games - Sisler, Vit (New Media & Society, 2017)
The article discusses the methodological aspects of studying religion in video games. It examines the concept of “procedural religion,” that is, the representations of religion via rule-systems in games, and investigates how we can formally analyze these representations. The article uses Petri Nets, a mathematical and a graphical tool for modeling, analyzing, and designing discrete event systems, in order to analyze how religion is represented in the rule-systems of two different mainstream video games—Age of Empires II, developed in the United States, and Quraish, developed in Syria. By comparing the rule-systems of both games, the article provides empirical evidence on how game rule-systems migrate between cultures and influence local game production by providing local game developers with pre-defined formulas for expressing their ideas while simultaneously limiting the scope of such expression with schematized patterns. On a more general level, the article discusses what rule-system analysis can tell us about video games as cultural and religious artifacts.

Palestine in Pixels: The Holy Land, Arab-Israeli Conflict, and Reality Construction in Video Games - Sisler, Vit (Middle East Journal of Culture and Communication, 2009)
This article explores the ways in which Palestine is envisioned, and its representation constructed, in contemporary video games. At the same time, capitalizing on Bogost's notion of "procedurality", this article discusses the potential and limitations of various game genres for modeling complex historical, social, and political realities. It focuses particularly on the ways in which the Arab-Israeli conflict is mediated and its perception and evaluation subsequently shaped by these games. By doing so, this article analyzes how the (re)constructions of reality as provided by the video games' graphical, textual, and procedural logic, serve parallel - albeit contradictory - political and ideological interpretations of real-world events. Essentially, this article argues that the procedural forms, i.e. the common models of user interaction as utilized by particular video game genres, fundamentally shape and limit the ways in which reality is communicated to the players. Therefore, on a more general level, this article aims to further develop the game genres' critique by focusing on two contrasting, but equally significant and simultaneous, aspects of video games - the persuasive power of procedurality and the inherent limitations thereof.

The Internet Movie Database and Online Discussions of Religion - Sjö, Sofia (Journal of Religion in Europe, 2013)
Religion and film scholars have long used the Internet Movie Database (IMDb) as a source for material on audience responses, but not much thought has been given to what the material found on the site constitutes. This article highlights possibilities and problems with researching sites such as the IMDb, discussing how studies of Internet communication, community, and fan culture can help contextualize the material and provide a better comprehension of the discussions of religion on the site. The potential of the IMDb to offer noteworthy voices on religion is exemplified with an analysis of reviews of three religiously themed Nordic films. The views on religion expressed are theorized as a form of ‘playable religion’ reflecting contemporary attitudes to religion.

Social media and Islamic practice: Indonesian ways of being digitally pious - Slama, M (Digital Indonesia: Connectivity and Divergence, 2017)
This book places Indonesia at the forefront of the global debate about the impact of 'disruptive' digital technologies. Digital technology is fast becoming the core of life, work, culture and identity. Yet, while the number of Indonesians using the Internet has followed the upward global trend, some groups -- the poor, the elderly, women, the less well-educated, people living in remote communities -- are disadvantaged. This interdisciplinary collection of essays by leading researchers and scholars, as well as e-governance and e-commerce insiders, examines the impact of digitalisation on the media industry, governance, commerce, informal sector employment, education, cybercrime, terrorism, religion, artistic and cultural expression, and much more. It presents groundbreaking analysis of the impact of digitalisation in one of the world's most diverse, geographically vast nations. In weighing arguments about the opportunities and challenges presented by digitalisation, it puts the very idea of a technological 'revolution' into critical perspective.
Keywords: Digital; Indonesian; Islamic; social media

The Internet and Society - Slevin, J. (Polity Press, 2000)
The Internet and Society explores the impact of the internet on modern culture beyond the fashionable celebration of 'anything goes' online culture or the overly pessimistic conceptions tainted by the logic of domination.

Atheisms Unbound: The Role Of The New Media In The Formation Of A Secularist Identity - Christopher Smith; Richard Cimino (Secularism and Non-Religion, 2012)
In this article we examine the Internet’s role in facilitating a more visible and active secular identity. Seeking to situate this more visible and active secularist presence—which we consider a form of activism in terms of promoting the importance of secularist concerns and issues in public discourse—we conclude by looking briefly at the relationship between secularist cyber-activism and secular organizations, on one hand, and the relationship between secularist activism and American politics on the other. This allows us to further underscore the importance of the Internet for contemporary secularists as it helps develop a group consciousness based around broadly similar agendas and ideas and secularists’ recognition of their commonality and their expression in collective action, online as well as off.
Keywords: Atheism; identity; New Media; Secular

The Christian potential of cyberspace: An appraisal - Alec Sonsteby (Gustavus Adolphus College, 2002)
Today the Internet is increasingly permeating industrial societies. Affluent people in these cultures are e-mailing their friends and family, browsing the Web, and participating in online discussions through newsgroups and "chat rooms." Churches are sprouting Web sites; online "communities," such as beliefnet.com, offer prayer groups and religion news and information; and some amateur theologians are using the Internet to publish their own theologies. But some believe that the Internet's contributions to religion may be far greater. For example, some people see the Internet leading to a greater and greater connectivity among all people, culminating in what Catholic theologian Teilhard de Chardin called the "Omega Point," a type of global consciousness. Others believe that it will be possible for individuals one day to transfer (upload) their consciousnesses into a computer and communicate electronically with other such people through a network. Some have suggested that the Internet might be a metaphor for God. People might easily dismiss these predictions, such as mind uploads, since the technology is not here yet or because they sound ridiculous. But the fact that some have conceptualized a computerized eschatology (such as the Omega Point) or a network god invites examination. Do these claims have any theological value, that is, do they contribute anything new to the discussion about God, or are they simply new manifestations of the dreams of immortality and omniscience that Western civilization has long sought to realize? This thesis assesses whether the Internet can contribute anything "new" to Christian theology, that is, whether the hopes of seeing in the Internet a metaphor for God or using it as a mechanism for searching for God are possible. Or does the Internet instead make possible for worldwide religious communities and an image for contemplating process theology? In other words, can religion speak theologically about the Internet?

Cybertheology. Thinking Christianity in the Era of the Internet - Spadaro, A; Maria Way (Fordham Press, 2014)
we think Christianity and its theology. Cybertheology is the first book to explore this process from a Catholic point of view. Drawing on the theoretical work of authors such as Marshall McLuhan, Peter Levy, and Teilhard de Chardin, it questions how technologies redefine not only the ways in which we do things but also our being and therefore the way we perceive reality, the world, others, and God. "Does the digital revolution affect faith in any sense?" Spadaro asks. His answer is an emphatic Yes. But how, then, are we to live well in the age of the Internet?
Keywords: Christianity; Cybertheology; internet

Between Secrecy and Transparency: Conversions to Protestantism Among Iranian Refugees in Germany - Stadlbauer, Susanne (Entangled Religions, 2019)
Present-day scholarship on religious conversions diverts from classic Protestant paradigms of sudden conversions and instant transformations of the self. Instead, it stresses that converts make active choices that are influenced by specific contexts and historical changes. This becomes evident in an ethnographic study of one controversial aspect of the recent refugee influx in Germany: the so-called mass conversions of Iranian refugees from Shia Islam to Christianity, which have been highly publicized and criticized since the height of immigration in 2015. The analysis draws on interview data with Iranian refugee converts and their pastors in Protestant churches in North Rhine-Westphalia between October 2017 and January 2018. The study reveals the need to theorize the symbiotic connection between religious contacts, forced migration, and conversion to Christianity. It applies Rambo’s (1993) stage model of conversion and the analytical concept of secrecy (Jones 2014, Manderson et al. 2015, Simmel 1906) to demonstrate that the Iranian refugees’ conversions are shaped by contexts, crises, encounters, quests, interactions, commitments, and consequences (Rambo 1993) as they negotiate the forces of secrecy, risk, transparency, and the benefits of being a Christian. The goal of this paper is to find thematic patterns in their narratives that can be systematized and can build a foundation for further study.

Seeking new language: Patriarch Kirill’s media strategy - Staehle, Hanna (Religion, State and Society, 2018)
Media have become important arenas where religious institutions, alongside other players, articulate moral values and seek to shape societal norms and identities. Patriarch Kirill recognised early on the potential of using the media in spreading the Russian Orthodox Church’s mission and reaching out to wider audiences. From the very first days of his enthronement on 1 February 2009 he has taken the lead in developing a comprehensive media strategy aimed at increasing the Church’s presence in the public sphere. Both his words and deeds provide evidence of a momentous turnaround in the Church’s information and communication policy. His pursuit to endorse a revisited media strategy is determined by attempts to influence and control the way Russian Orthodoxy is portrayed in the public sphere. Moreover, the development of a large-scale media policy is motivated by the rising criticism towards the Church, voiced most notably on the internet. Based on the analysis of original and previously unexplored sources, this article illustrates the impact of media on a traditional religious organisation such as the Russian Orthodox Church and the response of the Church’s leadership to emerging challenges in a radically changing media environment.

God and the Chip. Religion and the Culture of Technology - Stah, William (Wilfred Laurier University Press., 1999)
Our ancestors saw the material world as alive, and they often personified nature. Today we claim to be realists. But in reality we are not paying attention to the symbols and myths hidden in technology. Beneath much of our talk about computers and the Internet, claims William A. Stahl, is an unacknowledged mysticism, an implicit religion. By not acknowledging this mysticism, we have become critically short of ethical and intellectual resources with which to understand and confront changes brought on by technology.

Religion from Scholarly Worlds to Digital Games: The Case of Risen - Steffen, Oliver (Religions in Play. Games, Rituals, and Virtual Worlds, 2012)
A content analysis of the fantasy role-playing game Risen is conducted. Methodically, the case study shows that the ludological concept of hit points may be taken as a starting point for the investigation of the religious repertoire. In addition, the comparison with the original German work of Dutch phenomenologist Gerardus van der Leeuw suggests that Risen’s ludological-narrative complex of hit points (“life energy”) enacts a 20th century essentialistic and phenomenological conception of religion that has made its way into, and was specifically framed by, the new medium of digital games.
Keywords: Computer games; digital games; religion

Introduction: Approaches to Digital Games in the Study of Religions - Steffen, Oliver (Religions in Play. Games, Rituals, and Virtual Worlds, 2012)
The content and structure of entertaining digital games often refer to the imaginary worlds of historical religion. However, the religious dimensions of this new medium have hardly been addressed by scholars of both, game studies and religious studies. In this introductory article, initial thoughts on areas of study and approaches are given to scholars of religion who investigate computer games.
Keywords: Computer games; digital games; religion

Gaming at The End of the World: Coercion, Conversion and the Apocalyptic Self in Left Behind: Eternal Forces Digital Play - Steuter, Erin; Wills, Deborah (Reconstruction: Studies in Contemporary Culture, 2010)
Left Behind: Eternal Forces is a real-time strategy game based on Tim LaHaye and Jerry Jenkins' best-selling eschatological novels, an immensely popular series featuring embattled Christians fighting evil at the world's end. The spin-off game allows players to "wage a war of apocalyptic proportions" against the Antichrist's minions. The players defend themselves with prayer and hymn-singing; if spiritual means fail, however, more violent tactics are invoked as Christian alliances evolve into the military units of the "Tribulation Force." This merging of what the game's website calls "physical and spiritual warfare" has generated among critics the label "kill or convert"; the conflation of the two lies at the center of an ideological controversy that intensified when ABC News announced an evangelical group's plans to send the game to US troops in Iraq. This article explores eschatological representations like Eternal Forces as a way to instill, consolidate, and hierarchicalize identity by creating an apocalyptic self that is figured in violently contestatory terms. It addresses conservative evangelical leaders' mobilization of that apocalyptic self in order to re-invest twenty-first century evangelicals in a renewed "combat myth" tradition that sees those of differing beliefs as fodder either for conversion or for annihilation in an ultimate battle between God and Satan. Left Behind: Eternal Forces is explored as a contemporary pop-culture expression and a new form of soteriological play in which that two-pronged choice is embodied and enacted, situating its players as divine co-strategists in an either/or world of forced and often punitive affiliation.

A Study of Church/Ministry Internet Usage - Robert E. Stevens; Paul Dunn; David L. Loudon; Henry S. Cole (Journal of Ministry Marketing & Management, 2002)
This manuscript reports the results of a national survey of Internet use by churches and ministries. The mail survey to a random sample of 500 churches and ministries sought to determine the proportion of churches/ministries with Internet access, how the Internet was being used by their organization, and organizational characteristics. A total of 448 questionnaires were delivered and 113 were returned resulting in a response rate of 25.2%. About 93 percent of the respondents surveyed reported using a computer. Of that 93 percent, about 70 percent reported they had Internet access. When asked about how the Internet has helped their church, respondents reported communications with others as the most important benefit, followed by staying better informed on products and services, and as a research tool for sermons and Bible studies. Among respondent churches who had Internet access, about 37 percent had a webpage. Of those who did not have a webpage, 58 percent plan on having one within a year. The most common ways churches use their website were found to be (1) describing features of the church such as service times or scheduled events, (2) creating a way to communicate with others about the church, (3) providing a way for people to contact the church by e-mail, and (4) image creation. Respondents cited several benefits of having a website: (1) improved communication, (2) increased member knowledge about church programs and (3) increased attendance at church services or activities.
Keywords: Church; Computer; Contemporary Religious Community; cyberspace; internet; Internet access; Internet use by churches and ministries; Mass media; national survey; network; New Media and Society; new media engagement; New Technology and Society; online activities; online communication; Online community; religion; religion and internet; Religion and the Internet; religiosity; religious engagement; religious identity; Religious Internet Communication; Religious Internet Communities; religious organizations; sociability unbound; Sociology of religion; users’ participation; virtual community; virtual public sphere; “digital religion”; “media and religion”; “media research”; “online identity”; “religion online”; “religious congregations”; “religious media research”

Gender, Faith, and Storytelling: An Ethnography of the Charismatic Internet - Stewart, Anna (Department of Anthropology, 2012)
Although early predictions that an emerging ‘cyberspace’ could exist in separation from offline life have been largely discarded, anthropological studies of the internet have continued to find notions of ‘virtual reality’ relevant as individuals use these technologies to fulfil the “pledges they have already made” (Boellstorff, 2008; Miller & Slater, 2001: 19) about their own selfhood and their place in the world. There are parallels between this concept of ‘virtual reality’ and the on-going spiritual labour of Charismatic Christians in the UK, who seek in the context of a secularising nation to maintain a sense of presence in the “coming Kingdom” of God. The everyday production of this expanded spiritual context depends to a large extend on verbal genres that are highly gendered. For women, declarations of faith are often tied to domestic settings, personal narratives, and the unspoken testimony of daily life (e.g. Lawless, 1988; Griffith, 1997). The technologies of the internet, whose emerging genres challenge boundaries between personal and social, public and private, can cast a greater illumination on this inward-focused labour. This doctoral thesis is based on ethnographic research in four Charismatic Evangelical congregations and examination of the online practices of churchgoers. I have found that the use of the internet by Charismatic Christian women fits with wider religious preoccupations and patterns of ritual practice. Words posted through Facebook, blogs, Twitter, and other online platforms come to resemble in their form as well as their content Christian narratives of a life with meaning.
Keywords: anthropological studies; Computer; Contemporary Religious Community; cyberspace; declarations of faith; digital cultures; domestic settings; Evangelic; Faith; GENDER

The “Almost” Territories of the Charismatic Christian Internet - Stewart, A (The Changing World Religion Map, 2015)
The constantly emerging technologies of the internet are frequently described in terms that evoke space. As online technologies continue to grow in their global ubiquity, it is appropriate to consider how the virtual geographies that are conjured in online engagement extend beyond the web browser. This chapter builds upon anthropological approaches studying religious communication to consider how internet engagement with some religious Believers creates and provides a sense of presence in an inspirited world. I first discuss how anthropologists approached the relationship between religious communication and space before considering Charismatic Christians in the UK. Following 12 months of fieldwork in their churches in the South of England, I describe a range of everyday internet practices and the spiritual implications held by my informants. The key finding is that the technologies of the internet provide for Believers contexts in which they are able to perceive and directly experience the dimensions of their spiritual battles. While British Christianity continues to suffer steady decline, web-based resources allow Christians opportunities to experience connections with others as part of an unstoppable, global, wave of revival. This sense of sanctified online community is tempered by knowledge that words transmitted in some online contexts may be witnessed by non-Believers. While this knowledge is mostly welcomed by members, shared spaces such as Facebook or Youtube can become sites for spiritually hazardous confrontations. In their engagement with online media these Christians experience online comments lists, blog entries, and social networking platforms as sites in which struggles for global, national, and personal salvation are staged and restaged. For these Christians, the spaces of the internet come to be experienced as territories in constant transition.
Keywords: Christianity; Communication; internet; social media

Who watches the watchers? Towards an ethic of surveillance in a digital age - Stoddart, E. (Studies in Christian Ethics, 2008)
The essay considers contemporary surveillance strategies from a Christian ethical perspective. It discusses first surveillance as a form of speech in the light of biblical themes of truthfulness, then draws on principles of subsidiarity and solidarity. Surveillance is dignified as human work whilst its dehumanizing outcomes are challenged. It is concluded that surveillance must contribute to human dignity and that accountability for data must follow a revised model of subsidiarity, appropriate to network rather than linear socio-political relationships. Mutual responsibility for one another's data-image is derived from solidarity which, further, offers a response to the angst of a culture of suspicion.
Keywords: Digital; Privacy; Surveillance

Deus in Machina:Religion, Technology, and the Things in Betwee - Jeremy Stolow (Fordham University Press, 2013)
The essays in this volume explore how two domains of human experience and action--religion and technology--are implicated in each other. Contrary to commonsense understandings of both religion (as an "otherworldly" orientation) and technology (as the name for tools, techniques, and expert knowledges oriented to "this" world), the contributors to this volume challenge the grounds on which this division has been erected in the first place. What sorts of things come to light when one allows religion and technology to mingle freely? In an effort to answer that question, Deus in Machina embarks upon an interdisciplinary voyage across diverse traditions and contexts where religion and technology meet: from the design of clocks in medieval Christian Europe, to the healing power of prayer in premodern Buddhist Japan, to 19th-century Spiritualist devices for communicating with the dead, to Islamic debates about kidney dialysis in contemporary Egypt, to the work of disability activists using documentary film to reimagine Jewish kinship, to the representation of Haitian Vodou on the Internet, among other case studies. Combining rich historical and ethnographic detail with extended theoretical reflection, Deus in Machina outlines new directions for the study of religion and/as technology that will resonate across the human sciences, including religious studies, science and technology studies, communication studies, history, anthropology, and philosophy.
Keywords: Buddhist; Christian; Egypt; Haitian; Islamic; Japan; medieval; religion and technology; religious studies; Spiritualist movement; Vodou

Media and Religion: Foundations of an Emerging Field - Daniel A. Stout (Routledge, 2012)
This is the first text to examine the history, theory, cultural context, and professional aspects of media and religion. While religion has been explored more fully in psychology, sociology, anthropology, and the humanities, there is no clear bridge of understanding to the communication discipline. Daniel A. Stout tackles this issue by providing a roadmap for examining this understudied area so that discussions about media and religion can more easily proceed. Offering great breadth, this text covers key concepts and historical highlights; world religions, denominations, and cultural religion; and religion and specific media genres. The text also includes key terms and questions to ponder for every chapter, and concludes with an in-class learning activity that can be used to encourage students to explore the media–religion interface and review the essential ideas presented in the book.

Mediated Muslim martyrdom: Rethinking digital solidarity in the “Arab Spring” - Sumiala, Johanna; Korpiola, Lilly (New Media & Society, 2017)
In today’s world of networked, mobile, and global digital communication, Muslim martyrdom as a multi-layered communicative practice has experienced a new type of media saturation, thereby posing a challenge for the study of media, religion, and culture in a digital age. In this article, the analysis focuses on two cases of high symbolic relevance for the events later referred to as the “Arab Spring”—the deaths of a Tunisian fruit seller Mohammed Bouazizi and a young Egyptian man Khaled Saeed. Special focus is given to the discussion of digital solidarities and their construction in circulation and remediation of martyr narratives of Bouazizi and Saeed in diverse media contexts. In this global development of digital solidarities, we identify two categories of martyr images of particular relevance—a “living martyr” and a “tortured martyr”—and discuss their resonance with different historical, religious, cultural, and political frames of interpretation. In conclusion, we reflect on the question of the ethics of global mediation of Muslim martyrdom and its implications for the study field of media, religion, and culture in its digital state.

“No More Apologies”: Violence as a Trigger for Public Controversy over Islam in the Digital Public Sphere - Sumiala, Johanna; Harju, Anu A. (Journal of Religion, Media and Digital Culture, 2019)
This article investigates how violence associated with religion, here namely Islam, functions as a trigger for public controversy in the Turku stabbings that took place in Finland in 2017. We begin by outlining the Lyotard-Habermas debate on controversy and compound this with current research on the digital public sphere. We combine cartography of controversy with digital media ethnography as methods of collecting data and discourse analysis for analysing the material. We investigate how the controversy triggered by violence is constructed around Islam in the public sphere of Twitter. We identify three discursive strategies connecting violence and Islam in the debates around the Turku stabbings: scapegoating, essentialisation, and racialisation. These respectively illustrate debates regarding blame for terrorism, the nature of Islam, and racialisation of terrorist violence and the Muslim Other. To conclude, we reflect on the ways in which the digital public sphere impacts Habermasian consensus- and Lyotardian dissensus-oriented argumentation.

Hybrid Media Events: The Charlie Hebdo Attacks and the Global Circulation of Terrorist Violence - Sumiala, Johanna; Valaskivi, Katja; Tikka, Minttu; Huhtamäki, Jukka (Emerald Publishing Limited, 2018)
What are hybrid media events? Who creates them and what kind of purpose do they serve in contemporary societies? This book addresses these questions by re-thinking media events in the contemporary digital media environment saturated by intensified circulation of radical violence. The empirical analyses draw on the investigation of the Charlie Hebdo attacks in Paris, in 2015 and the global responses those attacks stirred in the media audience. This book provides a new way of thinking about the idea of the hybrid in global media events. The authors give special emphasis to the hybrid dynamics between the different actors, platforms and messages in such events, explaining how global news media, terrorists and political elites interact with ordinary media users in social media. It demonstrates how tweets such as "Je suis Charlie" circulate from one digital media platform to another and what kind of belongings are created in those circulations during the times of distraction. In addition, the book examines how emotions, speed of communication and fight for attention become hybridized in the digital media. All these aspects, the authors argue, shape the ways in which we make sense of global media events in the present digital age. The authors invite readers to critically reflect the technological, economical, political and socio-cultural challenges connected with today's global media events and the ethical encounters they may entail.

Media and Ritual: Death, Community and Everyday Life - Johanna Sumiala (Routledge, 2012)
This wide-ranging and accessible book offers a stimulating introduction to the field of media anthropology and the study of religious ritual. Johanna Sumiala explores the interweaving of rituals, communication and community. She uses the tools of anthropological enquiry to examine a variety of media events, including the death of Michael Jackson, a royal wedding and the transgressive actions which took place in Abu Ghraib, and to understand the inner significance of the media coverage of such events. The book deals with theories of ritual, media as ritual including reception, production and representation, and rituals of death in the media. It will be invaluable to students and scholars alike across media, religion and anthropology.

Introduction: Mediatization in Post-Secular Society—New Perspectives in the Study of Media, Religion and Politics - Sumiala, Johanna (Journal of Religion in Europe, 2017)
The way the media handle religion is deeply embedded in a set of historical, cultural, and political perceptions about religion’s natural, proper, or desirable place in democratic public life.

Implications of the Sacred in (Post)Modern Media - Sumiala-Seppänen, Johanna; Lundby, Knut; Salokangas, R. (Nordicom, 2006)
Keywords: Modern; Sacred

The influence of religion on Islamic mobile phone banking services adoption - Susan Sun; Tiong Goh; Kim-Shyan Fam; Yang Xue (Journal of Islamic Marketing, 2012)
The purpose of this paper is to explore the effects religious affiliation and commitment have on Southeast Asian young adults' intention to adopt Islamic mobile phone banking. An online self-administered survey was distributed to Southeast Asian young adults through convenience and snowball sampling and a total of 135 responses obtained. The study found Islamic mobile phone banking to be a novelty service, with little consumer awareness and experience, especially among non-Muslims. Religious affiliation and commitment were both effective segmentation strategies, as differences in adoption intention were found between Muslims and non-Muslims, as well as devout and casually religious Muslims. Overall, devout Muslims were socially-oriented with their adoption criteria whereas casually religious and non-Muslims relied upon the utilitarian attributes. The paper contributes to the existing mobile banking adoption literature by providing evidence of consumers' adoption intentions toward Islamic mobile phone banking. It also uses religious commitment in addition to affiliation as segmentation tools, an approach which has not been used in previous Islamic mobile banking research.
Keywords: banks; Islam; Mobile phone

Digitally Enhanced or Dumbed Down? Evangelists’ Use of the Internet - Douglas Swanson (Moebius, 2008)
Since renewalists’ prosperity theology is embraced by growing numbers of Christians, and since evangelical Christians are among the most active Internet users, it seemed appropriate to investigate renewalists’ use of the World Wide Web to reach followers. In the summer of 2007, I conducted a detailed content analysis of Web sites and podcasts produced by leading renewalist ministries. My theoretical grounding was in framing theory; I used constant comparative analysis to help organize themes that were prevalent in the media content. I identified ten areas of concern that relate to technology use, message issues, and listener responses called for by evangelists. What follows is a summary of my findings, and the obvious questions they raise as we consider whether digital media ‘dumbs down’ the Christian experience.

New Media, New Relations: Cyberstalking on Social Media in the Interaction of Muslim Scholars and the Public in West Sumatra, Indonesia - Syahputra, I (Jurnal Komunikasi: Malaysian Journal of Communication, 2018)
This article explains how the presence of social media as one of the forms of new media has prompted changes in the relations and communications between ulama and the public. The relationship between ulama, religious teachings, and the ummah (Muslim community/the public) undoubtedly undergoes constant changes. In the current era of new media, this relationship experiences mediatization of differing features compared to past era of traditional media. The era of new media ushered in participative, open, interactive characteristics encouraging development of virtual communities, and interconnectedness, consequently positioning ulama in two particular positions. Firstly, ulama have full control over the contents they intend to post and the choice of whom they wish to communicate with on social media. Secondly, due to the aforementioned characteristics of social media, ulama who actively post religious contents on social media had come to experience cyberstalking. Despite having to endure and suffer from cyberstalking, the ulama remained active on social media and continued posting religious contents as they consider social media to have numerous positive values beneficial to spreading good values and religious teachings to the wider public. The research findings show that social media as a form of new media has led to the emergence of new relations that are entirely unlike previous traditional media. The research data were collected through in-depth interviews with three Muslim scholars of West Sumatra who are active on social media and have extensive social influences.
Keywords: Cyberstalking; Indonesia; Muslim; New Media; social media

New Media, New Players: The Use of Social Media with Religious Contents among Muslim Scholars in West Sumatra, Indonesia - Syahputra, I (Jurnal Komunikasi: Malaysian Journal of Communication, 2018)
This article explains how Muslim scholars in West Sumatra utilized social media as one of the new media containing religious contents. The relationship between Muslim scholars, religious teachings, and their followers undergoes constant changes. The era of new media introduced participative, open, interactive characteristics encouraging development of virtual communities, and interconnectedness, consequently positioning Muslim scholars as new determining players in the relationship. There are two main patterns they employ in posting religious contents on social media. Firstly, it is a pattern characterized by the systematic use of religious texts originating from the Holy Koran and Hadith or ulamas’ opinions contained in various classical Islamic manuscripts. Secondly, it is conducted by using reflective sentences containing universal values. Both patterns have different social implications, and due to the aforementioned new media characteristics, these West Sumatra Muslim scholars who actively post religious contents on social media had come to experience cyber-stalking. Despite being harassed and threatened, they continued posting religious contents as they consider social media to have numerous positive values beneficial to spreading good values and religious teachings to the wider community. The research findings show that social media as a form of new media has led to the emergence of new players entirely unlike previous traditional media. The research data were collected through in-depth interviews with three Muslim scholars of West Sumatra who are active on social media.
Keywords: Indonesia; Muslim; New Media; social media

Malaysian Christians Online: Online/Offline Networks of Everyday Religion - Meng Yoe Tan (Post-Privacy Culture: Gaining Social Power in Cyber-Democracy, 2013)
Religion has already found its footing in cyberspace. Countless websites promoting particular religious organisations and ideals are easily found within a click or two online. Blogs are now an outlet for religious and spiritual discussion for different groups and individuals. Due to the relatively unfiltered nature of the Internet, it is more possible for new types of religious expressions to surface for public consumption, even if some of these expressions might not conform to conventional notions of spiritual expression. All of these new forms of online religion then, serve as a gateway to study different models and contexts of religious expression. A website, however, is in many ways only the expressed product. What about the dynamics behind these expressions? Because the online and the offline are inseparable entities, both simultaneously interact with and influence the individual’s identity and expression. This means that in order to further develop an understanding of ‘online religion’, the ‘offline’ must also be described extensively. Using two case studies of Malaysian Christian bloggers, this chapter demonstrates how with the use of Actor-Network-Theory (ANT) methods, it is possible to seamlessly describe everyday cyber-activity and everyday Christianity in relation to one another, thus providing a snapshot of how the larger context and framework in which Christianity in today’s day and age can be better understood.
Keywords: Actor; Christian; malaysian; network; Online; theory

Malaysian Christians Online: Online/Offline Interactions and Integration - Meng Yoe Tan (Cyberculture Now: Social and Communication Behaviour on the Web, 2013)
There has been a vibrant discussion in recent years since Christopher Helland’s novel definitions and differentiation of online-religion/religion-online came to the fore of cyber-religious research. Much of the discussion since then has dealt primarily with certain features of particular religious websites, such as its level of user interactivity. My chapter is an attempt to side-step what a ‘religious’ website is or is not, and to locate specific Christian individuals in Malaysia and their online habits within the larger context of what they consider to be their Christian life - be it online/offline. In short, this chapter explores the ways in which online Christianity, in its varied forms, as practiced by its users, play a part in engaging an individual’s faith. Drawing two case studies from my ethnographic fieldwork, this paper constructs and establishes the multiple contexts and environments that shape some Malaysian Christians’ online expressions of their faith, as well as how their current practice of blogging contributes back to their personal spirituality, contexts, and environments. Rather than dwelling on whether a website allows for physical or practical interactivity, this chapter explores the possibility that the Internet is yet another incorporated extension to the already diverse repertoire of Christian expression of spirituality.
Keywords: everyday; helland; malaysia; offline; Online; religion

Negotiating the Liberties and Boundaries of Malaysian Online Christian Expression: Case Studies - Meng Yoe Tan (Thinking Through Malaysia: Culture and Identity in the 21st Century, 2012)
How do Malaysian Christians express their personal Christianity online? Compared to other communication technologies, the Internet allows more non-institutional individual expression to come to the fore. This is mainly due to the nature of the Internet which allows greater flexibility in authorship of expression and content. Using case studies from my interviews with Christian bloggers in Malaysia who actively post Christian content online, we can see how the Internet has provided these bloggers with new tools to express their unique personal spirituality – but at the same time, how they recreate and maintain existing offline social boundaries in the context of their personal Christianity in this ‘liberating’ platform. These case studies also provide some insight into the many ways individuals interact with cyberspace – that individuals do, in fact, do new things on the Internet, do old things in new ways, and very importantly, do old things in old ways.
Keywords: Blog; boundaries; liberties; malaysia; Online; religion

Hijab Online: The Fashioning of Cyber Islamic Commerce - Tarlo, Emma (Interventions, 2010)
This essay looks at the world of cyber Islamic commerce and the marketing of new forms of hijab through tracing the connections between the British Muslim entrepreneur Wahid Rahman who runs a website called HijabShop.com and the Dutch designer Cindy van den Bremen, designer of a new form of sports head covering known as Capsters. It considers the lifestyles of these two individuals, their diverse philosophies and their personal involvement in the promotion of Islamic fashion for women and how cyberspace has provided them with an opportunity for a business partnership. The essay explores some of the representational challenges inherent in the reframing of hijab as fashion, showing how those involved in this niche market navigate complex tensions between different Muslim interpretations of the relationship between beauty and modesty, fashion and faith.

Cyber-Buddhism and the Changing Urban Space in Thailand - Taylor, Jin (Space and Culture, 2003)
Buddhism in Thailand has long been seen as a holistic cultural system, with an all-embracing normative cosmology that provides everyday meaning. However, it is also a diverse cultural system that produces alternative or Other counterstatist practices that have at times contested the power of the politico-administrative center. In this changing milieu, cyber-Buddhism has emerged as a response to the needs of an increasingly mobile, simulated, and fragmented transnational urban social order. Here, multiple sites essentially constitute the new (post-) metropolis and where material spatial practices and social arrangements have been recoded. This has affected the social practices of everyday life. The monasteries, the spiritual heart/center of the community, once the prime loci (and place) of much social activities and civic interests, now stand in the new middleclass imagination as icons of the past as a consequence of unfettered urban capitalism and the space of flows since the postwar years. Nevertheless, arising from the Thai experience with modernity are new spatial possibilities engendered in large part by hypertechnologies, especially the Internet; digitalized electronics potentially and markedly transforming religious space. In the privileging of space over many temporal (place-made) coordinates, human communities are left only with nostalgia and a simulated more real than real world where original, first-order things cease to exist. Perhaps now we are just beginning to realize the transformative possibilities in urban religion brought about by electronic space.

Formation of a Religious Technorati: Negotiations of Authority Among Austrailian Emerging Church Blogs - Teusner, P.; Campbell, H. (Digital Religion: Understanding Religious Practice in New Media Worlds, 2012)
Keywords: Authority; Blogging; Church; religion

Religious language: Towards a framework for religious language theory - Paul Teusner (2008)
George Lindbeck (1984: 39) writes that from a cultural-linguistic point of view, religious change is not understood as emerging from new religious experiences. It is rather seen as coming out of changing situations within a cultural-linguistic system. When a certain way of ordering or explaining the religious character of a cultural group creates anomalies in its application to new contexts (eg. new media, new places and times of reception), new concepts, symbols and ideas are discovered that solve the anomalies. I want to see how well this theory fits when we examine the differences in the language employed to communicate religious ideas in different contexts, and how this may impact on the way audiences receive and interpret the information to form a religious identity. The contexts I want to identify are: 1. Traditional mainstream Protestant communities 2. Evangelical Protestant communities (I know, I know: we could go to town trying to delineate between the two. I don't want to dwell on it, but will acknowledge that the definitions of such words, and the line drawn between them, are not clear, and both "mainstream" and "evangelical" streams exist in the same denomination) 3. Secular popular media (eg. film, TV shows - I'll just use a couple of examples) 4. Religious television, and 5. Religious web sites and accompanying discussion outlets Basically, I want to know what the conditions are that create new ways of talking about, interpreting and experiencing religion in these media spheres.

Resident evil: Horror film and the construction of religious identity in contemporary media culture - Teusner, P. (Colloquium, 2005)
Keywords: media; popular culture; religion

'Imaging Religious Identity: Intertextual Play among Postmodern Christian Bloggers' - Teusner, P.E. (Special Issue on Aesthetics and the Dimensions of the Senses, 2010)
Recent years have seen a growing interest in the research of religious content in online social media, including web logs, file sharing networks such as YouTube, and social networking sites like Facebook and MySpace. While much attention has been paid to the creation of media texts for the Web, their audiences and usage, little has been given to the aesthetic dimension. For the Internet is a medium for the communication of not just literal text, but also aural and visual text. All information found on computer screens is framed by visual design, according to the affordances give to users by the technology. Drawing from my PhD study of Australian bloggers involved in the ‘emerging church’ movement,1 I intend to show how the blogosphere has become more than an alternative space for religious discourse. In the design of personal web pages, use of colour schemes, templates and captioned images, these bloggers find a vehicle for the ongoing construction of religious identity in the formation of an aesthetic style.

Crossing Over or Crossing Out? Mass Media, Young People, and Religious Language - Paul Teusner (Papers from Trans-Tasman Research Symposium, 2005)
This article offers readers some background and preliminary findings of what will be a research paper into the interplay between mass media, religious identity and young people living in Australia. The working title of the research is “Crossing Over or Crossing Out? The Media’s Influence in Young People’s Religious Language and Imaginings.” This project seeks to answer the following questions: 1. How does the interplay between media, culture and religion set the “rules of play” for religious language to form and communicate a religious identity? 2. How are individuals freed by, and constrained by, media and culture to seek a religious identity outside the confines of religious institutions? The task involved in this research is two-fold. The first is to provide a theoretical framework that seeks to explain how religious language responds to cultural change. This framework should take into account the role of mass media in cultural shifts within contemporary society, provide an overview of the changing religious landscape in recent history, and seek to identify the relationship between them. The second part of the project is to set the framework against human research. It is hoped that some qualitative research may offer clear insight into the ways in which young people use mass media to inform their opinions about organised religion, as well as their own religious beliefs and values. It is also expected that interviews with young people will throw light on how mass media have influenced the ways in which they understand and use religious language to shape and communicate these opinions and ideas. This article will offer some background findings into the development of a theoretical framework for religious language, and some initial discoveries into young people’s attitudes towards traditional religion and the bases behind them.

The End of Cyberspace and Other Surprises - Thomas, S (Convergence: The International Journal of Research into New Media Worlds, 2006)
This article reports on Web 2.0, the end of cyberspace, and the internet of things. It proposes that these concepts have synergies both with the current fashion for modifying physical objects with the features of virtual objects, as evidenced in O'Reilly's MAKE magazine and similar projects, and with the potential technologies for collective intelligence described by Bruce Sterling, Adam Greenfield, Julian Bleecker and others. It considers Alex Pang's research on the end of cyberspace and asks whether the ‘new’ of new media writing will have any meaning in a world that is updated by the microsecond every time there is fresh activity in the system.
Keywords: cyberspace; media; Technologies

Religion and the Internet - Thumma, Scott (Hartford Institute for Religion Research, 2000)

Cyber Sisters: Buddhist Women's Online Activism and Practice - Tomalin, E; Starkey, C; Halafoff, A (Annual Review of the Sociology of Religion: Religion and Internet, 2015)
The interest of the book lies in the diversity of the geographical areas, religions, and online religious presence which nevertheless have a lot of points in common. Non-interactive websites, social networks, chat lines, and so on come together to provide a good panorama of the online opportunities to religions nowadays.
Keywords: Buddhist; cyber; online activism; Women

Gamevironments Special Issue: "Nation(alism), Identity and Video Gaming" - Trattner, Kathrin; Kienzl, Lisa (2019)
Video games are a prime example of globalized media cultures, hence, questions of nation and identity have been increasingly addressed in scientific and public discourses in recent years.For this special issue, we were especially interested in dissecting the specific relationship between national socio-political contexts and game development, the influence of the notion of the nation and nationalism as well as (national) identity building processes and religious systems and their various forms of representation in video games and in the gaming community.
Keywords: identity; nationalism; video games

Between “cultural enclave” and “virtual enclave”: Ultra-Orthodox society and the digital media - Tsarfaty, Orly; Blais, Dotan (Kesher, 2002)

Approaches to Digital Methods in Studies of Digital Religion - Tsuria, R; Yadlin-Segal, A; Virtillo, A; Campbell, H (The Communication Review, 2017)
This article reviews digital methodologies in the context of digital religion. We offer a tripod model for approaching digital methods: (a) defining research within digital environments, (b) the utilization of digital tools, and (c) applying unique digital frames. Through a critical review of multiple research projects, we explore three dominant research methods employed within the study of digital religion, namely, the use of textual analysis, interviews, and ethnography. Thus, we highlight the opportunities and challenges of using digital methods.
Keywords: Digital Religion

Israel - Tsuria, R; Yadlin-Segal, A (Online around the World: A Geographic Encyclopedia of the Internet, Social Media, and Mobile Apps, 2017)
Keywords: internet; Israel; mobile apps; social media

Representations de la diversité religieuse à la télévision publique - Tudor, Mihaela-Alexandra (4th Workshop international Essachess: Média, spiritualité et laïcité : Regards croisés franco-roumains, 2015)
Le problème que je pose dans ce cadre consiste à voir quel sont les pratiques des médias de service public à l’égard des représentations de la diversité religieuse et, plus précisément, à l’égard des représentations de transmission et communication de la foi dans deux pays européens dont l’un fort religieux et l’autre fort laïc, la Roumanie et la France. Il est question de voir en quoi le discours des médias publics sur la diversité n’altère pas le principe de la laïcité, la neutralité, le respect du pluralisme et l’intégralité des consciences. Pour ce faire, je vais retenir deux cas de figure, deux émissions télévisées diffusées sur les chaînes publiques de télévision en France et en Roumanie : l’émission « Le jour du Seigneur », avec ses déclinaisons d’intitulé au fil du temps « Programme du dimanche » et « Les chemins de la foi », diffusée sur France 2 et « Universul credintei » (« l’Univers de la foi ») diffusée sur TVR1. En considérant ces deux programmes de télévision, je vais tenter de répondre globalement aux questionnements suivants : est-ce que tous les mouvements religieux sont-ils présents dans les médias audiovisuels publics autant que les acteurs des confessions religieuses traditionnellement implantées ? Oui, c’est une réalité, certains mouvements disposent de leurs propres chaînes, mais leur présence sur leurs chaînes privées ne remplace pas un droit par un autre. S’agit-t-il alors d’une situation de monopole et de visibilité maximale des courants religieux dominants dans l’espace public au travers des médias publics ? Plus de normalisation garantit plus d’accès compte tenu que le principe de laïcité prévoit l’égalité et l’absence de hiérarchie entre les différentes croyances et cultes ?
Keywords: cultural diversity; Faith; freedom of opinion; laicism; pluralism; public institution; religion; religious community representation; Television

Multi-mediatization and religious event: the case of the evangelical campaign "Horizon of Hope" on Hope Channel Romania (Speranta TV)/Multimédiatisation et événement religieux : le cas de la campagne d’évangélisation l’« Horizon de l’espérance » de Hope - Tudor, Mihaela-Alexandra (tic&société, 2015)
Multi-mediatization and religious event: the case of the evangelical campaign "Horizon of Hope" on Hope Channel Romania (Speranta TV) – In this article we will question how the religious media engages with the new Information and Communication Technologies (ICTs) for evangelization by reconstructing neo-protestant Hope Channel Romania’s (Speranta TV) work to implement the evangelical "Horizon of Hope" campaign. Considering that ICTs cannot be regarded yet as stabilized, we suggest that the product of media evangelization created by this religious media is rooted in the logic of cross media convergence between old and new media rather than in a logic of transfer of authority toward the new media. *** Dans cet article nous questionnons les formes d’engagement des médias religieux avec les nouvelles technologies de l’information et de la communication (NTIC) pour « évangéliser » en reconstituant le chemin fait par la chaîne de télévision néo-protestante Hope Channel Romania (Speranta TV) pour la mise en œuvre de la campagne d’évangélisation l’ « Horizon de l’espérance ». Si l’on considère que les NTIC ne sont pas encore stabilisées, l’hypothèse mise à l’épreuve ici consiste à montrer que le produit d’évangélisation multimédia créé par Speranta TV s’inscrit davantage dans la logique de la convergence cross-media des médias traditionnels et des nouveaux médias que dans la logique du « transfert d’autorité » vers les nouveaux médias.
Keywords: convergence cross media; evangelization; neo-Protestant media; New Media

Life on the Screen: Identity in the Age of the Internet - Turkle, S. (Touchstone, 1995)
'Life on the Screen' is a fascinating and wide-ranging investigation of the impact of computers and networking on society, peoples' perceptions of themselves, and the individual's relationship to machines. Sherry Turkle, a Professor of the Sociology of Science at MIT and a licensed psychologist, uses Internet MUDs (multi-user domains, or in older gaming parlance multi-user dungeons) as a launching pad for explorations of software design, user interfaces, simulation, artificial intelligence, artificial life, agents, 'bots,' virtual reality, and 'the on-line way of life.' Turkle's discussion of postmodernism is particularly enlightening. She shows how postmodern concepts in art, architecture, and ethics are related to concrete topics much closer to home, for example AI research (Minsky's 'Society of Mind') and even MUDs (exemplified by students with X-window terminals who are doing homework in one window and simultaneously playing out several different roles in the same MUD in other windows). Those of you who have (like me) been turned off by the shallow, pretentious, meaningless paintings and sculptures that litter our museums of modern art may have a different perspective after hearing what Turkle has to say

Religious Authority and the New Media - Turner, Bryan S (Theory, Culture & Society, 2007)
In traditional societies, knowledge is organized in hierarchical chains through which authority is legitimated by custom. Because the majority of the population is illiterate, sacred knowledge is conveyed orally and ritualistically, but the ultimate source of religious authority is typically invested in the Book. The hadith (sayings and customs of the Prophet) are a good example of traditional practice. These chains of Islamic knowledge were also characteristically local, consensual and lay, unlike in Christianity, with its emergent ecclesiastical bureaucracies, episcopal structures and ordained priests. In one sense, Islam has no church. While there are important institutional differences between the world religions, network society opens up significant challenges to traditional authority, rapidly increasing the flow of religious knowledge and commodities. With global flows of knowledge on the Internet, power is no longer embodied and the person is simply a switchpoint in the information flow. The logic of networking is that control cannot be concentrated for long at any single point in the system; knowledge, which is by definition only temporary, is democratically produced at an infinite number of sites. In this Andy Warhol world, every human can, in principle, have their own site. While the Chinese Communist Party and several Middle Eastern states attempt to control this flow, their efforts are only partially successful. The result is that traditional forms of religious authority are constantly disrupted and challenged, but at the same time the Internet creates new opportunities for evangelism, religious instruction and piety. The outcome of these processes is, however, unknown and unknowable. There is a need, therefore, to invent a new theory of authority that is post-Weberian in reconstructing the conventional format of charisma, tradition and legal rationalism.
Keywords: Authority; Bureaucracy; Knowledge; New Media; Tradition

A relational model of authority in groups - Tyler, T.; Lind, A. (Advances in Experimental Social Psychology, 1992)
This chapter focuses on one particular aspect of authoritativeness: voluntary compliance with the decisions of authorities. Social psychologists have long distinguished between obedience that is the result of coercion, and obedience that is the result of internal attitudes. Opinions describe “reward power” and “coercive power”, in which obedience is contingent on positive and negative outcomes, and distinguish both of these types of power from legitimate power, in which obedience flows from judgments about the legitimacy of the authority. Legitimate power depends on people taking the obligation on themselves to obey and voluntarily follow the decisions made by authorities. The chapter also focuses on legitimacy because it is important to recognize, that legitimacy is not the only attitudinal factor influencing effectiveness. It is also influenced by other cognitions about the authority, most notably judgments of his or her expertise with respect to the problem at hand. The willingness of group members to accept a leader's directives is only helpful when the leader knows what directives to issue.

The Amish and the media - Umble, D.Z; Weaver-Zercher, D.L (JHU Press, 2008)
This collection is the first scholarly treatment of the relationship between the Amish and the media in contemporary American life. The essays not only focus on the Amish as subjects in mainstream media—news, movies, TV—but also view them as producers and consumers of media themselves. Of all the religious groups in contemporary America, few demonstrate as many reservations toward the media as do the Old Order Amish. Yet these attention-wary citizens have become a media phenomenon, featured in films, novels, magazines, newspapers, and television—from Witness, Amish in the City, and Devil's Playground to the intense news coverage of the 2006 Nickel Mines School shooting. But the Old Order Amish are more than media subjects. Despite their separatist tendencies, they use their own media networks to sustain Amish culture. Chapters in the collection examine the influence of Amish-produced newspapers and books, along with the role of informal spokespeople in Old Order communities. With essays from experts in the fields of film and media studies, poetry, American studies, anthropology, and history, this groundbreaking study shows how the relationship between the Amish and the media provides valuable insights into the perception of minority religion in North American culture.
Keywords: Amish; media

Manifestation of Religious Authority on the Internet: Presentation of Twelver Shiite Authority in the Persian Blogosphere - Valibeigi, Narges (Sociology, 2012)
Cyberspace has diversified and pluralized people’s daily experiences of religion in unprecedented ways. By studying several websites and weblogs that have a religious orientation, different layers of religious authority including “religious hierarchy, structures, ideology, and sources” (Campbell, 2009) can be identified. Also, using Weber’s definition of the three types of authority, “rational-legal, traditional, and charismatic” (1968), the specific type of authority that is being presented on blogosphere can be recognized. The Internet presents a level of liberty for the discussion of sensitive topics in any kind of religious cyberspace, specifically the Islamic one. In this way, the Internet is expanding the number and range of Muslim voices, which may pose problems for traditional forms of religious authority or may suggest new forms of authority in the Islamic world. The interaction between the Internet and religion is often perceived as contradictory, especially when it is religion at its most conservative practice. While the international and national applications of the Internet have increased vastly, local religious communities, especially fundamentalists, perceived this new technology as a threat to their local cultures and practices. If we look at the Internet as a central phenomenon of contemporary modernity that interacts with practiced fundamentalist religious traditions, we can ask how broad the interactions are between religious fundamentalism and the Internet and whether these relations can be reconciled. More specifically, this thesis presents a study of the junction of the Internet and religious fundamentalism reviewing the presentation of Shiite religious authority on the Persian blogosphere. As a case study, Persian weblogs are studied for content analysis for this thesis. Weblogs’ texts are analyzed to find evidences for Shiite beliefs and shared identity, usages and interpretations of the main Shiite religious texts, references to the role of recognized Shiite leaders, and descriptions of Shiite structural patterns of practices and organizations. This research will demonstrate how the Internet has been culturally constructed, modified, and adapted to the Iranian community’s needs and how the Shiite fundamentalist community of Iran has been affected by it. Based on one of the most structured research in this area, the study by Baezilai-Nahon and Barzilai (2005), in this article I identify four principal dimensions of religious fundamentalism as they interact with the Internet: hierarchy, patriarchy, discipline, and seclusion.
Keywords: Authority; Biosphere; Digital Religion; Iran; media and religion; new media engagement; New media praticipation; Persian; Religious Internet Communities; Shiite Muslim; sociability unbound

Web 2.0: technology for the postmodern sensibility and its implications for the church - Van den Heever, James (Journal Of Theology For Southern Africa, 2008)
Web 2.0 is a new technology approach that in essence builds on the Internet's existing culture of collaboration and individual freedom. This article argues that Web 2.0 is both creator and creation of the postmodern Zeitgeist, with technology and social development existing in a mutually reinforcing spiral. To minister effectively to the postmodern world, the Church needs to understand how to use these new technologies and, more importantly, respond to the new world they simultaneously reflect and create. The article outlines the main characteristics of postmodernism, the context of Web 2.0, before examining in some detail the nature of Web 2.0. This discussion is followed by an outline of the main technologies that enable Web 2.0. It then moves onto a consideration of what all this means for the Church. Tactical uses of some of the technologies are suggested before the article moves on to examine the main implications of the combination of Web 2.0 and postmodernism. It concludes with a summary of the opportunities and challenges this combination presents for the Church.

When 'Friend' Becomes a Verb: Religion on the Social Web - Daniel Veidlinger (God in the Details: American Religion in Popular Culture, 2010)
Keywords: Digital Religion; integration; Interaction; interpretation; social media; social networks

Christians in a.com World: Getting Connected without Being Consumed - Veith, Gene Edward; Stamper, Christopher (Crossway Books, 2000)
In the Internet we are facing the biggest information revolution since the printing press. This technology presents new challenges to our culture as a whole, making it essential that we as Christians be "plugged in." And while millions are online, you, like many, may be simultaneously uneasy about where this new medium is leading us. Noted culture critic Gene Veith and Chris Stamper, a leading voice in modern technology, want to help you understand the significance cyberculture has for us as Christians. The authors tackle the current controversies, including censorship, the possible demise of print, and how it all ties into postmodernism. As they challenge the myths, probe the weaknesses, and reveal the possibilities of this new and continually developing medium, you will become an informed and discerning traveler on the information highway. One who understands the cultural and worldview implications of the Internet and who knows how to be wired to it but not entangled by it.

Women responding to the anti-Islam film Fitna: voices and acts of citizenship on YouTube - Vis, F; van Zoonen, L; Mihelj, S (Feminist Review, 2011)
How feminists view the alternative videos uploaded to YouTube in response to the anti-Islam film 'Fitna' is discussed. The gender portrayal and narratives in 'Fitna' are contrasted with those in the alternative video. The videos were considered as acts of citizenship through which women constitutes themselves as global citizen by engaging in deliberation or by taking a voice.
Keywords: anti-Islam; citizenship; Digital Religion; Feminists; Fitna; gender studies; Islam; Religious Internet Communities; Research Political participation; YouTube

Religioni e Internet: Evangelizzazione o Reincantamento del Mondo? - Vitullo, A (Rapporto sull’Analfabetismo Religioso in Italia, 2014)
Il rapporto sull'analfabetismo religioso in Italia intende porre domande, tracciare percorsi e contestualizzare il tema dell'assenza del religioso nei processi educativi su scala internazionale. Il volume offre una riflessione organica su ciò che viene ignorato dal sistema scolastico e sui perché storico-teologici, oltreché storico-politici, di queste omissioni e lacune. A un'ampia analisi delle premesse teorico-critiche e dello scenario storico italiano da cui il fenomeno trae la propria natura si affiancano rassegne di studi, analisi delle esperienze riuscite e fallite e alcuni primi strumenti di cura che ambiscono a generare un dibattito pubblico sul tema e a costruire una riflessione capace di coinvolgere tutti gli attori sociali impegnati nel settore educativo e della formazione. Correda il volume una sezione info-grafica e di mappe che rende la lettura più intuitiva, trasferendo su immagini e simboli la complessità delle informazioni e dei dati raccolti.
Keywords: evangelism; internet; religion

God in the Game: Cosmopolitanism and Religious Conflict in Videogames - Wagner, Rachel (Journal of the American Academy of Religion, 2013)
Keywords: Cosmopolitanism; religion; video games

Our Lady of Persistent Liminality: Virtual Church, Cyberspace, and Second Life - Wagner, Rachel (God in the Details Routledge Press, 2010)

The Play Is the Thing: From Bible Fights to Passions of the Christ - Wagner, R (Halos and Avatars: Playing Video Games With God, 2010)
Keywords: Christianity; Immersion; interactivity; Jesus; narrativity; Parody; player-viewer; video games

You Are What You Install: Religious Authenticity and Identity in Mobile Apps - Wagner, R (Digital Religion: Understanding Religious Practice in New Media Worlds, 2012)
Digital Religion offers a critical and systematic survey of the study of religion and new media. It covers religious engagement with a wide range of new media forms and highlights examples of new media engagement in all five of the major world religions. From cell phones and video games to blogs and Second Life, the book: provides a detailed review of major topics includes a series of case studies to illustrate and elucidate the thematic explorations considers the theoretical, ethical and theological issues raised. Drawing together the work of experts from key disciplinary perspectives, Digital Religion is invaluable for students wanting to develop a deeper understanding of the field.
Keywords: Apps; identity; iPhone; religion; technology

You Are What You Install: Religious Authenticity and Identity in Mobile Apps - Wagner, R (Digital Religion: Understanding Religious Practice in New Media Worlds, 2012)
Keywords: Apps; identity; mobile; religious

Godwired: Religion, ritual and virtual reality - Wagner, R (Routledge, 2012)
Godwired offers an engaging exploration of religious practice in the digital age. It considers how virtual experiences, like stories, games and rituals, are forms of world-building or "cosmos construction" that serve as a means of making sense of our own world. Such creative and interactive activity is, arguably, patently religious.
Keywords: Godwired; religion; Ritual; virtual reality

Godwired: Religion, Ritual and Virtual Reality - Wagner, Rachel (Routledge, 2011)
Godwired offers an engaging exploration of religious practice in the digital age. It considers how virtual experiences, like stories, games and rituals, are forms of world-building or "cosmos construction" that serve as a means of making sense of our own world. Such creative and interactive activity is, arguably, patently religious. This book examines: the nature of sacred space in virtual contexts technology as a vehicle for sacred texts who we are when we go online what rituals have in common with games and how they work online what happens to community when people worship online how religious "worlds" and virtual "worlds" nurture similar desires. Rachel Wagner suggests that whilst our engagement with virtual reality can be viewed as a form of religious activity, today's virtual religion marks a radical departure from traditional religious practice -- it is ephemeral, transient, rapid, disposable, hyper-individualized, hybrid, and in an ongoing state of flux.

Video Games and Religion - Wagner, Rachel (Oxford University Press, 2015)
This article identifies key features of the comparison between video games and religion, focusing on contemporary video games based on specific ancient apocalypses including “The Book of the Watchers” in the Enoch corpus and the Book of Revelation in the Bible. Many contemporary video games function as rituals of order-making, creating spaces of play in which violence is a performative mode of metaphysical sorting, allowing for new negotiations between “good” and “evil.” Through a consideration of popular gaming elements (fragging, fiero, firepower, and fun), this article proposes that the strong relationship between video games and apocalyptic literature invites a closer examination of how eschatological tensions infuse contemporary times, too often inviting an overly simplistic apocalyptic response to contemporary global challenges.

The Buddhist Dharma for Sale: Who Owns the Past? The Internet and Objects of Worship - Wallinder-Pierini, Linda S E (2018)
Is it possible to claim ownership of the Buddhist dharma; the teachings of the Buddha? Does a group’s relationship to its cultural productions constitute a form of ownership? Can a religious image be copyrighted? This article will focus on the emergence and transformation of the Moji-Mandala or Gohonzon (御本尊), created by the Japanese monk Nichiren (1222-1282). Nichiren’s followers were persecuted, and some were executed when the scroll was found in their possession. Nichiren’s hanging mandala was previously available only to individuals seriously practicing Nichiren’s Buddhism. Currently, Nichiren’s mandala is reproduced electronically over the internet by websites claiming to represent various Buddhist lay organizations. The digital revolution has increased the ability of individuals to appropriate and profit from the cultural knowledge of religious groups that are largely unprotected by existing intellectual property law.

Why Muslim Women and Smartphones: Mirror Images - Waltorp, Karen (Routledge, 2020)
Using an assemblage approach to study how Muslim women in Norrebro, Denmark use their phones, Karen Waltorp examines how social media complicates the divide between public and private in relation to a group of people who find this distinction of utmost significance. Building on years of ethnographic fieldwork, Waltorp's ethnography reflects the trust and creativity of her relationships with these women which in turn open up nuanced discussions about both the subject at hand and best practice in conducting anthropological research. Combining rich ethnography with theoretical contextualization, Waltorp's book alternates between ethnography and analysis to illuminate a thoroughly modern community, and reveals the capacity of image-making technology to function as an infrastructure for seeing, thinking and engaging in fieldwork as an anthropologists. Waltorp identifies a series of important issues around anthropological approaches to new media, contributing to new debates around the anthropology of automation, data and self-tracking.

Keeping cool, staying virtuous: Social media and the composite habitus of young Muslim women in Copenhagen - Waltorp, Karen (MedieKultur: Journal of media and communication research, 2015)
This article builds on long-term anthropological fieldwork among young Muslim women in a social housing area in Copenhagen. It explores how morality, modesty, and gender- and generational relations become reconfigured in the ways in which young women use the Smartphone and social media to navigate their everyday lives. I focus on love and marriage, the imperatives of appearing cool among peers, and keeping the family’s honour intact through the display of virtuous behaviour. Building on Bourdieu’s writings on the split habitus, I introduce the term composite habitus, as it underscores the aspect of a habitus that is split between (sometimes contradictory) composite parts. The composite habitus of the young women is more than a hysteresis effect (where disposition and field are in mismatch and the habitus misfires), as the composite habitus also opens up to a range of possible strategies. I present examples of how intimate and secret uses of Smartphones have played out and show how social media have allowed for multiple versions of the self through managing public and secret relationships locally and across long distances.

Soul-Searching on Facebook - William Wan (The Washington Post, 2009)
Such public proclamations of beliefs used to require a baptism in water, or a circumcision, or learning the five pillars of Islam. Now Facebook users announce their spiritual identity with the stroke of a few keys. And what they are typing into the open-ended box offers a revealing peek into modern faith and what happens to that faith as it migrates online.

Investigating religious information searching through analysis of a search engine log - Rita Wan-Chik; Paul Clough; Mark Sanderson (Journal of the American Society for Information Science and Technology, 2013)
In this paper we present results from an investigation of religious information searching based on analyzing log files from a large general-purpose search engine. From approximately 15 million queries, we identified 124,422 that were part of 60,759 user sessions. We present a method for categorizing queries based on related terms and show differences in search patterns between religious searches and web searching more generally. We also investigate the search patterns found in queries related to 5 religions: Christianity, Hinduism, Islam, Buddhism, and Judaism. Different search patterns are found to emerge. Results from this study complement existing studies of religious information searching and provide a level of detailed analysis not reported to date. We show, for example, that sessions involving religion-related queries tend to last longer, that the lengths of religion-related queries are greater, and that the number of unique URLs clicked is higher when compared to all queries. The results of the study can serve to provide information on what this large population of users is actually searching for.
Keywords: Buddhism; Christianity; Digital; Hinduism; information; Islam; Judaism; queries; religion; search behavior; search engine

Celebrity Worship - Peter Ward (Routledge, 2019)
Celebrity Worship provides an introduction to the fascinating study of celebrity culture and religion. The book argues for celebrity as a foundational component for any consideration of the relationship between religion, media and culture. Celebrity worship is seen as a vibrant and interactive discourse of the sacred self in contemporary society. Topics discussed include: Celebrity culture. Celebrity worship and project of the self as the new sacred. Social media and the democratisation of celebrity. Reactions to celebrity death. Celebrities as theologians of the self. Christian celebrity. Using contemporary case studies, such as lifestyle television, the religious vision of Oprah Winfrey and the death of David Bowie, this book is a gripping read for those with an interest in celebrity culture, cultural studies, media studies, religion in the media and the role of religion in society.

Digital Religion and Media Economics: Concentration and Convergence in the Electronic Church - Ward, Mark (Journal of Religion, Media and Digital Culture, 2018)
The economics that push every medium toward market concentration have historically done likewise to every religious medium. “Online religion” is now, in its turn, colonized by an “electronic church” industry that, due to media deregulation, is dominated by religious media conglomerates—through whom North Americans are most likely to engage in digital religion. The largest conglomerate alone generates 110 million computer sessions and 79 million mobile sessions per month. This study reviews the economics of media concentration and applications to religious media, surveys the digital footprint of the institutional electronic church, and advocates integration of media practices into Digital Religion Studies.

Hope and Sorrow: Uncivil Religion, Tibetan Music Videos, and YouTube - Cameron David Warner (Ethnos: Journal of Anthropology, 2013)
Tibetan activists and their supporters are interpreting the lyrical and visual symbolism of contemporary Tibetan music videos from China as a call for Tibetans to return to a shared Tibetan identity, centered around religious piety and implied civil disobedience, in order to counter fears of cultural assimilation. As the popularity of some videos on social-networking sites dovetailed with the 2008 protests in Tibet, viewers employed a progressive hermeneutical strategy which demanded a sectarian political interpretation of the lyrics and imagery of the most popular videos out of Tibet. Within China, Tibetans have begun to add these videos to the growing canon of an emerging uncivil religion, which emphasizes Tibetan cultural, linguistic, and religious autonomy within China. Through comparing online and offline ethnography, this article explores the relationship between offline and online worlds and the connections between Tibetans in China and their supporters.
Keywords: China; media; Music; religion; Tibet; YouTube

Theory of social and economic organization - Weber, M. (Oxford University Press, 1947)

Religious discourse in the archived web: Rowan Williams, archbishop of Canterbury, and the sharia law controversy of 2008 - Webster, Peter (The Web as History: the first two decades, 2017)

Technology, ethics and religious language: early Anglophone Christian reactions to “cyberspace” - Webster, Peter (Internet Histories, 2018)

Religion and Web history - Webster, Peter (The SAGE Handbook of Web History, 2019)

Lessons from cross-border religion in the Northern Irish web sphere: understanding the limitations of the ccTLD as a proxy for the national web - Webster, Peter (The Historical Web and Digital Humanities: the Case of National Web domains, 2019)

Networks, Neighborhoods, and Communities: Approaches to the Study of the Community Question - Wellman, B.; Leighton, B (Urban Affairs Review, 1979)
We propose a network analytic approach to the community question in order to separate the study of communities from the study of neighborhoods. Three arguments about the community question-that "community" has been "lost," "saved," or "liberated"-are reviewed for their development, network depictions, imagery, policy implications, and current status. The lost argument contends that communal ties have become attenuated in industrial bureaucratic societies; the saved argument contends that neighborhood communities remain as important sources of sociability, support and mediation with formal institutions; the liberated argument maintains that while communal ties still flourish, they have dispersed beyond the neighborhood and are no longer clustered in solidary communities. Our review finds that both the saved and liberated arguments proposed viable network patterns under appropriate conditions, for social systems as well as individuals.
Keywords: community; media; Neighborhoods; networks; social network

Studying the Internet through the Ages - Wellman, B. (Handbook of Internet Studies, 2011)
The Handbook of Internet Studies brings together scholars from a variety of fields to explore the profound shift that has occurred in how we communicate and experience our world as we have moved from the industrial era into the age of digital media.

An Electronic Group is Virtually a Social Network - Barry Wellman (Culture of the Internet, 1997)
When a computer network connects people, it is a social network. Just as a computer network is a set of machines connected by a set of cables, a social network is a set of people (or organizations or other social entities) connected by a set of socially meaningful relationships. I show how social network analysis might be useful for understanding how people relate to each other through computer-mediated communication (see also Wellman & Gulia, in press; Wellman et al., 1996).
Keywords: computer-mediated communication; social network

The Internet in Everyday Life - Barry Wellman; Caroline Haythornthwaite (Information Age Series)
The Internet in Everyday Life is the first book to systematically investigate how being online fits into people's everyday lives. Opens up a new line of inquiry into the social effects of the Internet. Focuses on how the Internet fits into everyday lives, rather than considering it as an alternate world. Chapters are contributed by leading researchers in the area. Studies are based on empirical data. Talks about the reality of being online now, not hopes or fears about the future effects of the Internet.
Keywords: internet; Internet Studies; methodologies; social effects

Media Perceptions of Religious Changes in Australia: Of Dominance and Diversity - Weng, Enqi (Routledge, 2019)
This volume explores the contradiction between the news coverage given to issues of religion, particularly since 2001 in relation to issues such as terrorism, politics, security and gender, and the fact of its apparent decline according to Census data. Based on media research in Australia, and offering comparisons with the UK, the author demonstrates that media discussions overlook the diversity that exists within religions, particularly the country’s main religion, Christianity, and presents religion according to specific interpretations shaped by race, class and gender, which in turn result in very limited understandings of religion itself. Drawing on understandings of the sacred as a non-negotiable value present in religious and secular form, Media Perceptions of Religious Changes in Australia calls for a broader sociological perspective on religion and will appeal to scholars of sociology and media studies with interests in religion and public life.

The Pearly Gates of Cyberspace - Wertheim, Maragret (Virago, 1999)
Cyberspace may seem an unlikely gateway for the soul. But as science commentator Margaret Wertheim argues in this "marvelously provocative" (Kirkus Reviews) book, cyberspace has in recent years become a repository for immense spiritual yearning. Wertheim explores the mapping of spiritual desire onto digitized space and suggests that the modem today has become a metaphysical escape-hatch from a materialism that many people find increasingly dissatisfying. Cyberspace opens up a collective space beyond the laws of physics-a space where mind rather than matter reigns. This strange refuge returns us to an almost medieval dualism between a physical space of body and an immaterial space of mind and psyche.

The digital advantage: How digital leaders outperform their peers in every industry - Westerman, G.; Tannou, M.; Bonnet, D.; Ferraris, P.; McAfee, A. (MIT Sloan Management and Capgemini Consulting, 2012)

Remixing Images of Islam. The Creation of New Muslim Women Subjectivities on YouTube - Wheeler, Kayla Renée (Online - Heidelberg Journal of Religions on the Internet, 2014)
This study provides a textual analysis of YouTube videos produced by two popular Western English-speaking vloggers, Amenakin and Nye Armstrong using Guo and Lee’s hybrid vernacular discourse framework. Vernacular discourse is defined as speech and culture that includes music, art, and fashion, which resonates within a local community.The framework focuses on three components: content, agency, and subjectivity. I extend this framework by examining audience response to the new images through analyzing comments and response videos. Recognizing that the boundaries between vernacular and mainstream discourse are blurred, my research is guided by the following question: How are Muslim women rearticulating and renegotiating mainstream and vernacular discourses to introduce new and complex images of Muslim womanhood that challenge mainstream Western representations of Muslim women?

Islam, Community and the Internet: New possibilities in the digital age - Wheeler, Deborah (2002)
This essay uses three examples of Muslim cyberpractices as a means for understanding how the Internet enables the formation, maintenance, and management of certain kinds of Islamic communities. First is the case of the al-Qaeda movement and its critics. Case two is an Ask the Imam web site, where postings on cyberdating are analyzed as a means to define proper Muslim behavior in cyberspace. The third case is the gayegypt.com web site and the controversies surrounding it. It has been said that the Internet is producing a kind of Muslim Renaissance similar in scope and effect to the flowering of Islamic science, learning, and community values during the Abbassid period many centuries earlier. As this analysis illustrates, the kinds of changes in Muslim community enabled by the Internet are fundamentally altering the values and practices defined by Muslims in the Medieval period, especially in terms of the construction of authority.

Christian Worship and Technological Change - White, S. (Abingdon Press, 1994)
Arguing that a primary influence on the social context of Christian worship is the pervasive presence of technology and technological processes, White traces the interplay between technological processes and Christian worship, and gives suggestions as to how the church might approach scientific advances in a rapidly changing society.

The Evidence of Things Unseen: Authenticity and Fraud in the Christian Mommy Blogosphere - Whitehead, Deborah (Journal of the American Academy of Religion, 2015)
This article analyzes allegations of fraud and deception in two popular evangelical Christian “mommy blogs” in order to demonstrate how the rhetoric of authenticity in social media plays a central role in the formation of online communities. I argue that a personal religious blogger together with her readers constitutes an ongoing public conversation and community, one that is held together by a kind of belief or trust in the truthful representation of the blogger and her story. When a blog claims to be a story about the power of faith, hope, and miracles, it can be read and understood by its devoted readers as “evidence of things unseen,” that is, as a representation of the evidence of authentic religious faith and practice shared by the community. On the other hand, if credibility is doubted, the blog may become the focus of allegations of deception, leading to the creation of new forms of online community. These cases highlight the importance of attending to claims of credibility and authenticity as constitutive of religious practice and community formation in social media and in the academic study of religion more broadly.

“The story God is weaving us into”: narrativizing grief, faith, and infant loss in US evangelical women's blog communities - Whitehead, Deborah (New Review of Hypermedia and Multimedia, 2015)
This case study explores how US evangelical Christian "mommy blog" communities constitute spaces for the collective memorialization of infant loss. Personal religious blogs feature a rich combination of esthetics, narrative structure, description of religious practices and beliefs, reader interaction, and linked networks. Using a textual approach, I illustrate distinctive features in how pregnancy and infant loss and grief are experienced, shared and memorialized in US women's evangelical blogging communities. I argue that the blog format allows for a (re)narrativization of the devastating experience of infant loss as grieving mothers situate their traumatic personal experiences within the context of an ongoing religious narrative in which blog readers also come to participate. As the blogger tells the story of her own loss to a listening public, it becomes a larger shared story, so that it is not just the child's story but also the author's story, their family's story, and "our story" inclusive of the blog community of readers, "the story God is weaving us into," post by post, day by day. Personal religious blogs and their reading publics, therefore, can provide a medium for the ongoing creation of meaning, faith and community in the context of infant loss.

When religious ‘mommy bloggers’ met ‘mommy porn’: evangelical Christian and Mormon women’s responses to fifty shades - Whitehead, D (Sexualities, 2013)
While some conservative religious women have rejected Fifty Shades of Grey as contrary to their values and beliefs, others have embraced it. This article analyzes commentaries and reflections on the book series in US evangelical Christian and Mormon women’s blog communities, and shows how many of these women find value in the books because of their personal, cultural, and religious significance. I argue that attention to the reading strategies employed by evangelical and Mormon women in relation to Fifty Shades demonstrates a complex set of responses to ‘secular’ culture as well as ongoing negotiations of gender, sexuality, and authority within these conservative religious traditions.
Keywords: Evangelical Christian; Fifty Shades; Mormon; religious

Islamic Activism: A Social Movement Theory Approach - Quintan Wiktorowicz (Indiana Series in Middle East Studies)
This volume represents the first comprehensive attempt to incorporate the study of Islamic activism into social movement theory. It argues that the dynamics, processes, and organization of Islamic activism can be understood as important elements of contention that transcend the specificity of "Islam" as a system of meaning and identity and a basis for collective action. Drawing on extensive fieldwork, the contributors show how social movement theory can be utilized to address a wide range of questions about the mobilization of contention in support of Muslim causes. The book covers myriad examples of Islamic activism (Sunni and Shi‘a) in eight countries (Arab and non-Arab), including case studies of violence and contention, networks and alliances, and culture and framing.
Keywords: activism; Egypt; Iran; Islam; Islamic; Muslims; Shi‘a; social movement; Sunni; Yeman

Religious authority and divine action - Wiles, M. F. (Religious Studies, 1971)

Vatican rules out online confessions - Wilian, P. (PC World Online, 2001)

The social shaping of technology - Williams, R.; Edge, D. (Research Policy)
This paper reviews the growing body of research that explores ‘the social shaping of technology’ (SST) — how the design and implementation of technology are patterned by a range of ‘social’ and ‘economic’ factors as well as narrowly ‘technical’ considerations. It shows how researchers from a range of disciplinary backgrounds were brought together by a critique of traditional conceptions of technology (for example, ‘linear models’ of innovation that privileged technological supply or restricted the scope of social inquiry into technology to assessing its ‘impacts’). Though their analytical frameworks differ to a greater or lesser extent in terminology and approach, some explanatory concepts have emerged, and constitute an effective model of the innovation process. Here, it is suggested, SST offers a deeper understanding and also potentially broadens the technology policy agenda. These claims are assessed through a review of recent research into specific instances of social shaping, particularly in relation to information technology. Finally the article discusses some of the intellectual dilemmas in the field. Though the intellectual cross-fertilisation has been creative, points of tension and divergence between its constituent strands have resulted in some sharp controversies, which reflect upon the theoretical and policy claims of SST.

Authentic Identities: Straightedge Subculture, Music, and the Internet - Williams, Patrick J. (Journal of Contemporary Ethnography, 2006)
In this article, the author examines the relative roles of music and the internet for self-identifying members of the straightedge youth subculture. For nearly 30 years, subcultures have been conceptualized primarily in terms of music and style. Participation has therefore typically been characterized by the consumption of specific types of music and clothing and participation in local, face-to-face music scenes. However, with the recent growth of information and communication technologies like the internet, opportunities have emerged that enable individuals to participate in subcultures in which they otherwise might not participate. The author shows that a new type of subculturalist is emerging—one whose subcultural participation is limited to the internet.Using the concepts of authenticity and scene, the author explores how participants in a straightedge internet forum negotiate their affiliations with the subculture and how some members attempt to halt others’ claims to a straightedge identity. The study suggests that the internet is emerging as a new, but highly contested, subcultural scene.
Keywords: authenticity; identity; internet; scene; straightedge; subculture

Humor and Identity on Twitter: #muslimcandyheartrejects as a Digital Space for Identity Construction - Wills, Emily Regan; Fecteau, AndrÉ (Journal of Muslim Minority Affairs, 2016)
Through examining the hashtag #muslimcandyheartrejects, a one-time, short-term, joke hashtag used on Twitter among a group of Muslim tweeters in 2012, we argue that members of Muslim digital diaspora communities use social media to construct and reinforce a Muslim diaspora identity. The architecture of Twitter provides the structure for these engagements, while humor serves meaning-making, cohesion building, and tension-relief functions within the conversation. The conversation itself combines a variety of topics to both describe Muslim identity in diaspora and to critique both Muslim community practices and conditions for Muslims in non-Muslim countries.

The Internet Church - Wilson, Walter (Word Publishing, 2000)
With rapid technological advances and the increasing impact of the internet, the world is literally at our fingertips. Yet many churches have yet to discover how to tap into this powerful resource. The Internet Church shows church leaders how to start from square one in creating an interactive website that can greatly expand the ministry potential of a church. Walter Wilson, an internet expert and committed Christian, describes how technology can enhance evangelism outreach, and challenges leaders to take advantage of unprecedented opportunities in the new digital age.

How algorithmic cultural recommendations influence the marketing of cultural collections - Wilson-Barnao, C. (Consumption Markets & Culture, 2017)
Museums make their collections available online to keep pace with developments in how people access and share information. While museums have traditionally understood the notion of public access as part of their institutional remit, in this paper I draw on policy documents and qualitative interviews with Australasian cultural professionals, to examine how the discourse of access might account for the museum’s transformation from a community space to a resource that is beneficial to marketers. I use Google Arts & Culture as a case study, to suggest the terms of public access have altered to adapt to the needs of commercial “digital enclosures.” When people engage with the museum in virtual spaces data are collected. Algorithms work as a set of instructions that make it possible to search, sort and organise the data, linking together people and their online practices in order to enact a form of algorithmic cultural recommendation.

The Bishop, the Mullah, and the Smartphone - Bryan Winters (Wipf & Stock)
Not so long ago the world resisted change, often using religious-reasoning. Small wonder--the printing press, a sixteenth century disruptive device, split Christianity. Now the globe welcomes digital disruption, even praising it as a solution for faltering economies. Religions don't have much choice but to follow, because information is a prime asset of faith. Believers treasure and reframe their past, and present. However, both old and current data is now available in huge quantities, visually and instantly. Movies provide more spiritual guidance than holy texts, and terror merchants use the uncontrollable Internet to gain hearts and minds. Nevertheless a turbulent re-mythologization of adherents towards peaceful versions of their belief can be tracked. There are positive things we can all do to help, which is just as well in a world that suggests only political acts count.
Keywords: bishop; Christianity; Digital; history; Islam; mullah; smartphone

Virtual Morality: Morals, Ethics and New Media - Wolf, Mark (Peter Lang Publishing, 2003)
New technologies continue to shape communication and how we think about and relate to the world around us. What is rarely examined is how these new media relate to morals and ethics in society and culture. In a series of twelve essays, written from a variety of viewpoints including philosophy, communication, media and art, and situating its arguments around the three poles of technology, community, and religion, this collection examines the relationship between morals and ethics and new media, ranging from the ways in which new communication technologies are employed to their effects on the messages communicated and those who use them.

Church share: Investigating technology use and adoption among culturally different religious groups - Susan P. Wyche (Georgia Institute of Technology, 2008)
Outside the workplace, technologies support a new range of activities such as exploring, wondering, loving, and worshipping. Yet, we know little about how individuals appropriate technology to support these activities. Understanding this becomes more pressing as computing’s presence increases in daily life. For my dissertation, I am investigating use of ICTs to support a subset of these activities, those related to religious aspects of life, or techno-spiritual practices. I focus on techno-spiritual practices within a specific faith and their worship settings — Protestant Christianity and megachurches. I conducted formative studies investigating how megachurches, their pastors, and their laity use ICTs for religious purposes in Atlanta, Ga., U.S., Nairobi, Kenya, and São Paulo, Brazil. Findings from these studies motivated an ICT intervention called ChurchShare, a photo-sharing site that allows laity to take digital photographs and share them with others during church worship services. I hypothesize that this technology will increase laity involvement in worship services and create new socialization styles among megachurch laity. I am exploring this technology through real world deployments. Research conducted in the U.S. primarily informed ChurchShare’s development; however, I draw from knowledge gained during fieldwork conducted abroad when evaluating ChurchShare. Specifically, I will ask individuals from three culturally distinct churches to use the site. One church will be comprised of U.S. born laity and the others will have predominately immigrant Kenyan and Brazilian worshippers. This will allow me to investigate how culturally different groups appropriate technology for religious purposes. In turn, this will lead to a broader understanding ICT adoption among individuals typically targeted by HCI researchers and ones who are not. This research is expected to yield empirical and theoretical finding that will contribute to human-centered computing research.

Surveying digital religion in China: Characteristics of religion on the Internet in Mainland China - Xu, Shengju; Campbell, Heidi A. (The Communication Review, 2018)
China’s distinct development of the Internet has provided religious populations within its mainland access, allowing them to create practices and resources related to the development of religion online. Yet this phenomenon has been understudied both within the current Chinese research on the Internet and international studies of digital religion online. This article provides an overview of digital religion in the Chinese context by identifying and exploring the main characteristics of Buddhism, Islam, and Protestantism manifest online. This is done by providing an overview of current research and profiling the development of different forms of digital religious expression found in China. Through this we show how the concept of digital religion is manifest in China and how this compares to Western understandings of such practices, and we highlight the unique characteristics defining the Chinese religious digital landscape.

New technologies, new relationships. Promoting a culture of respect, dialogue and friendship - Pope Benedict XVI (2009)

Erbi et orbi message of his holiness Pope Benedict XVI - Pope Benedict XYI (2006)

Connecting the Actual with the Virtual: The Internet and Social Movement Theory in the Muslim World—The Cases of Iran and Egypt - Lernerת Melissa Y (Journal of Muslim Minority Affairs, 2010)
The rapid expansion of Internet use in the Muslim world has called into question what role—if any—this medium can play in political action in these countries. This paper seeks to analyze the extent to which the Internet offers space for an expansion of social movement theory in the Muslim world. It relies on a number of case studies from two Muslim countries, the One Million Signatures Campaign and “Weblogistan” in Iran, and the Kefaya Movement and Muslim Brotherhood blogging in Egypt. When placing Internet use in the context of political scientist and historian Charles Tilly’s “repertoire” of social movement characteristics (worthiness, unity, numbers, and commitment) and political scientist Robert Putnam’s theory that the Internet can isolate individual users, it appears that the key to the successful collaboration of the web and social movements is an adaptive dynamic, through which groups function in both the cyber-world and the real world. This paper presents a potential vision for the future of the Internet and Islamic activism based on the assumption that an online element will help generate some of the elements of Tilly’s social movement repertoire, particularly if the Internet is used to inspire sympathetic individuals to real world political action.
Keywords: Blogging; Egypt; Internet use; Iran; Islam; Kefaya Movement; Muslim Brotherhood; Muslim minorities; New Media; Weblogistan

Communicating Identity through Religious Internet Memes on the ‘Tweeting Orthodoxies’ Facebook Page - Yadlin-Segal, A (Digital Judaism: Jewish Negotiations with Digital Media and Culture, 2015)
It is the well-known “bulletproof” scene from The Matrix movie. We see Keanu Reeves in a green hallway, wearing a black trench coat, dark sunglasses, and a Kippah. His hand is stretched out, holding back a stream of hovering candies, instead of machine-gun bullets. The caption above the photo states “Neo’s Bar-Mitzvah.” This is not a Jewish remake of The Matrix, it is an internet meme shared on the religious Facebook page “Tweeting Orthodoxies,” that playfully presents the custom of throwing candies at the Bar-Mitzvah boy after reading the Haphtarah on his Aliyah La-Thorah. This meme, and many others like it, demonstrates how digital culture provides a group of National Religious Jews with unique opportunities to communicate about and engage in the reconstruction of their religious identity. This engagement is studied in the current chapter by investigation of the ways a specific National Religious Facebook group employs internet memes.
Keywords: internet meme; Orthodox; religious

Internet Accessibility of the Mizuko Kuyo (Water-Child Ritual) in Modern Japan: A Case Study in Weberian Rationality - Mieko Yamadaa; Anson Shupea (Sociological Focus, 2013)
The mizuko kuyo is a Japanese (Buddhist, Shinto, New Religious, other) memorial service for infants or young children who have died through some misfortune, including disease, miscarriage, and, increasingly, elective abortion. Indeed, abortion is the predominant form of contraception for many Japanese families. Here we consider, in Weberian terms of the rationalization of institutions, how Internet accessibility and its created virtual reality of the mizuko kuyo has driven its popularity along the dimensions of privatization, bureaucratization, and commodification in decisions to perform the ritual by Internet. We utilize a sample of Tokyo mizuko kuyo Web sites and the contexts of their advertisements and available services for mizuko kuyo, including fee structures and other advertising “lures,” to analyze this merging of traditional and modern technological paths of spirituality along Weberian theoretical lines.
Keywords: Buddhist; children; infants; Japan; memorial service; mizuko kuyo; New Religious; religion; Ritual; Shinto; Spirituality; websites

Reading and praying Online: The Continuity in Religion Online and Online Religion in Internet Christianity - Young, Glenn (Religion Online: Finding Faith on the Internet, 2004)
After sex, religion is one of the most popular and pervasive topics of interest online, with over three million Americans turning to the internet each day for religious information and spiritual guidance. Tens of thousands of elaborate websites are dedicated to every manner of expression.Religion Onlineprovides an accessible and comprehensive introduction to this burgeoning new religious reality, from cyberpilgrimages to neo-pagan chatroom communities. A substantial introduction by the editors presenting the main themes and issues is followed by sixteen chapters addressing core issues of concern such as youth, religion and the internet, new religious movements and recruitment, propaganda and the countercult, and religious tradition and innovation. The volume also includes thePew Internet and American Life ProjectExecutiveSummary, the most comprehensive and widely cited study on how Americans pursue religion online, and Steven O'Leary's field-definingCyberspace as SacredSpace.

Extrapolating Psychological Insights from Facebook Profiles: A Study of Religion and Relationship Status - Sean Young; Debo Dutta; Gopal Dommety (CyberPsychology & Behavior, 2009)
Online social network users may leave creative, subtle cues on their public profiles to communicate their motivations and interests to other network participants. This paper explores whether psychological predictions can be made about the motivations of social network users by identifying and analyzing these cues. Focusing on the domain of relationship seeking, we predicted that people using social networks for dating would reveal that they have a single relationship status as a method of eliciting contact from potential romantic others. Based on results from a pilot study (n = 20) supporting this hypothesis, we predicted that people attempting to attract users of the same religious background would report a religious affiliation along with a single relationship status. Using observational data from 150 Facebook profiles, results from a multivariate logistic regression suggest that people providing a religious affiliation were more likely to list themselves as single (a proxy for their interest in using the network to find romantic partners) than people who do not provide religious information. We discuss the implications for extracting psychological information from Facebook profiles. To our knowledge, this is the first study to suggest that information from publicly available online social networking profiles can be used to predict people's motivations for using social networks.
Keywords: dating; Facebook; online profiles; participants; relationship; religion; religious information; social network

The Soul of Cyberspace - Zaleski, Jeff (HarperEdge, 1997)
In a pioneering journey to faith's new frontier--cyberspace, where traditional religions are reinvented and new ones are created--the acclaimed coauthor of "Transformations: Awakening to the Sacred in Ourselves" charts technology's radical impact on the ways in which the world prays, worships, preaches, and believes.

Silicon Valley New Age: The Co-Constitution of the Digital and the Sacred - Zandbergen, Dorien; Aupers, Stef; Houtman, Dick (Religions of Modernity: Relocating the Sacred to the Self and the Digital, 2010)
Keywords: New Age; religon and technology

New Producers of Patriarchal Ideology: Matushki in Digital Media of Russian Orthodox Church - Zasanska, Nadia D (Journal for Communication Studies, 2019)
The recent research on patriarchal ideology has mainly considered it in relation to politics, society, economics and religion while the studies of actors in mediatization of patriarchal ideas remain fragmented. This study addresses the roles of matushki, the wives of Orthodox Christian priests, as (un)aware producers of extra-institutional forms of patriarchal ideology in social media. Matushki, highly respected women within Orthodox communities, increase the patriarchal power of the Russian Orthodox Church (ROC) through the promotion of Orthodox women’s identity as a basis of social and ethnic identities in post-Soviet societies. The latter reveals in the standardization of views on Orthodox women’s behavior, family life, upbringing children and ritual practices within the fixed patriarchal categories of ‘man’ and ‘woman’.
Keywords: patriarchal ideology; religious blogger; religious identity; Russian Orthodox Church

Digital Religion in China: A Comparative Perspective on Buddhism and Christianity's Online Publics in Sina Weibo - Zhang, Y (Journal of Religion, Media and Digital Culture, 2017)
The proliferation of social media in China has provided traditional religious authorities with multifarious digital features to revitalise and reinforce their practices and beliefs. However, under the authoritative political system different religions pick up the new media to varying degrees, thereby showing different characteristic and style in their social media use. This paper examines the public discourse about Buddhism and Christianity (two of the great official religions in China) on China’s largest microblogging platform-Sina Weibo, and seeks to reveal a distinct landscape of religious online public in China. Through a close look at the social media posts aided by a text analytics software, Leximancer, this paper comparatively investigates several issues related to the Buddhism and Christianity online publics, such as religious networks, interactions between involved actors, the economics and politics of religion, and the role of religious charitable organizations. The result supports Campbell’s proposition on digital religion that religious groups typically do not reject new technologies, but rather undergo a sophisticated negotiation process in accord with their communal norms and beliefs. It also reveals that in China a secular Buddhism directly contributes to a prosperous ‘temple economy’ while tension still exists between Christianity and the Chinese state due to ideological discrepancy. The paper further points out the possible direction for this nascent research field.
Keywords: Buddhism; China; Christianity; Digital Religion; Online

Younger Americans' Reading and Library Habits - Zickuhr, Katheryn; Rainie, Lee; Purcell, Kristen; Mary Madden; Brenner, Joanna (Pew Internet and American Life Project, 2012)
More than eight in ten Americans ages 16-29 read a book in the past year, and six in ten used their local public library. Many say they are reading more in the era of digital content, especially on their mobile phones and on computers.
Keywords: e-books; internet; Mobile phone; Reading habits

Re-engaging Avery Dulles’ theology of revelation in the context of using internet-mediated communication in religious education - Daniella Zsupan-Jerome (Religious Education Association Conference, 2009)
Re-engaging Dulles’ theology of revelation as symbolic communication, where revelatory symbols engage the community in this fourfold way of participation, transformation, new commitment and behavior, and new understandings opens a profound way to dialogue with the internet, itself entirely a symbolic medium. Can we claim then, that because of this commonality of symbol, that the internet therefore is an appropriate medium for the transmission of revelation in the context of religious education? This is the guiding question of the present paper. This essay first constructs the theological foundation for pursuing this question, by revisiting Avery Dulles’ theology of revelation as symbolic communication, and his fourfold schema of participation, transformation, new behavior and commitments, and new awareness and understanding. Bringing the internet into the discussion, this essay next investigates how the category of symbolic communication fits with the internet as the specific communicative medium. Finally, this essay explores specific points of convergence and divergence between Dulles’ fourfold schema and internet-mediated communication.

Do Digital Decisions Disciple? - Sarah Eekhoff Zylstra (Christianity Today, 2015)
Online evangelists report the equivalent success of one Billy Graham crusade per day. Three years ago, the Billy Graham Evangelistic Association (BGEA) shifted its focus to online evangelism. It laid off about 50 people—10 percent of its staff—and “redeployed resources to focus on areas of greater impact.” The change seems to be paying off. In 2014, the BGEA shared the gospel with almost 9.5 million people around the world. Of those, only about 180,000 were in a live audience at a crusade, while 7.5 million were reached through BGEA websites. Of the 1.6 million people who told the BGEA they prayed “to accept Jesus Christ as [their] Savior” in 2014, less than 15,000 did so in person, while more than 1.5 million did so with the click of a mouse.